Comparative Materials-Level Evaluation of 3′- and 5′-Thiol DNA Aptamer Conjugation on Gold Nanospheres and Nanoflowers: Apparent DNA Loading Output, Morphology Retention, and Qualitative Salt-Challenge Response - Sun, Jingchun; Zhang, Linbing; Gonçalves, David; Kuang, Shaoping; Yang, Hongsheng (Sensors, 2026)
Gold nanospheres (AuNPs) and gold nanoflowers (AuNFs) are widely used as platforms for DNA aptamer functionalization, while conjugation behavior and colloidal tolerance remain important factors affecting subsequent sensing-oriented optimization. In this study, 82-nt thiolated DNA aptamer constructs bearing either 3′-SH or 5′-SH terminal modification were immobilized onto citrate-stabilized AuNPs and AuNFs under matched stepwise salt-aging conditions. Apparent nanoparticle-associated DNA output was estimated by Qubit-based measurement of unbound ssDNA in the supernatant and expressed as mass-based loading output (ng). Under the tested stock-dispersion conditions, AuNP samples showed higher apparent conjugation output than AuNF samples. Specifically, the apparent conjugation yields for AuNPs were 80.65 ± 1.64% (3′-SH) and 84.76 ± 1.98% (5′-SH), whereas those for AuNFs were 66.64 ± 3.36% (3′-SH) and 73.65 ± 1.36% (5′-SH). The corresponding apparent DNA loading outputs were 2329.7 ± 47.4 ng and 2448.7 ± 57.1 ng for AuNPs, and 1925.1 ± 97.0 ng and 2127.4 ± 39.3 ng for AuNFs. DLS size increases and zeta potential shifts toward more negative values were consistent with the formation of a DNA-associated interfacial layer, while TEM images supported morphology retention after conjugation. A qualitative visual salt-challenge assessment indicated that aptamer-functionalized nanoparticles displayed improved resistance to salt-induced aggregation relative to bare particles under the tested conditions. Because the commercially supplied AuNP and AuNF dispersions were not normalized to identical particle number or accessible surface area, the reported values should be interpreted as comparative apparent outputs rather than intrinsic loading capacities. Within this scope, the present study provides a convenient preliminary materials-level evaluation of thiolated aptamer conjugation behavior and may support future glyphosate aptasensor optimization.

The Russian Civil War in Chinese Turkestan (Xinjiang), 1918–1921: A Little Known and Explored Front - Share, Michael (Europe-Asia Studies, 2010)
A very important yet little known front in the Russian Civil War existed in neighbouring Xinjiang, a region in China's northwest, that was at that time self-governing. In Xinjiang, Russian White Commanders and their troops gained sanctuary, financial assistance, food and shelter from Chinese provincial leaders, and then used those sanctuaries to launch operations against Soviet forces. However, by 1921, Red Army troops destroyed any remaining organised White forces, which then melted into the Chinese landscape. The ramifications of the Russian Civil War in Xinjiang had important impacts on the people of Xinjiang, and on Russia and China as well.

The Christian Transformation of Greek Philosophical Concepts – the Distinction of Ousia and Hypostasis in the Formation of the Trinitarian Formula “One Ousia and Three Hypostases" - Xia, Sonja (2024)
The Trinity, i.e., one God in three persons (Father, Son, and Holy Spirit), is the core doctrine of Christianity. It confesses that God truly exists as one, and the three persons truly exist each in themselves. The seemingly paradoxical doctrine was from the beginning of the Church imprinted on the popular faith witnessed in the New Testament, the liturgy, especially the rite of baptism, and the catechetical practice. (Kelly, 1960/1968, pp. 88-90) Yet it took four centuries of controversies and synods to transform the initial faith into a doctrine. The main achievements were made in the 4th century: first, the Ecumenical Council of Nicaea I in 325 acknowledged the common substance of the Trinitarian persons by accepting the Greek term homoouios (homo means same, and ousios means being, substance, or essence); second, in the decades after Nicaea I, the common substance of the three and the distinctiveness of each person are expressed as “mia ousia, treis hypostaseis” (one substance, three persons). 三一论,即一体三位,是基督教的核心教义。它意味着天主为一、真实存在,同时天主拥有三个真实存在的位格,即圣父、圣子、圣神。这一看似自相矛盾的教义从教会建立之初就蕴含在《新约圣经》、礼仪(尤其是圣洗圣事)和信仰实践中。然而,这一原初的信仰要经过四个世纪的理论争辩和教会会议才被转化为教会教义。其中至关重要的是325年的尼西亚大公会议通过接受希腊词“同一体性(homoouios)”一词来表述圣父和圣子之间的关系,认定了天主圣三的共同体性;以及尼西亚大公会议之后,卡帕多西亚教父用希腊语中两个同为表示存在、体质的近义词ousia和hypostasis分别指代天主的同一体性和三位各自的独特存在,由此提出了“mia ousia, treis hypostaseis”(一体三位)这一三一论的经典表述。本文将根据哲学所提供的术语框架,阐述卡帕多西亚教父在三一论神学中对ousia和hypostasis的区分,然后阐释这种区分的神学意义。

Being Spiritual in Life Vicissitudes – The Present Time and Perpetual Spiritual Journey in the Light or Gregory of Nyssa’s Mysticism - Xia, Sonja (2022)
With the outbreak of the Covid-19 pandemic, we find ourselves living in a time of crisis. Our cultural and technological developments are being largely challenged. The pandemic tells us that the ultimate solution for all the problems we face is not in our own hands. God is where we find the final hope and salvation. In this regard, the present crisis may not be totally negative for our lives. To read the situation positively and even spiritually, we turn to the 4th-century Church Father Gregory of Nyssa, who is famous for his apophatic Mysticism. Viewing through the apophatic lens, the crisis has reminded us of the limitations of human intellectual power, which may turn our eyes to the final cause of the world, the ultimate meaning of life, and eventually what is essential for our final salvation. That is where we start our spiritual transformation anew.

普羅提諾的宇宙生成理論 - Xia, Sonja (2024)
內容摘要:古羅馬的普羅提諾作為新柏拉圖主義的開創者,針對亞里斯多德對柏拉圖理念論中無限逆推問題的批判,以第一原則太一作為世界的第一本原建構起自太一逐級向下生成各級存在的宇宙生成模式。在這個宇宙模式中,太一對理智的的生成決定了各級存在的生模式,並成為了普羅提諾理論體系的特點之一。本文對太一生成學說進行梳理,重點澄清作為太一生成的前提的太一的特性、太一生成中的核心概念「動能」和「雙重活動」,從而總結普羅提諾的生成觀的特色。

天主的恩寵和人的自由:對尼薩的額我略《真福八端講道集》的解讀 - Xia, Sonja (2025)
本文透過教父尼薩的額我略的早期著作《真福八端講道集》，探討其神學體系中天主的恩寵和人的自由之間的關係。作者著眼於天主的恩寵和人的自由在聖化過程中的動態關係，首先闡釋額我略對人的聖化即是回歸本性的縱向旅程的理解；其後具體分析該講道集中額我略對天主的恩寵（外在恩寵、內在恩寵）和人的自由（選擇的自由和自主性的自由）的理解；最後分析兩種恩寵和兩種自由在靈性旅程中本質上是並行發展、相容互惠的關係。

Lost horizons? - Morrison, Keith (2025)

Fair play for contract in Macau - Morrison, Keith (2025)

A jolly afternoon out in Macau - Morrison, Keith (2025)

Paradigm changes in Macau - Morrison, Keith (2025)

An uneasy phoenix - Morrison, Keith (2025)

Big changes for small Macau? - Morrison, Keith (2025)

Challenging overtourism in Macau - Morrison, Keith (2025)

Bringing Macau’s policy to life - Morrison, Keith (2025)

Are Macau’s civil servants ready for change? - Morrison, Keith (2025)

The illusion of control - Morrison, Keith (2025)

A Christmas morality story - Morrison, Keith (2025)

Teaching and learning with older adults: Research ethics, risk analysis, and covert research - Bhroin, Áine Ní; Morrison, Keith (Educational Gerontology, 2024)
This article reports a case study of older adults learning English in China. It indicates how, founded on consequentialist ethics, risk analysis, and safeguarding, it was decided to use covert research, drawing on the confluence of risk analysis, risk evaluation, risk management, safeguarding, research ethics, and important contextual and cultural features. Ethical principles of nonmaleficence, beneficence, safeguarding, and protection were addressed, and account was taken of the strength, likelihood, and consequences of risks, safeguards, and benefits, informed by Chinese cultural contexts, values, behaviors, and features of teaching and learning based on andragogy and geragogy. Implications are drawn for teaching and learning with older adults, advocating significant account to be taken of contextual factors.

The spectacle of the Chinese city: urban atmospheres, the built environment and everyday practices - Zuev, Denis; Kobi, Madlen (Visual Studies, 2024)

Multimodal representation learning for tourism recommendation with two-tower architecture - Cui, Yuhang; Liang, Shengbin; Zhang, YuYing (PLOS ONE, 2024)
Personalized recommendation plays an important role in many online service fields. In the field of tourism recommendation, tourist attractions contain rich context and content information. These implicit features include not only text, but also images and videos. In order to make better use of these features, researchers usually introduce richer feature information or more efficient feature representation methods, but the unrestricted introduction of a large amount of feature information will undoubtedly reduce the performance of the recommendation system. We propose a novel heterogeneous multimodal representation learning method for tourism recommendation. The proposed model is based on two-tower architecture, in which the item tower handles multimodal latent features: Bidirectional Long Short-Term Memory (Bi-LSTM) is used to extract the text features of items, and an External Attention Transformer (EANet) is used to extract image features of items, and connect these feature vectors with item IDs to enrich the feature representation of items. In order to increase the expressiveness of the model, we introduce a deep fully connected stack layer to fuse multimodal feature vectors and capture the hidden relationship between them. The model is tested on the three different datasets, our model is better than the baseline models in NDCG and precision.

Chemical and Visual Cues as Modulators of the Stress Response to Social Isolation in the Marine Medaka, Oryzias melastigma - Lebel, Alexandre; Zhang, Libin; Gonçalves, David (Zebrafish, 2024)
The marine medaka is emerging as a potential behavioral model organism for ocean studies, namely on marine ecotoxicology. However, not much is known on the behavior of the species and behavioral assays lack standardization. This study assesses the marine medaka as a potential model for chemical communication. We investigated how short exposure to visual and chemical cues mediated the stress response to social isolation with the light/dark preference test (LDPT) and the open field test (OFT). After a 5-day isolation period, and 1 h before testing, isolated fish were randomly assigned to one of four groups: (1) placed in visual contact with conspecifics; (2) exposed to a flow of holding water from a group of conspecifics; (3) exposed to both visual and chemical cues from conspecifics; or (4) not exposed to any stimuli (controls). During the LDPT, the distance traveled and transitions between zones were more pronounced in animals exposed to the conspecific's chemical stimuli. The time spent in each area did not differ between the groups, but a clear preference for the bright area in all animals indicates robust phototaxis. During the OFT, animals exposed only to chemical cues initially traveled more than those exposed to visual or both stimuli, and displayed lower thigmotaxis. Taken together, results show that chemical cues play a significant role in exploratory behavior in this species and confirm the LDPT and OFT as suitable tests for investigating chemical communication in this species.

Pharmaceutical Residues in Edible Oysters along the Coasts of the East and South China Seas and Associated Health Risks to Humans and Wildlife - Wu, Rongben; Sin, Yan Yin; Cai, Lin; Wang, Youji; Hu, Menghong; Liu, Xiaoshou; Xu, Wenzhe; Kwan, Kit Yue; Gonçalves, David; Chan, Benny Kwok Kan; Zhang, Kai; Chui, Apple Pui-Yi; et al. (Environmental Science & Technology, 2024)
The investigation of pharmaceuticals as emerging contaminants in marine biota has been insufficient. In this study, we examined the presence of 51 pharmaceuticals in edible oysters along the coasts of the East and South China Seas. Only nine pharmaceuticals were detected. The mean concentrations of all measured pharmaceuticals in oysters per site ranged from 0.804 to 15.1 ng g–1 of dry weight, with antihistamines being the most common. Brompheniramine and promethazine were identified in biota samples for the first time. Although no significant health risks to humans were identified through consumption of oysters, 100–1000 times higher health risks were observed for wildlife like water birds, seasnails, and starfishes. Specifically, sea snails that primarily feed on oysters were found to be at risk of exposure to ciprofloxacin, brompheniramine, and promethazine. These high risks could be attributed to the monotonous diet habits and relatively limited food sources of these organisms. Furthermore, taking chirality into consideration, chlorpheniramine in the oysters was enriched by the S-enantiomer, with a relative potency 1.1–1.3 times higher when chlorpheniramine was considered as a racemate. Overall, this study highlights the prevalence of antihistamines in seafood and underscores the importance of studying enantioselectivities of pharmaceuticals in health risk assessments.

Spatio-Temporal Variation in Landforms and Surface Urban Heat Island in Riverine Megacity - Gorai, Namita; Bandyopadhyay, Jatisankar; Halder, Bijay; Ahmed, Minhaz Farid; Molla, Altaf Hossain; Lei, Thomas (Sustainability, 2024)
Rapid urbanization and changing climatic procedures can activate the present surface urban heat island (SUHI) effect. An SUHI was considered by temperature alterations among urban and rural surroundings. The urban zones were frequently warmer than the rural regions because of population pressure, urbanization, vegetation insufficiency, industrialization, and transportation systems. This investigation analyses the Surface-UHI (SUHI) influence in Kolkata Municipal Corporation (KMC), India. Growing land surface temperature (LST) may cause an SUHI and impact ecological conditions in urban regions. The urban thermal field variation index (UTFVI) served as a qualitative and quantitative barrier to the SUHI susceptibility. The maximum likelihood approach was used in conjunction with supervised classification techniques to identify variations in land use and land cover (LULC) over a chosen year. The outcomes designated a reduction of around 1354.86 Ha, 653.31 Ha, 2286.9 Ha, and 434.16 Ha for vegetation, bare land, grassland, and water bodies, correspondingly. Temporarily, from the years 1991–2021, the built-up area increased by 4729.23 Ha. The highest LST increased by around 7.72 °C, while the lowest LST increased by around 5.81 °C from 1991 to 2021. The vegetation index and LST showed a negative link, according to the correlation analyses; however, the built-up index showed an experimentally measured positive correlation. This inquiry will compel the administration, urban planners, and stakeholders to observe humanistic activities and thus confirm sustainable urban expansion.

YOUNG ADULTS' USE OF ELECTRONIC DEVICES IN MACAO: A CONTRIBUTION TO UNDERSTANDING HUMAN BEINGS IN THE DIGITAL ERA - Leong, Cynthia (2024)
A greater amount of existing literature suggests that personal electronic devices (PEDs), such as smartphones, are detrimental to individuals in different aspects; a smaller amount of existing literature looks at the positive impacts of PEDs. Also, most of the literature used a quantitative approach, whereas very few of them used qualitative and mixed methods approaches. Based on my observation and experience, and talking to some young adults, it seems that what the existing literature suggests may not be truly revealing what is actually happening nowadays. With this, the present study was conducted to answer the questions: 1) What is young adults' PED use? 2) How does PED use affect (associate with) young adults' development? The present study used explanatory sequential mixed methods research design, with quantitative survey conducted first, and then followed by qualitative interviews in which questions were developed based on the findings in the quantitative phase. A sample of 736 undergraduates from five universities in Macau (M = 21.9, SD = 4.1) participated in quantitative phase, and a subsample of 13 participants from quantitative phase participated in the qualitative phase interviews. Respondents’ scores on a self-report measure of personal electronic device (PED) use were compared sociodemographic factors (i.e., age, gender, maternal language, and type of family). Qualitative data were analysed using thematic analysis. Quantitative results showed that PED use is a continuous and integral part of young adults' daily lives in Macau. Increased internet use and specific activities correlate with developmental outcomes, but only extreme use is associated with negative outcomes. Interaction and communication with others are key to happiness, regardless of call duration. Using diverse devices relates to less smartphone addiction and more happiness and social satisfaction, but mobile phones and laptops are not linked to positive or negative outcomes. PED use itself is not harmful; it is only problematic when used excessively. Qualitative results showed that PED use is an integral part of young adults' daily lives in Macao due to the powerful characteristics of PEDs that enable various tasks (Theme 1), and the necessity of PED use across different contexts and with different people (Theme 2). PEDs are used for fundamental purposes like communication, productivity, and psychosocial needs (Theme 3), leading to both positive and negative impacts on individuals' lives (Theme 4). PED use is a spectrum, not a dichotomy, distinguished by factors like maladaptation, compulsivity, overuse, and attachment (Theme 5). This qualitative study deepens the understanding of PED use beyond the quantitative findings. By linking and integrating quantitative and qualitative data and applied the theoretical framework of the present study, an extension of the bioecological theory, cloudsystem is proposed. It is believed that the cloudsystem contributes to a better understanding of the person in this specific moment of human’s existence. Practical implications, strengths and limitations of the study, suggestions for future studies were also discussed.

Technological solutions for air pollution control to mitigate climate change: an approach to facilitate global transition toward blue sky and net-zero emission - Kurniawan, Tonni Agustiono; Khan, Sajid; Mohyuddin, Ayesha; Haider, Ahtisham; Lei, Thomas; Othman, Mohd Hafiz Dzarfan; Goh, Hui Hwang; Zhang, Dongdong; Anouzla, Abdelkader; Aziz, Faissal; Mahmoud, Mohamed; Ali, Imran; et al. (Chemical Papers, 2024)
The convergence of air pollution control and climate change mitigation is critical in the pursuit of sustainable development. Therefore, technological innovations are pivotal in addressing the dual challenges of air pollution and global warming. This work presents an overview of technological solutions aimed at reducing air pollution and mitigating GHG emissions. While evaluating their technological strengths and limitations in real applications, this work offers a framework to promote a transition toward blue skies and net-zero emissions. This work also identifies the main sources and negative impacts of air pollution on public health and the environment. A literature overview of published articles from 1976 to 2024 showed that integrating emission reduction technologies are vital in real-word applications. More than 98% of the SO2 in the flue gas can be removed using cutting-edge desulfurization technology. SO2 is eliminated from the environment either unaltered or as sulfuric acid and sulfates. Meanwhile, thermal incinerators boast an impressive efficiency, capable of eliminating 99% of gaseous pollutants. Although existing pollution control technologies are promising to mitigate climate change, they still require further research, development, demonstration, and deployment to overcome barriers and achieve their potential. By examining the effectiveness of control technologies and proposing adaptable strategies, this work highlights the potential of integrating air quality improvement efforts with climate actions. Not only this addresses the global need for cleaner air, but also contributes to the overarching goal of climate stabilization. © The Author(s), under exclusive licence to the Institute of Chemistry, Slovak Academy of Sciences 2024.

Identification of Anticancer Peptides from the Genome of Candida albicans: in Silico Screening, in Vitro and in Vivo Validations - Cheong, Hong-Hin; Zuo, Weimin; Chen, Jiarui; Un, Chon-Wai; Si, Yain-Whar; Wong, Koon Ho; Kwok, Hang Fai; Siu, Shirley (Journal of Chemical Information and Modeling, 2024)
Anticancer peptides (ACPs) are promising future therapeutics, but their experimental discovery remains time-consuming and costly. To accelerate the discovery process, we propose a computational screening workflow to identify, filter, and prioritize peptide sequences based on predicted class probability, antitumor activity, and toxicity. The workflow was applied to identify novel ACPs with potent activity against colorectal cancer from the genome sequences of Candida albicans. As a result, four candidates were identified and validated in the HCT116 colon cancer cell line. Among them, PCa1 and PCa2 emerged as the most potent, displaying IC50 values of 3.75 and 56.06 μM, respectively, and demonstrating a 4-fold selectivity for cancer cells over normal cells. In the colon xenograft nude mice model, the administration of both peptides resulted in substantial inhibition of tumor growth without causing significant adverse effects. In conclusion, this work not only contributes a proven computational workflow for ACP discovery but also introduces two peptides, PCa1 and PCa2, as promising candidates poised for further development as targeted therapies for colon cancer. The method as a web service is available at https://app.cbbio.online/acpep/home and the source code at https://github.com/cartercheong/AcPEP_classification.git.

Reply to the Comment by L. Filipe O. Costa et al. - Arraut, Ivan (Europhysics Letters, 2024)

博物館體驗如何影響本地參觀者重遊博物館的意願? - Leong, Si Man (2024)
近年來，博物館的休閒、教育、娛樂功能等日益重要，其對文化教育的貢 獻也越來越受到博物館參觀者的認可。相關的文獻大多數探討於博物館的服務 質量與參觀者參觀博物館體驗的滿意度之間的關係。目前，以參觀者的博物館 體驗如何影響他們重遊博物館的專門論述或深入研究並不多。因此，本研究的 研究目的是以博物館的體驗為中心，探討哪些因素會影響參觀者參觀博物館的 體驗，以及這些因素如何影響參觀者對博物館的重遊意願。本研究以篩選的方 式隨機抽查了 10 位參觀過博物館體驗的參觀者進行半結構式訪談(Semi- structured interview)，深入地了解受訪者的博物館體驗以及影響他們重遊博物 館的因素等問題，並以文獻及理論為基礎探討參觀者在參觀博物館過程會影響 他們的因素。採訪會在博物館附近進行，並採用深度定性訪談法(In-depth qualitative interview)，研究對象為澳門的本地參觀者。

Evaluation of Machine Learning Models in Air Pollution Prediction for a Case Study of Macau as an Effort to Comply with UN Sustainable Development Goals - Lei, Thomas; Cai, Jianxiu; Molla, Altaf Hossain; Kurniawan, Tonni Agustiono; Kong, Steven Soon-Kai (Sustainability, 2024)
To comply with the United Nations Sustainable Development Goals (UN SDGs), in particular with SDG 3, SDG 11, and SDG 13, a reliable air pollution prediction model must be developed to construct a sustainable, safe, and resilient city and mitigate climate change for a double win. Machine learning (ML) and deep learning (DL) models have been applied to datasets in Macau to predict the daily levels of roadside air pollution in the Macau peninsula, situated near the historical sites of Macau. Macau welcomed over 28 million tourists in 2023 as a popular tourism destination. Still, an accurate air quality forecast has not been in place for many years due to the lack of a reliable emission inventory. This work will develop a dependable air pollution prediction model for Macau, which is also the novelty of this study. The methods, including random forest (RF), support vector regression (SVR), artificial neural network (ANN), recurrent neural network (RNN), long short-term memory (LSTM), and gated recurrent unit (GRU), were applied and successful in the prediction of daily air pollution levels in Macau. The prediction model was trained using the air quality and meteorological data from 2013 to 2019 and validated using the data from 2020 to 2021. The model performance was evaluated based on the root mean square error (RMSE), mean absolute error (MAE), Pearson’s correlation coefficient (PCC), and Kendall’s tau coefficient (KTC). The RF model best predicted PM10, PM2.5, NO2, and CO concentrations with the highest PCC and KTC in a daily air pollution prediction. In addition, the SVR model had the best stability and repeatability compared to other models, with the lowest SD in RMSE, MAE, PCC, and KTC after five model runs. Therefore, the results of this study show that the RF model is more efficient and performs better than other models in the prediction of air pollution for the dataset of Macau.

Optimization Design of a Multi-String Standing Wave Electrospinning Apparatus Based on Electric Field Simulations - Chen, Xiaoqing; Liang, Jiahao; Tan, Xiang; Ding, Jiazheng; Xie, Wenyu; Li, Changgang; Cai, Yebin (Polymers, 2024)
The mass production of uniform, high-quality polymer nanofibers remains a challenge. To enhance spinning yield, a multi-string standing wave electrospinning apparatus was developed by incorporating a string array into a standing wave electrospinning device. The process parameters such as string spacing, quantity, and phase difference were optimized, and their effects on the electric field distribution within the spinning area were analyzed using electric field simulations. When the string spacing was less than 40 mm or the number of strings exceeded two, the electric field strength significantly decreased due to electric field interference. However, this interference could be effectively mitigated by setting the string standing wave phase difference to half a period. The optimal string array parameters were identified as string spacing of 40 mm, two strings, and a phase difference of half a period. Multi-string standing wave electrospinning produced fibers with diameters similar to those obtained with single-string standing wave electrospinning (178 ± 72 nm vs. 173 ± 48 nm), but the yield increased by 88.7%, reaching 2.17 g/h, thereby demonstrating the potential for the large-scale production of nanofibers. This work further refined the standing wave electrospinning process and provided valuable insights for optimizing wire-type electrospinning processes.

Digital Influencers: Catalysts for Customer Engagement and Purchase Intention - Hani, Ghamama; Haider, Syed Waqar; Raza, Aamir; Silva, Susana C.; Dias, Joana Carmo (Studia Universitatis Babes-Bolyai Oeconomica, 2024)
Social Media Influencer (SMI) marketing represents a contemporary addition to the arsenal of digital advertising tools. Digital Content Creators are individuals who regularly share a variety of content, including visuals, audio recordings, and updates, across multiple social media platforms to shape consumers' perceptions of a brand and its products. The focus of this study is to examine how the credibility aspects of social media influencers (expertise, attractiveness, and trustworthiness) influence purchase intention and brand intimacy while also considering the mediating role of consumer engagement. This study used a quantitative, cross-sectional design with convenience sampling targeting social media-active individuals. Data were collected via a questionnaire distributed through email and social media, selecting participants who followed influencers. To gather data, 250 participants were engaged in an online questionnaire distributed via Google Forms. The findings indicate that the credibility dimensions of SMIs, particularly their attractiveness and trustworthiness, positively influence brand intimacy and purchase intention. Furthermore, consumer engagement serves as a critical mediator, connecting the authenticity of social media influencers with purchase intention and brand intimacy. In line with these results, it becomes evident that consumer engagement indirectly influences influencer credibility (trustworthiness and attractiveness), purchase intention, and brand intimacy. Notably, expertise does not exert any discernible impact on either brand intimacy or purchase intention. This study's outcomes provide valuable insights for marketing managers, underscoring the significance of partnering with influencers who possess a high level of trust within their respective marketing niches.

Canonical History of the Macao Firecracker Industry in the 20th Century (1920s-1970s) (2024)
In the first half of the 20th century, Macao’s three traditional handicraft industries were: making matches, firecrackers, and incense, and these three became important pillars of Macao's economy. These industries were supported by four other industries, namely: shipbuilding, wine, printing and the clothing that are integral to understanding the history of Macao. The purpose of this research has been to document the importance of Macao's seven traditional industries, in particular the firecracker factories with special reference to the Yick Loong factory. This dissertation makes a significance contribution to the subject of the historical development of Macao’s traditional handicraft industries in reviewing each of the traditional industries and in particular detailing the Yick Loong factories operations and the understanding of the local Macao people to the past importance of this operation. These industries need to be discussed so that society can have a deeper understanding of the importance of them, as up to now they have been little explored. So, by visiting the location of the Yick Loong Firecracker Factory, gathering knowledge, and conducting in-depth research and in books and through a survey about the Macao firecracker business, the author has been able to show that there appears to be limited understanding of the significance of the firecracker industry in Macao. Though, people most recall the Yick Loong factory’s name when prompted about naming a firecracker factory in Macao and associate firecrackers with the Lunar New Year celebrations. However, they seem to have limited understanding of the significance of the firecrackers to Macao, except for childhood memories of them being released.

“LET’S READ TOGETHER”: SHARED PICTURE BOOK READING, CHILDREN’S EMOTIONAL COMPREHENSION AND PARENT-CHILD RELATIONSHIP, A CASE STUDY WITH A GROUP OF NURSES IN MACAU - Cheong, Wai Lai (2024)
The purpose of this study was to investigate the impact of parents engaging in dialogic reading with their children while reading picture books on children's emotional understanding and parent-child relationships. The study also attempted to investigate the potential of picture books as useful instruments for parent-child communication, fostering meaningful parent-child connection and augmenting children's emotional comprehension. The study lasted for 11 weeks. The initial three weeks were focused on a parent-child reading session specifically designed for mothers, and the next eight weeks consisted of a picture book reading program in the participants' homes. Convenience sampling was employed to choose 11 families for participation in the study. Throughout the 8-week reading program, families actively participated in parent-child picture book reading sessions at home, ensuring a minimum frequency of once per week. The study used a combination of multiple case studies and a case study-mixed methods design. The data collection process involved gathering quantitative data through various means, including administering primary background surveys, utilizing the Child-Parent Relationship Scale (CPRS), and employing the Children’s Emotional Development Scale. The qualitative data consisted of interviews conducted before the intervention and records documenting parental reading observations. The analysis methodologies used in this study encompassed thematic and content analysis, which involved combining qualitative and quantitative findings to facilitate comparison. The quantitative data analysis of the Child Emotional Development Scale revealed notable disparities in emotional cognition, comprehension, expression, and overall emotional competence scores between the initial and final examinations. Although the CPRS results did not reveal any notable disparities in family intimacy and conflict; it is worth noting that seven families had higher post-test scores in family intimacy, indicating that mothers perceived an improved level of closeness with their children. Qualitative data analysis revealed that through shared reading of picture books on various emotional themes, children learned more emotional vocabulary and engaged in deeper parent-child conversations beyond daily interactions. This increased children's opportunities for emotional expression and helped mothers better understand their children's emotional needs, reflect on their parenting skills, and foster parent-child interaction and communication. In conclusion, this study demonstrated the significant impact of engaging in dialogic parent-child picture book reading on emotional understanding in preschool children. Furthermore, it is believed to be a valuable parent-child interaction strategy for dual-income families in Macau, enhancing parent-child relationships.

Optimising User Experience in Game-Based Language Learning: Interface Design for Chinese and English Learners – App Prototype - Lin, Rongsi (2024)
In today's rapidly changing educational landscape, parents and children demand personalised, innovative, and engaging learning experiences beyond the standard curriculum. Modern education places a premium on igniting curiosity, encouraging critical thinking, and cultivating creativity. Collaborative learning between parents and children is critical for improving academic performance and strengthening relationships. This article discusses the "Yay Island" platform's game-based technique, which combines Mandarin Chinese and English in a multicultural and multilingual setting. Initial study shows that digital technologies dramatically increase children's motivation and interest when paired with peer and parent participation and game-based teaching, resulting in a pleasant learning environment. Further research demonstrates that collaborative and game-based learning and teaching improves motivation, respects individual differences, and strengthens parent-child connections. As a game, "Yay Island" uses integrated learning, child psychology concepts, modern educational methodologies, and user-centred design. It seeks to develop a collaborative learning environment and encourage growth in children, parents, and educators. The game emphasises knowledge, personal discovery, and innovation, laying the groundwork for children's growth and future competition. Through constant research and optimisation, "Yay Island" solves digital transformation concerns in education by providing personalised, efficient, and entertaining learning experiences.

A Design Research Perspective on Exploring Interactive Augmented Reality Children's Illustration Books in Macau: Case Study - Macau Temple Legends - Liang, Shi Yue (2024)
This project represents a comprehensive study of an interactive picture book employing augmented reality (AR) technology, focusing on the narratives of the A-Ma Temple and Nezha Temple in Macau. The target audience comprises children aged 6-9 years to enhance their concentration on aesthetic development and deepen their understanding of Macau's historical and cultural heritage. The study resulted in the creating of a picture book that integrates an interactive AR experience, resulting in highly satisfactory user feedback. The findings suggest the potential for further development of interactive picture books as a valuable medium for disseminating Macanese culture. Future efforts should prioritise continuous attention to user feedback and the AR technology's stability to ensure the work's long-term effectiveness and impact.

Enhanced Tetracycline Adsorption Using KOH-Modified Biochar Derived from Waste Activated Sludge in Aqueous Solutions - Ding, Jiazheng; Liang, Jiahao; Wang, Qinghong; Tan, Xiang; Xie, Wenyu; Chen, Chunmao; Li, Changgang; Li, Dehao; Li, Jin; Chen, Xiaoqing (Toxics, 2024)
Antibiotic pollution poses a serious environmental concern worldwide, posing risks to ecosystems and human well-being. Transforming waste activated sludge into adsorbents for antibiotic removal aligns with the concept of utilizing waste to treat waste. However, the adsorption efficiency of these adsorbents is currently limited. This study identified KOH modification as the most effective method for enhancing tetracycline (TC) adsorption by sludge biochar through a comparative analysis of acid, alkali, and oxidant modifications. The adsorption characteristics of TC upon unmodified sludge biochar (BC) as well as KOH-modified sludge biochar (BC-KOH) were investigated in terms of equilibrium, kinetics, and thermodynamics. BC-KOH exhibited higher porosity, greater specific surface area, and increased abundance of oxygen-based functional groups compared to BC. The TC adsorption on BC-KOH conformed the Elovich and Langmuir models, with a maximum adsorption capacity of 243.3 mg/g at 298 K. The adsorption mechanisms included ion exchange, hydrogen bonding, pore filling, and electrostatic adsorption, as well as π-π interactions. Interference with TC adsorption on BC-KOH was observed with HCO3−, PO43−, Ca2+, and Mg2+, whereas Cl−, NO3−, and SO42− ions exhibited minimal impact on the adsorption process. Following three cycles of utilization, there was a slight 5.94% reduction in the equilibrium adsorption capacity, yet the adsorption capacity remained 4.5 times greater than that of unmodified sludge BC, underscoring its significant potential for practical applications. This research provided new insights to the production and application of sludge biochar for treating antibiotic-contaminated wastewater.

Regulatory Effects of Maternal Intake of Microbial-Derived Antioxidants on Colonization of Microbiota in Breastmilk and That of Intestinal Microbiota in Offspring - Wu, Dangjin; An, Ran; Wang, Di; Jiang, Luoxin; Huang, Liu; Lu, Tenghui; Xu, Weina; Xu, Jianxiong; Zhang, Jing (Animals, 2024)
In this study, sixteen Sprague Dawley (SD) female rats and eight SD male rats were co-housed to mate. Pregnant SD female rats were fed with a control diet or an MA diet. Breast milk, maternal ileum, and intestinal samples of the offspring were collected at the day of birth and ten days afterwards. The results showed that the impact of MA was more obvious on the microbiota of mature milk (p = 0.066) than on that of colostrum. In addition, MA additive did not significantly affect maternal ileal microbiota, but affected offsprings’ colonic microbiota significantly ten days after birth (p = 0.035). From the day of giving birth to ten days afterwards, in addition to the increase in microbial richness and diversity, at genus level, the dominant bacteria of breastmilk changed from Pseudomonas veronii to Bacillus and Lactococcus. Different from breastmilk microbiota, ten days after giving birth, the maternal ileal microbiota and the offsprings’ intestinal microbiota were dominated by Lactobacillus. Instead of ileal microbiota, offsprings’ colonic microbiota is a key action site of maternal MA additive. Therefore, the current findings have significant implications for the development of maternal feed aimed at modulating the intestinal microbiota of offspring, ultimately leading to improved health outcomes for both mothers and their offspring.

Sediment geochemistry reveals abundant off-axis hydrothermal fields on the ultraslow-spreading Southwest Indian Ridge - Liao, Shili; Tao, Chunhui; Dias, Ágata; Liu, Jia; Su, Xin; Lv, Shihui; Jamieson, John W.; Zhou, Jianping; Deng, Xianming; Liang, Jin; Yang, Weifang; Li, Wei; et al. (Earth and Planetary Science Letters, 2024)

Analysing The Forms of Aid Delivered to Guinea by The Traditional and Re-Emerging Aid Donors: Contrasting Aid Policies from China and France - Diakité, Ansoumane Douty (2024)

Curipod's Artificial Intelligence Assistant in the Proofreading Process - Moura, Adelina; Tchiang, Isabel (Advances in Educational Technologies and Instructional Design, 2024)
The use of artificial intelligence (AI) tools in writing and proofreading is beginning to develop. Studies show that AI tools can positively influence students' writing and proofreading skills. This study presents the perceptions of vocational education students regarding the assessments and suggestions for improvement provided by the AI assistant Curipod and followed by students in the proofreading phase. It centres on a case study, with data collected using a survey with open and closed questions, participant observation, and an interview. The students positively perceived the feedback they received from the AI assistant on their initial text and consider that it helped them to revise and improve the final versions of the texts written on paper and digitally. The students are interested in using tools like these in writing revision activities, as they see the potential they have for the classroom and autonomous learning.
ISBN: 9798369361702

An Exploratory Comparison of Stock Price Prediction: Using Multiple Machine Learning Approaches based on Global Stock Indices - Lin, Chin Yang; Lobo Marques, Joao Alexandre (Palgrave Studies of Entrepreneurship and Social Challenges in Developing Economies, 2024)
Predicting stock prices is difficult because of their multiple input variables, volatility, and unpredictable nature. To provide a suitable model for forecasting the global stock market, this study conducts an exploratory analysis comparing two models based on Artificial Intelligence: Support Vector Machine (SVM) and Long Short-Term Memory (LSTM) Neural Networks. The work considers a publicly accessible dataset and uses feature engineering to extract time-series features. Stock price predictions are made using the SVM and LSTM algorithms. For this purpose, Accuracy (ACC) and Root Mean Squared Error (RMSE) are considered accuracy and performance measures. According to the results, LSTM with mean accuracy (ACC) = 0.9061 achieved better accuracy than SVM with mean accuracy (ACC) = 0.881. SVM with mean RMSE = 0.729 achieved better performance and the degree of fit to the data than LSTM with mean RMSE = 427.1. According to the results, the study demonstrates the effectiveness and applicability of machine learning methods for estimating the values of the global stock market and providing valuable models for researchers, analysts, and investors.
ISBN: 9783031653131

Identification of mild cognitive impairment using multimodal 3D imaging data and graph convolutional networks - Liang, Shengbin; Chen, Tingting; Ma, Jinfeng; Ren, Shuanglong; Lu, Xixi; Du, George (Physics in Medicine & Biology, 2024)
Abstract Objective. Mild cognitive impairment (MCI) is a precursor stage of dementia characterized by mild cognitive decline in one or more cognitive domains, without meeting the criteria for dementia. MCI is considered a prodromal form of Alzheimer’s disease (AD). Early identification of MCI is crucial for both intervention and prevention of AD. To accurately identify MCI, a novel multimodal 3D imaging data integration graph convolutional network (GCN) model is designed in this paper. Approach. The proposed model utilizes 3D-VGGNet to extract three-dimensional features from multimodal imaging data (such as structural magnetic resonance imaging and fluorodeoxyglucose positron emission tomography), which are then fused into feature vectors as the node features of a population graph. Non-imaging features of participants are combined with the multimodal imaging data to construct a population sparse graph. Additionally, in order to optimize the connectivity of the graph, we employed the pairwise attribute estimation （PAE） method to compute the edge weights based on non-imaging data, thereby enhancing the effectiveness of the graph structure. Subsequently, a population-based GCN integrates the structural and functional features of different modal images into the features of each participant for MCI classification. Main results. Experiments on the AD Neuroimaging Initiative demonstrated accuracies of 98.57%, 96.03%, and 96.83% for the normal controls (NC)-early MCI (EMCI), NC-late MCI (LMCI), and EMCI-LMCI classification tasks, respectively. The AUC, specificity, sensitivity, and F1-score are also superior to state-of-the-art models, demonstrating the effectiveness of the proposed model. Furthermore, the proposed model is applied to the ABIDE dataset for autism diagnosis, achieving an accuracy of 91.43% and outperforming the state-of-the-art models, indicating excellent generalization capabilities of the proposed model. Significance. This study demonstrate s the proposed model’s ability to integrate multimodal imaging data and its excellent ability to recognize MCI. This will help achieve early warning for AD and intelligent diagnosis of other brain neurodegenerative diseases.

Speaking Truth to Power Structures: Integrity and Identity in Ecclesiology - Percy, Martyn (Journal of Anglican Studies, 2024)
Abstract Speaking truth ought to be normative in churches, and yet when it does, the foundations and structures of power are often shaken to the core. This paper explores the issues of identity and integrity in ecclesiology and is concerned with the ethical paradigms and moral frameworks that need to be in place if churches are to be places where honesty and truthfulness can be normative. Churches often fail as institutions because they presume they can conduct their affairs as organizations might. Churches become anger-averse, resisting the voices and experiences of victims, in order that the flow of power and its structures are unimpeded. At that point, churches become inherently committed to re-abusing victims and are unable to hear their pain and protests, which only leads to the perpetration of further abuse.

Turning up the heat: Effects of temperature on agonistic acoustic communication in the two-spotted goby (Pomatoschistus flavescens) - Penim, Jorge; Beauchaud, Marilyn; Millot, Morgane; Faria, Ana M.; Vieira, Manuel; Fonseca, Paulo J.; Vasconcelos, Raquel; Amorim, M. Clara P. (Marine Environmental Research, 2024)

Afterword: Safeguarding – The Future of Risk and Responsibility - Percy, Martyn (Journal of Anglican Studies, 2024)

A Narrative Study on the Professional Development of Inclusive Teachers of Preschools in Macao - Hong, Sut Mui (2024)
The purpose of this study is to understand the problems and experiences of Macao's regular classroom pre-school teachers in teaching and counseling children with special needs, in order to further explore the professional growth and development process of regular classroom pre-school teachers in the orientation of integrated education. This study adopts a qualitative narrative research methodology, using semi-structured in-depth interviews and textual data collected from the research participants' research journals and teaching diaries to analyze the stories related to the three preschool teachers in the educational field, and according to the results of the data analysis were as following: 1. The professional growth and development of the three teachers in pre-school integration, from novice teachers to professional teachers, need to go through a long period of exploration and adaptation, where teachers continue to refine their professional knowledge and teaching skills to cope with the challenges of problems in the education process, but the progression from professional to expert teachers is affected by both internal and external factors, that teachers are unable to make the transition into it. 2. The three teachers' dilemmas are at different stages. It was found that among the four major dilemmas faced by the teachers, there were teaching, classroom management, support system and professional knowledge in IE, and among them, the support system and professional knowledge in IE were the ones that the teachers considered the most desirable to get in order to have good conditions for implementing IE in ordinary classes. 3. This study suggests that teachers need to be able to adapt their mindset to face different challenges at work. Active Enhancement of IE Knowledge to Cope with Various Educational Issues; schools should assist teachers in the implementation of IE and act as a bridge between parents and teachers. Define the development intention of the school so as to establish a clear direction and avoid internal confusion; government needs to consider the extension of the policy to safeguard the learning rights of Pupils with Special Educational Needs (Pupils with Special Educational Needs). Promote the concept of IE in the community so that it can be widely recognized by the public, thereby gaining more support. There must be a comprehensive training and continuous growth and development for IE Teachers, in order to establish a clear and standardized curriculum. Organize cross-school professional exchanges for qualified IE teachers to enhance their professional knowledge. 本研究旨在透過瞭解澳門普通班學前教師對特殊需要幼兒教學與輔導的問題與經驗，以進一步探討普通班學前教師融合教育導向的專業發展歷程。 本研究採用質性敘事研究方法，使用半結構式深度訪談，並透過研究參與者的研究日記、教學日誌等蒐集文本資料，分析三位學前教師在教育現場內的相關故事，根據資料分析結果發現如下： 一、三位教師的學前融合專業成長發展，從新手型教師到專業型教師需要經歷一段漫長的時間探索和適應，在此教師持續精進自己的專業知識和教學技能，以應對教育過程中的問題挑戰，但從專業型教師到專家型教師這個進階過程受到內在和外在的因素影響，因此，教師雖然初現這階段的特質，但未具備相應的專業力能。 二、通過三位教師不同階段的困境問題發現，所面對的四大困境中，包括有教 學方面、班級管理方面、支援系統方面和融合教育專業知能方面，而當中 支援系統和融合教育專業知能方面是教師認為最希望獲得的支持，才能讓 教師擁有良好的條件在普通班中實施融合教育。 三、本研究建議，教師需要懂得調適心態，以面對工作上的不同挑戰。積極增 進融合教育知能，以應對各類的教育問題；學校方面應協助教師開展融合 教育的工作，做好家長與教師的橋樑。明確學校的發展意向，從而建立清 晰的目標走向，避免造成內部混亂；政府方面需要考量政策的延伸性，以 保障普特幼兒的學習權益。將融合教育的理念推進社區，讓大眾廣泛認 識，從而獲得更多的支持力。建立明確標準化的融合教育教師培育模式， 使融合教育教師的培育過程有着全面性和連續性的成長發展。組織合資格 的融合教育教師跨校專業交流，以提升教師專業知能。

THE MEDIATION EFFECT OF BURNOUT ON SELF EFFICACY AND JOB SATISFACTION FOR SOCIAL WORK IN MACAU - Wong, Kit Ieng (2024)
In many studies of social workers, topics such as burnout and job satisfaction are relatively frequently studied and discussed. There are even fewer relevant studies on social workers in Macau. Therefore, research on self-efficacy, burnout, and job satisfaction among social workers in Macau will be a relatively new research topic. The purpose of this study is to investigate whether and to what extent job burnout mediates the effects of self-efficacy and job satisfaction. We explored the relationships between: (1) the positive relationship between self-efficacy and job satisfaction; (2) the negative relationship between self-efficacy and burnout; (3) the negative relationship between burnout and job satisfaction; and (4) burnout has a mediation effect in the relationship between self-efficacy and job satisfaction. Quantitative and cross-sectional design research was applied by using an online self-response survey (N = 100), conducted using a snowball sampling technique among Macau's full-time social workers. Results from simple linear regression showed that the findings demonstrate significant results on the relationship between social workers' self-efficacy, burnout, and job satisfaction in Macau. Overall burnout had a significant negative prediction towards overall self-efficacy (r = -.47, p <.001); overall self-efficacy can significantly positive predict overall job satisfaction (r =.31, p <.01); Burnout can significantly negatively predict job satisfaction (r = -.43, p <.001), so multiple linear regression analysis was performed. The results showed that when burnout was used as one of the predictors, although burnout had a significant negative prediction on job satisfaction, burnout had a significant negative impact on self-efficacy and job satisfaction. The relationship between them has a very complete mediating effect. This means that the relationship between self-efficacy and job satisfaction is fully mediated by burnout. If corresponding resource policies and strategies are developed to improve social workers' self-efficacy, thereby reducing burnout and improving job satisfaction, this may be beneficial to both employees and organizations. Our study contributes to the direction in which positive expectations influence individual turnover intentions of Macau social workers. This study has theoretical implications for organizations and employees, and future research should continue to explore suggestions such as the limits and causal relationships of self-efficacy to help policymakers develop strategies to reduce social worker turnover.

A STUDY ON JOB BURNOUT AND SUBJECTIVE WELL-BEING AMONG PRIMARY SCHOOL TEACHERS IN MACAO DURING THE POST- PANDEMIC ERA - Chan, Wat (2024)
The aim of this study was to investigate the relationship between job burnout and subjective well-being among primary school teachers in Macao during the post- pandemic era. The research questions included understanding the current status of teachers' job burnout and subjective well-being, analyzing the differences in these aspects across different background variables, and examining the relationship between them. Data were collected through an online questionnaire designed to measure teachers' job burnout and subjective well-being. SPSS 25 and Mplus 8 statistical software were used to ensure the reliability and validity of the questionnaire through Cronbach's alpha analysis and confirmatory factor analysis, ensuring that both were within acceptable ranges. The collected data were analyzed using descriptive statistics, independent samples t-tests, one-way ANOVA, Pearson correlation analysis, and linear regression. The results indicated that Macao primary school teachers' job burnout and subjective well-being were both at a moderate level. There were no significant differences in job burnout and subjective well-being among teachers of different genders, ages, school types, and school sizes. Moreover, there was no significant relationship between different educational backgrounds and subjective well-being among Macao primary school teachers. However, regarding educational background and teaching experience, primary school teachers with a "Master's degree or above" and those with teaching experience of "1-3 years" showed significant differences in the "Emotional Exhaustion" dimension. Additionally, the data revealed a significant relationship between job burnout and subjective well- being among Macao primary school teachers, with job burnout predicting subjective well-being. Teachers, as frontline educators, deserve attention to their mental health, particularly in the post-pandemic era. Therefore, this study provided empirical evidence for educational authorities, schools, and the public to reduce job burnout and enhance the well-being of primary school teachers in Macao, thereby supporting the development of primary education in the region. 本研究旨在探討後疫情時期澳門小學教師職業倦怠感與主觀幸福感之間的關係。研究問題包括瞭解教師的職業倦怠感與主觀幸福感現況，分析不同背景變量對教師職業倦怠感與主觀幸福感的差異。透過線上問卷形式蒐集資料，以測量教師的職業倦怠感和主觀幸福感。通過SPSS25和Mplus8統計軟件，以克隆巴赫係數分析和驗證性因子分析確定問卷的信效度均在可接受的範圍內，並對蒐集所得之數據進行描述性統性、獨立樣本 t 檢定、單因子變異數分析、皮爾森積差相關分析及線性迴歸進行分析。 研究結果顯示，澳門小學教師的職業倦怠感與主觀幸福感分別處於中位程度。不同性別、年齡、任教學校類型及學校規模對教師職業倦怠感與主觀幸福感無顯著差異，而且不同學歷的澳門小學教師在主觀幸福感無顯著差異。然而，在學歷和教師年資方面，除主觀幸福感外，具備「碩士或以上」學歷及教學年資為「1-3 年」的小學教師與「情感耗竭」維度之間呈現顯著差異。此外，數據也顯示，教師的職業倦怠感與主觀幸福感之間存在相關關係，且教師職業倦怠感對主觀幸福感有預測作用。 教師作為教育工作的前線人員，其心理健康值得被關注，尤其在後疫情這特殊時期，教師的心理健康問題更突出。因此，本研究為教育行政當局、學校、 社會大眾提供實證依據，為減輕澳門小學教師職業倦怠感，提高主觀幸福感提出建議，以促進本澳小學教育事業的發展。

澳門幼兒教師勝任力調查研究 - Kuan, On Kei (2024)
As Macau's society rapidly develops, the education system of Macau also continues to develop, including early childhood education. The competency of early childhood teachers in Macau plays an important role in the future development of education. Teacher competency includes four main dimensions: educational ability, work attitude, psychological factors, and motivation. This paper focuses on exploring these dimensions and the differences in teacher competency among Macau's early childhood educators, considering their personal background variables. Moreover, this research investigates the factors such as the working attitude of teachers, their professional development needs, and motivation that affect their teaching in early childhood education. Historically, understandings of teacher competency in Macau's early childhood education were primarily analyzed through t-tests and one-way Anova of survey data, which tend to have lower reliability and validity. This paper employs confirmatory factor analysis among other methods to conduct empirical research on the current state of teacher competency, aiming to advance the development of teacher competency in Macau with more reliable data. This paper uses literature review methodology to gather relevant research and analyzes the information gathered, by using a self-assessment questionnaire on early childhood teacher competency to conduct a survey among 187 early childhood teachers in Macau. This can help to understand their competency levels and how these correlates with their personal background variables. The integrated data from the teacher self-assessment questionnaires indicate that the overall level of teacher competency in Macau is acceptable. In terms of the 4 early childhood teacher competency factors, the psychological factors got the highest score, while their educational abilities got a lower score. The differential analysis conducted on the evaluated teachers shows there are significant differences in early childhood teacher competency among different age groups and years of teaching experience. This research aims to provide more data and information to Macau's education related departments and kindergarten management, to formulate targeted teacher training and career development plans of teachers, which can help to improve the overall teaching quality and job satisfaction of teachers in Macau's early childhood education. The research suggests that future research should expand the research subjects to early childhood teachers from different cultural backgrounds, increase the use of interviews and case analysis (adopting mixed research methods), and analyze the differences in personal background variables and the competency of Macau's early childhood teachers. 澳門社會飛速進步的同時，其教育體系也在不斷發展，而幼兒教育在塑 造孩子未來發展的基礎上扮演著至關重要的角色。故澳門幼兒教師勝任力對於 幼兒教育的未來發展具有不可忽視的重要性。教師勝任力(Teacher Competency) 包含教育能力、工作態度、心理因素和動機等四大維度。本文著重探討這四個 維度和教師的個人背景變項與澳門幼兒教師勝任力的差異性。同時，也會關注 教師的工作態度、專業發展需求及動機等因素對幼兒教師教學的影響。過去， 人們對澳門幼兒教師勝任力的了解較多使用 t 檢驗及單因數變異數進行問卷數 據分析，其有效性及可靠性相對較低。針對上述問題，本文採用驗證性因素分 析等方法對幼兒教師的勝任力現狀進行了實證研究，期望以更可靠的數據推動 澳門幼兒教師勝任力的發展。本文使用文獻分析法整合相關文獻及就研究資訊 進行分析，並使用幼兒教師勝任力自評定問卷對澳門 187 名幼兒教師進行問卷 調查，以了解澳門幼兒教師的勝任力及個人背景變項與澳門幼兒教師勝任力的 差異性。整合教師自評問卷數據後結果如下: 澳門幼兒教師勝任力總體水準尚可， 就勝任力特質表現而言，幼兒教師的心理因素最好，幼兒教師的教育能力較差。 而對被評價幼兒教師進行差異分析的結果顯示：不同年齡段和教齡與幼兒教師 勝任力有顯著差異。 本研究有望為澳門教育相關部門和幼稚園管理層提供更多數據和資訊， 以制定針對性的教師培訓和職業發展計劃，提高澳門幼兒教育整體教學品質和 教師職業滿意度。建議未來研究擴展研究對象至不同文化背景的幼兒教師、增加訪談和個案分析的部分(採用混合研究方法)和分析個人背景變項與澳門幼兒 教師勝任力的差異性。

澳門博彩從業員工作調整措施、壓力應對方法對職場疲勞、情緒健康之影響調查研究 - Tang, Sin U. (2024)
The gaming industry has always been the leading sector in Macau and is one of the main occupations in the region. In 2023, gaming employees accounted for 18.2% of the total employment in Macau, making them a significant portion of the workforce. Research shows that gaming employees experience high levels of work stress, which can directly affect occupational fatigue and may also trigger anxiety and depression. Workplace fatigue and emotional health not only impact individual physical and psychological well-being but also affect their families, work, and interpersonal relationships. Therefore, the emotional health and workplace fatigue of gaming employees deserve public attention. This study aims to explore the work adjustment measures, stress coping methods, emotional health, workplace fatigue, and their relationships among gaming employees. The research focuses on Macau’s gaming employees, employing a quantitative approach. Using non-random sampling, electronic questionnaires were sent to managers of Macau's six major gaming companies from October to December 2023, ultimately collecting 563 valid responses, with males accounting for 45.6% and females for 54.4%. The study utilized SPSS 23 statistical software for quantitative analysis, first conducting descriptive statistics, followed by independent samples t-tests, one-way ANOVA, and finally Pearson correlation coefficients and regression analysis. The study found differences in coping methods based on gender, age, education level, marital status, shift patterns, and monthly salary among gaming employees. Differences in workplace fatigue were found related to gender, age, education level, marital status, living conditions, years of work experience, job position, and monthly salary. Age, education level, and marital status also showed differences in emotional health. In terms of work adjustments, 67.1% of respondents took parental leave, followed by 54.2% who took unpaid leave, and 9.8% who were transferred. The average score for personal fatigue was 40.90 ± 23.125, while the average score for work fatigue was 40.62 ± 21.405, followed by client-related fatigue at 36.65 ± 21.056, and work over-involvement at 24.22 ± 18.987. The average score for depression was 10.60 ± 8.974, indicating mild to moderate levels; anxiety had an average score of 11.26 ± 8.567, indicating moderate to severe levels; and stress averaged 9.96 ± 8.418, falling within the normal to mild range. Among the respondents, 33.9% exhibited severe to very severe anxiety symptoms, while 16% showed severe to very severe depression symptoms. We also found a positive correlation between workplace fatigue and emotional health among gaming employees: the higher the level of workplace fatigue, the poorer the emotional health, and vice versa. There was no correlation between work adjustment measures and workplace fatigue. However, work adjustment measures were related to emotional health and could predict it, with more adjustments correlating to better emotional health. Finally, in terms of stress coping, the use of emotional expression methods showed a negative correlation with emotional health and workplace fatigue, indicating that the more these methods were employed, the better the emotional health and the lower the workplace fatigue. Leisure activities and online gambling categories can reduce both personal and work-related fatigue. However, online gambling and physical gambling can increase symptoms of depression and anxiety among gaming employees, while online gambling can also increase stress symptoms. The study recommends that gaming companies and relevant departments provide on-the-job training for employees, enhance skills to cope with stress, establish mental health indicators, and regularly evaluate employees to implement individualized measures aimed at improving workplace fatigue and emotional health. The results of this study can provide valuable insights for policymakers and the management of gaming establishments in Macau to formulate relevant policies to reduce workplace fatigue among gaming employees and improve their emotional health, thereby enhancing their working environment and career development. 博彩業一直是澳門的龍頭產業，是澳門主要的職業行業之一， 2023年博彩從業員佔澳門就業人數18.2%，是澳門主要的就業勞動人口。研究顯示博彩從業員的工作壓力很大，而工作壓力會直接影響職業疲勞，也可能引發焦慮和抑鬱。職場疲勞和情緒健康不但影響個人生理和心理問題，還會影響其家庭和工作，以及人際關係，因此，他們的情緒健康和職場疲勞值得社會大眾關注。 本研究旨在探討博彩從業員工作調整措施，壓力應對方法、情緒健康、職場疲勞以及它們的相關性。研究以澳門博彩從業員為研究對象，採用量化方式進行，以非隨機抽樣方法，在2023年10月至12月向澳門六大博企管理人員發送電子問卷，最終回收問卷563份，男性佔45.6%，女性佔54.4%。研究使用SPSS 23 統計軟件進行量化分析，資料首先作描述性統計分析、再以獨立樣本t檢定、其次以單因數變異數（ANOVA）、最後以Pearson相關係數和迴歸分析檢定數據。 研究發現，博彩從業員的性別、年齡、教育程度、婚姻狀況、輪班模式和每月薪酬與壓力應對方法呈現差異。性別、年齡、教育程度、婚姻狀況、居住狀況、工作年資、工作職位和每月薪酬與職場疲勞有差異。年齡、教育程度、婚姻狀況與情緒健康有差異。博彩從業員在工作調整上，放親子假最多佔67.1%，其次放無薪假佔54.2%，被調職佔9.8%。個人疲勞平均數為40.90±23.125分及工作疲勞平均數40.62±21.405分最高，其次是服務對象疲勞平均數為36.65±21.056分，工作過度投入平均數為24.22±18.987分。抑鬱平均數為10.60±8.974分屬於輕度至中度水平；焦慮平均數為11.26±8.567分，屬於中度至重度水平；壓力平均數為9.96±8.418分，屬於正常至輕度範圍。當中有33.9%的人士的焦慮徵狀顯示出嚴重和非常嚴重程度，而有16%的受訪者的抑鬱徵狀呈現嚴重和非常嚴重程度。我們還發現，博彩從業員的職場疲勞與情緒健康存在正相關，職場疲勞程度越高，情緒健康越差，反之亦然。工作調整措施與職場疲勞沒有相關性。然而工作調整措施與情緒健康存在關係，並可以預測情緒健康，工作調整越多，情緒健康越好。最後，在壓力應對上，傾訴類別與情緒健康和職場疲勞呈現負相關，並有預測效果，亦即傾訴類別使用的方法得分越多，情緒健康越好，職場疲勞也越低。休閒類別和網上博彩類別能減低個人和工作疲勞。網上博彩類別、實體博彩類別會增加博彩從業員的抑鬱、焦慮徵狀，而網上博彩類別會增加壓力徵狀。研究建議博企及相關部門為員工提供在職培訓，加強技能應對壓力，制定精神健康指標並定期為員工評估，因應個別化推出措施，改善職場疲勞和情緒健康。 本研究的結果能為政策制定者和澳門幸運博彩娛樂場管理部門提供有價值的見解，制定相關政策，以減低博彩從業員的職場疲勞和改善他們的情緒健康，改善他們的工作環境和職業發展。

Balancing Economic Development and Environmental Protection in Macau Based on the United Nations Sustainable Development Goals - Ho, Nga Lai (2024)
Macau is facing problems on how to moderately diversify its economy, improving its air quality, water quality, and waste management, and improving its biodiversity. The research aim is to investigate and propose how Macau can achieve moderate economic diversification, environmental protection, ecological protection and preservation in line with sustainable development goal 8, 9, 12, 13, and 15. Using documentary analysis, extensive literature review, and analyzing of Macau situation, the following findings are suggested: - Research and development using the university institutions on areas ranging from hospitality and tourism management, telecommunication engineering, electrical & electronic engineering, automation and control, computer science and engineering, transportation science and technology, nanoscience & nanotechnology, instrument science and technology, biomedical engineering, as well as relevant infrastructure, policy and financial support, - Talent attraction for specialised industries with stringent requirements due to the limited capacity of Macau, - Financial market development for financing, capital accumulation, and wealth management, - Focus on tourism-related industry, then big data and technology leveraging Hengqin, and then financial industry for supporting, - Better method to reduce air pollution through more energy efficient industrial facilities with less greenhouse gases emission, - Better water quality and pollution management through water pollution management, water resource conservation, the development of environmentally friendly technologies to control water pollution, - Polluter pay law such as Japan's Basic Environment Law, Waste Management and Public Cleansing Law, - Producer’s responsibility law such as home appliance recycling law, containers and packaging recycling law, and - A framework for biodiversity protection including a combination of legislative, technical, and community-based initiatives, as well as a comprehensive wildlife protection law.

A STUDY ON THE PERCEPTIONS AND PRACTICES OF GENDER EQUALITY AND GENDER STEREOTYPES AMONG KINDERGARTEN TEACHERS IN MACAO - Lao, In Kam (2024)
This study employs a qualitative research method to explore kindergarten teachers' perceptions of gender stereotypes, their views on gender equality education, and how these concepts are implemented in their teaching practices. Additionally, it analyses the challenges faced in promoting gender equality education in Macao and offers relevant recommendations. The study participants comprised eight in-service kindergarten teachers (four males and four females) working at four kindergartens in Macao. Through semi-structured in-depth interviews, the study delves into the teachers' experiences and perspectives on implementing gender equality education in kindergartens. The study concludes with the following findings: 1. Teachers have a basic understanding of gender equality; however, influenced by societal traditions and family cultures, gender stereotypes still persist in their teaching. While teachers can recognise and reflect on the presence of these stereotypes and understand the core concepts of gender equality education, they still lack a comprehensive grasp of its substantive content. 2. When practising gender equality education, teachers exhibit varying degrees of gender stereotyping and bias. Male teachers, in particular, display more evident gender bias compared to female teachers, especially in their disciplinary approaches towards male and female students, with male teachers being more stringent with boys. However, no significant gender differences were observed in classroom performance, behavioural discipline, academic achievements, or task distribution. This suggests that teachers treat students of both genders relatively equally, with no clear link to their personal backgrounds. 3. Regarding gender equality and social status, male teachers generally express higher satisfaction levels than female teachers. Male teachers believe that gender equality has been achieved, whereas female teachers feel that women remain at a disadvantage in terms of work conditions and family responsibilities. 4. Teachers identify several challenges in promoting gender equality in education in Macao. This includes deep-rooted societal cultures, insufficient awareness and understanding of gender equality education among the government, the public, teachers, and parents; gender stereotypes in textbooks and school environments; the lack of gender-related content in textbooks; and the gender imbalance among kindergarten teachers, with a marked shortage of male teachers. 5. Teachers suggest that the government should collaborate with experts to provide more relevant teacher training or community seminars for teachers and the public. These initiatives should aim to challenge gender stereotypes, re-evaluate the content of textbooks and the setup of school environments, and promote the feasibility and necessity of male kindergarten teachers. Based on the study's findings, the researcher offers several recommendations for advancing gender equality education in Macao, providing concrete ideas and reasonable references. It is hoped that these suggestions will serve as valuable references for future related research. 本研究採用質性研究法，旨在探討幼稚園教師對性別刻板印象的看法、性別平等教育的理念以及在教學中實踐的情況，並分析在澳門推行性別平等教育所面對的挑戰及相關建議。研究對象來自澳門四所幼稚園的八位在職幼稚園教師（4男4女），研究透過半結構式深度訪談，深入探討教師在幼稚園推行性別平等教育中的經驗和觀點。本研究得出以下結論： （一） 教師對性別平等已有基本概念，但因受到社會傳統文化及個人家庭文化的影響，在教學中仍存在性別刻板印象。教師能察覺和反思這些刻板印象的存在，並瞭解性別平等教育的基本核心概念，然而對其實質內容的理解仍有不足之處。 （二） 在實踐性別平等教育時，教師表現出不同程度的性別定型及性別偏見。其中，男教師相較於女教師表現出更為明顯的性別偏見，尤其體現在針對兩性的學生的管教方式上，男教師對男生的態度較為嚴厲。然而，教師在課堂表現、行為紀律、學業成績、職務分配等方面則未顯示出顯著的性別差異，能相對平等地要求及對待兩性的學生，這與教師的個人背景因素並沒有明顯關聯。 （三） 在兩性平等與社會地位問題上，男性教師的滿意度普遍高於女性教師。男性教師認為兩性地位已達至平等，而女教師則認為在工作待遇和家庭層面上，女性仍處於較為不利的地位。 （四） 教師認為在澳門推行性別平等教育面臨的挑戰包括：根深蒂固的社會文化，政府、大眾、教師及家長對性別平等教育的關注和認知不足；教科書及學校環境設置存在的性別刻板印象，以及教科書中缺乏性別議題內容；幼稚園教師的性別比例失衡，男教師明顯偏少。 （五） 教師建議政府需要與專家合作，提供更多相關的師資培訓或社區講座，供教師及市民參與，並以突破性別刻板印象為目標，重新審視教科書及學校環境的設置，同時加強宣傳男性幼稚園教師的可行性及必要性。 基於上述研究結果，研究者對澳門性別平等教育的推行提出了若干建議，並提供了具體的思路和合理的參考依據。期望這些建議能為未來相關研究提供參考。

Examining Primary School Teachers’ Pedagogical Expertise and Implementation of Differentiated Instruction in Macao: A Mixed-Methods Investigation - Leong, Hio Cheng (2024)
As the number of students with diverse learning needs continues to rise in Macau, teachers face numerous challenges in addressing individual differences in the classroom. This research aims to explore the awareness and implementation of differentiation instruction among Macau primary school teachers, as well as the challenges encountered in its practice. Differentiation instruction is an instructional approach that seeks to cater to the individual learning needs of students by adapting teaching methods, content, and assessment strategies. It involves recognizing and responding to the readiness, interest, and learning profile of students within a classroom. This study employs a mixed-methods approach, primarily utilizing questionnaires to assess the knowledge and skills of Macau primary school teachers in both regular and inclusive classrooms regarding differentiation instruction. Additionally, semi-structured interviews will be conducted with a purposive sample of eight professional Macao primary school teachers who have implemented differentiation instruction. The findings were organized and analyzed, revealing as follows: （1） Macau Primary School Teachers' Knowledge and Skills in Differentiated Instruction: The motivation of Macau primary school teachers to receive training in differentiated instruction is relatively low. However, most teachers have gained a basic understanding of the definition and concept of differentiated instruction through participation in professional development courses and school training. Teachers also accumulate experience in teaching practice, enhancing their ability to implement differentiated instruction. （2） Models of Differentiated Instruction Implementation by Macau Primary School Teachers: Macau primary school teachers primarily reflect students' learning profile through basic background information, classroom observation, and reviewing assignments and tests. When designing teaching content, teachers adjust according to learning profile, personal interests, and readiness, aligning with the differentiated instruction practices. （3） Macau Primary School Teachers' Attitudes Toward Implementing Differentiated Instruction: Most Macau primary school teachers have a positive attitude towards differentiated instruction, agreeing that adjusting teaching according to individual student needs can enhance learning outcomes and motivation. However, they face numerous challenges during implementation. （4） Challenges Faced by Macau Primary School Teachers in Implementing Differentiated Instruction: The educational policies in Macau pose challenges to the implementation of differentiated instruction. Schools lack clear guidelines, teachers face heavy workloads, have limited knowledge and experience in differentiated instruction, parents have insufficient understanding of the concept and purpose of differentiated instruction, and unbalanced educational resource limit its effective implementation. （5） Favorable Conditions for the Development of Differentiated Instruction: Positive progress in the allocation of human resources, resource distribution, and tiered assessments in schools, as well as cooperation between families and schools, has promoted the successful implementation of differentiated instruction. Based on the research findings, specific recommendations are provided offer recommendations to optimize teaching effectiveness and better address the diverse learning needs of students, ultimately ensuring optimal learning outcomes. 隨着本澳有着不同學習需要的學生的數量漸增，教師在課堂上面對不少困難與挑戰，因此教師關顧學生間個別差異不容忽視。本研究旨在瞭解澳門小學教師對於差異化教學概念的認知程度、如何作教學實踐，及當中遇到的問題。 根據研究目的，本研究以「詮釋主義」作理論框架，採用混合研究法，「以質性研究為主，量化研究為輔」，先以問卷調查瞭解本澳小學普通班和融合班教師對差異化教學的知識與技能，繼而透過半結構訪談法，並經立意採樣，選取曾實踐差異化教學的小學教師進行訪談，整理和分析研究結果顯示： （1） 本澳小學教師對差異化教學的知能程度：澳門小學教師對差異化教學的培訓動機較低。通過參加專業發展課程和校本培訓，大多數教師對差異化教學的定義和概念有一定程度的掌握。教師亦可在教學實踐中累積經驗，提升實施差異化教學的能力。 （2） 本澳小學教師實施差異化教學的模式：澳門小學教師查閱學生的基本背景資料、觀察課堂學習進度，以及通過批改作業和測試檢視學生能力，主要反映學生的學習水平。教師在設計教學內容時，根據學習風格、個人興趣和學習準備度進行調整，符合差異化教學實踐形式。 （3） 本澳小學教師對實施差異化教學的態度：多數澳門小學教師對差異化教學持積極態度，認同根據學生個別需求進行教學調整能提升學習效果和動機，但在實施過程中面臨諸多挑戰。 （4） 本澳小學教師在實施差異化教學時面對的困難：澳門的教育政策對差異化教學實施造成阻力，學校缺乏清晰的指導方針，教師面臨繁重的工作負擔，教師對差異化教學的知識與經驗有限、家長對差異化教學的概念與目的理解不夠，和有限的教學環境和統一教材，限制了差異化教學的有效實施。 （5） 有利發展差異化教學條件：學校在人力資源配置、資源調配和評估分層等方面的積極進展，以及家庭與學校的密切合作，推動了差異化教學的成功實施。 基於研究結果，提出具體建議，從而讓本澳的教育工作者有所參考，使得學生能獲得最適合的學習方式。

EXPLORATION OF THE APPLICATION OF MIND INTERPRETATION TRAINING IN SOCIAL BEHAVIOR OF STUDENTS WITH AUTISM - Ng, Nga Wai (2024)
Nowadays, inclusive education has become increasingly popular in various places. And it becomes more and more common for students with special education needs to be placed in general education environments. However, students with special education needs often have problems getting along with their classmates because of their own physical and mental disabilities and behavioral traits. In schools, social interaction has always been a major issue for students with autism spectrum disorder to integrate into the group. Due to their physical limitations or internal psychological differences, they often encounter difficulties in interacting with classmates. The researcher of this study is a primary school resource teacher in an integrated school. During the teaching process, she found that students with autism spectrum disorder in regular classes have some difficulties in adapting, especially in getting along with others . Therefore, the researcher hopes to improve their social behavior through Mind-Reading training, so that they can develop well in interacting and socializing with others. This study intends to explore the effect of Mind-Reading training on improving the mind reading ability and social interaction ability of five autistic spectrum disorder students in primary school, and conduct research and discussion on their ability to understand others and social interaction . Comparison and data analysis were conducted through pre-test, six-session of Mind-Reading training course, Mind-Reading learning record form filled in by the researcher, and post-test. The pre-test and post-test tools include: "Vinlan Adaptive Behavior Scale 3 (Chinese version) - Children's Version" filled out by the parents of the research participants, interviews with the head teachers of the research participants, and a theory of mind test completed by the research participants (ToMTB test). The study concluded as follows: 1.Children with autism spectrum disorder can improve the ability to understand others after receiving Mind-Reading training. 2.Children with autism spectrum disorder can show the improvement in social interactions after receiving Mind-Reading training. In this study, the researcher hopes to improve autistic students' ability to understand other people 's thoughts and improve their social interaction through Mind-Reading training, so that autistic spectrum disorder students can integrate into ordinary classes and get along with their classmates. They try to use Mind-Reading training to explore whether this method is effective. And the conclusion confirms that Mind-Reading training can improve autistic spectrum disorder students' abilities to understand others , improve their social interactions , and promote social relationships with their classmates. It is recommended that in future research on Mind-Reading training in Macao, the teaching content should be combined with social interaction skills and life experience. In addition, we will increase the understanding of peer perceptions, observations of class entry or recess time, and extend the follow-up time to make the research more complete. 現今，融合教育在各地已漸趨普及化，特殊教育需要學生安置於普通教育環境是越來越常見的現象。然而，特殊教育需要學生因自身的身心障礙及行為特質，導致他們與同儕相處時經常出現問題。在學校，社交互動一直是自閉症譜系障礙學生融入群體的一大重點議題，他們因自身的生理限制或心理內在的差異，導致其在與同儕互動時常遇到困難。本研究的研究者為融合學校的小學資源教師，在教學的過程裏，發現就讀於普通班的自閉症譜系障礙學生在適應上出現了一些困難，特別是與人相處方面，因此，研究者希望能透過心智解讀訓練來改善他們的社交行為，讓他們能在與他人互動和社交方面獲得良好的發展。 本研究擬探討心智解讀訓練對提升五位低小自閉症譜系障礙學生的心智解讀能力與社交互動能力的效果，對他們理解他人的能力及社交互動方面進行研究和討論，通過前測、六節的心智解讀訓練課程、研究者填寫的心智解讀學習記錄表、後測來進行比較及資料分析。前測及後測工具包括：由研究參與者之家長填寫的「文蘭適應行為量表第3(中文版)-兒童版」、研究參與者之班主任訪談，以及研究參與者完成的心智理論測驗(ToMTB測驗)。 研究得出的結論如下： 1.自閉症譜系障礙兒童在接受心智解讀訓練後理解他人的能力有所提升。 2.自閉症譜系障礙兒童在接受心智解讀訓練後在社交互動方面有相對的改善。 本研究中，研究者期望透過心智解讀訓練提升自閉症譜系障礙學生理解他人想法的能力，以及改善其社交互動，使自閉症學生能融入普通課室，與同齡人相處，所以嘗試透過心智解讀訓練來探討此方法是否有效，而結論證實心智解讀訓練能提升自閉症譜系障礙兒童理解他人的能力，以及改善他們的社交互動，促進與同儕之間的社交關係。 建議本澳未來的心智解讀訓練研究中，教學內容結合社交互動技巧及生活經驗。另外，增加了解同儕觀感、入班或小息時間之觀察，以及延長追蹤時間，以令研究變得更為完善。

Study of the Policies Regulating Juvenile Delinquency in Macau - Leung, Weng Tong (2024)
This thesis first discusses the situation and trends of juvenile crime in Macau in recent years, then reviews the current measures of Macao's juvenile criminal justice system, and the existing policies and regulations on juvenile delinquency, to see what possible impacts of the implementation in preventing juvenile delinquency in Macau. Through analyzing their behavior and causes of juvenile crime in Macau and the youth crime prevention policies in both Macau and neighboring regions. Analyzing the existing policies and regulations on juvenile delinquency, explore the effectiveness of the main existing measures and policies to control this problem, and then make suggestions for control measures based on the future trend of the problem. Throughout the research, it is found that the causes of the problem are not only affected by the subjective psychological state of teenagers, but also affected by differences in social status, socioeconomics, family and school and other external factors.

探討澳門普通班幼稚園教師對融合教育的態度及面對融合教育生的困難和挑戰 - Tam, Hio U. (2024)
現時澳門全力推行融合教育，促使融合教育逐漸普及化，幼稚園教師是學 前融合教育實踐的主力軍，因此在融合教育發展中，幼稚園教師的態度是重 要的因素。本研究以澳門普通幼稚園教師對融合教育的態度及面對融合教育 生的困難和挑戰為目標，透過對七位澳門普通幼稚園教師進行訪談，瞭解研 究對象對融合教育的認知與瞭解、情感體驗與支持度、行為傾向及面對融合 教育生的困難和挑戰。 從研究結果發現：在教師態度的認知分析結果中，有超過一半的受訪教師 對融合教育的認知都能夠符合融合教育的精神及理念，但是，仍然有少部分 受訪教師的認知是偏離融合教育的理念。在態度的情感分析結果中，過半數 的受訪教師對融合教育出現被動消極的負面情感，亦有近過半數教師主動積 極接納融合教育。值得一提的是，教師對融合教育的情感體驗會發生動態轉 變的特徵，當中包括教師初期對融合教育的情感是正面主動的或負面抗拒 的，經過對自身實踐融合教育後，教師會對融合教育的情感形成轉變，初期 對融合教育的情感是正面積極的教師可能因為在實施融合教育上遇到不同的 困難或問題從而對融合教育的接納度由主動積極轉變為被動消極。另一方面 初期對融合教育的情感是負面消極的教師因為在實踐融合教育後積極報名參 加與融合教育有關聯的課程，提高自我的能力，有實踐的經驗累積增強了實 施融合教育的信心後對融合教育產生了由被動消極變為主動積極的情感轉 變。在行為傾向來看，大部分受訪教師會以個性化針對性教學方式對融合生 進行教學，同時亦會調整教學環境、教學準備、評核標準調適，亦注重與家 長及駐校社工的合作溝通。 最後結合本研究結果，分別對回應研究問題提出具體的建議，旨在為政 府、教育機構、教師和學生提供參考，以促進澳門的融合教育。 Macao is fully committed to promoting integrated education and promoting the gradual popularization of integrated education. As the frontline workers of education, kindergarten teachers’ attitude towards integrated education is the key to the success or failure of the development of integrated education. This study aims at the attitudes of Macao ordinary kindergarten teachers towards inclusive education and the difficulties and challenges faced by students in inclusive education. Through semi-structured interviews with seven Macao ordinary kindergarten teachers, we have an in-depth understanding of the research subjects’ cognition and understanding of inclusive education. Understanding, emotional experience and support, behavioral tendencies, and the difficulties and challenges faced by students in integrated education. From the research results, it is found that: from a cognitive perspective, most of the interviewed teachers’ cognition of inclusive education is in line with the spirit and concept of inclusive education, but there are still some interviewed teachers whose cognition of inclusive education deviates from the spirit and concept of inclusive education. Spirit. At the emotional level, more than half of the teachers surveyed have passive and negative feelings towards inclusive education, while nearly half of the teachers actively accept inclusive education. It is worth mentioning that teachers’ emotional experience of inclusive education will undergo dynamic changes, including whether teachers’ initial emotions towards inclusive education are positive or negative. After practicing inclusive education, teachers will have different feelings about inclusive education. Emotions change. Teachers who initially had positive emotions towards inclusive education may change their acceptance of inclusive education from proactive to passive because they encounter different difficulties or problems in implementing inclusive education. On the other hand, teachers who had negative feelings towards inclusive education in the early stage have actively enrolled in courses related to inclusive education to improve themselves after practicing inclusive education. The accumulation of practical experience has enhanced their confidence in the implementation of inclusive education. There was an emotional change from passive to active. In terms of behavioral tendencies, most of the teachers interviewed will teach integrated students with personalized and targeted teaching methods. They will also adjust the teaching environment, teaching preparation, and assessment standards, and also focus on cooperation with parents and school social workers. communicate. Finally, combined with the results of this study, specific suggestions are put forward to respond to the research questions, and some reference opinions are provided for the government, schools, teachers, etc., in the hope of promoting Macao's integrated education to further progress.

FUTURE OF MACAU GAMING INDUSTRY AFTER THE NEW GAMING LAWS: A study on the development of the non-gaming initiatives - Liao, JianFeng (2024)
The development of non-gaming facilities will shape the future of Macau's gaming industry. These amenities include food and retail, which have become vital in increasing customer satisfaction and loyalty since they offer other services other than gambling. In the future, as casinos shift their strategies to focus on non-gaming aspects, it will be crucial to build detailed profiles of casino visitors based on how much they spend on non-gaming products and services. Changes in the legal framework of the gaming industry and shifts in market demand have forced casinos to turn to other forms of tourism and cultural services, address legal requirements, and minimize risk. Furthermore, external factors such as stringent gaming laws, fiscal measures, and increasing competition from other regional gambling jurisdictions, including Singapore and the Philippines, threaten the casino gaming business. In response to these threats, Macau's casinos are paying more attention to cooperation within the tourism industry and enhancing their non-gaming offers to sustain their market position and grasp new options. Therefore, the future of Macau's gaming industry will be determined by the strategic planning of its future developments, focusing on non-gaming activities, target visitors, compliance with the new laws, and the ability to overcome external challenges to ensure market competitiveness.

THE RELATIONSHIP BETWEEN INTERNALIZING PROBLEMS, GENDER AND ACADEMIC ACHIEVEMENT FROM THE PERSPECTIVE OF BOTH PARENTS AND HIGH SCHOOL STUDENTS - Sou, Fernandes; Marcelo, Joel (2024)
The current study aimed to analyse the differences in the internalising problems including anxious/depressed, withdrawn-depressed and somatic complaints, from the perspective of parents and high school students. Considering varying levels of academic achievement. Additionally, the gender differences in the level of internalising problems will also be examined. Finally, we analysed the different perspectives of parents and high school students according to internalising problems. The Achenbach System of Empirically Based Assessment (ASEBA) was used for data collection in Macao. The sample consisted of 698 high school students (316 males and 382 females). There were no significant differences in internalising problems according to three levels of academic achievement (low, average and high) from the perspective of parents and high school students. Furthermore, from the high school students' perspectives, adolescent females present more interesting problems than males. Finally, the findings indicate a low agreement between parents and students concerning internalising problems. It is suggested that parents should learn and explore different parenting styles in order to reduce their children's internalising problems.

Customer Adoption of Internet Banking Service in Macau- A quantitative approach based on Customer Survey - Wong, Tsz Ying (2024)
This study investigates the factors influencing customer adoption of Internet Banking Services in Macau through a quantitative approach utilizing a customer survey. As digital banking continues to evolve, understanding the determinants of adoption is critical for financial institutions seeking to enhance their offerings and engage with diverse customer segments. A sample of over 100 respondents was surveyed, capturing essential demographic information, technological proficiency, and attitudes toward Internet banking. The analysis employed descriptive and inferential statistical techniques, including regression analysis and factor analysis, to identify key relationships and underlying factors influencing adoption. The findings reveal that perceived ease of use, security concerns, and prior banking experience significantly affect customers' likelihood of adopting Internet banking services. Additionally, demographic variables such as age, occupation, and nationality emerged as important predictors of customer attitudes toward online banking. The results of this research provide actionable insights for banks and financial institutions in Macau, highlighting the need for targeted marketing strategies and enhanced user experience to foster greater adoption of Internet banking. This study contributes to the existing literature on digital banking adoption in the region and serves as a foundation for future research in this dynamic field.

KINGERGARTEN TEACHER’S ATTITUDES TOWARDS CHINESE EARLY LITERACY IN MACAU - Cheang, Pui U. (2024)
This study aims to explore the attitudes of kindergarten teachers in Macao towards early Chinese literacy. Using semi-structured interviews and purposive sampling, eight kindergarten teachers from seven different private schools in Macao were invited as study participants. Based on the interview data, the study further understands teachers' cognition, emotional experiences, and support towards early Chinese literacy, as well as their behavioral tendencies in practicing early Chinese literacy. The research findings indicate: (1) Kindergarten teachers have insufficient cognition of early Chinese literacy, mainly due to a lack of awareness and understanding of early Chinese literacy. (2) From the perspective of emotional experiences and support, all interviewed teachers support the development of early Chinese literacy at the kindergarten stage. (3) Kindergarten teachers exhibited positive, negative, and neutral emotions in the process of organizing early Chinese literacy, with emotions influenced and transformed by students' performance, from negative to positive emotions. (4) Kindergarten teachers face shortages of resources, such as teaching aids and training, in practicing early Chinese literacy. Based on the study results, recommendations were made for kindergarten teachers, the government, and schools. It is hoped that schools can provide sufficient teaching materials for early Chinese literacy and conduct relevant research activities. Kindergarten teachers should enhance their professional knowledge of early Chinese literacy. Additionally, the Macao government should formulate related policies and training courses for early literacy, enabling kindergarten teachers to design appropriate teaching curricula. 本研究旨在探討澳門幼稚園教師對中文早期讀寫的態度，研究採用半結構式訪談，透過立意取樣的方式，邀請到來自本澳七所不同的私立幼稚園的八位前線幼稚園教師作研究对象，依據訪談所獲得的資料，深入瞭解教師們對中文早期讀寫的認知，其情感體驗與支持度，以及在實踐中文早期讀寫的行為傾向。 研究結果顯示：（一）幼稚園教師對中文早期讀寫的認知不足，造成認知不足的原因主要有幼稚園教師缺乏對中文早期讀寫的認知。（二）從情感體驗及支持度來看，全部受訪教師都支持在幼稚園階段發展中文早期讀寫。（三）幼稚園教師在組織中文早期讀寫的過程，會呈現出正面、負面及中立的情緒，而情緒表現亦會受到學生的表現而發展轉變，由消極的情緒轉化為正面情緒。（四）幼稚園教師在實踐中文早期讀寫會受到資源短缺，如：缺乏教學用具，欠缺中文早期讀寫的培訓。 本研究依據研究結果，研究者對幼稚園教師，政府及學校等提出相關建議，期望學校能夠提供充足的中文早期讀寫教學材料，以及開展相關的教研活動，而幼稚園教師應提升對中文早期讀寫的專業知識。同時，澳門政府應該制定相關早期讀寫政策及培訓課程，使幼稚園教師能設計適切的教學課程。

普通班教師在融合教育實踐中的困擾與挑戰研究 - Un, Chi San (2024)
融合教育作為當今教育改革的重要方向，旨在為所有學生提供公平的學習 機會，尤其是為特殊需求學生融入主流教育創造條件。儘管融合教育的概念已 經被廣泛認同，但在實際操作中，普通班教師在面對多樣化的學生需求時，仍 面臨著許多挑戰和困擾。目前已有的研究主要集中在融合教育的理論探討和政 策分析上，對於第一線教師在融合教育實踐中的實際困境和應對策略研究較 少，尤其是在澳門這樣一個多元文化背景下，相關的實證研究更為稀缺。因 此，深入探討一般班教師在融合教育實踐中的困擾與挑戰，不僅有助於完善融 合教育的理論體系，也能為實際教學提供強大的支持與指導。本研究旨在探討 普通班教師在融合教育實踐中的困擾與挑戰之現況，並進一步分析不同背景變 項的差異情形，為進一步推動融合教育實踐提供參考依據。本研究採用問卷調 查的方式，以自編之「小學普通班教師在融合教育實踐中之困擾問卷」進行量 化資料蒐集，以任職於澳門小學之普通班教師為研究對象，取得有效問卷數 150 份，有效回收率為 97.4%。問卷調查所得之資料以描述性統計、項目分析、 探索性因素分析、信度檢驗、獨立樣本 t 檢驗、和單因素方差分析等進行資料 分析。本研究得出以下結論： 一、普通班教師在融合教育實踐中之困擾情形為中等偏高程度，以「特教知 能」層面的教學困擾程度最高，而在「班級經營」層面的教學困擾程度最 低。 二、不同性別之普通班教師在融合教育實踐中整體教學困擾情形達顯著差異， 其中男性教師在面對融合教育的挑戰時，感受到的困擾更為強烈，男性教 師在「特教知能」、「班級經營」、「課程與教學」、「親師合作」和「支援系 統」五個層面的困擾得分都高於女性教師。 三、不同學校類型之普通班教師在融合教育實踐中整體及各分向度教學困擾情 形達顯著差異，私立學校教師在融合教育實踐中的整體及各分向度的教學 困擾皆顯著高於公立學校教師。 四、不同學校類型之普通班教師在融合教育實踐中整體及各分向度教學困擾情 形達顯著差異，私立學校教師在融合教育實踐中的整體及各分向度的教學 困擾皆顯著高於公立學校教師。 五、任教不同班級人數之普通班教師在融合教育實踐中整體教學困擾情形達顯 著差異，班級人數在20人以上的教師困擾程度高於班級人數在20人以下的 教師。 基於以上研究，本文提出以下建議：第一，加強教師特教知能培訓，幫助 教師掌握因應身心障礙學生需求的專業知識和技能；第二，增加資源和政策支 持，提升普通班教師在融合教育中的教學效能，確保所有學生都能獲得公平的 教育機會；第三，合理配置班級人數，提升整體教學品質及學生的學習效果； 第四，促進親師合作，提升教學質量，減輕教師的工作壓力；第五，完善支援 系統，政府和學校應提供全面的支援服務，確保教師在整合教育實踐中能得到 充分的支持和幫助。

ORGANISATIONAL CULTURE, COMMITMENT, AND TURNOVER IN MACAO - Ho, Ka Lon (2024)
The present study explored the effect of organisational culture on turnover intentions of full-time workers in financial sector in Macao, and the mediating effect of organisational commitment. The following research questions were examined in this study: (1) how do organisational cultural values affect workers’ turnover intentions? (2) what is the role of organisational commitment in the relationships between organisational cultural values and turnover intentions? A cross-sectional design was used by applying a self-response bilingual (Chinese and English) questionnaire to a sample of 123 full-time workers in the financial sector in Macao. Results show that the organisational culture factors with a stronger impact on turnover are entrepreneurial, hierarchical and team cultural values. Entrepreneurial values (ßa=-.323, p=.004), followed by team values (ßa=-.260, p=.011), show the strongest effects and a negative relationship with turnover intentions. Meanwhile, hierarchical values (ßa=.208, p=.012) show the weakest effect and a positive relationship with turnover intentions. Regarding the affective commitment in the relationships between organisational cultural values and turnover intentions, the values with the strongest impact were entrepreneurial, followed by hierarchical and team values. Affective commitment fully mediates the effects of entrepreneurial and hierarchical values and partially mediates the effect of team values on turnover intentions. Regarding theoretical implications, our findings seem consistent with the social exchange theory. Regarding practical implications, we discuss some strategies to promote entrepreneurial and team values and prevent hierarchical values as strategies to increase affective commitment and decrease turnover in the financial sector.

The Factors Affecting Customer’s Purchase Intention and Preference towards Quiet Luxury Fashion Brands Focusing on Generation Z (2024)
The quiet fashion trend is becoming one of the most common fashion trends among Gen Zs. Quiet normally means not making noise. Within the fashion industry it refers to style of luxury fashion that is understated, subtle, and free from obvious branding. The study that was reported in this paper is about the factors that affect consumer preference and purchase intention towards quiet luxury fashion products, with a focus on the Gen Z population. This research is important since it will help in outlining how different factors affect consumer purchase intention and preference towards various products within the fashion industry. Thus, enabling decision-makers and marketers to make effective decisions. The research method that was used was quantitative research with primary and secondary data. The primary data was collected through a survey questionnaire, which included 300 responses. The research found that social media influencers, brand collaboration, and status value are among the factors that have a significant relationship with consumer preference and purchase intention toward the quiet luxury brand among Gen Zs. Also, the research found that sustainability value does not have a direct impact on consumer preference and purchase intention for quiet luxury products. Hence, the research concluded that social media influencers, brand collaboration, and status value are part of the factors that have a significant impact on consumer preference and purchase intention.

LONGING FOR THE PAST IN VIEW OF THE FUTURE: A PHILOSOPHICAL ANALYSIS OF NOSTALGIA AS AN ACT OF HOPE THROUGH HEIDEGGER’S EXISTENTIALIST PHILOSOPHY - Wong, Ka Leng (2024)
This research investigates the philosophical question of whether nostalgia, often viewed as irrational and unproductive, truly hampers the present. While some philosophers consider it an obstacle to progress, this study highlights its positive and hopeful aspects. With a focus on Heidegger’s existentialist philosophy, the link between nostalgia and the concept of “home” as a metaphysical sanctuary is explored. Using a phenomenological approach, this research reveals how nostalgia intertwines with hope, demonstrating that nostalgia can be an act of hope. The openness of Dasein allows humans to experience their presence in the world. Mood reveals one's current state of being, with nostalgia being one such mood. Nostalgia discloses the objects of longing, ultimately rooted in the notion of “home.” At its foundation, this exploration is fundamentally tied to the essence of hope. This leads to a renewed interpretation of nostalgia as a crucial part of growth, highlighting its significance in life. Moreover, the thesis advocates for using nostalgia as an instrument to foster hope, effectively bridging the individual with hope itself.

SURVEY ON MACAO KINDERGARTEN TEACHERS’ DEMAND FOR AND SATISFACTION OF RESOURCE TEACHERS' SUPPORT IN INCLUSIVE EDUCATION (2024)
Inclusive preschool education in Macao is in its infancy and resource teachers (RTs) play a pivotal role in supporting kindergarten teachers. This study aimed to investigate Macao kindergarten teachers’ demand for and satisfaction of RTs’ support services in inclusive education. Using a mixed method design, the researcher administered a self-developed questionnaire (including a need scale and a satisfaction scale) to 70 kindergarten teachers and interviewed four kindergarten teachers. Based on the quantitative and qualitative data analyses, results showed that: 1) Kindergarten teachers had a high demand for RTs’ support services no matter whether they had previously received such services, and kindergarten teachers who had received RTs’ support services (N = 43) were moderately satisfied with their support services. 2) There was a moderate correlation between the demand and satisfaction scales and respective dimensions. The need level was significantly higher than the satisfaction level on all six dimensions. Teachers reported highest scores on both their need and satisfaction on the dimension of Cooperation, Interaction, and Communication. 3) Kindergarten teachers’ need level increased significantly when the number of inclusive students taught during the school year was three or more, compared to a number below three. Teachers’ satisfaction level did not differ significantly across any demographic variables. 4) Kindergarten teachers were satisfied with RTs’ support services in terms of improved classroom management by handling inclusive students’ problem behaviors, pull-out instruction, test-taking assistance, reduction of IEP workload, and the provision of professional support to parents. 5) Kindergarten teachers were dissatisfied with RTs’ support services in terms of cooperative interaction and communication, co-teaching, assessment of inclusive students’ performance, and supervision of RTs' work. Based on the kindergarten teachers’ expectations for RTs’ support services, the implications of this study were discussed to provide meaningful and evidence-based directions for the research and practice of inclusive preschool education in Macao. 澳門學前融合教育處於發展階段，資源教師在支持幼稚園教師學前融合教育中起著舉足輕重的作用。本研究旨在探究澳門幼稚園教師對資源教師支援服務的需求及滿意度情況。通過問卷調查法和半結構訪談法相結合的混合研究方法，研究者採用自編問卷調查了澳門70名幼稚園教師並訪談了4名幼稚園教師，其中問卷的需求和滿意度量表均分別由六個維度組成，包括：「專業知能」、「擬定和執行個別化教育計劃」、「教學資源與課程」、「成績評量」、「合作互動溝通」、「家長溝通」。量化及質性數據分析結果顯示：1）無論之前是否接受過資源教師的支援服務，幼稚園教師對資源教師的支援服務都有著較高的需求，而接受過資源教師支援服務的幼稚園教師（N = 43）對其支援服務的滿意度則達到一般滿意的水準；2）需求與滿意度量表及各維度之間呈現中度正相關，同時需求程度在各維度上均顯著高於滿意度；需求與滿意度得分最高的都是「合作互動溝通」維度；3）在不同的背景變量下，需求程度只有在「本學年為多少位融合生提供教學」該變量上有顯著差異，當融合生人數達到3名或以上時，教師對資源教師的需求有所增加，而滿意度在不同的背景變量下則沒有顯著差異；4）幼稚園教師對資源教師在改善融合生行為問題造成的班級影響、抽離教學、測考協助、減少IEP工作量、以專業角度向家長提供支援服務方面感到滿意；5）幼稚園教師對資源教師在合作互動溝通、合作教學模式、成績評量、對資源教師工作監管等方面感到不太滿意。最後，結合幼稚園教師對資源教師所提出的期望，筆者提出本研究的啟示，包括完善資源教師的政策規定、加強資源教師的專業化程度、拓展幼稚園教師與資源教師合作教學的模式，以及促進雙方之間的溝通與合作互動關係，為本澳學前融合教育的研究與實踐提供有意義的、循證的方向。

A STUDY ON THE PROFESSIONAL AWARENESS AND ATTITUDES OF THE POST 90S NEW GENERATION EARLY CHILDHOOD EDUCATION TEACHERS IN MACAU INCLUSIVE EDUCATION - Tam, Ho Ieng (2024)
With the rise of the awareness of human rights, students with special educational needs (SEN) are receiving more attention. As many mainstream schools adopt inclusive education, society is focusing on teachers' professional awareness and attitudes toward inclusive education. This study examines the professional awareness and attitudes of post-90s early childhood teachers in Macau regarding inclusive education, aiming to improve policies and training programs. The research employs both qualitative and quantitative methods to explore teachers' views on inclusive education. The qualitative research consists of semi- structured interviews to understand teachers' readiness, attitudes, and the challenges they face in implementing inclusive education. The quantitative aspect uses a questionnaire adapted from the ""Survey on Equal Learning Opportunities for Students with Special Educational Needs under the Hong Kong Inclusive Education System,"" tailored for Macau. By combining interview findings and data, the study analyzes and summarizes the results. The results indicate that the professional awareness of inclusive education among post-90s early childhood teachers in Macau is at a relatively low to moderate level, and their willingness to engage in inclusive education is not high. Factors influencing teachers' willingness to implement inclusive education include a lack of professional knowledge (such as development history, relevant regulations, and guidance methods), insufficient resources, and unclear attitudes from schools toward the implementation of inclusive education. 隨著人權意識的掘起，特殊教育需要學生(SEN 學生)的學習受到關注， 澳門的融合教育逐漸受到關注，許多主流學校開始實施融合教育。就著學校教 育的轉型，教師對融合教育的知識和開展的態度受到社會所關注。因此，是次 研究以質量結合的方式進行調查，為廣泛地、深入地暸解澳門 90 後新生代幼兒 教師在融合教育方面的專業認知和態度，從而對澳門融合教育政策和教師課程 提出建議，促進融合教育的發展。 質性研究以半結構性的深度訪談暸解教師對實施融合教育的預備度和態 度，並探討當中的影響因素和教師在教學中的困擾與需求。量化的研究則參考 了《香港融合教育制度下有特殊教育需要學生的平等學習機會調查》的教師問 卷，向澳門 90 後新生代幼兒教師對融合教育認知和態度作調查。研究透過結合 訪談資料與數據，對研究問題作分析、討論與歸納，並撰寫出研究結果。 研究結果指出澳門 90 後新生代幼兒教師的融合教育專業認知處中等偏低的 水平，同時對融合教育開展的意願不高。而影響教師融合教育開展意願的因素 包括教師缺乏融合教育專業知識(如:發展歷史、相關法規和輔導方式)、資 源不足和學校對融合教育開展的態度不明確。

THE RELATIONSHIP BETWEEN TEACHERS’WORK STRESS AND SCHOOL SUPPORT IN MACAU INTRGRATED SCHOOLS - Cheang, Ka Wa (2024)
The purpose of this study is to examine the current situation of work stress and school support among teachers in integrated schools in Macau, to analyze the differences and correlations between work stress and school support among different background variables. This study utilized the questionnaire survey method as the research method, with secondary, primary and kindergarten teachers of integrated schools in Macau as the research subjects. The research instrument was a self-administered questionnaire on the relationship between work stress and school support among teachers of integrated schools in Macau, which was filled out in the form of an electronic questionnaire. A total of 253 questionnaires were collected and 253 questionnaires were usable, with a usability rate of 100%. The collected data were analyzed by descriptive statistics, independent sample t-test, single factor analysis of variance, and Pearson's cumulative difference correlation analysis, among other statistical methods. Based on the analysis, the following conclusions are as follows: (1) The overall work stress of Macau's integrated teachers is moderately high, and the mean values of each level are ranked from highest to lowest as workload, professional knowledge, and administrative cooperation, among which workload and professional knowledge belong to the medium-high level, and administrative cooperation belongs to the medium level. (2) The overall school support of Macau's integrated teachers is of medium-high level, with the mean values of each level ranked from high to low as family and friends' support, peer support, parents' support and administrative support, among which family and friends' support, peer support and parents' support are of medium-high level, while administrative support is of medium-low level. (3) The overall work stress of Macau's integrated teachers varies significantly across the highest level of education and stages of education. (4) The overall school support of Macau's integrated teachers varies significantly by marital status, highest academic qualification, years of teaching experience, position held, integrated education courses pursued, number of students in the classroom, and the size of the school. (5) The relationship between total work stress and total school support of Macau's integrated teachers was found to be low and negative. In Macau, there are no systematic research has been conducted on these two topics. Through this study, the authors localize these existing research findings, explore their applicability in Macau, and make recommendations for the education sector, school units, and integration teachers respectively, based on the actual situation in Macau. 本文旨在探討澳門融合學校教師的工作壓力及學校支持之現況，分析不同教師背景變項在工作壓力及學校支持的差異情況及兩者之間的相關性。 本研究以問卷調查法為研究方法，以澳門融合學校的中、小、幼教師為研究對象。研究工具為自編的澳門融合學校教師工作壓力與學校支持關係之研究問卷，以電子問卷的方式進行填寫。共回收問卷253份，可用問卷為253份，可用率為100%，回收的數據以描述性統計、獨立樣本t檢定、單因數變異數分析法、皮爾遜積差相關分析等統計方法進行分析。 根據分析所得結論如下：（一）澳門融合學校教師總體工作壓力屬於中等偏高程度，在各個層面平均值由高至低排列為工作負荷、專業知能及行政配合，其中工作負荷及專業知能屬於中高水準，行政配合屬中等水準。（二）澳門融合學校教師總體學校支持屬於中等偏高程度，在各個層面平均值由高至低排列為親朋支持、同儕支持、家長支持及行政支持，其中親朋支持、同儕支持及家長支持屬於中高水準，行政支持屬中低水準。（三）澳門融合教師總體工作壓力在不同學歷及任教教育階段有顯著差異。（四）澳門融合教師總體學校支持在不同婚姻狀態、學歷、教學年資、擔任職務、融合教育課程進修、任教班級學生數目及校部規模有顯著差異。（五）澳門融合教師總體工作壓力與總體學校支持兩者之間的關係為顯著低度負相關。 在澳門地區，目前尚未進行過針對這兩個主題相關的系統性研究。作者透過本研究，將已有的研究成果進行本土化，探索它們在澳門環境下的適用性，結合當地的實際情況，分別為教育部門、學校單位及融合教師提出建議。

Chromosome-level genome assembly of the highly-polymorphic peacock blenny (Salaria pavo) - Cardoso, Sara D.; Jiang, Chunxi; Sun, Lina; Zhang, Libin; Gonçalves, David (Scientific Data, 2024)
The peacock blenny Salaria pavo is notorious for its extreme male sexual polymorphism, with large males defending nests and younger reproductive males mimicking the appearance and behavior of females to parasitically fertilize eggs. The lack of a reference genome has, to date, limited the understanding of the genetic basis of the species phenotypic plasticity. Here, we present the first reference genome assembly of the peacock blenny using PacBio HiFi long-reads and Hi-C sequencing data. The final assembly of the S. pavo genome spanned 735.90 Mbp, with a contig N50 of 3.69 Mbp and a scaffold N50 of 31.87 Mbp. A total of 98.77% of the assembly was anchored to 24 chromosomes. In total, 24,008 protein-coding genes were annotated, and 99.0% of BUSCO genes were fully represented. Comparative analyses with closely related species showed that 86.2% of these genes were assigned to orthogroups. This high-quality genome of S. pavo will be a valuable resource for future research on this species’ reproductive plasticity and evolutionary history.

Optimizing Fetal Health Status Detection Using Quantum Intelligent Deep-Learning Methods on Cardiotocographic Data - Al-Razgan, Muna; Ali, Yasser A.; Neira-Molina, Harold; Ma, Hauwei; Du, George; Ain, Qurat Ul (SPIN, 2024)
This work compares the performance of different algorithms — quantum Fourier transform, Gaussian–Newton method, hyperfast, metropolis-adjusted Langevin algorithm, and nonparametric classification and regression trees — for the classification of fetal health states from FHR signals. In the conducted research, the effectiveness of each algorithm was measured using confusion matrices, which gave information about class precision, recall, and total accuracy in three classes: Normal, Suspect, and Pathological. The QFT algorithm gives an overall accuracy of 90%, where it is highly reliable in recognizing Normal (94% F1-score) and Pathological states (91% F1-score), but performs poorly regarding the Suspect cases, at 58% F1-score. On the other hand, using the GNM method gives an accuracy of 88%, whereby it performed well on Normal cases, at 93% F1-score, and poor performance with Suspect, at 50% F1-score, and Pathological classifications, at 82% F1-score. The hyperfast algorithm yielded an accuracy of 89%, thus performing well on Normal classifications with an F1-score of 93%, but less well on the Suspect states with an F1-score of 56%. The MALA algorithm outperformed all other algorithms tested in this study, giving an overall accuracy of 91% and adequately classifying Normal, Suspect, and Pathological states with corresponding F1-scores of 94%, 63%, and 90%, respectively; therefore, the algorithm is quite robust and reliable for fetal health monitoring. The NCART algorithm achieved an accuracy of 89%, thus showing great capability for classification in Normal cases with 94% F1-score and in Pathological cases with 88% F1-score; this is moderate for Suspect cases with 53% F1-score. Overall, while all algorithms exhibit potential for fetal health classification, MALA stands out as the most effective, offering reliable classification across all health states. These findings highlight the need for further refinement, particularly in enhancing the detection of Suspect conditions, to ensure comprehensive and accurate fetal health monitoring.

Trans-EffNet: A Hybrid Model for Brain Tumor Detection Using EfficientNet and Transformer Encoder - Nizamani, Abdul Haseeb; Chen, Zhigang; Nizamani, Ahsan Ahmed; Bhatti, Mughair Aslam; Ma, Hauwei; Du, George (2024 IEEE Smart World Congress (SWC), 2024)
Accurate classification of brain tumors from MRI is critical for effective diagnosis and treatment. In this study, we introduce Trans-EffNet, a hybrid model combining pre-trained EfficientNet architectures with a transformer encoder to enhance brain tumor classification accuracy. By leveraging EfficientNet's deep CNN capabilities for localized feature extraction and the transformer encoder for capturing global contextual relationships, our model improves the identification of intricate tumor characteristics. Fine-tuned with ImageNet-derived weights and utilizing extensive data augmentation, Trans-EffNet was validated on both multi-class and binary datasets. Trans-EffNetB1 achieved 99.49 % accuracy on the multi-class dataset, while Trans-EffNetB2 recorded 99.83 % accuracy on the binary dataset, with perfect precision, recall, and F1-Score. These results underscore Trans-EffNet's robustness and potential as a significant advancement in brain tumor detection and classification.

From Semi-democracy to Autocracy - Correia, Sérgio de Almeida (Asia-Pacific Journal on Human Rights and the Law, 2024)
Abstract Under the agreement signed with Portugal, which defined the terms of the handover to China, Macau became a Special Administrative Region on 20 December 1999. China undertook to maintain the way of life, the rights and freedoms of the residents and the essence of the laws previously in force, and guarantee the inapplicability of the socialist system. Events in Hong Kong since 2019 and the concerns of the Central Government have led to changes in the national security law and electoral laws which, among other things, have imposed political screening on candidates for the Legislative Assembly and Chief Executive, which can lead to their exclusion without appeal, while criminalising calls for blank votes, null votes, and abstentions. This article answers the question of whether these changes are compatible with the guarantees provided, the Luso-Chinese Joint Declaration and Macau’s Basic Law.

Exploring a model for ensuring language learner autonomy via technological buttressing - Baker-Malungu, Laurie (Applying Technology to Language and Translation, 2024)
Having navigated up to two years of online course delivery worldwide as a result of the Covid-19 pandemic. Education systems are now in a better position to leverage the benefits of technology in facilitating the language acquisition process more effectively. Regardless of the student population served, there is no longer a concern as to whether students have access to facilities necessary for online delivery as the smartphone has become a standard household necessity. This conceptual literature review introduces a potential model for second language instruction utilizing a flipped classroom approach based on evidence gained through empirical research interpreted through the lens of present reality. Technology enables learners to explore the form and structure of language through the use of online autonomous learning units with no limitation of time or accessibility, while scheduled classroom engagement allows opportunity for authentic language practice and refinement. The implications of this study add value to second and foreign language instruction, providing language teachers with a pragmatic approach to enhance their instructional delivery. © 2025 selection and editorial matter, Leung Sze Ming and Chan Sin-wai; individual chapters, the contributors.
ISBN: 9781003399261

Conflicts Of Jurisdiction Over Transnational Cybercrime A Case Study of China Approach - Tam, Pou Leng (2024)
In the virtual space of the Internet, the boundaries of countries tend to be blurred, and the harmful results caused by criminal acts committed thousands of miles away may very likely be close at hand, and criminal acts committed in the territory of a country may be widespread all over the world, which can be said to be a global plague in the Internet era. As a starting point for the criminalisation of cyberspace crimes, Criminal jurisdiction, which is an important form of national sovereignty exercised by a state, is an important prerequisite for a state to exercise its penal power over cyberspace crimes. Many states, out of a desire to maximise their own national interests, have made constant efforts to expand the jurisdictional scope of application of their domestic laws, resulting in circumstances of positive conflict between two or more states. Exploring possible paths to solving the conflict of criminal jurisdiction over transnational cybercrime should begin by identifying why traditional criminal law is not well suited when entering cyberspace, and by examining the strengths and weaknesses of the legislative practices of more advanced jurisdictions with regard to criminal jurisdiction over transnational cybercrime, the shortcomings of the relevant international law and the generally adopted jurisdictional principles, and the feasibility of the new international theories regarding the establishment of jurisdiction over cybercrime, as the main aspects of this study to disentangle the reasons behind the conflict in establishing criminal jurisdiction over transnational cybercrime.

A STUDY ON THE CURRENT SITUATION OF CLASS TEACHERS IN MACAO PRIMARY SCHOOLS CREATING AN INCLUSIVE ENVIRONMENT IN INTEGRATED EDUCATION - Lao, In In (2024)

EXPLORING THE CURRENT SITUATION OF MACAU KINDERGARTEN TEACHERS IMPLEMENTING GAMIFICATION FOR CHILDREN'S LEARNING IN AN INCLUSIVE CLASSROOM - Sou, Iok Heng (2024)
In Macao, the curriculum guidance based on games as the basic learning method in early childhood education, that has been in place for almost 10 years. In recent years, there are many studies in Macao which have proved the positive impacts of implementing gamification for children's learning. Under gamification for learning education policy implemented by the government, the purpose of this study is to explore the teachers’ current situation of implementing gamification for children’s learning in an inclusive classroom. This study focuses on Macau kindergarten teachers to explore their current situation of implementing gamification for children’s learning in an inclusive classroom. The research is divided into four aspects to conduct the explanation and elaboration: firstly, the aspect of teachers’ cognition of gamification for children’s learning, secondly, the aspect of their attitude towards the implementation of gamification for children’s learning in an inclusive classroom, thirdly, the aspect of the challenges or difficulties encountered in practices, and fourthly, the teachers’ strategies to cope with challenges. Through the method of semi-structured in-depth interviews of qualitative research, are the perspectives and opinions of 14 kindergarten teachers, from 10 schools that provide inclusive education services in Macao. The results are as follows: Firstly, the teachers have a clear understanding of the connotation of gamification for children’s learning in general. They understand that the games must be designed, based on the teaching objectives and teaching content. The teachers also recognize that gamification for learning has two characteristics of both education and pleasure. Secondly, regarding the attitude of teachers, most of them hold a positive attitude towards this approach, which can be attributed to the positive impact of gamification for learning on students with special educational needs, the school’s supporting system, parents’ trust, and the accumulation of practical experiences. However, one of the teachers does not agree with the implementation of gamification for student’s learning in an inclusive classroom, and holds a negative attitude of passive acceptance, which can be attributed to the lack of teaching strategies to support students with special educational needs as they participate in games, the relevant training experiences are not helpful, and unfavorable with school policies. Thirdly, in regards to the challenges faced by teachers implementing this approach, there are six aspects: firstly, it is challenge to support the whole class students participation in a gamification activity; secondly, it is difficult to design the playing method of games; thirdly, the negativity influence of gamification for learning increases the burden of classroom management; fourthly, it is necessary to support students with special educational needs to participate in games; fifthly, there might be some misunderstandings of gamification for learning from peer teachers or parents; sixthly, classrooms are limited with space and the resources of schools are insufficient. Fourthly, as for teachers’ strategies to cope with challenges, the strategies used by teachers are related to their attitudes. When teachers have a positive attitude to the approach, they are willing to try and solve the difficulties while implementing gamification for children’s learning with positive strategies. Vice versa, if teachers have a passive acceptance attitude, they may struggle to establish effective coping strategies. Finally, according to the results of this study, the researcher summarized the issues that need to be further addressed, and made several specific suggestions for the government, schools and teachers to implement gamification for children’s learning in future. At the same time, according to this study, the researcher would also like to make some suggestions for a future study, which can provide some references for the scholars of the related research field. 澳門幼兒教育階段以遊戲為基本學習方式的課程指引將近有10年時間，近年本土也有不少研究證實遊戲教學法應用於孩子的學習上，能帶來正面的影響。在政府推行遊戲為本的教育方針下，本研究目的旨在探討幼稚園教師對應用遊戲教學法於融合教育班的現況。 本研究以澳門幼稚園教師為焦點，探討其對遊戲教學法應用於融合教育班的實踐現況，分為四方面論述，一是教師對遊戲教學法的認知層面，二是其對遊戲教學法應用於融合教育班的態度，三是其實踐過程遇到的挑戰或困難，四是其應對挑戰的策略。透過質性研究的半結構式深度訪談法，了解來自本澳10所有參與融合教育學校的14位幼稚園教師之想法及意見。研究結果如下： 第一，整體教師能釐清遊戲教學法的內涵，明白遊戲活動須按從教學目標及教學內容為依據，其普遍認同遊戲教學法兼具教育性與愉悅性的特色。 第二，關於教師態度方面，大部份教師抱持積極正向的態度，歸其原因包括肯定遊戲教學法對特殊教育需要學生的正面影響、校方支持體系、家長的信任、實踐經驗的累積；同時，亦有個別教師是不贊成遊戲教學法應用於融合教育班，抱持被動接納的負向態度，歸其原因包括缺乏支援特殊需要學生參與遊戲的策略、相關培訓經歷幫助不大、學校政策的不利因素。 第三，關於教師面對的挑戰，包括六方面，一是遊戲活動需支持全班參與，二是難以構思遊戲活動的形式；三是遊戲教學負面的影響造成課堂管理的負擔；四是需要支援特殊需要學生在遊戲活動的狀況；五是同儕教師或家長對遊戲教學的誤解；六是教室空間狹窄以及學校資源配備不足。 第四，關於教師應對挑戰的策略，教師使用的策略與教師態度相關，當教師抱有積極正向的態度，便具信心，並會嘗試以正向的策略解決遊戲教學的困難；反之亦然，若教師產生被動接納的態度，便會感到退縮，未能建立有效的應對策略。 最後，根據本研究的結果，研究者總結出需進一步解決的問題，藉此對政府、學校及教師提出具體的建議，供日後推行遊戲化教學參考。同時依據本研究，提出研究展望，供未來進行相關研究領域的學者提供一些意見。

Macau school counselors’attitude toward inclusive education and challenges - Leong, Mei Ian (2024)
隨著教育理念的不斷發展，融合教育作為一種包容性強的教育模式，逐漸受到全球教育界的關注。在澳門，融合教育的實踐也逐步展開，而學生輔導員作為教育團隊中的重要一員，在融合教育工作中扮演著舉足輕重的角色。然而，在融合教育的實施過程中，學生輔導員也面臨著諸多挑戰，並因而需要不斷進行改正和完善。本文正是圍繞這些內容對澳門融合教育過程中學生輔導員角色作用的發揮方面的相關課題通過訪談調查等方法進行研究分析。 論文認為，從澳門學生輔導員對融合教育的認知與態度看，他們普遍認同融合教育的理念，認為這是一種促進學生全面發展、提升教育質量的有效途徑。然而，在融合教育的實際操作中，他們也深感責任重大，需要不斷學習和提升自己的專業能力，以更好地滿足融合生的多樣化需求。 在融合教育的實踐過程中，學生輔導員面臨著多方面的挑戰。一方面，他們需要識別融合生的多樣性與教育需求，制定個性化的教育計劃，並確保這些計劃的有效實施。這需要他們具備深厚的專業知識、豐富的實踐經驗和敏銳的觀察力。另一方面，他們還需要與教育團隊、家長以及社會資源進行有效的溝通和協作，共同為融合生創造一個良好的學習環境。 論文認為，當前澳門學生輔導員在融合教育的實踐中已經形成了一些有效的策略。例如，他們注重個性化教育計劃的制定與執行，通過多維度的輔導與激勵，激發學生的學習興趣和積極性；同時，他們也積極尋求家校合作與社會資源的整合，為融合生提供更多的支援和幫助。然而，學生輔導員在融合教育中仍然面臨著一些挑戰。首先，融合教育對學生輔導員的角色定位提出了更高的要求，他們需要不斷適應角色多樣性的挑戰，同時保持專業能力的提升。其次，融合教育中的特殊技能需求也讓學生輔導員感到壓力，他們需要在日常工作中不斷學習和提 升。最後，外部支持的不足也是學生輔導員面臨的一大挑戰，他們需要更多的政策支援和資源保障來更好地開展融合教育工作。 針對以上挑戰，澳門教育部門和學生輔導員團隊需要共同努力，明確學生輔導員的定位和職責，提升他們的專業能力和水準，並增強外部支援和保障。只有這樣，才能確保融合教育在澳門順利實施，為所有學生創造一個公平、包容、和諧的學習環境。 "With the continuous development of educational ideologies, inclusive education, as a highly inclusive educational model, has gradually garnered attention from the global education community. In Macau, the practice of inclusive education has also gradually expanded, and student counselors, as vital members of the educational team, play a pivotal role in the implementation of inclusive education. However, during the implementation process, student counselors face numerous challenges and are required to continually make improvements and enhancements. This paper focuses on these aspects and conducts research and analysis on the role of student counselors in Macau's inclusive education through methods such as interviews and surveys. The paper argues that from the perspective of Macau student counselors' cognition and attitudes towards inclusive education, they generally agree with the concept of inclusive education, believing it to be an effective way to promote students' comprehensive development and enhance the quality of education. Nevertheless, in the practical operation of inclusive education, they also feel a significant sense of responsibility and need to continuously learn and upgrade their professional skills to better meet the diverse needs of students with special educational needs. In the practical process of inclusive education, student counselors confront multifaceted challenges. On the one hand, they need to identify the diversity and educational needs of students with special needs, develop individualized educational plans, and ensure their effective implementation. This requires profound professional knowledge, rich practical experience, and keen observation skills. On the other hand, they must communicate and collaborate effectively with educational teams, parents, and social resources to create a favorable learning environment for these students. The paper posits that currently, Macau student counselors have developed some effective strategies in the practice of inclusive education. For instance, they emphasize the formulation and execution of individualized educational plans, stimulate students' interest and motivation through multidimensional counseling and incentives, and actively seek home-school cooperation and integration of social resources to provide more support and assistance to students with special needs. Nevertheless, student counselors still face challenges in inclusive education. Firstly, inclusive education imposes higher demands on the role positioning of student counselors, requiring them to continuously adapt to the challenges of role diversity while maintaining professional competence. Secondly, the special skill requirements in inclusive education create pressure for student counselors, who need to continually learn and improve in their daily work. Lastly, insufficient external support is also a significant challenge faced by student counselors, who require more policy support and resource guarantees to better carry out inclusive education work. In response to these challenges, the Macau education sector and student counselor teams need to work together to clarify the positioning and responsibilities of student counselors, enhance their professional capabilities and standards, and strengthen external support and guarantees. Only in this way can we ensure the smooth implementation of inclusive education in Macau, creating a fair, inclusive, and harmonious learning environment for all students. "

Exploring TikTok's impact on Macau’s youth culture and behavior - Ma, Man Hei (2024)
This proposed study looks into the popular TikTok app and its impact on the identity formation and expression of young people. It investigates how TikTok enables young individuals to create, share, and consume diverse and authentic content that reflects their interests, values, and experiences. People on the app can work together, take part in trends, and interact with others. Also, the paper dives into how TikTok gives people a place to chase their dreams and find out what other possibilities their lives could hold. It indicates how TikTok can have some good and bad effects on young generations in terms of culture and personal development. These youngsters could be the ones leading in the future. However, we also need to think about the possible dangers TikTok could pose to young people. This includes the chance that they come across something damaging, feel like they have to live up to hard-to-reach standards, have their private information leaked, or fall victim to someone with bad intentions. Because of these risks, it's very important to teach youngsters how to use TikTok in a way that's safe and responsible. The dissertation highlights the need for responsible usage, awareness of potential challenges, and the development of strategies to support the safe and healthy engagement of young people with TikTok and similar platforms.

THE COMMUNICATIVE-RECIPROCAL STRUCTURE OF THE FLESH: AN INVESTIGATION INTO THE LATER MERLEAU-PONTY’S ONTOLOGY OF THE BODY - Kan, Nga Lon (2024)
Though Cartesian dualism has been criticized for decades, it still prevails as a strongly dominant cultural mindset rooted in people’s minds, especially in the social environments that we experience. Along with it, there is not only a loss of attention to our own bodies but also a loss of the recognition of the experience of inter-subjective reciprocity. Therefore, I hope, through the methodology and virtue of phenomenology, especially from the phenomenological-ontological account of the body/flesh from the modern French philosopher Maurice Merleau-Ponty, to help my readers to overcome convincingly and detach themselves from the traditional Cartesian mindset. I argue that the body is born as a communicative-reciprocal being that sustains a priori connection with all other things in the world, and with the world. The body is a lived body and a transcendental being that cannot be reduced to fit in the present reductionistic mathematical-scientific idealized frameworks. After pointing out the insufficiencies in traditional mathematical scientific and Cartesian accounts of the body in Chapter One, my argument will be unfolded along with reflections on the common experiences in daily life and the textual analyses respectively contributed by Merleau-Ponty’s works The Phenomenology of Perception, especially in Chapter Two, and The Visible and the Invisible, especially in Chapter Three.

A STUDY ON THE RELATIONSHIP BETWEEN TEACHERS EMOTIONAL INTELLIGENCE, PERCEIVED STRESS AND TEACHING EFFICACY OF KINDERGARTEN TEACHERS IN MACAO - Ng, Man Teng (2024)
The purpose of this study was to explore the current situation and the correlations between emotional intelligence, perceived stress and teaching efficacy of kindergarten teachers in Macao. The research method was questionnaire survey that used “The relationship between emotional intelligence, perceived stress and teaching efficacy of kindergarten teachers in Macao.” as a data collection tool, while the research object were the kindergarten teachers in public and private schools in Macao. A total of 269 valid questionnaires are recovered, the valid return rate was 100%. Statistical analysis was performed after the questionnaires were collected, the research results are summarized as follows: 1. The teachers’ emotional intelligence was at a high intermediate level. The significant differences of emotional intelligence were found among teachers with varying background variables such as marital status, teaching experience and inclusive education experience. 2. The teachers’ perceived stress was at a low intermediate level. The significant differences of perceived stress was found among teachers with varying background variables such as teaching experience. 3. The teachers’ teaching efficacy was at a high intermediate level. The significant differences of teaching efficacy were found among teachers with varying background variables such as marital status, teaching experience and inclusive education experience. 4. There was significant negative correlation between teachers’ emotional intelligence and perceived stress. 5. There was significant positive correlation between teachers’ emotional intelligence and teaching efficacy. 6. There was significant negative correlation between teachers’ perceived stress and teaching efficacy. 7. The teachers’ emotional intelligence and perceived stress could predict teaching efficacy. 本研究旨在探討澳門幼稚園教師情緒智力、壓力知覺與教學效能關係之現況及相關情形。研究方法是以問卷調查方式進行，以本澳公立及私立學校的幼稚園教師作研究對象。是次回收有效問卷為269份，問卷回收率達100%，問卷回收後進行統計分析。本研究結果顯示如下： 一、本澳幼稚園教師情緒智力達到中高程度，整體情緒智力因婚姻狀況、教學年資及融合教育經驗的不同而有顯著差異； 二、本澳幼稚園教師壓力知覺呈現中下程度，整體壓力知覺因教學年資的不同而有顯著差異。 三、本澳幼稚園教師教學效能達到中高程度，整體教學效能因婚姻狀況及融合教育經驗的不同而有顯著差異； 四、情緒智力與壓力知覺呈現負相關； 五、情緒智力與教學效能呈現正相關； 六、壓力知覺與教學效能呈現負相關。 七、情緒智力、壓力知覺對整體教學效能具有顯著預測力。 本研究依據上述研究之結果提出建議給予政府、學校行政機關、幼稚園教師及未來研究者作參考。

The relationship between family education environment and children’s online behavior-the mediating role of parents’ intervention in children’s online behavior - Lou, Si Man (2024)
In the era of data, Internet use has become the most forward-looking way of education and interaction for children. How does parental upbringing and Internet cognition in the family education environment affect children's Internet use behavior? The different influences derived from parental intervention. The different influences of parental intervention models are also of concern to parents. Children's Internet use is not only related to personal growth, but also involves family education models and effects. Most of the past research has focused on children rather than parents’ opinions and feelings. Through this research gap, we explore parents’ own opinions and evaluations on their children’s upbringing and Internet cognition. The research aims to expand the attention of policy advocates, social sectors and parents on issues related to parenting in Macao. During the period from April to June this year, quantitative research and statistical analysis will be used to provide targeted and convenient information to primary school students in Macao. Parents of children in high school and high school were taken as targets. Questionnaires were filled out in person and collected on online platforms. A total of 224 samples were collected. The study will further discover the relationship between parental upbringing and Internet cognition and children's Internet behavior. Parents' involvement in their children's Internet behavior may have an impact on these associations. Derived intermediary effects. Through data collection and research analysis, regression analysis is conducted on variables to determine the relationship between variables, explore the family upbringing and Internet cognition factors behind the Internet behavior of Macao children, and increase the theoretical and practical reference basis for parents. Provide reference for practical promotion of education, social services and family relations, and improve parents' insight into their children's online behavior. The research results emphasize that there is a correlation between parenting styles and children's online behavior. Authoritative parenting represents a higher defensive ability of children's online behavior, while authoritarian and permissive parenting represent weak defensive capabilities. The results also show that parents' involvement in online behavior is a pathway in relationships and affects the relationship between parenting and children's online behavior to a certain extent. Since there are not many related studies in Macao, the survey results are conducive to enriching the data on education, Internet cognition and Internet behavior in Macao, and can provide relevant people with beneficial data support to better understand the education methods in Macao. and family relationships. 數據化時代下，網絡使用成為子女最前瞻性的教育和互動方式，在家庭教育環境下的父母教養和網絡認知如何影響著子女網絡使用行為，在父母介入干預下所衍生的不同影響力，當中父母介入模式的不同影響亦是父母所關注的。子女網絡使用不僅關乎個人成長亦牽涉到家庭教育模式和效果。過往研究大多傾向子女身上而非父母觀點和感受上，透過本研究缺口探討父母自身對子女的教養、網絡認知等看法和評價。 研究旨在探討本澳子女網絡行為背後的家庭教養和網絡認知因素，增加父母在理論和實踐上的參考依據，提供教育、社會服務和家庭關係等的實務推動上的參考，提高父母對子女網絡行為的洞察力。本論文透過今年4至6月期間以量化研究。以有目的性和方便性向本澳育有初小至高中子女的父母作為對象，以當面填寫及網絡平台收集問卷，共收取樣本224份，研究將進一步發現父母教養和網絡認知與子女網絡行為的關係，而父母介入子女網絡行為對這些關聯可能衍生之中介效果。透過數據整埋和研究分析等在變數上進行迴歸分析，確定變數之間的關係。 研究結果強調，父母教養方式與子女網絡行為具有相關關係，權威型教養代表著子女網絡行為的防禦能力較高，相反專制型和寬容型教養則呈現防禦力較弱。結果亦顯示，父母介入網絡行為是關係中的途徑，一定程度下影響著父母教養和子女網絡行為的關係。由於本澳相關的研究並不豐富，調查結果有利於本澳在教養、網絡認知和網絡行為上的數據資料豐富，可以為相關人士提供有利的數據支援，更好地瞭解本澳的教養方式和家庭關係。再者，可透過研究結果擴大政策提倡者、社會業界和父母等對本澳父母教養等相關問題的關注。

Work-family balance: Research on strategies for coordinating work and family among dual-career families in Macao - Ho, Iok Cheng (2024)
澳門於1994年頒佈《家庭政策綱要法》，旨在支持家庭提升工作、房屋等的生活條件。澳門特區政府於2020年中修改《勞動關係法》，增加對家庭的支援，以回應澳門的發展需要。回顧有關工作與家庭衝突的文獻，大多針對弱勢家庭作探討，忽略雙職家庭也同樣面對困境。本研究之目的是為探討本澳雙職家庭的工作與家庭衝突情況，並在家庭友善政策推行不足的情況下，雙職家庭為求達致工作與家庭能夠平衡的協調策略。 為了作出深入的了解，本研究採用質性研究，邀請了20位雙職家庭的父母作為研究對象，與他們通過半結構式訪談收集資料。獲得資料後，以紮根理論進行編碼及分析。 本次研究發現有利於平衡雙職家庭的工作與家庭，與三大要有密切關係，包括1)家庭協調與資源；2)時間管理及3)社會支持。雙職父母運用自身家庭的資源協調模式，訂立出屬於個別家庭獨有的時間管理模式及分工；工作單位的友善氛圍及相應的彈性工作協調措施，也扶助了雙職家庭，達致家庭與工作中取得較為平衡的狀態。研究者根據以上的研究發現，為優化家庭友善政策作出一些建議，使雙職家庭能減少工作與家庭衝突的發生。

EFFECTS OF INFORMATION TECHNOLOGY INTEGRATED INTO 5E INQUIRY INSTRUCTION ON THE LEARNING ACHIEVEMENT AND ATTITUDE OF JUNIOR STUDENT IN BIOLOGY LEARNING: TAKING "IMMUNE SYSTEM" AS AN EXAMPLE - Chao, Kuan Peng (2024)
With the continuous reform of education and the ongoing development of teaching methods by the Macao government, the teaching model of biology is also constantly evolving. The “5E” instructional model, proposed and developed by the Biological Sciences Curriculum Study (BSCS) in the United States, consists of a learning cycle divided into five phases: Engagement, Exploration, Explanation, Elaboration, and Evaluation. Each phase begins with the letter “E,” hence it named as the 5E teaching model. This model is currently widely applied in inquiry-based teaching across multiple countries. This article is a research study on practical teaching, where the researcher attempts to integrate information technology with the 5E learining method in an 8th Grade biology class. The aim is to explore whether the learning attitudes and academic performance of middle school students can be enhanced in the context of the 21st century. The focus of this study is on the chapter about the “Immune System,” selecting two parallel classes of 8th Grade students from a secondary school in Macao as research subjects. One class uses the 5E model, while the other teaching with traditional lecturing methods. Through Document Analysis, equivalent-group design, and questionnaire surveys and lesson plan based on 5E model, statistical software SPSS 22 is used to analyze the data regarding students’ biology learning attitudes and academic performance, thereby assessing the effectiveness of teaching using the 5E model and identifying issues encountered during the teaching process to provide targeted teaching strategies. The research findings indicate: (1) There is no significant difference in the learning attitudes and performance of students in the experimental class compared to the control class regarding the immune system unit. (2) There is no significant difference in the learning attitudes and performance of students in the experimental class before and after receiving 5E teaching. (3) For students with average academic performance, the experimental class shows significant differences in learning interest and strategies compared to the control class after undergoing 5E teaching. (4) Among students with average academic performance in the experimental group, there is a significant difference in learning interest after 5E teaching compared to before. (5) Students express high satisfaction with the teacher’s integration of information technology into the 5E teaching model, which can stimulate their interest in learning natural sciences.

An Empirical Analysis of the Role of Xiaohungshu [Little Red Book] on Chinese tourists' Visiting Macao - Lam, Ka Kit (2024)
Today, social media has become one of the main marketing strategies used by marketers and practitioners to target travelers from all over the world. Macau is a city that relies heavily on tourism for economic development, however, little is known about how social media affects tourists’ choices to travel to Macau. This study explores the role of the popular social media platform Xiaohongshu in influencing Chinese tourists’ travel decisions and information acquisition when visiting Macau. This article uses qualitative research methods to conduct semi-structured interviews with 15 participants. Research shows travelers rely on Xiaohongshu’s user-generated content and detailed guides. Food, route selection and itinerary arrangements, and short-term itinerary arrangements are the most frequently mentioned search tags by travelers. The platform’s personalized recommendations and efficient content presentation enhance the user experience, but concerns about content credibility remain, especially the potential for commercial bias in food recommendations. Travelers assess the credibility of content through a variety of strategies, including looking at multiple posts, evaluating user interactions, and the platform’s IP address display capabilities. Although travelers pay more attention to positive reviews when deciding to travel to Macau, users also consider travel pitfalls posts to improve their travel experience. In addition, travelers are less willing to share content on the Xiaohongshu platform after the trip, which is attributed to personal habits and perceived creativity complexity. The research results provide relevant practitioners with the perspectives and decision-making behaviors of Chinese travelers who use Xiaohongshu when making itineraries to Macau, and provide guidance for their marketing strategies.

GLOBAL ADOPTION OF CRYPTOCURRENCY: A THEMATIC NETWORK ANALYSIS OF EXTANT DOCUMENTS - Man, Tak Wa (2024)
Since the advent of Bitcoin, cryptocurrencies have emerged as a transformative financial technology. Over the years, blockchain has provided decentralised and secure transaction methods that have become increasingly attractive to individuals and businesses, leading to their rapid global adoption driven by consumer preferences and the growing digitalisation of the financial system. This dissertation examines the factors influencing the widespread acceptance of cryptocurrencies, including their potential for the financial market, the impact of regulatory frameworks, and the role of blockchain technology. The research questions are: (RQ1) What is the degree of adoption of cryptocurrencies in different countries and regions (RQ2) What are the factors that influence the adoption of cryptocurrencies in different countries or regions as identified in extant research? (RQ3) What are the implications for countries or regions that have not adopted cryptocurrencies? This study analyses 108 documents, including university academic papers, financial report articles, etc. The analytical tools include automatic coding, manual coding, word cloud, word frequency table, cluster analysis, hierarchical chart in NVivo, followed by a thematic network analysis. Six keywords, ‘bitcoin’, ‘blockchain’, ‘financial’, and ‘market’ have the highest frequency. This study also analyse different regions with different degrees of cryptocurrency adoption separately: countries where cryptocurrencies are legal, countries that use Bitcoin as a legal tender, and countries that ban cryptocurrencies. The thematic network model indicates that while cryptocurrencies offer significant opportunities for innovation and economic growth, social awareness, government institutions, technology, security, price value, and individual consumer factors are critical to addressing inherent challenges and fostering a stable adoption environment. For non-cryptocurrency regions, rethinking their stance on cryptocurrencies is key to avoiding derailing world financial markets.

A STUDY OF MUSIC CURRICULUM PRACTICES ACROSS KINDERGARTENS IN MACAO - Ng, Ka Sin (2024)
This study employs qualitative research methods, conducting semi-structured interviews with ten kindergarten teachers in Macao. The study further analyses and summarises the participants' perceptions of music teaching, music curriculum design, teaching practices, practical challenges, and the support needed to develop music education. The findings of the study are as follows: 1. The study explores kindergarten teachers' perceptions and attitudes towards music teaching, revealing that all participants recognise the importance of fundamental music knowledge and skills, although there is a noticeable variation in the music proficiency level among teachers. A solid foundation in music is essential for delivering high-quality music instruction. Further to professional skills, teachers' attitudes towards music teaching also vary. While most participants are passionate about music education, some hold neutral or conservative views, and a few lack much interest. Their involvement in teaching is primarily driven by professional duties and school curriculum requirements, with some missing intrinsic motivation or enthusiasm for teaching music. Additionally, some teachers' limited interest in music teaching may be related to a lack of musical talent or confidence. 2. This study analyses the current state of music curriculum teaching in kindergartens. Most music instruction within kindergartens in Macao aligns with the guidelines provided by the Education and Youth Development Bureau, with two music classes arranged per week, each session lasting about 30 minutes. While thematic teaching is a significant model in kindergarten music curricula, over-reliance on it should be avoided. The study suggests that teachers should balance thematic teaching with systematically cultivating fundamental music knowledge and skills. Regarding staffing, music classes are typically co-taught by two classroom teachers, with one required to have instrumental skills. This arrangement supports more professional music instruction, enriches teaching content, and enhances children's musical experiences. However, challenges remain due to heavy teacher workloads and insufficient resources and facilities. Despite these limitations, kindergarten teachers in Macao continue to implement personalised teaching approaches and adopt diverse, innovative, and individualised teaching methods in their music curricula. The interviewed teachers demonstrated a broad and innovative approach to curriculum design and practice, reflecting their deep understanding and professional competence in early childhood music education. 3. Kindergarten teachers in Macao face various challenges in teaching music curricula, most due to the comprehensive and objective assessment of children's musical abilities. The study finds that teachers typically struggle to evaluate musical concepts, rhythm, creativity, interest, and engagement. Additionally, pronunciation accuracy and developmental differences among children are significant factors in the assessment process. 4. This study aims to delve into the challenges and needs faced by kindergarten teachers in music curriculum practice, particularly in music education. The findings indicate that the development of music education in kindergartens is influenced by multiple factors, with the level of importance and support given to music education by schools being a critical issue. Specifically, some participants noted that schools place limited emphasis on music education, prioritising core subjects such as language and English, while others reported that schools provide ample recognition and support for music education. This disparity leads to an imbalance in music teaching resources and environments, affecting teachers' ability to conduct music teaching activities effectively. While some schools place a high value on music education, overemphasising certain aspects of training may lead to an imbalanced development of music education. Furthermore, the study finds that kindergarten teachers have varying levels of musical background and teaching experience. Despite having a basic understanding of music, some teachers fall short in teaching methods and strategies, while others lack systematic music knowledge and skills. These differences in capability limit the quality of music instruction and hinder the comprehensive development of children's musical literacy. Finally, the researcher provides relevant recommendations based on these conclusions to guide future research. 本研究採用質性研究法,通過半結構訪談10位澳門幼稚園教師,並進一步加以分析與歸納探討了受訪者對音樂教學的認知、音樂課程設計、教學實況、實踐困境以及發展支持等方面的情況。研究結論如下： 1. 探討幼稚園教師對音樂教學的認知和態度,研究發現,所有受訪教師均認識到音樂基礎知識和技能的重要性,但教師之間的音樂技能水準存在一定差異。紮實的音樂基礎是開展高品質音樂教學的前提。除了專業技能外,教師對音樂教學的態度也有所不同,大部分受訪者對音樂教學充滿熱忱,但也有部分教師持中立或保守的態度,少數教師則缺乏興趣。他們參與教學主要是出於職責和學校課程安排,可能缺乏內在動力和熱情。此外,個別教師對音樂教學的興趣不足,這可能與其音樂天分不夠或自信心不足有關。 2. 本研究分析了幼稚園音樂課程的教學現狀。大多數澳門幼稚園的音樂教學安排符合教青局的指引,每週安排兩次音樂課,每節課時長約為30分鐘。雖然主題教學是幼稚園音樂課程的重要模式之一,但不宜過度依賴。研究指出,教師在進行主題教學的同時,應重視系統性培育音樂基礎知識和技能,並在兩者之間找出平衡。在教師配置方面,音樂課通常由兩位班主任共同執導,其中一位教師需具備樂器演奏能力,這樣的安排有助於提供更專業的音樂指導,豐富教學內容,並提升幼兒的音樂體驗。然而,問題在於教師的工作負擔較重,且在師資力量和教學設施等方面仍有不足。儘管面對環境的限制,澳門幼稚園教師仍靈活地開展自己的個性化教學,並在音樂課程中採用了多樣化、創新性和個性化的教學方法。受訪的幼稚園教師展現出了多元化、創新性的教學設計理念和實踐,充分體現了他們對幼兒音樂教育的深刻理解和專業素養。 3. 澳門的幼稚園教師在進行音樂課程教學時面臨多種挑戰,這些挑戰主要集中在如何全面且客觀地評估幼兒音樂能力。研究發現,教師們普遍在音樂概念、節奏感、創造力、興趣和參與度的評估方面遇到困難。此外,發音準確性和幼兒之間的發展差異也成為評估過程中的重要考慮因素。 4. 本研究旨在深入探討幼稚園教師在音樂課程實踐中面臨的挑戰與需求,尤其是在音樂教育方面。研究結果顯示,幼稚園的音樂教育發展受到多種因素的影響,其中學校對音樂教育的重視程度和支持力度的差異是關鍵問題之一。具體而言,有部分受訪者指出,學校對音樂教育的重視程度有限,更側重於語文、英語等主學科的教學；而另一些受訪者則表示,學校對音樂教育給予了充分的認可和支持。這種差異性導致了音樂教學資源和環境的不平衡,影響了教師開展音樂教學活動的能力和效果。 儘管一些學校非常重視音樂教育,但如果過度強調某一方面的培養,可能會導致音樂教育的發展失衡。此外,研究還發現,幼稚園教師的音樂專業背景和教學經驗存在較大差異,有些教師雖然具備音樂基礎,但教學方法和策略上有所欠佳,另一些教師缺乏系統的音樂知識和技能。這種能力上的差異不僅限制了音樂教學的品質,還阻礙了幼兒音樂素養的全面發展。最後,研究者依據上述結論據出相關建議,以提供給後續研究者為參考。

The Production of Marketspaces: Urbanization and Street Vendors in Areia Preta, 1970 - 1994 - Lou, Ka U. (2024)
This thesis applied Henri Lefebvre's “Production of Space” to analyze two productions of marketspaces to understand the urbanization of Areia Preta (黑沙環) between 1970 and 1994. In the early 1920s through the 1980s, Areia Preta (黑沙環) underwent land reclamation and urbanization, but its development lagged behind other reclaimed areas. The government seemed to lack a clear development plan for Areia Preta (黑沙環) and instead used it as a reserve land for future city expansion. From the 1940s to the 1960s, large numbers of refugees and immigrants flooded into Macau, overwhelming the government's ability to properly settle the population. As a result, Areia Preta (黑沙環) became an agricultural area with informal settlements. In 1966, the government announced an Urbanization Plan for Areia Preta (黑沙環), but it was limited in scope and did not fully develop the area. Another wave of immigrants arrived in the late 1970s, further increasing the shanty settlements in Macau. It was not until 1985 that the government began establishing “economic housing” to settle the shanty area inhabitants, marking the start of Areia Preta (黑沙環) ’s transition from agricultural to urban residential development. As more immigrants settled in Areia Preta (黑沙環) in the late 1970s, informal marketspaces emerged organically, with hawkers and street vendors occupying public spaces. This led to issues around 5 traffic, hygiene, crime, and food safety. In 1986, the government formalized these informal markets by establishing designated hawker zones and registering vendors. The culmination of this process was the opening of Iao Hon Market in 1994, which combined the functions of a marketplace, park, and social facilities. This influenced the development of market buildings in Macau in the 21st century.

Resource teachers’ attitudes toward and implementation of Inclusive Educational Plans (IEP) in Macau secondary schools: a case study approach - U, Sio Ian (2024)
This study explores the attitudes of resource teachers toward IEPs, identifies the challenges and facilitators that influence their implementation and the overall effectiveness of inclusive education practices in Macau. The findings of the study revealed resource teachers play a pivotal role in establishing and implementing IEP for students with special educational needs. Nevertheless, it is discovered that there is little significance of IEP for catering the needs of students with SEN in the actual inclusive educational environment despite the fact that most teachers recognize the importance of IEP. Findings also revealed that the current IEP is often seen as a limited reference tool, lacking practical application in the classroom. The absence of progress monitoring and effective evaluation negatively impacts the value of the IEP. Teachers'insufficient skills in assessing students’ progress and the limited content of the IEP further hinder its effectiveness in supporting students with SEN. The study highlights the need for improvements in practicality, evaluation, and content to enhance the effectiveness of IEP oncatering the needs of students with SEN. Meanwhile, the findings revealed obstacles including teachers' lack of professional knowledge, cumbersome administrative processes, limited human resources, low parent involvement, and inconsistent progress monitoring. These challenges hinder the effectiveness of IEP implementation. Oppositely, the only key facilitator, which is student progress, allows for reflection and adjustments in teaching practices. Improving teacher training, streamlining administrative procedures, increasing resources, enhancing parent involvement, and standardising progress monitoring are crucial for optimising IEP implementation and supporting students with special educational needs.

Teachers' Perspectives, Challenges, and Strategies for Integrating STEM Education into the Curriculum - Lam, Chi Seng (2024)
"This study investigates the perspectives, challenges, and strategies of STEM teachers in Macau as they integrate STEM education into their curricula. STEM teachers in Macau generally consider the integration of STEM education essential for enhancing students' creativity and problem-solving abilities. However, during the implementation process, they face challenges such as insufficient resources, limited opportunities for professional development, and difficulties in interdisciplinary collaboration, which restrict the effectiveness of STEM teaching. This study employed a qualitative research approach, conducting in-depth, semi-structured interviews with STEM teachers in primary and secondary schools in Macau to understand their experiences and needs. Purposeful sampling was used to ensure diversity and representativeness of the sample. The findings indicate that schools lack sufficient STEM teaching resources (such as equipment and materials), and limited professional development opportunities prevent teachers from effectively mastering new technologies and teaching methods. Furthermore, interdisciplinary teaching is constrained by challenges in collaboration and curriculum design. Low student engagement and insufficient parental support also affect the effectiveness of STEM education. The results suggest that schools should enhance resource allocation, promote professional development for STEM teachers in Macau, and encourage interdisciplinary teaching collaboration to improve the quality of STEM education, thus strengthening students' creativity and problem-solving skills. These findings offer valuable insights for STEM educators and policymakers to foster the comprehensive development of STEM education.

Exploring the Emotional Connection Through User Interfaces and Aesthetic Design to Improve User Experience in Macau's Mobile Food Delivery Apps - Cheang, Hoi Kan (2024)
In the everchanging environment of the digital era, incorporating new technologies has become a critical engine for company development and progress Mobile applications, for example, have emerged as important tools for reaching and engaging a diverse client base These apps° user interface ¥UI¦ design is essential to this engagement since it directly influences the ease of use, user experience ¥UX¦, and, ultimately, the organisation°s overall reputation Macau has experienced a significant shift in food delivery service in recent years, with a quick transition to an online platform Three significant companies have emerged in this fastpaced atmosphere, each vying for a piece of the market These platforms act as meal order brokers, linking customers and restaurants, with most eateries available on all three apps In this situation, it is vital to identify the factors that influence clients to pick one application over another Simultaneously, pinpointing the pain points inside competitors° applications that generate unhappiness among certain customers becomes a crucial goal This research aims to uncover the primary factors influencing user app preferences in the Macau food delivery business, providing insight into the strengths and weaknesses that impact customer choices and, as a result, the trajectory of these organisations

Enhancing consumer purchase intentions for sustainable packaging products: An in-depth analysis of key determinants and strategic insights - Duarte, Paulo; Silva, Susana C.; Roza, Afonso S.; Dias, Joana Carmo (2024)
Environmental concerns drive corporate and consumer focus on sustainable packaging. Research explores key factors influencing consumer intent, emphasizing the importance of strategic integration for enhanced purchase intentions and environmental goals. A comprehensive literature review identifies factors such as perceived value, willingness to pay, environmental concern, and attitude toward sustainable packaging. Empirical validation using survey data demonstrates the statistical significance of these factors on consumer purchase intentions, with the willingness to pay to emerge as the most influential determinant. Stakeholders are urged to incorporate these findings into strategies for sustainable packaging, fostering positive environmental impact, and informing academic and managerial discussions.

COUPLE THERAPY IN MACAO: SOCIETY AND PROFESSIONALS’ PERCEPTION - Nascimento, Do; Maria, Rejane (2024)
The current quantitative study aims to understand/investigate the perception of Macao society towards couple therapy and therapists and the perception of Macao's professionals working with couples about couple therapy services in Macao. Given the small sample of this study of professionals who work as therapists for couples in Macao, this indicates that there is not a large number of them. The result of the research indicates also a general positive attitude of professionals towards clients but also indicates that couple therapy needs improvement. The sample used to measure the society shows that the society manifested moderate positive attitudes toward couple therapy. However, the findings may reveal that there are still weak points of societal knowledge and contact for couples therapy services. The outcome manifested that Macao has limited literature about Family and Couple Therapy which may be relevant to understand the poor knowledge of the society related to this field. The current study suggests the elaboration of future studies about Couple Therapy services and about the concept of couple therapy to promote therapeutic service to couples and academic researchers that promote governmental support to offer professionals validation.

Right Turn Only? Review of God is an Englishman: Christianity and the Creation of England. Bijan Omrani £25; 394 pages; Forum Books. - Percy, Martyn (Journal of Anglican Studies, 2025)

The Importance of Being Earnest - Percy, Martyn (Journal of Anglican Studies, 2025)

Forgetting: Its Meaning in the Zhuangzi’s Philosophy of Self-Cultivation - Bai, Ziqiang (Religions, 2025)
The significance of forgetting in the Zhuangzi and its methodological significance for living a good life in particular has long been recognized by Zhuangzian scholars. However, with regard to what is really meant by forgetting, scholars are still far from reaching some clear consensus. Thus, with the aim of clarifying what is meant by forgetting in the Zhuangzi, I propose a wholistic understanding of forgetting in terms of the Zhuangzian conception of human self-cultivation. On the one hand, it involves an analysis of how forgetting is used negatively in the Zhuangzi to characterize and explain human fallenness. On the other hand, it also entails a careful analysis of all positive uses of forgetting in the text to mean our elimination of chengxin, orientation to the Dao, and fitness with all things in harmony.

A Company-Based View on Sustainable Packaging Orientation - Duarte, Paulo; Ribeiro, Maria Inês; Silva, Susana C.; Pinhal, Rúben; Estima, Ana (Sustainability, 2025)
This study aims to understand how companies address and integrate sustainability challenges in packaging design, as well as the motivations and processes that influence managers’ decisions when adopting sustainable practices. Semi-structured interviews were conducted with managers from five major Portuguese companies to gather qualitative data on the motivations and processes related to sustainable packaging strategies and actions. The list of questions was developed based on the literature review, from which the dimensions to be analyzed were identified. The results indicate that several factors influence companies’ decisions regarding sustainability in packaging. Despite some factors being beyond the control of companies, the interviews reveal that companies possess the necessary knowledge and are committed to adopting more sustainable packaging.

High variability in aggression and habituation to the mirror assay in ornamental Siamese fighting fish Betta splendens - Silva, Melina Coelho da; Canário, Adelino V. M.; Hubbard, Peter C.; Cardoso, Sara D.; Gonçalves, David (acta ethologica, 2025)
Understanding consistent inter-individual variability in animal behaviour, known as personality traits, is essential for exploring the mechanisms and evolutionary consequences of behavioural diversity. Aggressive behaviour influences survival, resource acquisition, and reproduction, so clarifying individual differences can enhance our understanding of ecological dynamics and improve experimental design accuracy in behavioural studies. In this study, ornamental male Betta splendens, a model organism for aggression research, were analysed for intra- and inter-individual variability in aggressive responses to their mirror image-a standard method for assessing aggression in fish-once per week, and their consistency was evaluated over three consecutive weeks There were significant differences in aggressive behaviour across individuals, with coefficients of variation ranging from 29 to 60%. While most fish exhibited the full suite of aggressive displays, some showed no aggressive behaviour, while others only displayed threat behaviours but did not advance to the attacks. The consistency of individual threat and attack behaviours varied, but repeatability was high overall (intra-class correlation coefficients >= 0.5), indicating that individual fish have different levels of aggression. There was habituation to the mirror assay, with aggression decreasing significantly by the second week, though the degree of habituation, a form of learning, varied among individuals in some behaviours. Air-breathing frequency correlated positively with aggression behaviours and can be considered an indicator to infer aggression level in this species. These results indicate that inter-individual variation in aggressive behaviour and habituation to repeated testing using the mirror assay should be considered in aggression studies using B. splendens and potentially in other species.

Uneasy Allies: Sino-American Relations at the Grassroots, 1937-1949. Edited by Zach Fredman and Judd C. Kinzley - Roberts, Priscilla (Journal of Social History, 2025)
This anthology has been skillfully edited by two excellent young scholars of the impact of grassroots and non-formal transnational interactions upon Sino-American relations during the late 1930s and 1940s, years when first war with Japan and then an internecine civil war consumed China. The collection highlights “a motley array of Chinese and Americans who have long flown under the radar,” neglected by the official narrative of dealings between China and the United States which, according to the authors, has focused primarily upon a rather restricted cast of characters, most of them high-level official figures (3). The authors also deliberately draw upon both Western and Chinese sources, utilizing archival and printed materials from repositories in Taiwan, mainland China, North America, and beyond. The selection of individuals and enterprises featured in this fascinating collection is undoubtedly eclectic, ranging from Herbert Yardley, an expert cryptographer who spent 1938 to 1940 in China, training young Chinese codebreakers to decipher Japanese codes, to Lieutenant Colonel Arthur Evans, who took advantage of his military position in Taiwan following the Japanese surrender to appropriate and sell a small fortune in confiscated gold. Along the way, one encounters Chinese, British, and American guerrilla operatives in World War II South China; Gong Peng, the young Chinese spokeswoman for the Communists in Chongqing, the wartime capital, who enchanted and won over to her cause a wide swathe of Western journalists and diplomats; Gu Gengyu of Sichuan, who gained control of China’s lucrative hog-bristle production during the 1940s, selling in bulk to the United States government; and General Haydon Boatner, righthand man to Joseph W. Stilwell, the U.S. commander in the World War II China-Burma-India theater.

Perspectives for the School Management: A Qualitative Study of EFL Teacher's Self‐Efficacy and its Related Factors - Lam, Stacy M. I.; Kuok, A. C. H.; Baker‐Malungu, Laurie; Negreiros, Joao G. M. (Psychology in the Schools, 2025)
As societies globalize, mastery of a second language or multiple languages has become an important index to enhance interaction in the society, in that English is a widely used medium of communication globally. For engagement in international business, commerce, science, technology, and governance, the benefits of an efficacious English language teaching force to facilitate the English acquisition process of students in classrooms around the world is highly valued. The objective of the research was to investigate the possible factors (internal and organizational) related to EFL teacher's self-efficacy in Macao (Chinese Medium Instruction context) via qualitative approach. As evidenced through the EFL teachers' interviews, teachers' experience, as well as some external factors in term of working environment, organizational socialization, and work engagement can be possible factors positively related to their self-efficacy. Recommendations for the school management and educational department to enhance and sustain the efficacy of EFL teachers were discussed.

INNOVATIVE USE OF GAMIFICATION FOR CHILDREN'S ENVIRONMENTAL EDUCATION IN MACAU :THE CASE STUDY OF “ I MACAU ” - Chen, Si Yu (2025)
With the rapid development of mobile network, APP has become an important platform for children to acquire knowledge, entertainment and learning. Environmental education APPs have great potential to cultivate children's environmental awareness with the feature of “edutainment” and “fun”, as well as to stimulate their interest in learning and change their behavioral habits. Starting from children's UI and UX design, we use creative and child-friendly design to enhance the attractiveness of the product and the user's adhesion. Through quantitative research, we investigate the market and user needs, and analyze competitors. Through qualitative research, we analyze the content of the product using educational psychology as a starting point. The main motivation of this study is to enhance children's interest in environmental protection and their sense of social responsibility through game- based teaching, in view of the environmental problems in Macao and the world.

A FINANCIAL VALUATION OF FORD MOTOR COMPANY - Brito, Martins De; Ermickson, Staline (2025)
Ford Motor Company (Ford) is an American car manufacturer and one of the leading automobile manufacturers with over a century of history in the auto industry. The Company is headquartered in the United States, in Dearborn, Michigan. However, it has operations in over 125 countries around the world, including Europe, Africa, Asia, and South America, offering a wide range of vehicles under the Ford and Lincoln brands. The Company has demonstrated resilience and adaptability in response to shifts according to consumer preferences, technology advancements, and government regulations. The company has been investing constantly to restructure and position itself and remain competitive. Therefore, finding strategies to boost sales and get high returns from invested capital is a must for the company to keep its market share, even though this is still a challenge due to the nature of the automotive industry, which brings intense competition from both traditional and new entrants, particularly EV manufacturers. In this study the focus is not only to estimate the intrinsic value of Ford Motor Company as of 31, December 2023, but also to analyze essential aspects of the company including SWOT, PESTEL, and Porter’s five forces analysis to get a framework of internal and external environment of the company which enables us to identify strategic opportunities, competitive advantage, vulnerabilities, and threats of the Company. After understanding the dynamics of the company and the economic overview, which are crucial to predict the impact of key assumptions when evaluating the company’s intrinsic value. For the second part of our study, the attention goes to the financial analysis of both historical and forecasted financial statements that are extremely important to apply for the Discounted Cash Flow valuation methods and later to perform a sensitivity analysis to understand the Company’s financial performance. Therefore, Ford Motor Company’s intrinsic value from the three discounted cash flow models leads us to conclude that the Ford stock’s price is currently undervalued, and it is expected to grow in the future.

INDOOR AIR QUALITY(IAQ) ASSESSMENT IN SEVERAL SITES IN MACAO - Ye, Wen Long (2025)
Indoor air quality (IAQ) is a critical public health concern given that individuals spend approximately 90% of their time in enclosed environments. Poor IAQ has been linked to respiratory diseases, cardiovascular conditions, and cognitive impairment, while improvements in air quality have demonstrated measurable benefits, including enhanced workplace productivity (2 to 7 times greater efficiency) and reduced prevalence of asthma and allergies. This study investigates IAQ across diverse occupational settings in Macao, employing a combination of environmental sampling and the U.S. Environmental Protection Agency (USEPA) exposure model to assess health risks associated with prolonged indoor exposure. Field sampling was conducted in five representative workplaces (restaurants, student dormitories, auto repair shops, offices, and parking security rooms), and particulate matter was collected from air conditioning filters to detect heavy metal content in the samples. Subsequently, we applied the PMF model to analyze the pollution sources and the US EPA exposure model to assess health risks and evaluate the carcinogenic risks in the five representative workplaces. The forward matrix factorization (PMF) model identified six major pollution sources: traffic emissions (23.8%, Zn/Sb), building materials (21.6%, Al/Ti), cooking activities (18.5%, Na/Ca), chemicals (15.2%, Ag/B), electronic devices (12.3%, Tl), and outdoor activities (8.6%, Co/Ni). The health risk assessment using the US Environmental Protection Agency (USEPA) exposure model showed that the overall non-carcinogenic risk (HI = 6.16×10-6) and carcinogenic risk (6.57×10-9) were below the safety threshold, indicating that its direct health hazard was minimal. However, nickel and chromium were identified as the main contributors to potential long-term risks.This study is currently only a preliminary exploratory study and provides a basis for subsequent research.These findings underscore the necessity for site-specific IAQ management strategies, such as enhanced mechanical ventilation, air filtration upgrades, and occupancy regulations. The study provides policymakers with evidence-based insights to mitigate health risks in high-exposure environments while establishing a framework for future IAQ monitoring in urban settings.

ABUNDANCE AND DISTRIBUTION OF MICROPLASTICS IN THE COASTAL ENVIRONMENTS OF MACAO: ANALYSIS OF MANGROVE AND NON-MANGROVE AREAS - Lam, Hao Cheng (2025)
The pervasive presence of microplastics in the environment constitues a significant challenge for internationalntern conservation efforts. Since the increase in anthropogentic activities and inadequate plastic waste management over all years, Macao coastal ecosystems have been greatly impacted. Therefore, it is essential to assess the presence and characteristics of microplastics in both waters and sediments along the coastlines of Macao particularly focusing on mangrove and non-mangrove areas. This evaluation aims to gather data on the sources, transport mechanisms, and ecological impacts of microplastics in Macao's coastal waters. A recent local report has indicated that Macao's water sources are not completely free from contamination. This has become a significant concern, as coastal and wastewater sources are heavily polluted with microplastic particles. Macao has been referred to as one of the world's most pressing plastic ocean pollution areas, with one of the highest rates of such pollution globally. Microplastics, however, are not the only plastic pollutant found, as nanoplastics have been found in shore waters, harming ocean ecosystems and becoming incorporated into the food chain. This research was used to quantitatively estimate the density and occurrence of microplastics in Macao coastal ecosystems in mangrove and non-mangrove areas (Taipa Mangroves Wetland, Cotai Ecological Reserve, Coloane Village Wetland) and Hac Sa beach. The results show that the non-mangrove site has a density of microplastics at 267.98 pieces/kg, which has the lowest of all the sampling stations, and Taipa Mangroves Wetland, with the highest concentration of microplastics within the forest among the sampling stations in the mangrove zone of Macau. This research can also provide useful information for environmental conservation and management plans.

澳門特殊教育教師職業成就感現狀調查研究 - Pun, Lai Ieng (2025)
The Administrative Regulation No. 29/2020 on the Special Education System has been officially implemented since September 2021. The promulgation and enforcement of this important regulation mark that Macao's special education cause has entered a new era of development. In the overall system of special education, the teaching staff has always played a vital role. Their professional literacy, teaching status, and career feelings directly affect the quality and effectiveness of special education, and further concern the growth and future development of special students. This study focuses on the group of special education teachers in Macao, with the core goal of in-depth exploring various situations in their career. Specifically, it mainly revolves around teachers' current status, including their actual feelings in the teaching process, faced difficulties and challenges, as well as their demands and expectations for professional development. Meanwhile, it emphasizes the analysis of the current situation of teachers' professional achievement motivation, understanding the inner satisfaction and achievement gained in special education work, and further explores various factors affecting teachers' professional achievement motivation, such as the school management environment, parents' cooperation degree, society's cognition and support for special education, and teachers' own professional growth background. This study adopts qualitative research methods and semi-structured interviews, uses Grounded Theory three-level coding to carefully and deeply interpret teachers' statements, so as to extract core information and key themes. On this basis, it summarizes and draws research conclusions: Social perception shows obvious polarization in the public's cognition of special education teachers;School environment indicates that the working environment has an important impact on teachers' professional achievement motivation. The lack of effective communication and collaboration mechanisms among colleagues, and even interpersonal conflicts, lead to teachers' difficulty in obtaining good interpersonal support and cooperative atmosphere at work, reducing their work enthusiasm and achievement motivation; Personal development shows that teachers generally lack clear plans and specific schemes for career planning, thus hindering long-term career development. This study further proposes a series of practical countermeasures and suggestions, aiming to improve the professional achievement motivation of special education teachers in Macao from multiple aspects, including school management, educational policy formulation, social support system construction, and teachers' own professional development, so as to provide solid talent support and guarantee for the sustainable development of Macao's special education cause. It ensures that every special student can obtain sufficient growth and development opportunities in a high-quality educational environment, better integrate into society, and realize their own value and potential. 《特殊教育制度》第29/2020號行政法規自2021年9月起正式落地實施，這一重要法規的頒布與執行，標誌著澳門特殊教育事業踏入了一個全新的發展時期。在特殊教育的整體體系中，教師隊伍始終扮演著至關重要的角色，其專業素養、教學狀態以及職業感受等各個方面，均直接影響著特殊教育的質量與成效，進而關乎特殊學生的成長與未來發展。 本研究將目光聚焦於澳門特殊教育教師群體，以深入探究其在職業生涯中的多種情況為核心目標。具體而言，主要圍繞教師自身當下的狀態，包括其在教學過程中的實際感受、面臨的困難與挑戰，以及在專業發展方面的訴求與期望；同時著重對教師職業成就感的現狀進行剖析，了解在特殊教育工作過程中收穫的內心滿足感及成就感；並進一步挖掘影響教師職業成就感的各類因素，如學校管理環境、家長配合程度、社會對特殊教育的認知與支持力度，以及教師自身的專業成長背景等多個層面。本研究採用質性研究方法和半結構訪談法，運用紮根理論三級編碼對教師們的言辭進行細緻拆解與深入解讀，從而提取出核心資訊與關鍵主題，並在此基礎上進行歸納總結，最終得出的研究結論，社會評價：大眾對特殊教育教師的認知呈現出明顯的兩極分化。學校環境： 工作環境方面對教師職業成就感產生重要影響。同事之間缺乏有效的溝通協作機制，甚至存在人際衝突，導致教師在工作中難以獲得良好的人際支持與合作氛圍，降低其工作積極性與成就感。個人發展： 教師在職業生涯規劃方面普遍缺乏明確的打算與具體的計劃，從而對長期職業發展產生了一定的阻礙。 本研究進一步提出了一系列切實可行的對策與建議，旨在從學校管理、教育政策制定、社會支持體系建設以及教師自身專業發展等多個方面著手，提升澳門特殊教育教師的職業成就感，為澳門特殊教育事業的可持續發展提供堅實的人才支撐和保障。確保每位特殊學生都能在優質的教育環境中獲得充分成長與發展的機會，更好地融入社會，實現自身價值與潛能。

了解照顧者與幼兒互動對語言發展的影響：澳門的社會工作研究 - Lam, Fong Chan (2025)
This study explored the influence of Macao caregivers' interaction with young children on language development, and analyzed the family language environment,sociolect-cultural influence and the current language development support system from the perspective of social work. A qualitative research method was used to analyze the interaction pattern and the progress of language development through in-depth interview and observation. The study found that the overuse of electronics, caregiver interaction and multilingual environment affected language development to different degrees, and made suggestions on how social workers should intervene and improve the support system for language development.

THE EFFECTIVENESS OF A PICTURE CARD EXCHANGE COMMUNICATION SYSTEM TRANINING ON THE COMMUNICATION BEHAVIOR OF NON-VERBAL STUDENT WITH RETT SYNDROME. - Lio, Ka Ian (2025)
本研究旨在圖卡兌換溝通系統訓練對無口語能力的雷特氏症學生溝通行爲之學習成效，此研究會以單一個案研究的A-B設計進行，以一位高中的雷特氏症學生為研究對象，以圖卡兌換溝通系統（Picture Exchange Communication System，簡稱 PECS）的第一階段和第二階段作為研究目標。由研究者及助理員一同記錄個案在進行研究時的結果，經過研究結果顯示： 一.圖卡交換溝通系統（PECS）階段一對雷特氏症狀的學生具有學習之成效。 二.圖卡交換溝通系統（PECS）階段二對雷特氏症狀的學生具有學習之成效。 本研究綜合上述結果，提出對教導雷特氏症學生溝通行爲教學提供相關建議。 This study aims to investigate the learning outcomes of Picture Exchange Communication System (PECS) training on the communication behaviors of non-verbal students with Rett Syndrome. The research will adopt a single-case A-B design, focusing on a high school student with Rett Syndrome. The first and second phases of PECS will be set as the research objectives. The researcher and assistant will jointly record the case's performance during the study. The results show that:. Results show: 1.PECS Stage 1 is effective for students with Rett syndrome. 2.PECS Stage 2 also shows effectiveness for these students. Based on these findings, the study offers relevant suggestions for teaching communication behaviors to students with Rett syndrome.

CHANGES IN THE CONCEPT OF “HYGIENE” IN THE LATE QING DYNASTY – TAKING MACAU AS AN EXAMPLE - Wong, Si Nga (2025)
“Hygiene”, a “concept” discussed throughout this thesis, is now regarded as a necessary means to ""protect life"". It is generally believed that hygiene has a certain relationship to infectious diseases, and its definition is based on modern Western “hygiene” theory. In fact, the concept of “hygiene” also existed in ancient China, but the definition of “hygiene” differed from that in the West. In order to better distinguish between the two, the following thesis uses the word “wei sheng” for the traditional Chinese concept of “hygiene”. Its meaning refers to how people prevent diseases in their daily lives, including eating habits, daily life, and so forth, in order to achieve the related ideal of longevity, an interpretation that differs from the current definition of hygiene introduced from the West. This thesis will explain the difference between the two. In addition, this thesis uses Macau as a case study and example. As a place that was once colonized by Western countries, Macau has been particularly directly influenced by these modern ideas. Among them, the Western concept of “hygiene” was spread and implemented with the Portuguese management of Macau, especially in the construction of hospitals and measures taken in response to multiple plagues in the 19th century. How did the Chinese in Macau view these Western concepts? What changes did they prompt in Macau? This thesis will mainly discuss four questions. How did hygiene concepts change in China during the late Qing Dynasty? Taking Macau as an example, how did the Chinese view these changes? Did they prompt any conflicts between cultures? What was the relationship between changes in hygiene concepts and measures implemented to handle plagues and epidemics?

A STUDY ON THE ATTITUDES OF SECONDARY SCHOOL TEACHERS TOWARDS INCLUSIVE EDUCATION AT A SCHOOL NOT PARTICIPATING IN INCLUSIVE EDUCATION PROGRAM IN MACAU - Lao, Nim Teng (2025)
This study focuses on the field of inclusive education using qualitative methods, conducting semi-structured interviews with eight secondary school teachers in a school in Macau that is not participating in inclusive education programs. Employing ecological systems theory, it explores their understanding, perceptions, willingness toward inclusive education, the challenges they face, and their suggestions. The findings reveal that interactions among various systemic levels shape teachers' attitudes. At the macrosystem, limited societal understanding and prevalent public prejudices against students with special needs influence teachers' perceptions and acceptance. The exosystem highlights a lack of professional training and policy support, undermining teachers' capabilities and confidence. Communication barriers between teachers, parents, and colleagues within the mesosystem hinder the exchange of information about students with special needs. At the microsystem, teachers' personal perceptions and experiences mold their attitudes, where stereotypes and negative experiences impact their approach and, consequently, student learning. To address these challenges, teachers suggest that Macau should establish bachelor's degree programs, enhance teacher training, and increase societal advocacy. Additionally, schools should create teams focused on inclusive education and ensure the provision of necessary resources. Based on these insights, this study suggests that school should build inclusive education teams and provide school-based training programs, and the government should improve the practicality of teacher training and enhance public and parental understanding of inclusive education, to facilitate its effective implementation by teachers. 本研究聚焦於融合教育領域，採用質性研究方法，透過半結構式訪談收集 八位澳門非參與融合教育計劃學校中學教師的見解，並以生態系統理論為框 架，探討他們對融合教育的認知、看法、實施意願和挑戰，以及他們的建議。 研究發現，各系統間相互的影響形成了教師的態度。在宏觀系統上，社會 對融合教育的認識不足、大眾對融合生的偏見會影響教師對融合生的看法和接 納程度。在外部系統中，教師感受到專業培訓和政策支持的缺失，削弱了他們 實施融合教育的能力和信心。而在中間系統，教師與家長及同事的溝通上出現 障礙，使得教師在獲取融合生信息方面遭遇挑戰。微觀系統中，教師的認知和 經驗進一步塑造了他們的態度，他們雖認識到融合生有特殊需求，但對融合生 的刻板印象影響着學生的發展。此外，失敗的經驗、工作壓力也對他們的態度 造成負面影響，繼而影響到學生的學習。受訪教師提出，高等院校應設立學士 學位，政府應加開教師培訓，同時加強社會宣導，學校亦應建立融合教育小組 和提供適當的設備，以改善現存的問題。 基於上述發現，本研究建議學校成立融合教育小組和提供校本培訓，並呼 籲政府加強教師培訓的實用性、提高家長和公眾對融合教育的宣導，以協助教 師有效實施融合教育。

STRESS LEVELS AMONG MAINSTREAM SCHOOL TEACHER IN MACAO WORKING WITH STUDENTS WITH SPECIAL EDUCATIONAL NEEDS: A QUANTITATIVE STUDY - Lei, U. Teng (2025)
This study investigates the stress levels experienced by mainstream schoolteachers in Macao when working with students with special educational needs (SEN). Using a quantitative research approach, the study examines the current conditions faced by these educators. ""Mainstream schools"" in this context refer to private school not participating in the government’s inclusive education program. The research employed a questionnaire survey targeting kindergarten, primary, and secondary school teachers across Macao’s mainstream schools. Data were collected using a self-designed instrument, the Macao Mainstream Teachers’ Stress Questionnaire in Working with SEN Students, through via snowball sampling. A total of 92 valid responses were received. Statistical analyses—including one-sample t-tests, independent t-tests, one-way ANOVA, confirmatory factor analysis (CFA), and structural equation modeling (SEM)— were conducted, obtaining the following results: 1. Macao mainstream schoolteachers reported moderate-to-high stress levels when working with SEN students, with the ""student behavioral issues"" representing the most significant stress domain. 2. No significant differences in overall stress or subscale scores were observed across teachers’ gender, teaching experience, educational qualifications, or teaching stages（kindergarten/primary/secondary 3. Teachers with different professional backgrounds exhibited significant differences in overall stress, student-related issues, curriculum and teaching , and professional competence, but not in support systems. 4. Significant differences in support systems were found among teachers holding different roles or teaching different student types, though no disparities emerged in other dimensions. 5. Student-related issues, professional competence, and support systems with a notable directional influence with curriculum and teaching. Also significant correlations were identified between Professional competence and support systems. Based on these findings, the study proposes actionable recommendations for educational authorities, school administrators, frontline teachers, and future researchers. 本研究主要探討澳門普通學校教師在面對有特殊教育需要學生時的壓力情 況，透過量性研究的方法，了解澳門普通學校教師的實際情況。普通學校是指沒 有參與政府融合教育計劃的私立學校。 本研究採用問卷調查法，以全澳普通學校的中、小、幼教師為研究對象，以 自編的「澳門普通教師在面對有特殊教育需要學生時的壓力調查問卷」為研究工 具蒐集數據。研究採用滾雪球方式填答，共收回有效問卷91 份。使用單一樣本 t 檢定、獨立樣本t 檢定、單因子等級變異數據分析、單因子變異數據分析、驗證性因子分析、構建結構方程模型統計方法，進行資料處理分析，獲得結果如下： 一、 澳門普通學校教師在面對有特殊教育需要學生時壓力現況呈「中等程度」， 其中「學生問題」層面的壓力相對最大。 二、 不同性別、服務年資、最高學歷、任教學段在整體教師壓力及各層面上沒有顯著差異。 三、 不同專業背景教師在「整體壓力」、「學生問題」、「課程教學」、「專業能力」上有顯著差異。而在「支持系統」上沒有顯著差異。 四、 擔任不冋職務及教授不同學生類型的教師在「支持系統」上有顯著差異。 而在其他層面上沒有顯著差異。 五、 「學生問題」、「專業能力」及「支持系統」與「課程教學」呈預測效應。 「專業能力」與「支持系統」呈顯著相關。 最後，本研究根據研究成果提出具體建議，供教育相關部門、學校行政、前線教師及未來研究者參考應用。

A STUDY ON THE ENGLISH LEARNING OUTCOMES AND MOTIVATION OF FIRST-GRADE PRIMARY SCHOOL STUDENTS USING DIGITAL GAME-BASED LEARNING: A CASE STUDY OF THE WORDWALL DIGITAL GAME PLATFORM - Ng, Weng I. (2025)
This study explores the influence of digital game-based learning on the English learning outcomes and learning motivation of first-grade primary school students in a private girls' school in Macau. The researcher used the Wordwall digital game platform as the medium and conducted teaching experiments using the quasi-experimental research method. Two classes were divided into the experimental group (n=24) and the control group (n=21) according to the convenient sampling method. The digital game-based learning method was integrated into the teaching materials and school-based self-compiled content. The experimental group implemented the digital game-based learning method for 8 weeks. Using the Wordwall game platform once a week, and 20 minutes each time, the control group maintained the traditional didactic teaching method. The research tools included a self-compiled learning effectiveness test and a learning motivation scale. The total score of the learning effectiveness test was 40 points, and the total score of the learning motivation scale was 120 points. Data analysis was conducted using paired sample t-tests and independent sample t-tests. The research results show that: (1) The score of the experimental group in the post-test of learning outcomes was slightly higher than the control group, indicating that the digital game-based learning method has a positive impact on students' learning outcomes. (2) In terms of learning motivation, the post-test score of the experimental group was slightly higher than the pre-test score, while the control group showed the opposite, indicating that the digital game-based learning method has a positive impact on students' learning motivation. According to the research results, it is suggested that the following can be revised in future studies including (1) expand the scope of research samples and objects, (2) extend the time of teaching experiments, (3) adopt diversified assessment tools, (4) consider teaching environment and teacher factors, (5) conduct learning analysis for individual differences, and (6) carry out cross-disciplinary integration and teaching mode innovation. Exploring the impact of digital game-based learning on students' learning outcomes and motivation from more diverse perspectives. 本研究旨在探討數位遊戲式學習對澳門某私立女校小學一年級學生的英語學習成效和學習動機之影響。研究者以Wordwall數位遊戲平台為媒介，並透過準實驗研究法來進行教學實驗，將兩個班級按方便取樣的方式分為實驗組（n=24）和控制組（n=21），把數位遊戲式學習法融入教材和校本自編內容當中，實驗組實施為期8週的數位遊戲式學習法，每週使用Wordwall遊戲平台1次，每次使用時間為20分鐘；控制組則維持傳統講述法教學，研究工具包含自編的學習成效測驗卷和學習動機量表，學習成效測驗卷的總分為40分，學習動機量表的總分為120分，並以配對樣本t檢定與獨立樣本t檢定進行數據分析。 研究結果顯示：（1）在學習成效方面，實驗組的後測得分稍微高於控制組，顯示數位遊戲式學習法對學生的學習成效具正面影響。（2）在學習動機方面，實驗組的後測分數稍微高於前測分數，控制組則相反，顯示數位遊戲式學習法對學生的學習動機具正面影響。 根據研究結果顯示，建議未來的研究可擴大研究樣本和對象範圍、延長教學實驗的時間、採用多元化的評量工具、考慮教學環境和教師因素、針對個別化差異進行學習分析、進行跨領域整合和教學模式創新，以更多元的角度探討數位遊戲式學習對學生學習成效和學習動機的影響。

Financial Valuation of Starbucks Ltd. - Vong, Ho Kio (2025)
Financial Valuation of Starbucks Ltd.

澳門長期線上教學融合教育資源教師的工作壓力與之因應之研究 - Tang, Ieng I. (2025)
This study aims to explore the work stress and coping strategies of inclusive education resource teachers in Macau primary schools during long-term online courses. Based on the findings, the study seeks to understand the characteristics of work stress and coping mechanisms among primary school resource teachers, providing recommendations for future practices and references for relevant educational authorities. The research methodology involved interviewing seven primary school resource teachers, with interview data analyzed through thematic analysis. The findings revealed six sources of work stress for resource teachers in long-term online courses: First, parental and Societal Expectation Stress: Pressure from parental supervision, passive cooperation, and challenges in teaching innovation exacerbate psychological burdens, impacting online teaching effectiveness and teacher-student interaction quality. Second, technological Adaptation and Resource Limitations: Teachers face technological challenges, financial burdens, and environmental disruptions, affecting online teaching quality and efficiency. Third, workload and Career Development Stress: Online teaching intensifies dual responsibilities, peer competition, and salary inequity, worsening occupational stress and job dissatisfaction. Fourth, student Learning Outcomes and Behavior: Students’ technological inadequacies, lack of focus, low cooperation, difficulty in receiving feedback, and emotional issues increase teaching burdens and hinder online interaction effectiveness. Fifth, personal Health and Work-Life Balance: Online teaching exacerbates physical and mental strain, including physical fatigue, role conflict, and pandemic-related anxiety, undermining teaching stability and occupational security. Sixth, policy and Institutional Constraints: Ambiguous policies and poor course arrangements during the pandemic heighten decision-making pressure and psychological strain, diminishing teaching efficacy. In response to these stressors, teachers adopted tailored coping strategies. Finally, based on the findings, this study proposes recommendations for educational authorities, schools, primary school resource teachers, personal well-being, and future research. 本研究旨在探討澳門小學長期線上教學融合教育資源教師的工作壓力和因應的方式，並根據研究結果，了解小學資源教師的工作壓力與因應特性，以作為未來實務之建議及相關教育單位參考。在研究方法上，共訪談七位小學資源教師，並透過主題分析法分析訪談資料。研究結果發現小學資源教師的長期線上教學工作壓力來源有六個：（1）家長與社會期望壓力：家長監督壓力、消極合作與教學創新挑戰加劇教師心理負擔，影響線上教學成效與師生互動品質；（2）技術適應與資源限制：教師面臨技術挑戰、經濟負擔與環境干擾，影響線上教學品質與效能；（3）工作負擔與職業發展壓力：線上教學加重教師雙重任務、同儕競爭與薪資失衡，加劇職業壓力與工作不滿；（4）學生學習效果與行為：學生技術與專注力不足、配合度低、回饋難掌握及情緒問題，加劇教師教學負擔，影響線上互動成效；（5）個人健康與生活平衡：線上教學致教師身心負荷加劇，其中包括生理疲勞、角色衝突與疫情焦慮，衝擊教學穩定性與職業安全感；（6）政策與制度限制：疫情間政策模糊與課程安排失當，加劇教師決策壓力與心理負荷，影響教學效能。而針對疫情期間不同的壓力源，教師採取相對應的壓力因應方式。最後，本研究根據研究結果對教育主管機關、學校單位、小學資源教師、生活方面及未來進行之研究，提出相關建議。

ANALYSIS OF MICROBIAL CONTAMINATION IN RAINWATER COLLECTION SYSTEMS WITH DIFFERENT ROOF MATERIALS IN MACAO - Xie, Xin Ran (2025)
This study examined the microbial contamination characteristics of three different roof materials (green roof, metal roof, and concrete roof) during rainfall events. Through runoff samples collected from multiple rainfall events in the experimental rainwater collection system model, the pollution characteristics of total colony-forming units, Escherichia coli, and total coliforms were analyzed in combination with water quality parameters such as pH, turbidity, chemical oxygen demand (COD), and electrical conductivity. The study using the Wilcoxon Signed Ranks Test and found that the microbial contamination load of initial rainwater was significantly higher than that of subsequent runoff. The Mann-Whitney U test was used to compare the differences in microbial contamination caused by different roof materials. The results show that the metal roof performed the best in terms of microbial control, while the green roof had the poorest microbial control efficiency. The Spearman correlation analysis revealed that turbidity and conductivity were significantly positively correlated with microbial contamination, confirming that pollutants and nutrient ions are core factors driving microbial proliferation. Moreover, the metal roof exhibited outstanding disinfection efficacy under direct sunlight (microbial survival rate 0.00003% - 0.0004%), its high reflectivity and thermal conductivity working in synergy with UV radiation to destroy microbial DNA, while under shaded conditions, the sterilization efficiency decreased by approximately 100 times. The study suggests that metal roofs should be prioritized for use in water quality-sensitive scenarios. Green roofs need to be equipped with initial rainwater retention and substrate antibacterial improvement, and concrete roofs can enhance their antibacterial ability through hydrophobic surface treatment. The study provides a scientific basis for improving the design of rainwater collection systems in Macau, enriching the research cases of roof runoff pollution in tropical coastal cities, and is of great significance for improving the urban rainwater management system and protecting water environmental quality. 本研究考察了三种不同屋顶材料（绿色屋顶、金属屋顶和混凝土屋顶）在降雨期间的微生物污染特征。通过在实验雨水收集系统模型中多次降雨事件所采集的径流样本，结合 pH 值、浊度、化学需氧量（COD）和电导率等水质参数，对总菌落形成单位、大肠杆菌和总大肠菌群的污染特征进行了分析。研究采用威尔科克森符号秩检验，发现初期雨水的微生物污染负荷显著高于后续径流。采用曼 - 惠特尼 U 检验比较了不同屋顶材料造成的微生物污染差异。结果表明，金属屋顶在微生物控制方面表现最佳，而绿色屋顶的微生物控制效率最差。斯皮尔曼相关性分析表明，浊度和电导率与微生物污染显著正相关，这证实了污染物和营养离子是驱动微生物增殖的核心因素。此外，金属屋顶在阳光直射下表现出卓越的消毒效果（微生物存活率 0.00003% - 0.0004%），其高反射率和热导率与紫外线辐射协同作用，破坏微生物 DNA，而在遮阴条件下，其杀菌效率降低约 100 倍。该研究建议，在水质敏感的场景中应优先使用金属屋顶。绿色屋顶需要配备初期雨水截留装置和基质抗菌改进措施，而混凝土屋顶可通过疏水表面处理来增强其抗菌能力。该研究为澳门雨水收集系统的设计改进提供了科学依据，丰富了热带沿海城市屋顶径流污染的研究案例，对于完善城市雨水管理系统和保护水环境质量具有重要意义。

ENVIRONMENTAL EDUCATION ASSESSMENT WITH SEMANTIC NETWORK ANALYSIS: EXAMPLE FROM A UNIVERSITY IN THE GUANGDONG PROVINCE - Chen, Zi Jie (2025)
This study explores how to effectively evaluate the efficiency of environmental education (EE) among college students in Guangdong Province by comparing two complementary methods: (1) traditional statistical analysis of structured questionnaires using chi-square tests, and (2) semantic network analysis (SNA) of open-ended responses. The structured questionnaire assessed students' environmental knowledge, attitudes, behaviors, and education needs using multiple-choice and Likert-scale items. An open-ended question was included to capture students’ understanding of ""environmental protection"" in their own words, which was then analyzed through semantic network modeling. The study collected 225 valid responses from students at Guangdong University of Science and Technology. Chi-square tests revealed significant differences between first-year students and those in later years in their knowledge of environmental issues (e.g., χ², p < 0.05 across 35 indicators), but no significant differences were observed based on gender or place of residence. Semantic network analysis, using centrality, density, and clustering coefficients, showed similar cognitive divergences between academic years but confirmed no meaningful structural differences in conceptual associations across gender or residence groups. For instance, the semantic network of first-year students had lower density (0.031) and fewer central nodes than that of senior students, indicating a simpler understanding of environmental concepts. The convergence of results from both methods validates the use of semantic network analysis as a complementary, quantitative tool for evaluating students’ cognitive structures and discourse in environmental education. This integrated approach offers a richer and more nuanced perspective than traditional surveys alone. The findings suggest that environmental education efforts should focus more on advancing conceptual depth as students progress through university. Curriculum designers can use semantic analysis as an innovative diagnostic tool to improve the cognitive and discourse-based effectiveness of environmental education programs.

本澳長者生命自主與生活品質之相關探討 - Ho, Sut Ieng (2025)
With continuous advancements in technology leading to extended lifespans, a question arises: Are we adequately prepared to face and accept death when it eventually comes? What factors prompt us to proactively plan our end-of-life arrangements? These are important issues that merit understanding and attention. Therefore, this study aims to explore the current status and related factors between life autonomy and quality of life among the elderly in Macau. This study adopts a mixed-methods approach, primarily utilizing convenience sampling and snowball sampling. Data were collected through both online and offline methods using questionnaires. The questionnaire consists of three main sections: 1) demographic background information of respondents, 2) the Good Death Inventory (GDI), and 3) the World Health Organization Quality of Life-BREF Taiwan Version. A total of 512 questionnaires were collected, with 480 valid responses, accounting for approximately 94% of the total. Among the respondents, 61.1% were female, the majority had primary school education, 51.6% were married, but only 36.5% lived with their partners. Nearly 60% of participants rated their physical condition as average, 60% had chronic illnesses, though the prevalence of severe chronic diseases was low. Over 50% of participants had no religious beliefs and did not participate in any elderly services. The results show that 60% of participants exhibited moderate or above levels of attitudes toward a good death and quality of life. Analysis using one-way ANOVA and T-tests revealed significant differences in attitudes toward a good death across all demographic variables. Participants who were ""older,"" had ""lower education levels,"" were ""single"" or ""cohabiting,"" ""lived with friends,"" had ""no religious beliefs"" or were ""Catholic,"" had ""poor physical condition,"" ""did not receive elderly services,"" or participated in ""elderly daycare centers"" displayed poorer attitudes toward a good death. Additionally, participants considered ""anticipating future conditions,"" ""seeing desired people,"" ""natural death,"" ""living in a peaceful environment,"" and ""independent living"" as key aspects of a good death. Regarding quality of life, differences were observed across various demographic variables. In overall quality of life, participants who were ""older,"" ""never educated,"" ""single"" or ""cohabiting,"" ""lived with friends,"" had ""poor physical condition,"" or were ""using home support services"" reported poorer quality of life. In the physical health domain, those who were ""older,"" ""never educated,"" ""cohabiting,"" had ""poor physical condition,"" or were ""using home support services"" had lower quality of life. In the psychological health domain, those who were ""older,"" ""never educated,"" ""cohabiting,"" ""lived with friends,"" were ""Catholic,"" had ""poor physical condition,"" or were ""using home support services"" had poorer quality of life. In the social relationships domain, those who were ""older,"" ""single"" or ""cohabiting,"" ""lived with friends,"" had ""poor physical condition,"" or ""did not receive elderly services"" had poorer quality of life. In the environmental domain, those who were ""older,"" ""never educated,"" ""cohabiting,"" ""lived with friends,"" had ""poor physical condition,"" or were ""using home support services"" had poorer quality of life. Across the four domains (excluding overall quality of life), participants scored highest to lowest in the following order: physical health > social relationships > environment > psychological health, indicating that psychological health was the weakest domain. A positive correlation of varying degrees was found between attitudes toward a good death and different domains of quality of life, meaning that better quality of life was associated with better attitudes toward a good death. However, only the ""environmental"" and ""social relationships"" domains of quality of life showed a linear relationship with the Good Death Inventory, indicating that these domains are predictive of attitudes toward a good death, though their explanatory power is limited.

正向學習環境中教師對同儕合作與師生關係之影響﹕個案研究 - Ng, Ka Man (2025)

"MACAU’S STRATEGIES FOR IMPLEMENTING MART CITY POLICY: A STUDY OF THE STRENGTHS AND WEAKNESSES FROM THE PERSPECTIVE OF MACAU CITIZENS (2025)
This dissertation explores how smart city strategies are being used in Macau, focusing on what everyday citizens think about them. It explores both the positive aspects and the problems with how these policies are being put into action. While the Macau government has introduced several digital services. For example, the Macau One Account, electronic payments, and smart transport systems. There are many people who feel there’s a gap between technology and how well it actually includes everyone. The research is based on a close look at government plans (like the Macau SAR Five- Year Plan 2016–2020) and interviews with people from different age groups. Using a method of analyzing themes in the data, the study found that younger and middle- aged people generally find these tools useful and convenient. However, older adults often struggle because they aren’t as comfortable with smart city services and don’t get enough support. Also, even though the government says it welcomes public input, most people said they weren’t really involved in decisions, showing that the process is mostly top-down. The study points out some big challenges, like digital inequality, lack of public participation, and a mismatch between what policies aim for and what people actually need in daily life. It suggests making smart city planning more inclusive by offering digital tools in multiple languages, involving citizens in budgeting decisions, and providing digital training for those who need it. Overall, it argues that smart city development should focus more on fairness, access, and building public trust to truly improve urban life in a lasting and meaningful way.

澳門教師對融合教育培訓看法之探究 - Wu, Ho I. (2025)
The essence of education, which is 'to foster goodness and rectify the lost,' profoundly reveals that it is about promoting students' strengths and compensating for their shortcomings. The core concept of inclusive education follows this vein, emphasizing acceptance and integration to ensure that every student can learn and grow in the same educational environment, and providing the most appropriate teaching based on the characteristics of the students. However, teachers face many challenges in implementing inclusive education, including a lack of professional knowledge, scarce resources, etc. This study conducted in-depth interviews with frontline teachers in Macau, collecting views on inclusive education from teachers who have never received inclusive education training and those who have received different types of training, elucidating the difficulties they encounter in teaching practice, and their views on the existing training system, in order to further improve teacher training in inclusive education. The results show that most teachers have a positive attitude towards inclusive education and agree with its concept and value, but teachers who have never received and those who have received professional inclusive education training still face many difficulties in actual teaching. Therefore, teachers have expressed the need for inclusive education training to better cope with the challenges in inclusive education. Based on the interview results, two specific suggestions were made for the current inclusive education training: one is to increase targeted short-term training courses and establish a feedback mechanism; the other is to enhance the localization of the curriculum to make the training content more in line with Macau's educational environment and actual needs. This study aims to propose specific plans to optimize inclusive education training by analyzing teachers' actual needs and suggestions, in the hope of enhancing teachers' professional competence and further promoting the development and practice of inclusive education. “教也者，長善而救其失者也”，深刻揭示教育的本質，即發揚學生的優點並彌補其不足。融合教育的核心理念與此一脈相承，強調通過接納與共融，確保每位學生都能在同一教育環境中共同學習與成長，並根據其特質提供最適合的教學。然而，教師在實施融合教育的過程中面臨諸多挑戰，包括專業知識不足、資源匱乏等問題。本研究通過對澳門前線教師進行深度訪談，收集未曾接受融合教育培訓和接受不同融合教育培訓的教師對融合教育的看法、闡述其在教學實踐中遇到的困難，以及對現有培訓體系的看法，以期能夠進一步完善融合教育的師資培訓。 研究結果顯示，大部分教師對融合教育持正面態度，認同其理念與價值，但未曾接受和已接受融合教育培訓的教師，在實際教學中仍面臨諸多困難。因此，教師表達對融合教育培訓的需求，以更好地應對融合教育中的挑戰。 基於訪談的結果，對現行的融合教育培訓提出兩方面的具體建議：一是增加具針對性的短期培訓課程，並建立反饋機制；二是加強課程的本土化，使培訓內容更貼合澳門的教育環境與實際需求。 本研究旨在通過分析教師的實際需求與建議，提出優化融合教育培訓的具體方案，以期能夠提升教師的專業素養，並進一步推動融合教育的發展與實踐。

EXPLORING THE SPATIAL DISTRIBUTIONS OF HEAVY METALS FROM ROAD DUST IN MACAO - Liu, Yu Yang (2025)
Road dust contains a variety of heavy metals and is a widely used indicator for monitoring pollution and assessing environmental and health risks in urban ecosystems. In this study, road dust was collected from 8 representative areas in Macao. The spatial distribution of heavy metal content in road dust in Macao was determined by extracting the heavy metal content in each sample. Heavy metals in road dust are mainly found on busy roads, and the production of these heavy metals mainly comes from the particles worn off in the work of transportation vehicles, such as tires, brake pads, road dust, and emissions from exhaust pipes, These heavy metal particles scattered on the road will remain on the road surface for a long period and cause environmental pollution. This sampling was also collected when there was no rainfall in Macao for more than 7 days, which also ensured that the heavy metal content in road dust distributed in time and space was as close to accurate data as possible. At the same time, in this collection of road dust regulations, the sampling is strictly followed by recording the area, traffic flow, weather, humidity, and other factors. The addition of a large statistical analysis of variables helped to correlate the elements studied with several local sources of pollution: from local industrial plants and related activities, pavement modifications, power plants, road traffic, and the resuspension of particulate matter (RPM). Our findings suggest that combining chemical and isotopic monitoring of road dust may help implement more effective environmental management measures to reduce its adverse effects on ecosystems and human health. This study analyzed the temporal and spatial distribution of heavy metals in road dust from different locations in Macao, revealing the current situation of heavy metal pollution and its potential threat to human health. The results show that heavy metals primarily originated from human activities such as transportation emissions, industrial activities, and road construction. Through detailed analysis of the sampling points in G 1-G8, it was found that the concentration of heavy metals varied significantly in different areas, especially in areas with heavy traffic flow, in which the heavy metal content was generally higher.

"DREAM-EATINGTAPIR” ADREAMDETECTIONAROMATHERAPY INTELLIGENTDIFFUSER - Xu, Ying (2025)
With the cross development of neuroscience and artificial intelligence, the bio signal-based environmental adaptive technology has become a research frontier in the field of smart home. In this paper, we propose a smart aromatherapy machine system that can combine brainwave (EEG) monitoring and AI-driven, aiming to achieve dynamic optimisation of the home environment through real-time EEG signal analysis. The study first builds a multimodal data acquisition module to extract the characteristic frequency bands such as α-wave and β-wave to identify the user's relaxation, concentration or fatigue state. Secondly, a lightweight deep learning model is designed to classify EEG signals in real-time and ensure low-latency interaction through edge computing architecture. The system dynamically regulates the aromatherapy machine based on the classification results. Users can self-select a theme in the system according to their preferences or emotions, and then the aromatherapy device releases the corresponding aroma according to the selected theme to help the user fall asleep more easily. During sleep, the system continuously tracks the user's sleep dynamics through an integrated sleep monitoring application, which transmits the data to the device. At the same time, the system collects and analyses detailed data on sleep quality, dream activity and scent adjustment to generate a comprehensive report that is sent to the user's smartphone. This innovative design not only enhances the user experience, but also provides a scientific basis for assessing individual sleep conditions. Current research shows that aromatherapy has a positive effect on improving sleep quality and relieving anxiety symptoms. However, there is still a lack of research on the dynamic adjustment of fragrance based on real-time sleep data. This study aims to fill this gap by developing a system that enables personalised fragrance release based on user preferences and real-time sleep monitoring data, providing users with an unprecedented sleep experience.

Collaborative Partnerships for Driving Social Innovation: A Search for an Effective Collaboration Model for Cambodia - Pov, Srey Phoum (2025)
This study investigates the key challenges and success factors influencing collaborative partnerships for social innovation in Cambodia, aiming to develop an effective partnership model tailored to the local context. Employing a mixed-methods approach, the research synthesizes findings from a survey of 109 organizations across various sectors—including private companies, government agencies, NGOs, and academic institutions—and an extensive review of relevant literature. The study identifies critical obstacles such as trust deficits, communication breakdowns, resource constraints, organizational misalignments, and cultural differences that impede effective collaboration. Conversely, it highlights essential success elements, including open communication, shared goals, mutual trust, clear roles, ongoing engagement, and capacity building. The findings suggest that addressing systemic barriers while fostering trust and shared understanding are vital for sustainable social innovation in Cambodia. Based on these insights, the research proposes a practical collaborative partnership model emphasizing transparency, joint planning, flexibility, and stakeholder empowerment. The study contributes valuable theoretical frameworks and actionable strategies for practitioners, policymakers, and scholars seeking to enhance social innovation through effective collaboration in Cambodia and similar developing contexts.

DESIGNING FOR SAFETY: A USER INTERFACE STUDY ON PERSONAL SECURITY APPLICATION FOR WOMEN’S URBAN COMMUTES IN CHINA. - Yi, Qing Xi (2025)
Against the backdrop of the current rapid social and economic development, the scope and duration of urban women's travel activities have expanded significantly. Consequently, personal safety issues, especially violent incidents encountered during travel, have become increasingly prominent. This study focuses on the field of UI design, specifically the development of applications for women's safety, aiming to address the crucial issue of how to customize applications to meet women's safety needs. Although various safety applications already exist in the market, those specifically designed for women are scarce. To this end, we employed a quantitative research method, conducting an in-depth exploration of urban women aged between 18 and 65 through questionnaires, case analyses, and literature reviews. This research aims to design a mobile application specifically targeting urban women aged 18 to 65, with the goal of enhancing their safety and autonomy during travel. The main objective of the study is to use technological means to assist women's travel safety, while emphasizing that technological solutions should be part of a comprehensive approach that includes legal, educational, and other measures to improve women's sense of security. Through function optimization and intelligent design, a user-friendly and efficient interface will be created, enabling women to take immediate action and obtain necessary help and support when facing potential threats. Future work will focus on function optimization and intelligence enhancement, establishing a user feedback loop, and conducting long-term follow-up research, in order to continuously improve and refine the application and further safeguard women's travel safety.

EXPLORING MENTAL HEALTH PROFESSIONALS’ EXPERIENCE IN INTERACTING WITH ADULTS WITH INTELLECTUAL DISABILITY IN MACAU - Cheang, Chon Kit (2025)
This qualitative study explored the experiences of 15 Mental Health Professionals in Macau who interact with adults with intellectual disabilities (ID), aiming to understand how these interactions shape perceptions, relationships, and service practices. Using a phenomenological approach, semi-structured interviews were conducted with professionals from government-funded NGOs, including social workers, therapists, and healthcare providers. Data were analysed through thematic analysis, yielding seven key themes: (1) New perception of Service Users with ID (e.g., shifting from deficit-based to strength-based perceptions), (2) bidirectional personal transformations in professionals (e.g., increased patience, resilience, irritable), (3) Relationship Dynamics and Emotional Connections (e.g., familial, collegial, or mentor-like relationships), (4) A professional core service share by the perceived role (5) development of best practices emphasizing rapport and knee observations, (6) creation of safe worry-free spaces fostering mutual emotional support, (7) and Needs to be fulfilled in aging services, learning and community integration. Practical implications highlight the need for the addition of course structures related to people with intellectual disabilities in relevant occupational college courses, expanded staffing ratios, and policy reforms to address care gaps related to aging. By revealing the mutual influence of professional service-user relationships, where interactions foster staff growth and client empowerment, this study contributes to the global discussion on disability support, while providing actionable recommendations for Macau’s upcoming Ten-Year Rehabilitation Plan in 2026-2036. The findings hold value for policymakers, service providers, and educators seeking strategies to enhance workforce well-being and service quality in intellectual disability service.

心智圖教學對小學四年級學生中文閱讀能力的成效 - Cheong, Lai Ian (2025)
This study aims to explore the effectiveness of mind mapping instruction on Primary 4 students’ Chinese reading ability. Using a pre-and post-test quasi-experimental design with a control group, two classes of fourth-grade students from a girls' school in Macao participated in the study, with one class as the experimental group (n = 25) receiving mind mapping reading instruction, and the other as the control group (n = 16) receiving general reading instruction. Both groups received instruction for about four weeks, with approximately three sessions per week for a total of 11 sessions of 40 minutes each (i.e., 440 minutes in total). The first five sessions focused on narrative texts, and the next five sessions focused on expository texts, with the last session as a summary session. Both groups took the pre-tests using the narrative text from PIRLS (2021) and the expository text from the A3 version of the Reading Comprehension Growth Test, and the post-tests using the narrative text from PIRLS (2016) and the expository text from the A2 version of the Reading Comprehension Growth Test. The experimental group also completed the form regarding their post-instruction feedback for mind mapping instruction. Mann-Whitney tests found that general reading instruction did not significantly improve Grade 4 students’ Chinese reading ability, whereas mind mapping instruction significantly improved Grade 4 students’ Chinese reading ability, with moderate effect sizes (rank-biserial correlation of 0.70 [narrative text] and 0.57 [expository text]). Multiple regression analysis showed that the experimental group scored 0.11-unit higher on the post-test scores of narrative text reading than the control group after controlling their pre-test scores on narrative text reading; the experimental group scored 0.13-unit higher on the post-test scores of expository text reading than the control group after controlling their pre-test scores on expository text reading. In addition, 19 (76%) students in the experimental group gave positive feedback for the mind mapping reading instruction. Recommendations for Chinese teachers, schools’ initiatives at advancing reading instruction, and the government’s endeavor at teacher training related to mind mapping instruction. Limitations of the current study and future research directions were also discussed. 本研究者旨在探究心智圖教學對提升小學四年級學生中文閱讀能力的成效。採用有對照組的前後測準實驗研究設計，選取澳門某女校四年級兩個班級的學生作為研究對象，一個班級作為實驗組（n = 25）接受心智圖閱讀教學，另一個班級作為對照組（n = 16）接受一般閱讀教學。兩組均接受為期大約4週的教學，每週大約3節課，共11節，每節課40分鐘，總共440分鐘;首5節進行記敘文教學，後5節進行說明文教學，最段1節進行教學總結。兩組在接受相應的閱讀教學前，均接受了PIRLS（2021）的文藝性文章和《閱讀理解成長測驗》A3版本的說明文閱讀測驗;在完成教學後，均接受了PIRLS（2016）的文藝性文章和《閱讀理解成長測驗》A2版本的說明文閱讀測驗。實驗組在完成心智圖教學後也填寫了《對心智圖教學的反饋問卷》。Mann-Whitney檢驗發現，一般閱讀教學沒有顯著提升四年級學生中文閱讀能力；心智圖閱讀教學顯著提升四年級學生中文閱讀能力，效應值達到中等程度（rank-biserial correlation為0.70[記敘文]和0.57[說明文]）。多重回歸分析表明，控制了記敘文閱讀前測分數之後，接受心智圖閱讀教學的學生在記敘文後測分數上會比接受一般閱讀教學的學生高0.11個單位；控制了說明文閱讀前測分數之後，接受心智圖教學的學生在說明文後測分數上會比接受一般閱讀教學的學生高0.13個單位。此外，19名（76%）接受心智圖教學的學生對心智圖教學給出正向的反饋，認為心智圖能幫助她們提升閱讀能力、分析和統整文章內容、歸納文章重點、增強對文章的記憶，以及提升閱讀的趣味性。研究者針對中文老師、學校閱讀教學的推動以及政府在心智圖教學培訓方面，提出相應的建議；對本研究的不足之處和未來研究的方向也給出了建議。

INTERACTIVE PRODUCT DESIGN FOR ORGANIC PACKAGING： THE STUDY CASE OF ECOZEN - Ma, Jing Fei (2025)
With the rapid development of the food delivery industry, the burden of single-use packaging on the environment has become increasingly severe, highlighting the need for sustainable and eco-friendly alternatives. This paper proposes an innovative solution based on interactive product design for organic packaging, integrating organic takeaway boxes with a mobile app platform to enable the repeated use of personal organic food containers. This study explores the selection of organic packaging materials, product structural design, app functionality planning, and the construction of the courier-based recycling process. Through prototype design, user research, and data analysis, the feasibility and environmental benefits of this solution are demonstrated. The research findings provide a new design perspective for the circular economy in food packaging, contributing to the promotion of green consumption and sustainable development.

Effects of Microplastics on Kandelia obovata: Investigating Stress and Responses for Conservation and Management - Wong, Weng In (2025)
Mangrove resilience to anoxic conditions primarily occurs through adaptations in their root systems. Notably, increased root growth of existing pneumatophores in response to plastic suffocation has been observed in mangroves and can serve as a proxy to assess tree stress. The objective of this study is to determine the impact of varying levels of microplastic pollution on the morphological characteristics of mangrove plants. Fresh Kandelia obovata seedlings were collected from the Cotai Ecological Reserve, cultivated for 27 weeks, and subsequently exposed to polyethylene (PE) particles of 600 μm, 150 μm, and 13 μm in size at concentrations of 5% and 10% (w/w). The wet weight of the plant samples was measured at the beginning and end of the experiment, and morphological characteristics were recorded weekly. Morphological parameters including germination rate, number of leaves, root morphology, and survival rate, as well as environmental conditions (temperature and humidity), were evaluated to determine the influence of microplastic size, concentration, and environmental factors on plant development. Results indicate that smaller microplastics (13 μm) adversely affected the germination rate, leaf production, and survival of K. obovata. Furthermore, a higher concentration (10% w/w) of medium-sized microplastics (150 μm) led to a lower survival rate compared to the lower concentration group. These findings shows the negative impact of microplastic pollution on mangrove species and highlight the importance of addressing plastic contamination for effective mangrove conservation.

EXPLORING BIODIVERSITY IN MACAU’S URBAN WETLAND ECOSYSTEMS THROUGH E-DNA ANALYSIS - Kei, Leong Mei (2025)
Macau’s rapid urban development has significantly altered its natural landscapes, leading to the degradation and fragmentation of wetland ecosystems. Although diminished in size, these urban wetlands continue to deliver vital ecological services and sustain a range of biodiversity. Conventional methods for biodiversity assessment are often labor-intensive and unsuitable for regular monitoring in urban environments. This study utilized environmental DNA (eDNA) metabarcoding as a non-invasive and effective approach to survey biodiversity in 2 coastal and 7 freshwater urban wetlands in Macau. Environmental DNA was extracted from water samples collected from these nine representative wetland sites and analyzed using metabarcoding techniques to detect fish species. Three genetic markers were targeted to enhance taxonomic resolution, which included COI (mlCOIintF/LoboR1, 313 bp), 12S (miFish-U, 170 bp) and 18S (V4, 400 bp). Bioinformatic pipelines were used to process sequencing data, identify taxa, and compute biodiversity indices, providing a comprehensive snapshot of aquatic biodiversity in Macau’s urban wetlands. A total of 90 fish species were detected, including native species, migrants, and invasive taxa. Beta diversity analysis shows site and season together explained 50% of the variation in community composition (PERMANOVA R² = 0.50, p = 0.001), shaped by environmental gradients and seasonal turnover. These results highlight eDNA metabarcoding as an effective tool for biodiversity monitoring in urban wetlands and emphasize the need to preserve habitat diversity and management strategies in Macau.

MONITORING AND EVALUATION OF THE QUALITY OF RAINWATER HARVESTED FROM ROOFTOPS FOR REUSE AND SUSTAINABLE APPLICATION IN MACAO - Lu, Xiao Yu (2025)
Macao, a densely urbanized region with limited freshwater resources, faces significant challenges in water security, relying on over 90% of raw water imports from the Mainland. This study investigates the quality of rainwater harvested from three representative rooftop types (blue metal, concrete, and green garden roofs) to establish a scientific basis for sustainable reuse. The research reveals distinct water quality patterns and first-flush effects across roof materials through field sampling and laboratory standard of parameters, including organic matter, turbidity, and nutrients. Key findings show that green roofs exhibit the highest pollutant concentrations (e.g., COD: 52.27 ± 26.00 mg/L and conductivity: 525.75 ± 203.60 μS/cm) due to vegetation decomposition and soil leaching. In contrast, blue steel tile roofs yield relatively cleaner runoff but with pronounced initial pollutant surges. Concrete roofs produce alkaline runoff (pH up to 8.63) due to cement mineral dissolution. Statistical analysis confirms conductivity and turbidity as robust predictors of dissolved pollutants, with significant correlations to other parameters, enabling rapid water quality assessment. The study further evaluates the first flush effect; recommendations include material-specific collection strategies, IoT-integrated smart monitoring systems, and policy incentives for green roof adoption to balance ecological benefits with water quality management. This research addresses critical gaps in Macao's rainwater management, providing a sustainable urban water resource optimization framework.

澳門非高等教育教師效能感與抗逆力關係之研究 - Sam, Wai Chi (2025)
Teacher efficacy and resilience are critical factors influencing educational quality and student development. Teacher efficacy refers to teachers' beliefs in their capability to manage classrooms, implement instructional strategies, and engage students effectively. Resilience, on the other hand, denotes teachers' ability to adapt and respond positively to stress and challenges. This study aims to examine the current status of teacher efficacy and resilience among non-tertiary education teachers in Macao and to explore their differences and interrelations across various demographic variables. The target population comprised non-tertiary teaching staff in the 2024/2025 academic year. A questionnaire survey was conducted using the Teachers' Sense of Efficacy Scale （TSES） and the Connor-Davidson Resilience Scale （CD-RISC）, via the Tencent Questionnaire platform, with 125 valid responses collected from Macao non-tertiary teachers. Data analysis included descriptive statistics, independent sample t-tests, and one-way ANOVA to assess differences in teacher efficacy and resilience across demographic groups. Structural equation modeling was employed to test the predictive effect of resilience on teacher efficacy. In total, eleven demographic variables were collected, including gender, age, marital status, highest educational qualification, teacher training background, years of service (including the current academic year), school type, school size, main teaching level, primary job role, and religious belief. Given the focus and scope of the study, and with reference to commonly explored variables in related literature, gender, age, and years of service (including the current academic year) were selected for detailed analysis to examine differences in teacher efficacy and resilience. Other demographic variables were also subjected to preliminary statistical examination; however, the results did not show significant differences. Findings revealed a significant positive correlation between resilience and teacher efficacy, with resilience shown to be a significant predictor. While most background variables showed no significant impact, age was found to significantly affect teacher efficacy. This study provides empirical evidence on the connection between teacher efficacy and resilience in Macao's educational context, offering insights for the development of teacher support systems and professional growth strategies. 教師效能感與抗逆力對教育品質與學生發展具有關鍵影響。前者反映教師對自身教學能力的信念，影響其教學策略、班級經營與學生互動；後者則指教師面對壓力與挑戰時的適應與調節能力。本研究旨在探討澳門非高等教育教師的教師 效能感與抗逆力之現況，並分析不同背景變項下兩者之差異與關聯。 本研究以2024/2025學年非高等教育教學人員作研究對象，採用問卷調查法， 分別運用「教師效能感量表」（TSES）與「抗逆力量表」（CD-RISC）在「騰訊問 卷」平台進行線上問卷調查，對125名澳門非高等教育教師進行測量。數據分析方面，除採用描述性統計外，亦運用獨立樣本T 檢驗與單因子變異數分析，探討 背景變項在教師效能感與抗逆力上的差異；並透過結構方程模型進一步檢驗抗逆力對教師效能感的預測作用。 本研究共蒐集十一項背景變項，包括性別、年齡、婚姻狀況、最高學歷、師資培訓背景、服務年資（含本學年）、學校類別、學校規模、主要任教階段、主 要擔任職務及宗教信仰。考量到篇幅安排及研究焦點在於教師效能感與抗逆力的關係上，參照文獻中較常探討之變項，本研究選擇針對性別、年齡與服務年資（含 本學年）進行詳細分析，作為探討教師效能感與抗逆力差異情形之依據。其餘背景變項亦曾進行初步統計檢視，惟分析結果未呈現顯著差異。 研究結果顯示，大部分背景變項對教師效能感與抗逆力皆無顯著影響，惟年齡對教師效能感具有顯著差異。教師抗逆力與教師效能感之關係呈正相關，且抗逆力具預測效能感之作用。 本研究藉了解澳門教師效能感與抗逆力之間的關聯，為澳門教育環境下教師支持系統與專業發展策略提供參考。

初探疫情前中後不同類型家長（單親及雙親）的親子互動體驗變化 - Lao, Sin Mei (2025)
This study explores the changes in the parent-child interaction experience of different types of parents (single parents and two parents) before, during and after the epidemic. The study adopted qualitative research methods and conducted in-depth interviews with 10 families (5 single-parent families and 5 two-parent families), and analyzed from three levels: educational support, interaction model and emotional support.Research has found that the epidemic has not only changed families' lifestyles, but also affected the pattern and quality of parent-child interaction.Especially during the shutdown of work and school, the time parents spend with their children has increased sharply from the original 2-3 hours to 12-14 hours.This abnormal lifestyle has brought unprecedented challenges and opportunities to the parent-child relationship. The research results show that 14 important themes emerged from the interviews, and there are significant differences between single-parent parents and dual-parent parents in facing the impact of the epidemic.In terms of educational support, two-parent families can provide more comprehensive educational support through the division of labor and cooperation between parents.The father is mostly responsible for tutoring in math and science subjects, while the mother focuses on tutoring in Chinese subjects.In contrast, although single parents face resource constraints, they are often able to develop more innovative educational strategies, such as making good use of community resources and establishing mutual aid networks.In terms of interaction patterns, two-parent families tend to optimize the quality of interaction through role division, while single-parent families focus more on improving the effect of a single interaction.At the level of emotional support, the support methods of two-parent families have experienced a transformation from division of labor and collaboration to overall integration, while single-parent families have developed more direct and in-depth emotional connection strategies. Research has found that both single-parent and two-parent families can maintain the development of parent-child relationships through different strategies and adaptations. Some good interactive habits formed during the epidemic, such as regular in-depth conversations and joint participation in housework, are still retained and developed by many families after the epidemic.This suggests that crises may also be an opportunity to promote the optimization of family relationships.The research results not only help understand the unique needs of different types of families, but also provide an empirical basis for formulating differentiated family support policies.Based on the research findings, it is recommended that the government and social service agencies should pay more attention to the diversity of families when formulating policies and provide more targeted support services for different types of families. 本研究探討疫情前中後不同類型家長（單親及雙親）的親子互動體驗變化。研究採用質性研究方法，通過深度訪談10個家庭（5個單親家庭和5個雙親家庭），從教育支援、互動模式和情感支援三個層面進行分析。研究發現，疫情不僅改變了家庭的生活方式，更影響了親子互動的模式和品質。尢其是在停工停學期間，家長和子女的相處時間從原來的2-3小時急增至12-14小時，這種非常態的生活方式為親子關係帶來了前所未有的挑戰和機遇。 研究結果顯示，在訪談中得出14個重要主題，單親家長和雙親家長在面對疫情衝擊時呈現出顯著差異。在教育支援方面，雙親家庭能夠通過父母分工合作的方式提供更全面的教育支援，父親多負責數理科目輔導，母親則專注於語文學科輔導。相比之下，單親家長雖然面臨資源限制，但往往能發展出更具創新性的教育策略，如善用社區資源、建立互助網絡等。在互動模式方面，雙親家庭傾向於通過角色分工來優化互動質量，而單親家庭則更注重提升單次互動的效果。在情感支援層面，雙親家庭的支援方式經歷了從分工協作到整體融合的轉變，而單親家庭則發展出更直接和深入的情感連結策略。 研究發現，無論是單親還是雙親家庭，都能通過不同的策略和適應方式維持親子關係的發展。疫情期間形成的一些良好互動習慣，如定期深度對話、共同參與家務等，在疫情後仍被許多家庭保留和發展。這表明危機也可能成為推動家庭關係優化的契機。研究結果不僅有助於理解不同類型家庭的獨特需求，也為制定差異化的家庭支援政策提供了實證基礎。基於研究發現，建議政府和社會服務機構在制定政策時應更加注重家庭的多樣性，為不同類型的家庭提供更有針對性的支援服務。

以家庭為中心之「回應式互動」技巧對提升語言發展遲緩幼兒語言能力的實驗研究 - Lai, Ut Tong (2025)
Language delay is an important issue that affects the early communication and learning abilities of young children. In recent years, there has been a great deal of interest in the family-centered intervention model, which emphasizes the teaching of Responsive Interaction Strategies to parents in order to optimize the family language environment. The purpose of this study is to investigate the effectiveness of this model of intervention for children with language delays and to understand the factors that contribute to their language progress. This study adopted a Mixed Methods Research Design, which combined quantitative experiments with qualitative interviews to analyze the effectiveness of the intervention and parents' perceptions of the family-centered model. The study was conducted with 10 children with speech and language delays aged between 2 and 3 years old. The subjects were randomly divided into experimental and control groups, and received the family-centered ""responsive interaction"" technique and the clinician-directed approach ""direct instruction"" respectively. The 12-week study consisted of a pre-test, an intervention period and a post-test. The quantitative study was conducted using the long version of the Macao contonese language screening scale for preschool children (MacCLASS-P), together with the Chinese Child Development Inventory(Cantonese version) to standardize the children's language comprehension and expression skills. Both the experimental and control groups received weekly 45-minute interventions during the intervention period, with the experimental group receiving a family-centered “responsive interaction” technique, where the therapist taught the parents the relevant skills and provided them with opportunities for practice, and the control group receiving clinician-directed approach ""direct instruction"". The control group received the clinician-directed approach ""direct instruction"". The qualitative study involved semi-structured interviews with the parents of the experimental group to investigate the experience of using the techniques and the changes in their children's language. The quantitative results showed that the experimental group made significantly more progress than the control group in overall language comprehension and expressive skills, but did not achieve significant differences in grammatical comprehension and pragmatics. The qualitative data further reflected that parents generally recognized the usefulness of the “responsive interaction” skills in facilitating children's progress from single words to complete sentences. In conclusion, this study demonstrated that the family-centered “responsive interaction” intervention model was effective in improving the language comprehension and expression of children with language delays, and that parental involvement strengthened the children's categorization and motivation in language learning. 語言發展遲緩是影響幼兒早期溝通與學習能力的重要議題，近年來，以家庭為中心的介入模式備受關注，強調透過教導家長「回應式互動」技巧（Responsive Interaction Strategies）來優化家庭語言環境。本研究旨在探討此模式對語言遲緩幼兒的介入成效，並了解造成其語言能力進步的因素。 本研究採用混合方法研究設計（Mixed Methods Research Design），將量化實驗與質性訪談相結合，以分析介入效果及家長對以家庭為中心模式的看法。本次研究對象為十名年齡介乎2至3歲的語言遲緩幼兒。受試者隨機分為實驗組及控制組，分別接受以家庭為中心的「回應式互動」技巧和以治療師主導的「直接教學法」介入。共十二週的研究包含前測、介入期與後測三部分。 量化研究採用《澳門粵語學前語言篩查測驗》長版，並配合《漢語溝通發展量表（廣東話版）》對幼兒語言理解和表達能力作標準化測量。實驗組及控制組幼兒在介入期均接受每週45分鐘介入，其中實驗組接受以治療師為主導的「直接教學法」並結合以家庭為中心的「回應式互動」技巧介入，治療師在堂上教授家長相關技巧和給予實踐機會；而控制組則接受以治療師為主導的「直接教學法」。質性研究則針對實驗組家長進行半結構式訪談，探討技巧應用經驗與幼兒語言變化。 從量化結果顯示，實驗組在整體的語言理解和表達能力的進步幅度皆顯著優於控制組，惟語法理解和語用並未達至顯著差異。質性資料則進一步反映家長普遍認同技巧實用性，促進幼兒從單詞進階至完整句子表達。 綜合而言，本研究證實以家庭為中心的「回應式互動」介入模式能有效提升語言遲緩幼兒的語言理解和表達能力，且家長參與強化了幼兒在語言學習的類化與積極性。

適應體育體適能課程對特殊教育學生 動作技能之影響－以澳門某校特教班為例 - Kuok, Chan Heng (2025)
This study took 14 students with mild intellectual disabilities from a special education class in a Macao school as the research objects. Using the comparative method of experimental group and control group, it explored the influence of adaptive physical education fitness courses on the motor skills of special education students. The experimental group received a 12-week adaptive physical education fitness course, while the control group carried out traditional physical education teaching. The study adopted the motor skills assessment scale compiled by Liu Yijun to conduct pre-tests and post-tests on the two groups of students, and used SPSS software for statistical analysis. The results showed that the adaptive physical education fitness course had significant effects on improving most physical fitness and motor ability indicators of special education students. The experimental group showed significant differences (p<0.05) in the pre-test and post-test scores of 11 indicators, including BMI, sit-and-reach, one-minute knee flexion sit-ups, two-minute step test, etc. The traditional course only showed significant effects in the standing long jump project, and the differences in other indicators between the pre-test and post-test did not reach the statistical significance level. In addition, the experimental group was significantly better than the control group in the total manipulative movements and throwing indicators (p<0.05). The study indicates that adaptive physical education fitness courses can effectively improve the physical fitness and motor skills of special education students. Based on this, it is suggested to increase the class hours of healthy physical fitness, expand opportunities for diversified sports participation, integrate technological elements into innovative teaching methods, and incorporate interdisciplinary integration into daily teaching, providing new ideas and practical directions for physical education teaching in special education. 本研究以澳門某學校特殊教育班的 14 名輕度智能障礙學生為研究對象，採用實驗組與控制組對比的研究方法，探討適應體育體適能課程對特殊教育學生動作技能的影響。實驗組接受為期 12 週的適應體育體適能課程，控制組則進行傳統體育教學。研究採用劉怡君編制的動作技能評估量表，對兩組學生進行前測與後測，並運用 SPSS 軟體進行統計分析。 結果顯示：適應體育體適能課程在改善特殊教育學生的多數體適能和動作能力指標上具有顯著成效。實驗組在 BMI、坐姿體前屈、一分鐘屈膝仰臥起坐、兩分鐘登台階等 11 項指標上前後測分數差異顯著（p<0.05）。而傳統課程僅在立定跳遠項目上呈現顯著效果，其餘指標前後測差異均未達統計學顯著水準。此外，實驗組在操縱性動作總量與投擲指標上明顯優於對照組（p<0.05）。 研究表明，適應體育體適能課程能夠有效提升特殊教育學生的身體素質和動作技能。據此建議：增加健康體適能課時、拓展多元運動參與機會、創新教學方法融入科技元素以及跨學科融合滲透日常教學，為特殊教育體育教學提供了新的思路和實踐方向。

子女由普通生轉為融合生的過程中澳門小學家長的經歷及感受之質性研究 - Lam, Choi I. (2025)
In Macau, inclusive students refer to students with special educational needs who can receive education alongside their peers in regular classes with minimal special education support. With the advancement of inclusive education policies, an increasing number of students with special educational needs are placed in regular classrooms. However, whether parents are willing to transition their children from regular students to inclusive students plays a key role in the practice of inclusive education. This study aims to explore the experiences and feelings of parents at a Catholic primary school in Macau during the process of their children transitioning from regular to inclusive students. The research questions include: What is the psychological journey of parents during the transition of their children from regular to inclusive students? What factors facilitate or hinder parental decision-making? What are parents’ feelings and thoughts after their children became inclusive students? The researcher employed a qualitative research method using semi-structured one-on-one interviews with six parents (all mothers) and analyzed the interview data using grounded theory. The findings reveal that parents' psychological journey involves a dynamic shift from recognizing their children's difficulties, experiencing doubt and resistance, to accepting assessment and identity confirmation. The decision-making process is influenced by multiple factors, including family support, support from teachers or professionals, the ‘inclusive student’ label, and public information about inclusive education. The study also found that parents generally found that their children's academic performance improved after becoming inclusive students, and that the family atmosphere became more harmonious than before. However, they also had concerns about their children's social skills and future transition to secondary school after becoming inclusive students. They hope that schools and educational authorities can provide more publicity, resources, and support to better implement inclusive education, such as enhancing teacher professional training, offering educational resources, and improving public understanding of inclusive education and inclusive students. Overall, despite the challenges of the transition process, parents demonstrate their own adaptation and growth throughout this journey. 在澳門融合生是指只需要小量的特殊教育支持就能在普通班與同班同學一 起接受教育的有特殊教育需要的學生。隨著融合教育政策的推進，越來越多有特 殊教育需要的學生被安置於普通班中。然而，家長是否願意讓子女由普通生轉為 融合生，是融合教育實踐中的關鍵環節。本研究旨在探討澳門某天主教小學家長 在子女由普通生轉為融合生過程中的經歷與感受。研究問題包括：將子女從普通 生轉為融合生的過程中，家長的心理歷程是怎樣的？有哪些因素會促進或阻礙家 長的決策？將子女從普通生轉為融合生之後，家長的感受和想法是怎樣的？研究 者採用半結構化一對一訪談的質性研究方法對六位家長（均為母親）進行深入訪 談，並採用扎根理論進行訪談數據分析。研究發現家長的心理歷程經歷了從覺察 子女的困難、懷疑與抗拒，到接受評估與身份確認的動態轉變。決策過程受多重 因素影響，包括家庭支持、教師或專業人員的支持、“融合生”標籤、融合教育 的公共資訊等。研究也發現，家長在子女成為融合生後普遍認為子女的成績有所 進步，家庭氣氛比以往更加和諧，但同時對子女的社交能力和未來升中學的問題 有擔憂。她們普遍希望學校及教育當局能提供更多宣傳、資源和支持，以更好地 實施融合教育，例如提升教師專業培訓、加強輔助教學資源、提升公眾對融合教 育和融合生的正確認識。整體而言，儘管轉變過程充滿挑戰，但家長在這個過程 中呈現了自身的適應與成長。

澳門融合學校小學教師對語言治療了解 及對校本語言治療的看法 - Chao, Ho Wan (2025)
Objectives: Appropriate support services have an important impact on inclusive students. If there is sufficient and appropriate support in school, it will help improve the learning, social interaction and social adaptation of inclusive students. The Macau SAR government has proposed to promote school-based therapy services in the future. This policy will help improve the appropriateness of school support for inclusive students. Language is the basis of learning, so the implementation of school-based speech language therapy services will inevitably help support the learning needs of inclusive students with language disorders in school. However, a deeper understanding of the current situation is needed in order to formulate an appropriate implementation plan. This study aims to understand the current front-line primary school teachers' understanding of the work of speech language therapists, characteristics of related impairments, difficulties in implementation, suggestions for school-based speech language therapy, so as to serve as reference information for future implementation plans. Method: This study conducted semi-structured interviews with 8 current primary school teachers from inclusive schools with different backgrounds. The interviews were recorded in the form of audio recordings, transcribed verbatim, and then coded and organized according to the research questions. Combined with the support of literature review, implementation suggestions were given for the school-based speech language therapy. Conclusion and limitations: The results show that teachers who studied special education and educational psychology have a higher understanding of the scope of speech language therapy than teachers who studied general education. Most teachers believe that the work scope of speech language therapists is mainly in oral expression, communication skills, and articulation correction. The interviewees all pointed out that there is currently no communication channel and direct contact point between teachers and speech therapists. The current difficulties related to speech language therapy include multiple aspects: teachers, parents and policies, such as teachers' lack of understanding of related impairments, low social acceptance, and lack of transparency of school information. The study also summarized government policies, school resources, environment and other factors that affect the effectiveness of speech language therapy, including evaluation process and waiting time for the evaluation, school support for government policies, parents and teachers' understanding and acceptance of speech language therapy, etc. The interviewees all agreed that there is a need to provide school-based speech language therapy services to solve the current difficulties in implementation, and also provided a number of implementation suggestions as a reference for the Macau SAR government in implementing relevant policies. However, the number of respondents was small, and it is suggested that a larger-scale study should be conducted. In addition to considering the number of samples, different stakeholders should also be included as respondents to formulate a well-balanced implementation guideline for promoting school-based treatment services from a more neutral perspective, so as to improve the teaching quality of students with special learning needs. 目的：合適的支援服務對融合生有著重要的影響，若在校內有足夠且適宜的支援，有助提升融合生的學習、社交、以及其適應社會的能力；澳門特區政府提出未來致力於推行校本治療服務，此政策有助提升在校支援對融合生的適切性；其中語言為學習的基礎，故校本語言治療服務的推行必然有助支援伴隨語言障礙融合生校內之學習需要。然而，在推行前需要對現況有更深入的了解，以便制定合宜的落實方案，是次研究旨在了解目前前線教師對語言治療師工作的認識、對相關障礙的了解、與語言治療相關的支援及溝通、實行上面對的困境、對校本語言治療的想法及推行建議，以作為日後推行計劃的參考資訊。 方法：是次研究透過與 8位不同背景現職融合學校小學教師進行半結構性訪談，訪談以錄音形式記錄，以逐字稿形式轉錄後，再根據探研究問題進行編碼及整理，結合了文獻回顧的支持，為日後落實校本語言治療給予落實建議。 結論及限制：結果顯示修讀特殊教育系、教育心理學系的教師對語言治療工作範疇的認識較修讀一般教育系的教師為高；大部分教師認為語言治療師的工作範疇主要在口語表達、溝通能力，以及構音糾正等面向，可見對語言治療師工作了解不透徹；受訪者均指出現時教師與語言治療師處於零溝通、零接觸的狀況，現時與語言治療相關的困境包括多個面向：教師、家長及政策，例如教師對相關的障礙認識不足、社會接納度低、校內資訊不透明等；研究亦歸納了政府政策、校內資源、環境等多項影響語言治療成效的因素，包括評估流程及輪候時長、校方對政府政策的支持度、家長及教師對語言治療的認識及接受程度等；受訪教師均一致認為有需要提供校本語言治療服務，以解決現時實行上的困境，亦對推行校本語言治療服務提供多項落實建議，以作為澳門特區政府在推行相關政策的參考資料；然而是次受訪人數太少，建議進行更大型的研究，除了人數的考量，亦可加入不同持份者作為受訪對象，以更中立的角度研判並平衡各持份者對推行校本治療服務的實施方針，以提升有特殊學習需要學生的教學品質。

澳門教育碩士生學習體驗與課程期望之質性探究 - Chan, Chio U. (2025)
本研究採用質性研究法，旨在探討澳門教育碩士二年級學生的學習體驗、影響學習體驗的主要因素、學習過程中所面對的挑戰與困難，以及學生對課程優化的建議與期望。研究透過半結構式深度訪談十位教育碩士生，並加以整理與分析，以深入回應研究問題並歸納研究結論。研究結果顯示： （一）受訪學生普遍肯定課程對其專業知識和實務能力的提升作用，但指出理論與實踐之間存在明顯落差，特別是在統計分析與研究方法教學方面的支援不足。此外，積極的師生互動與同儕合作有助提升學習動機與成效，惟小組合作中常見的角色衝突、任務分配不均及教師指導不足等情況亦對學習體驗造成負面影響。 （二）影響學生學習體驗的關鍵因素包括：師資專業素質、院校資源配套、同儕互動質量及時間管理壓力。教師教學策略與專業水準對學習成效有直接影響，學生偏好案例導向與互動性強的教學形式。而院校資源方面，如數據庫使用受限、設施老化等問題亦限制了學生的學術發展。在職學生則面臨工作與學業角色衝突，影響學習的持續性與專注度。 （三）受訪學生普遍面臨理論與實踐銜接困難、學術能力落差、時間壓力與團隊協作挑戰等問題。跨專業學生對學術論文與與研究設計的掌握不足，需要更有系統的研究方法訓練。隨機分組亦導致成員能力不均，降低了合作效率。部份學生在資源使用與情緒管理方面亦顯得較為薄弱，進一步削弱其學習投入。課程定位與職業發展期望之間的落差對學習動機構成不利影響。 （四）學生建議課程可加強案例教學與實踐機會，增設研究方法進階訓練，並優化評價設計。採用更多元的評估形式。同時，應明確學術型與專業型課程的培訓目標，建立清晰的課程命名與專業認證制度，以提高學歷認受性及學生未來的就業競爭力。 最後，根據研究結果，本文提出若干針對澳門教育碩士課程之優化建議。並指出未來可延伸之研究方向，以持續深化對本澳教育碩士學習體驗的理解與關注。 This study adopted a qualitative research approach to explore the learning experiences of second-year Master of Education students in Macao. It investigated the factors that influenced their learning experiences, the challenges and difficulties encountered during their studies, and their expectations for curriculum improvement. Through semi-structured in-depth interviews with ten Master of Education students, the collected data was organized and analyzed to thoroughly address the research questions and summarize the research findings. The results indicate that: 1. Findings indicated that while participants generally affirmed the programme’s contribution to enhancing their professional knowledge and practical skills, they also identified a clear imbalance between theoretical instruction and practical application, particularly in the area of statistical analysis and research methodology. Positive student-teacher interactions and peer collaboration were seen to support motivation and learning outcomes. However, issues such as role conflict in group works, unequal task distribution, and insufficient teacher guidance negatively impacted their overall experience. 2. Key factors influencing students’ learning experiences included teacher quality, institutional support, peer relationships, and stress related to time management. Teaching strategies and educator’s expertise were found to directly affect course quality, with participants favouring case-based and interactive teaching approaches. However, limited access to databases and outdated facilities were seen as barriers to academic development. Working students also faced a conflict of roles between their professional responsibilities and academic commitments, which hindered their ability to maintain engagement. 3. Challenges commonly reported included difficulties bridging theory and practice, gaps in academic preparedness, time pressures, and team collaboration issues. Cross-disciplinary students often lacked a strong foundation in academic writing and research design and expressed a need for more structured research training. Random group allocation was seen to reduce group effectiveness. Additionally, some participants demonstrated limited capacity for resource use and emotional regulation, and this affected their learning engagement. Misalignment between course orientation and career expectations was also a factor in the decline in motivation. 4. Participants recommended increasing opportunities for case-based learning and hands-on experience, as well as enhancing research training and diversifying assessment methods. They also suggested clearer distinctions between academic and professional degree pathways and the establishment of a standardised course naming and a professional accreditation framework to improve recognition and employment competitiveness. Based on the findings, this study proposed several recommendations for improving the Master of Education curriculum in Macao. Future research directions are also suggested that may deepen an understanding of and support the development of postgraduate learning experiences within the local context.

澳門中學教師面對融合學生的教學困擾與融合教育專業知能關係之研究 - Ieong, Ao; Un, Kuok (2025)
This study aims to investigate the current status of teaching difficulties and professional competencies among secondary school teachers working with students with special educational needs (SEN) in inclusive classrooms in Macao. It examines differences in teachers' teaching difficulties and professional competencies across various demographic variables. Furthermore, it explores the relationship between teachers' professional competencies and their teaching difficulties, as well as identifying the predictive factors influencing both aspects. A questionnaire survey method was employed, collecting 171 valid responses. Data analysis methods included descriptive statistics, independent samples t-tests, one-way ANOVA, Pearson correlation, and linear regression analysis. Key findings include: • Teachers reported a moderately low level of teaching difficulties related to inclusive education. • Teachers reported a moderately high level of professional competencies in inclusive education. • Significant differences in teaching difficulties were observed based on teachers' gender and participation in inclusive education training courses. • Significant differences in professional competencies were observed based on teachers' years of experience in inclusive education and their participation in inclusive education training courses, seminars and workshops. • A low negative correlation was found between teachers' teaching difficulties and their professional competencies. • Teachers' professional competencies significantly predict their teaching difficulties. • Gender significantly predicted teaching difficulties in inclusive education contexts. Based on these findings, relevant recommendations are provided. 本研究旨在瞭解澳⾨融合教育學校中學教師⾯對融合學⽣的教學困擾及融 合教育專業知能的現況與相關性，並分析不同背景變項下澳⾨中學教師的教學困 擾及融合教育專業知能之差異、融合教育專業知能對教學困擾的預測⼒，以及背 景因素對教學困擾的預測⼒。 本研究採⽤問卷調查法，回收有效問卷171份。問卷數據以描述性統計、獨 ⽴樣本T檢驗、單因⼦變異數分析、⽪爾遜積差相關、線性迴歸分析進⾏分析。 研究結果歸納如下： ⼀、 澳⾨中學教師融合教育教學困擾屬「中等偏低」程度。 ⼆、 澳⾨中學教師融合教育專業知能屬「中等偏⾼」程度。 三、 不同性別及融合教育課程進修的澳⾨中學教師融合教育教學困擾有顯著差 異。 四、 不同融合教育年資、融合教育課程進修及講座、⼯作坊參與的澳⾨中學教師 融合教育專業知能有顯著差異。 五、 澳⾨中學教師融合教育教學困擾與專業知能呈「低度負相關」。 六、 澳⾨中學教師的整體融合教育專業知能對融合教育教學困擾具微弱預測⼒。 七、 「性別」對融合教育教學困擾具微弱預測⼒。 本研究最後根據研究結果提出相關建議。

Cord blood cytokines/chemokines linked to delays in toddlers exposed to SARS-CoV-2 prenatally - Kehdi, Renata Castro; Silva, Maria Francilene Souza; Cavalcante, Letícia Régia Lima; Fiorenza, Natália Gindri; Viana, Marylane; Leite, Isabel Bessa; Silva, Bruno Riccelli dos Santos; Assis, Débora Ferreira de; Cortez, Paulo Cesar; Bezerra, Deniele Lós; Motta, Pedro Crosara; Lobo Marques, Joao Alexandre; et al. (Pediatric Research, 2025)
Background: Maternal infections are linked to neurodevelopmental impairments, highlighting the need to investigate SARS-CoV-2-induced immune activation. Objective: This study aimed to evaluate the impact of maternal infection on neurodevelopment and investigate whether cytokine and chemokine profiles predict delays at 24 months. Methods: Conducted in Brazil (January 2021–March 2022), this follow-up study included 18 SARS-CoV-2 positive pregnant women at 35–37 weeks’ gestation, 15 umbilical cord blood samples, and blood samples from 15 children at 6 months and 14 at 24 months. Developmental delay was defined using the Bayley Scales of Infant and Toddler Development, Third Edition, with scores below 90 in cognitive, communication, or motor domains. Results: At 6 months, 33.3% of infants exhibited cognitive delays, 20% communication delays, and 40% motor delays, increasing to 35.71%, 64.29%, and 57.14% at 24 months, respectively. Elevated interferon-gamma and tumor necrosis factor-alpha in cord blood correlated with cognitive delays, while interleukin (IL)-6, IL-8, IL-17, and IL-1β were associated with motor delays. Increased C-X-C motif chemokine ligand 10 and other cytokines were associated with communication delays. Conclusion: Maternal SARS-CoV-2 may impact infant neurodevelopment, as early cytokine elevations correlate with delays, highlighting the importance of early monitoring and interventions to reduce long-term effects. Impact: Prenatal SARS-COV-2 infection in pregnant women is linked to developmental delays in toddlers, with cytokine and chemokine changes associated with neurodevelopmental outcomes at 24 months. This study shows the long-term impact of maternal SARS-COV-2 infection on child development, highlighting inflammatory markers like IFN-γ, TNFα, IL-6, IL-8, IL-17, IL-1β, and CXCL10. Identifying specific cytokines correlating with cognitive, communication, and motor delays suggests potential biomarkers for early intervention. Conducted in Fortaleza, Brazil, the study emphasizes understanding local epidemiological impacts on child development, especially in regions with high infection rates. (Figure presented.)

Analyzing Consumer Responses to Warwashing Amidst the Russia–Ukraine Conflict: A Comparative Study of Portuguese and Danish Perspectives - Silva, Susana C.; Duarte, Paulo; Kanne, Benjamin (Progress in International Business Research, 2025)
The ongoing Russia–Ukraine conflict has had significant repercussions for businesses, with many scaling back operations in Russia due to international sanctions. However, some companies continue operating there while making superficial gestures to appear supportive of the oppressed side (a practice known as ‘warwashing’). These actions conflict with profit motives and contribute to consumer skepticism and potential boycotts. This study examines how Portuguese and Danish consumers respond to warwashing, aiming to assess if cultural differences influence reactions. A quantitative survey, including nine questions based on literature and key differences between the two countries, was conducted using a deductive approach. Results were analyzed via JMP statistical software, with paired t-tests applied. Findings reveal a significant difference in reactions between Portuguese and Danish consumers, with Danish consumers showing a heightened response, engaging more frequently in impactful actions. This aligns with Hofstede’s cultural model, which portrays Danes as more open to change and expecting transparency. Boycott theory is also supported, suggesting that Danes are more inclined to boycott products and services, while Portuguese consumers show less faith in the effectiveness of such actions. This cross-country comparison reaffirms Hofstede’s Cultural Value Dimensions, providing insight into real-world cultural differences. Additionally, the study highlights the concept of collective action, where individuals avoid certain products or services as a form of protest, revealing variations in the prevalence of this behaviour across different societies.
ISBN: 9781836627654

A study on the architectural features and value of modern Catholic churches in Macau - Wu, Yao; Wu, Yonglan; Pinheiro, Francisco; Miao, Mingrui (Journal of Asian Architecture and Building Engineering, 2025)
The study of Catholic churches in Macau is of significant importance for both architectural heritage conservation and the transmission of cultural values. As religious structures, these churches serve as tangible representations of religious ideology and spiritual essence, thereby embodying the core principles of cultural expression. This paper aims to critically examine the Catholic churches of Macau, exploring their intrinsic values through an architectural research framework that emphasizes three key morphological elements: spatial characteristics, stylistic features, and structural composition. By contextualizing the historical background and architectural attributes, this study sheds light on the multifaceted significance of Catholic church construction in modern Macau, while offering a comprehensive analysis of the intersection, fusion, and coexistence of Eastern and Western cultural influences in this unique locale. Through this investigation, the paper uncovers a range of compelling cultural phenomena, providing insights that may serve as valuable reference points for future practices in architectural heritage conservation in Macau.

A STUDY OF THE IMPLEMENTATION OF SMART POLICING IN MACAU: AN ASSESSMENT OF ITS ADOPTION AND CHALLENGES - Leong, Sio Mui (2025)
This dissertation examines the implementation of smart policing in Macau, focusing on the adoption and challenges of facial recognition technology within the Macau Urban Electronic Surveillance System. As Macau pursues its smart city ambitions, the integration of advanced technologies into law enforcement has become a central strategy for enhancing public safety and operational efficiency. However, the actual acceptance and use of these technologies by frontline police officers remain underexplored. The study adopts a mixed-methods approach. documentary analysis of government policies and strategic documents provides an overview of Macau’s smart policing initiatives and the legal and infrastructural frameworks supporting them. The core of the research is a quantitative survey of Macau police officers who have direct experience with the facial recognition system. The survey is structured around the Unified Theory of Acceptance and Use of Technology (UTAUT), with additional attention to compatibility and perceived legal knowledge. The results reveal that performance expectancy and perceived legal knowledge are the strongest factors influencing officers’ adoption of facial recognition while effort expectancy, social influence, facilitating conditions and compatibility are less influential. Practical challenges were discovered through the Macau police officers.

CONSUMER PERCEPTIONS OF BEVS IN MACAU: A PERCEPTION STUDY OF TESLA VEHICLE OWNERS - Tang, KeRui (2025)
This study examines consumer perceptions of all-electric vehicles in Macau, focusing on Tesla owners. As the Macau Special Administrative Region (MSAR) pursues its long-term carbon reduction strategy, adopting BEV is a key step towards sustainable urban mobility. However, consumer attitudes and behavioral responses to BEV in Macau's unique high-density urban environment remain underexplored. This study adopts the extended Unified Theory of Acceptance and Use of Technology (UTAUT-2) model with the addition of the “technological show-off” (TS) dimension to explore how Tesla owners perceive the challenges and opportunities of adopting BEV. This study used a qualitative methodology to conduct in-depth interviews with ten Tesla owners in Macau through semi-structured interviews and unstructured quantitative assessments. Data were analyzed across multiple UTAUT-2 dimensions, including Performance Expectancy, Effort Expectancy, Social Influence, Facilitating Conditions, Hedonic Motivation, Price Value, Habit, and the added factor of Technology Show-Off. The findings suggest that Tesla owners in Macau value their vehicles' convenience, efficiency, and technological sophistication, with a particular focus on Autopilot, acceleration, and low maintenance costs. However, issues such as limited charging infrastructure, service accessibility, and technology learning curve remain. Social status and identity are influential factors, especially in a compact and socially connected urban environment like Macau. By examining the experiences of EV users, this study fills a gap in the existing literature. It provides practical insights for policymakers and manufacturers aiming to accelerate the diffusion of BEVs. The study concludes that consumer perceptions are critical for practical benefits and emotional fulfillment for the continued growth of the electric vehicle market in Macau and similar regions.

In-vehicle interface design for passengers experience optimization of Level 4 autonomous vehicles - Wu, Jun Ting (2025)
This research focuses on the design of the in-vehicle interactive interface of L4 autonomous driving vehicles, aiming to explore how to improve the passengers experience by optimizing the interface interaction mode. With the development of autonomous driving technology, the shortcomings of existing interface design in transparent feedback, emotional adaptation and multi-modal interaction support have become the main obstacles affecting user trust and satisfaction. Based on user research and prototype design, the study proposed an interface design scheme that combines transparent feedback with emotional perception, focusing on real-time display of vehicle behaviour logic and dynamic adaptation to passenger emotional state. In user testing, the system showed some improvements in trust enhancement and ease of use, especially in response to complex road conditions and emergencies. Although this research has provided some preliminary results through innovative design, there are still limitations in technical implementation and scope of application. Future research will focus on sample diversification and accuracy improvement of emotional perception technology to further improve the design scheme and expand its application scenarios.

EXPLORING COPING STRATEGIES FAMILY MEMBERS OF PROBLEM GAMBLERS IN MACAU – A QUALITATIVE STUDY - Wong, Hio Fong (2025)
Legalizing gambling has brought numerous advantages to Macau, including employment opportunities, economic growth, improved quality of life, and accelerated urban development. While these macro-level benefits are evident, the industry has also significantly impacted local families and communities. In particular, the initial discovery of a family member's gambling problem inflicts immeasurable harm on the household, and the coping strategies adopted by affected family members critically influence their relationships with the gambler and the overall trajectory of the family unit. This qualitative study, conducted in collaboration between the University of Saint Joseph (USJ) and SKH 24-hour online gambling counseling service (SKH-24H), employed semi-structured interviews to explore the coping strategies of family members of problem gamblers. Nine participants were interviewed, and thematic analysis revealed eight key coping strategies: (1) Bailing out The Problem Gambler, (2) Maintaining Status Quo of the Family, (3) Help Seeking in Macau Community, (4) Coping by Self-Regulation, (5) Coping by Engagement, (6) Coping by Withdrawal, (7) Tolerance and (8) Seeking Psychiatric Consultations. The study aims to enhance the understanding of local gambling counseling professionals regarding the coping strategy employed by Macau families dealing with problem gamblers. By aligning intervention strategies with the lived experiences of these families, the findings can inform more effective, family-focused approaches to service delivery. Furthermore, the research provides insights for government agencies into the real-world challenges faced by families affected by problem gambling, offering evidence-based recommendations for evaluating and revising existing regulations to mitigate the adverse effects of the gambling industry on Macau's households. "

Regulatory Sandboxes in the Financial Sector in Macao - Chio, U. Ian Rowena (2025)

The Social Impact of Media Communication in Large-Scale Sports Events – A Case Study of the Tokyo 2020 Paralympic Games - Takashi, Suda (2025)
The Tokyo 2020 Olympic and Paralympic Games established themselves as a unique worldwide sports event, which took place in 2021 without spectators after a year-long delay due to the COVID-19 pandemic. The media became the sole information distributor about the Games because there were no live spectators present at the events. Academic research about the Paralympic movement showed substantial growth since the London 2012 as media attention alongside public interest expanded. Research about the Tokyo 2020 Paralympics faces limited availability because of immigration and infection control measures combined with spectator restrictions. There is insufficient research about the social consequences of the Paralympic media coverage especially from the viewpoint of people with disabilities. This study analysed the Tokyo 2020 Paralympics through qualitative methods to understand media communication effects on Tokyo and Aichi Prefecture residents with disabilities. Four main themes emerged through reflexive thematic analysis of semi-structured interview dataset which included: 1) the duality of the media, 2) the suspension between the medical and social models, 3) Japanese culture and the human rights movement, and 4) Paralympian decoded. By comparing with previous research on media perception among Japanese non-disabled people, this study revealed that people with disabilities viewed the Paralympic media coverage with both critical and objective perspectives by acknowledging its benefits and challenges. People with disabilities demonstrated little optimism regarding how the media could improve public disability awareness. The study also revealed that Paralympians carry diverse and widely recognised social meanings within disability communities and that a fundamental mismatch exists between disability goals and mainstream media representations, which tend to simplify disability into one-dimensional categories. This study established a social framework that recognised and respected the diverse differences within the disability population, rather than using reductionist classification systems.

Ecosystem services from nature-based solutions: Assessment and valuation of mangroves in macao - Jiang, Tao Sheng (2025)
Nature-based Solutions (NbS) offer a sustainable approach to mitigating climate change and biodiversity loss while delivering socio-economic benefits. This study examines mangroves as a key NbS in Macao, assessing their ecosystem services and economic valuation through a hedonic pricing model. Despite their limited spatial coverage, Macao's mangroves provide critical services, including coastal protection, carbon sequestration, and habitat provision, yet face threats from invasive species and urbanization. The research employs a hedonic pricing model to analyze the relationship between property prices and proximity to mangrove ecosystems in Macao Peninsula, Taipa, and Coloane. Results demonstrate a statistically significant negative correlation, indicating that residential properties closer to mangrove areas command higher prices, reflecting the premium placed on ecological amenities. The model explains 65.0% of price variation, underscoring mangroves' influence on real estate values. This study contributes a novel valuation framework for mangrove ecosystem services in high-density coastal cities, integrating ecological and economic perspectives. The findings support evidence-based policy recommendations for mangrove conservation and sustainable urban development. Future research should expand the model to incorporate additional variables and longitudinal data to enhance predictive accuracy and applicability across diverse coastal regions. Biodiversity assessment and conservation planning in highly urbanized environments. 基于自然的解决方案（NbS）为缓解气候变化和生物多样性丧失提供了一种可持续的方法，同时还能带来社会经济利益。本研究以澳门的红树林为例，探讨其作为关键的基于自然的解决方案的作用，通过享乐定价模型评估其生态系统服务和经济价值。尽管澳门红树林的分布面积有限，但它们提供了重要的服务，包括海岸保护、碳封存和栖息地提供，然而却面临着外来物种入侵和城市化的威胁。 研究采用享乐定价模型，分析澳门半岛、氹仔和路环地区房产价格与红树林生态系统距离之间的关系。结果表明，两者之间存在显著的负相关关系，即靠近红树林区域的住宅价格更高，这反映了人们对生态设施的重视。该模型解释了 65.0%的价格差异，突显了红树林对房地产价值的影响。 本研究为高密度沿海城市的红树林生态系统服务提供了一种新的估值框架，将生态和经济视角相结合。这些发现为红树林保护和可持续城市发展提供了基于证据的政策建议。未来的研究应扩展该模型，纳入更多变量和纵向数据，以提高预测的准确性和在不同沿海地区的适用性。在高度城市化环境中进行生物多样性评估和保护规划。

The Relationship of Parenting Styles on Mental Health: Looking at the Mediation of Resilience among University Students in Macao - Fong, Hio Wa (2025)
The suicide rate has been increasing these decades. A good mental health could prevent people from committing suicide. Parents are the ones whom we spend most of the time with. How parents treat us does have an impact on both our development and mental health. However, some people can always see the positive side of things and expect things to turn out well. Therefore, the present study aims to examine if resilience would mediate the relationship between parenting styles and mental health in bachelor students. A cross-sectional research method was used in this study. Data were collected through Google Forms. The sample consists of 110 Bachelor students in Macau, with 46 males (42%) and 64 females (58%). According to the findings of the study, the mediating role of resilience in the relationships between parenting styles and mental health were found to be not significant. However, bachelor students who perceived their mothers as authoritative parenting style were found to have better mental health. While higher resilience was found to have less impact on the mental health of bachelor students. This study has pointed out the importance of different parenting styles on bachelor students' mental health and further proves the positive influence of resilience towards mental health. There is a need to cultivate the resilience of bachelor students to help them better equip themselves for stressful situations and cope with crises. Workshops or interventions are also needed for parents to teach them better parenting skills and knowledge, so that the mental health of their children could be enhanced by that.

FINANCIAL VALUATION OF MARRIOTT INTERNATIONAL - Ng, Chi Long (2025)
Marriott International, Inc. (Marriott) is a worldwide company that operates, franchises, and licenses a diverse portfolio of hotels, residential properties, timeshares, and other lodging options across various brands, catering to multiple price levels and service standards. Currently, Marriott operates in the U.S. & Canada segment and the international segment, including Europe, the Middle East, Africa, Asia Pacific, the Caribbean, and Latin America. The major business segment is the U.S. & Canada, representing 80% of the consolidated net sales in 2023. To pioneer the development in the industry, Marriott has to expand its international operations to diversify geographic revenue streams and reduce dependence on the U.S. & Canada markets. Maintaining its competitive advantage is a constant challenge due to the intense competition in the global hospitality industry and the sector’s sensitivity to economic, political, and social changes. Understanding how these factors affect both the industry and Marriott is crucial for accurately assessing Marriott’s intrinsic value and its future positioning. Comparing the intrinsic value derived from three valuation models with Marriott’s market share price as of December 31, 2023, will offer valuable insights for investors.

EMPLOYEE INCENTIVE MECHANISM IN ENTERPRISES: A CASE STUDY OF GF COMPANY - Yang, Jia Zheng (2025)
This dissertation investigates the effectiveness and shortcomings of employee incentive mechanisms at GF Advertising Company, with a specific focus on the motivation of staff. Amid rapid changes in the advertising and printing materials industry, employee satisfaction and retention have become increasingly critical. However, the company’s current incentive system—characterized by an overreliance on material rewards and lack of development opportunities—has struggled to meet employees’ evolving needs. To explore this issue, the study adopts a mixed-methods approach, combining a quantitative survey of 115 employees with qualitative interviews of 7 selected staff members. The research draws upon Maslow’s Hierarchy of Needs and Herzberg’s Two-Factor Theory to analyze employee motivation and satisfaction. The findings reveal key challenges in four areas: insufficient economic incentives, weak organizational environment support, underdeveloped career growth mechanisms, and ineffective work-related motivation. Based on the results, the dissertation proposes a multi-layered, localized incentive model that incorporates both intrinsic and extrinsic motivators. Recommendations include optimizing communication platforms, strengthening team culture, refining promotion pathways, and diversifying reward structures to better align with employee expectations. The study concludes that a strategic and human-centered incentive mechanism not only improves employee engagement but also enhances organizational performance. Future research could further expand the sample scope and explore long-term impacts of different incentive models across companies and regions.

MAIN POSITIVE ASPECTS AND CONCERNS ABOUT YOUTH IN MACAO: A QUANTITATIVE CONTENT ANALYSIS OF MULTIPLE PERSPECTIVES - Chan, Pui Ian (2025)
The present research aimed to assess and compare the perspectives of teachers, parents, and youth regarding the main positive aspects and concerns they have about youth in Macao, namely: (1 and 2) What are the main positive aspects/concerns Macao teachers, parents, and youth focus on? And (2 and 3) How aligned are teachers, parents, and youth in Macao regarding the positive aspects/concerns? We applied a quantitative methodology based on a quantitative content analysis of open-ended questions included in the Macao validation (Simões et al., Unpublished report) of the Achenbach System of Empirically Based Assessment (Achenbach, 1991; “what are your concerns regarding your child/your student/yourself”, and “what are the most positive aspects about your child/your student/yourself”). We found alignment regarding positive aspects, with youth, parents and teachers focusing on personality, abilities, and attitudes, and parents additionally on independence. Regarding concerns, there was less alignment. All mentioned academic performance and interpersonal relationships, but parents and teachers also mentioned health, morality, attitudes, and teachers’ class engagement concerns. Teachers and youths mentioned future planning, while only the youth mentioned school activities and facilities, their abilities and character and class rules and assignments. These categories are aligned with development models, including ecological systems theory (Bronfenbrenner, 1994), social learning theory and social cognitive learning theory (Bandura, 1977, 1986), moral development perspectives (Mead, 1928; Gilligan 1933), self-determination theory (Deci & Ryan, 2000) and positive youth development perspectives (e.g., Lerner, 2005). The main practical implications are that (1) youth should have a greater awareness of their physical and mental health; (2) parents should build up a support system to enhance autonomy (3) schools play a crucial role in promoting students’ health by creating a supportive environment; (4) counsellors should promote re-connection between youth and their parents or teachers; and (5) decision-makers should invest in mental health education awareness to diminish the stigma, de-emphasise education strategies based on standardised testing, and address broader social and economic inequalities to reduce disparities and academic pressure among youths, parents and teachers.

澳門幼稚園教師和資源教師合作現況調查 - Che, Ka Sin (2025)
This study examines the collaboration between kindergarten teachers and resource teachers in Macau's inclusive early childhood education settings, focusing on the extent of their collaboration, challenges, satisfaction, support needs, and suggestions for improvement regarding collabroation. The study surveyed 53 kindergarten teachers and 15 resource teachers from inclusive kindergartens in Macau. Key findings are: (1) Over 60% of kindergarten teachers and all resource teachers had collaborative experience, and both parties reported they primarily used the ""one teaching, one assisting"" co-teaching model; (2) Over 70% of kindergarten teachers reported less than 30 minutes of weekly discussion time with resource teachers, while 40% of resource teachers reported about one hour per week for discussion with kindergarten teachers ; (3) Both groups identified communication as the main challenge; (4) Primary collaboration areas included case information exchange and teaching strategy discussions; (5) Overall satisfaction was above average, with highest satisfaction in ""positive attitude"" and lowest in ""support system;"" (6) Teachers expressed high support need for professional training and parent training; and (7) Both groups emphasized the key to improve collaboration relates to enhanced communication and more professional training and development. Based on these findings, recommendations were offered with a focus on establishing comprehensive support networks and communication platforms at policy, school, and teacher levels. 本研究旨在探討澳門幼稚園教師與資源教師在學前融合教育環境中的合作現況，包括合作程度、合作中遇到的狀況、合作滿意度、對合作的支援需求、以及對合作的建議。研究採用問卷調查法，研究對象包括澳門參與融合教育計劃的幼稚園中的53名幼稚園教師和15名資源教師。結果顯示，(1) 6成以上幼稚園教師與資源教師有合作經驗;資源教師全部都有與幼稚園教師合作的經驗，雙方教師都認為開展最多的合作教學類型是「一人教學，一人協助」;（2）雙方合作時間有限，7成以上的幼稚園教師表示每週與資源教師討論時間少於30分鐘，而有4成資源教師表示每週討論時間約1小時;(3)雙方教師表示合作時最大的困難是溝通協調;(4)最主要的合作領域是交流個案的基本情況和討論學生的教學策略;(5)兩組教師對合作的整體滿意度高於中等程度，其中「正面態度」維度滿意度最高，「支援系統」維度滿意度最低;(6)教師對專業培訓和家長培訓的支援需求較高;(7)雙方教師都認為「加強溝通」和「增加教師培訓與專業發展」是改善合作的關鍵。根據這些研究結果，筆者建議從政策、學校及教師三個層面著手，建立完善支援網絡、多元交流平臺，並持續提升教師專業能力。

FACTORS INFLUENCING THE PROGRESSION OF FEMALE EMPLOYEES IN THE PUBLIC SECTOR IN MACAU - Sun, Weng Hong (2025)
This research examines aspects that influence career development for women in the public sector in Macau. The combination of local customs and what remains from Portuguese rule in Macau has led to a special society that influences how gender is dealt with in public institutions. While nations promise gender equality, women do not hold many leadership positions in their government agencies. To conduct this study, qualitative research using semi-structured interviews was performed with 12 female public sector staff, some in leadership positions and some aiming for them. Analysis of interview data shows that cultural norms, organizational structures and new technological trends together block women from advancing at work. It appears that strong cultural habits about gender keep valuing women’s domestic duties over professional goals, supporting the belief that top management should be mostly male. Women in these sectors which are largely male, are doubted about their ability to lead. Organizational barriers, including opaque promotion practices, gender-biased recruitment, lack of mentorship, and limited access to gender-sensitive leadership development programs, further impede women's career advancement. Even though work-life balance policies exist in the handbook, managers often ignore them and consider them a hindrance for women hoping to move ahead.In parallel, the study explores how digital transformation—the so-called "Internet+" era— offers both opportunities and challenges for women in the public sector. Although digital tools improve skills and career paths, poor training often keeps women from gaining from these resources. The impact of digitalization brings out more gender inequality, because women find it harder to access major leadership roles in high-tech sectors. To tackle these different problems, the dissertation recommends strategies such as running gender-focused mentorship programs, making sure work-life balance policies are properly enforced, increasing transparency during promotions and launching digital skill training just for female employees. Equally importantly, it stresses the need for shifts in cultural values together with new policies, encouraging campaigns to raise awareness and welcoming new leadership models opposed to patriarchy. The research, by considering Macau’s special setting, helps advance the debate on gender equity in governance and provides useful tips for supporting inclusive leadership paths in societies with similar characteristics.

突破選擇困難：澳門35-40歲成年人對決策的體驗及對社工的啟示 - Tam, Kuai San (2025)
As individuals reach 35, they often find that others no longer view them as young. Various theories of adult development suggest that the shift into middle age officially begins at 40. This stage is seen as a transitional period leading toward middle age, commonly referred to in our context as the ""35-year threshold"" or ""35-year crisis."" Therefore, the transformations and significant decisions faced by those aged 35 to 40 deserve attention to better understand the support necessary for a smooth transition into middle age. Research on those in the 35 to 40 age bracket is limited in many regions. This study seeks to identify the needs of early adults within this age group in our area, utilizing qualitative methods. By conducting in-depth interviews about the life experience of the interviewees and starting up writing the stories with the dimension of phenomenological pedagogy, we aim to capture participants' subjective experiences, shedding light on the psychological aspects of their decision-making during pivotal life events. In total, 20 participants aged 35 to 40 from our region were invited to contribute to this study. After three months of interviews and five months of analysis, the research identified four key factors influencing their decision-making attitudes toward major life events: a primary focus on family considerations, a perceived urgency to enact changes before turning 40, a pursuit of stability, and a desire for self-actualization while letting go of rigid expectations. Additionally, based on participants’ insights regarding support systems for Macau adults in this age group, five recommendations were proposed: enhancing family welfare policies, regular reviews of housing policies, promoting life education and diversified development for youth, addressing workplace stress and fostering continuous professional development, and increasing awareness of mental health. These measures aim to provide better support for individuals navigating life transitions or challenges. In summary, the insights gathered from participants provide important implications for adults, government bodies, and social workers regarding the services needed. This research underscores the essential support services for those aged 35 to 40 and suggests the creation of more customized programs and resources. 當踏入35歲後在別人眼裡已不再年輕，在許多成人發展理論定義上則認為踏入40歲後才算中年階段，35歲後正要開始步向中年的過渡時期，國內更稱為「35歲門檻」及「35歲危機」，所以35至40歲這個年齡階段的生活遇到的轉變和重大事件決策歷程，從而了解那些支援能讓這個年齡階段能順利過渡至中年階段，亦是值得進行探討及研究。 不同地區亦較少對35至40歲這個年齡人士進行研究，本研究為了解本澳35至40歲成年早期人士的需要，研究會採用質性研究，以深度訪談了解受訪者在研究題目當中有關的生活體驗，並以教育現象學作分析，期望從受訪者主觀表述其經驗，以了解35至40歲成年人士對於生活中重大事件的決策深層心理意涵與其真實想法。 本次研究共邀請20位本澳35至40歲之成年人士為對象，經過3個月的訪談及歷時5個月進行探討及總結，研究分析得出這個年齡階段之人士，他們面對重大事件作出決策取態的結果有以下四大重要元素：本澳35至40歲成年早期人士首先以家庭角度出發，其次認為時間不多需要在40歲前作出轉變並且追求穩定的生活，追求自我價值及放下執着。 另外，從受訪者提及如何支援本澳35至40歲之成年人的生活，共歸納出五項建議：完善家庭福利措施、定期檢視房屋政策、青年生命教育及多元發展、在職人士壓力及持續進修發展、促進心理健康的關注，讓他們能更有支援的情況下應對生活的轉變或挑戰。 最後，從各位受訪者的建議中整理及歸納，為成年人、政府相關單位及社會工作者在服務提供相關啟示，更能補充35至40歲這個年齡階段人士的生活所需之服務，以及作出更合意的支援方案與服務資訊作參考。

Western Fast Food Market Satisfaction Survey in Macau: the case of Jollibee - Hong, Xiao Yang (2025)
This dissertation investigates consumer satisfaction with the Philippine fast food chain Jollibee in the highly competitive and multicultural Macau market. The study adopts a mixed method approach, combining semi-structured interviews with ten consumers (residents and non-local tourists) to analyze the important factors driving satisfaction. The results show that service quality, especially employee efficiency and the organization of events (such as birthday parties), has a significant impact on satisfaction. However, language barriers and cultural differences when ordering food pose challenges to non-local customers. Although Jollibee's core products (especially fried chicken) are appreciated by many respondents for their taste and freshness, the menu lacks diversity. It is not localized enough to meet Macau's unique Chinese-Portuguese fusion dining preferences fully. Price sensitivity is very significant, and Jollibee is often considered by customers to be more expensive than competitors such as McDonald's, which affects their value perception. Therefore, promotional strategies, especially experiential activities, should show effectiveness and cultural resonance. Finally, the study proposed suggestions on improving service quality, menu localization, strategic pricing, and culturally sensitive promotions to improve Jollibee’s positioning in the Macau market and provide a reference for other Western fast food brands to develop in the Macau market.

Exploring the Perceived Inclusion of Filipino Domestic Workers in Macao - Chan, Hang Wai (2025)
Inclusiveness has become a critical topic nowadays, serving as a benchmark of a nation and community’s level of civilization. As a core component of the United Nations' Sustainable Development Goals (SDGs), inclusiveness underscores its global significance in fostering equitable and justice societies. The changing dynamics of Macao households, characterized by both parents working or engaging in shift work, along with an increasingly aging population, have led to a growing reliance on domestic workers. As a result, these domestic workers often develop deep relationships with the children under their care, becoming integral members of the households. According to statistics from the Labour Affairs Bureau in Macao (2024), Filipino non-resident workers comprise the second-largest ethnic group, totaling 30,267 individuals. Of this group, 48% (14,604 individuals) are engaged in domestic work, highlighting their substantial presence in the sector. This study aims to investigate the experiences of the largest migrant working group in the region—female Filipino domestic workers—focusing on their experiences of inclusiveness within both the workplace and the Macao community. Utilizing a quantitative research methodology, the study conducts interviews with 10 female Filipino domestic workers in Macao. These interviews provide valuable insights into their lived experiences, illuminating their perceptions of inclusion within their employed families and society. Additionally, the research examines whether existing laws and regulations facilitate their inclusion in Macao. The results of this study revealed eight key themes and two new models of Perceived Inclusiveness in Domestic Workplace and Community , contributing to a deeper understanding of the inclusiveness experience of Filipino domestic workers in Macao.

FINANCIAL VALUATION OF PROCTER & GAMBLE CORP. - Chen, Yan Tong (2025)
Procter & Gamble (P&G) was founded in 1837 and is headquartered in Cincinnati, Ohio, USA. It is one of the giants of global consumer goods companies. The company has a high reputation in the daily chemical market, with factories and branches in over 80 countries worldwide. Its products from over 300 brands are sold in over 160 countries and regions, including shampoo, hair care, skincare products, cosmetics, baby care products, women's hygiene products, pharmaceuticals, fabrics, home care, personal cleaning products, etc. However, in the context of globalization and the global pandemic, maintaining a competitive advantage in the industry for a long time remains a huge challenge. The article analyzes P&G 's financial data and draws conclusions that will help evaluate its value and future positioning. A comparison between the intrinsic values from three valuation models as of December 31, 2023, will provide valuable information for investors and serve as a reference for the operation and development of other similar companies.

Nature exposure and well-being in Macao - Sazonova, Anastasiia (2025)
This dissertation investigated the impact of nature exposure, namely access to green elements, and time spent outdoors on well-being, specifically experiences of positive and negative affect and flourishing, in Macao. Drawing on existing literature, the study proposes the following hypotheses: H1: Access to green elements has a positive relationship with positive affect. H2: Time spent outdoors moderates the relationship between access to green elements and positive affect, in that more time spent outdoors will strengthen the relationship. H3: Access to green elements has a negative relationship with negative affect. H4: Time spent outdoors moderates the relationship between access to green elements and negative affect, in that more time spent outdoors will weaken the relationship. A quantitative methodology utilising cross-sectional self-response questionnaires was employed for data collection. The measures used were pre-validated and translated into Chinese through a rigorous translation and back translation process. The final sample consisted of 740 participants from different industries in Macao. The results highlight the significance of integrating natural elements in daily life to promote flourishing and positive affect. The implications of these findings, both in theoretical and practical terms, are thoroughly discussed. The findings offer valuable insights for the implementation of the biophilic practices by counsellors, educators, health professionals, urban planners, employers and other decision makers.

RECREATING THE 1990S LAI CHI VUN SHIPYARDS: VR APPLCATION IN HERITAGE CONSEVATION - Kong, Wai Peng (2025)
The shipbuilding industry in Macau, a significant cultural and economic pillar for over 150 years, faces challenges of fading memory and structural decay, particularly at the Lai Chi Vun Shipyards, a site protected under Macau’s Cultural Heritage Protection Law. This study adopts virtual reality (VR) technology to digitally reconstruct the 1990s shipyards, offering users an immersive exploration of historical structures and traditional shipbuilding practices. The VR prototype was evaluated in two distinct settings—outdoors at Song Veng Shipyard and indoors in a study room at the University of Saint Joseph (USJ) in Macau—using a combination of user recruitment, task-based interactions, and data collection through questionnaires, interviews, and observations. Results revealed that users appreciated the cultural significance and visual authenticity of the VR experience but identified limitations such as physical discomfort, text-heavy content, and a lack of interactivity. Outdoor settings generally provided a more positive experience, while indoor conditions exacerbated cybersickness symptoms. Recommendations for future iterations include enhancing interactivity, incorporating multisensory elements, and improving ergonomic design to maximize educational and cultural impact. This study highlights the potential of VR as a tool for preserving and promoting Macau’s maritime heritage while addressing key areas for refinement.

HOUSEHOLD FOOD WASTE PREVENTION AND MANAGEMENT IN DONGGUAN: RECOMMENDATIONS FROM REGIONAL PERSPECTIVES - Ye, Ru Qi (2025)
With the steady growth of the global population and the acceleration of the urbanization process, the carbon footprint generated by the food production system and thus by food waste (40 % of food is wasted globally) has a significant impact on the environment and for sustainable development. Dongguan, as a new first-tier city in China, has attracted many internal migrants from China to work and settle down. A large proportion of the city's waste is composed of organic waste, and household food waste is an important part of it. This may be due to the fact that families purchase too much food, set aside excessive amounts, or fail to consume the food before it spoils, resulting in a waste of resources that comes along with significant environmental impacts, especially in the form of greenhouse gas emissions. This research adopted the method of questionnaire survey. The questionnaire aims to gain an in-depth understanding of the food waste perception and situation in Dongguan’s household sector and its families. By covering questions in three aspects: the demographic information of the respondents, their views and perceptions of local food waste, and their behavioral habits, the questionnaire investigates the current situation and local challenges of household food waste in families (such as the situation of leftover dishes, the proportion of food waste in household garbage, etc.), analyzes the causes of waste (factors in links such as purchasing, cooking, and storing), explores the wider public's awareness and attitudes towards food waste (degree of attention, views on reduction measures, environmental awareness, etc.), and clarifies the behavioral habits of dealing with leftover food (handling methods, willingness to purchase discounted food, etc.), and analyzes the relationship between demographic characteristics and food waste, so as to provide a basis for formulating targeted strategies. The survey results show that there exists a significant degree of food waste in Dongguan households. The public's awareness and behavioral habits regarding food waste vary greatly, and there is much room for improvement and enhancement. It is urgent to strengthen publicity and education work, which will help improve the public's understanding of the harm of food waste and enhance their environmental awareness. The research finds that although the Dongguan Municipal Government attaches great importance to the problem of food waste, the current policies mainly focus on the catering industry. In terms of the governance of food waste at the family level, relevant measures still need to be further strengthened. This study analyzes the factors affecting household food waste generation and comprehensively reviews and evaluates relevant policies aimed at mitigating food waste in Dongguan. On this basis, this study provides preliminary suggestions for policymakers and government departments on regional and national level, aiming to point out the direction for future related research and work planning.

我城的集體記憶：澳門民間藝文活動如何形塑地方認同 - Lei, Cheok Ieng (2025)

A Financial Valuation of Nike, Inc. - Almeida, Melissa Sofia Barbosa (2025)
This research focuses on Nike, Inc., an American multinational corporation and global leader in the design, marketing, and sale of athletic footwear, apparel, and equipment. The study executes a financial valuation of Nike with the objective of estimating its intrinsic value and comparing it with the market value as of May 31st, 2023. The analysis combines a review of the company's overall strategic positioning in the industry and its historical financial performance. The methodology involved the reorganization of financial statements, the calculation of key financial metrics (NOPLAT, FCF, ROIC), the estimation of the cost of capital (WACC) using CAPM, and the application of valuation models based on discounted cash flows (Enterprise DCF, APV, DEP). The results imply that, as of May 31st, 2023, Nike's estimated intrinsic value was between $54.94 and $59.23 per share. Comparing this to the market price of $105.26 on the same date, the analysis concludes that Nike shares were significantly overvalued. The sensitivity analysis highlighted the vulnerability of the valuation to changes in the market risk premium and the perpetual growth rate. It is concluded that, despite Nike's strong market position, effective management of external risks, and maintenance of financial discipline are crucial to its future value.

GENDER MAINSTREAMING IN CAREER DEVELOPMENT WITHIN THE PUBLIC SECTOR: A CASE STUDY OF THE MACAO PUBLIC SECURITY POLICE FORCE - Chan, Wai Kit (2025)
This dissertation investigates the implementation of gender mainstreaming in career development in the Macao Public Security Police Force, specifically how the institutional policies and socio-cultural contexts interact within and influence careers in a traditionally structured organization. The study utilizes the Theory of Planned Behavior (TPB) to explore the impact of Attitude, Subjective Norms and Perceived Behavioral Control in influencing career development outcomes. Adopting a qualitative approach, utilizing policy analysis with in-depth interviews to identify gaps in academic studies and assess the effectiveness. Findings demonstrate that while some progress is observed, highly entrenched biases and traditional views of roles remain present and pose significant challenges. Police officers throughout the organization expressed a desire for reducing structural barriers, and enhancing support for employee work-life balance to benefit all personnel. By analyzing the local conditions in Macao and reflecting on relevant global practices in gender mainstreaming, this study concludes that sustainable equality in the workplace requires a balance of institutional and cultural factors, including organizational policies, workplace norms, gender stereotypes and societal expectations. In essence, the study contributes to the multidimensional discussion on how we can all leverage positive practices and offers valuable advice on improving workplace equality.

"SPIRITUALITY’S IMPACT ON WORK ENGAGEMENT AND WELL-BEING AMONG RELIGIOUS SISTERS: A CASE STUDY OF COPING STRATEGIES AND SUBJECTIVE WELL-BEING IN THE WORKPLACE" - CHERROPIHTUN (2025)
Spiritual beliefs enhance work engagement because religious and spiritual perspectives influence how individuals perceive their daily circumstances and organize their activities, impacting their overall happiness and satisfaction with life and reinforcing their meaning in the workplace. This study examines the impact of spirituality on work engagement and wellbeing among religious sisters, focusing on their unique workplace dynamics and coping strategies. Recognizing that work serves not only as a means of survival but also as a source of social, organizational, and spiritual experiences that create meaning, happiness, and a sense of purpose. Moreover, research indicates that spirituality plays a significant role in enhancing well-being, leading to higher levels of work engagement, life satisfaction, and flourishing. This research aims to fill a gap in existing literature about the well-being of religious workers and offer insights that benefit both individuals and organizations. Understanding how spirituality, work engagement, and well-being interact can help organizations and contribute to personal overall well-being. This study has adopted qualitative research as the research as methodology. Semi-structured interviews allow for an in-depth exploration of personal experiences and perceptions, providing flexibility for participants to elaborate on their thoughts. Thematic analysis was then applied to each interview to identify and interpret key themes emerging from the data, facilitating a comprehensive analysis of the participants’ insights (Braun & Clarke, 2006). Thematic analysis revealed several key findings: spirituality serves as a source of resilience, provides a sense of purpose, and fosters strong community ties, all of V which significantly enhance subjective well-being. The findings highlight that high levels of subjective well-being are linked to active engagement in spiritual practices and supportive community relationships. The findings suggest that religious organizations should create tailored support programs that address the specific needs of individual religious sisters, including mental health resources, opportunities for spiritual growth, peer support groups, and regular retreats. This research contributes to the understanding of the unique challenges faced by religious sisters and underscores the importance of integrating spirituality into workplace practices, offering valuable insights for religious communities and policymakers.

TO EXPLORE THE EXPERIENCE OF MACAU YOUNG PEOPLE PERCEPTION OF USING FOUL LANGUAGE - Iun, Keng In (2025)
Foul language is a common phenomenon in our daily lives. In the modern time, it is no longer a novelty in using foul language. However, the subjective impression of foul language as uncultured or rude is no longer rare. With the popularity of people speaking foul language in their daily life, especially we are witnessing more and more young people in Macau using foul language to communicate in different context. This study aims to explore the experiences of Macau youth in using foul language. This study adopts semi-structured interviews with study participants, and analyze what they understand and perceive as foul language in different certain situations in the context of Macau. Findings of this study indicate that foul language plays a role in emotional expression and relationship building, which are essential element of counselling service. Even with this factor, participants still felt that the use of foul language was more effective only when the client used than in other situations.

METAVERSE MARKETING: HOW THE METAVERSE WILL SHAPE THE DEVELOPMENT OF TOURISM AND PRACTICE,THE CASE STUDY OF MACAU (2025)
"The advent of the metaverse heralds a new era of unparalleled potential within digital ecosystems, significantly transforming industries such as tourism. This study explores the profound changes in tourism marketing induced by the metaverse, particularly through a focused examination of Macau's strategic initiatives. Predicated on the belief that immersive technologies like Virtual Reality (VR) and Augmented Reality (AR) are driving a marketing paradigm shift, this research clarifies the theoretical foundations and practical impacts of metaverse marketing in enhancing the tourism experience. Employing mixed-methods research combining qualitative and quantitative approaches, the analysis showcases Macau's utilization of metaverse marketing to bolster value creation and competitive positioning in the tourism sector. Findings indicate that metaverse marketing profoundly influences consumer behavior, highlighting nuanced consumer journeys within the virtual tourism market. Macau's case illustrates the success of its meta-universe initiatives and benchmarks them against global practices to extract sustainable competitive advantages and strategic insights. The study aggregates the marketing experiences of metaverse practitioners, revealing transformative effects on stakeholders ranging from revelant industries. It notes that while metaverse marketing provides some convenience for small and medium-sized enterprises (SMEs) in tourism, it lacks long-term effectiveness. Commending Macau's innovative approach in the meta-universe, the research outlines directions for future efforts and contributes to the burgeoning literature on metaverse marketing, offering actionable recommendations and underscoring the imperative for ongoing innovation in this dynamic digital realm."

MANAGEMENT ADJUSTMENTS FOR PREFABRICATED COMPONENT USING IN FIT-OUT WORKS: CASE ANALYSIS AND RECOMMENDATIONS - Ma, He (2025)
The purpose of this thesis is to assess how the use of prefabricated components alters management practices in fit-out projects and to propose effective adjustments based on real-world evidence. Focusing on the renovation of the Venetian Cotai Arena in Macau, conducted between January and October 2024, this study aims to help project managers anticipate and overcome the unique challenges introduced by prefabrication, especially in areas such as supply chain coordination, cost control, quality assurance, workforce management, and communication. Driven by rising labor costs and growing quality demands in Hong Kong, Macau, and Mainland China, prefabricated construction has emerged as a promising yet complex solution for interior fit-out projects. Despite its theoretical advantages—such as time efficiency and standardized quality—this research finds that practical management issues can offset these benefits if not properly addressed. The study adopts a qualitative case study approach, drawing on stakeholder interviews, internal meeting records, and dynamic cost analysis to investigate management failures and derive actionable insights. The findings reveal that delays in prefabricated material production and delivery were the root cause of construction inefficiencies. These delays disrupted work sequencing, led to labor idle time, and triggered costly overtime during final phases. Inadequate supplier capacity and outdated production processes contributed to this problem, while poor quality control caused dimensional mismatches and on-site rework. Cost analysis confirmed that rework expenses reached over MOP 22 million, while material and labor costs also significantly exceeded the original budget. Labor inefficiencies—driven by untrained workers and uncoordinated instructions—added further financial and scheduling pressures. Warehouse mismanagement and unclear material labeling further delayed installation work and increased operational overheads. The study concludes that prefabrication success is contingent not only on technical design but also on the implementation of proactive management strategies, including early supplier engagement, accurate production planning, effective logistics labeling, and structured site-level authority. This thesis contributes practical guidance for future projects by demonstrating how targeted management adjustments—based on real case data—can reduce cost overruns, improve coordination, and increase overall project efficiency when using prefabricated components.

THE IMPACT OF ESG-LINKED EXECUTIVE COMPENSATION ON GREEN INVESTMENT IN CHINESE LISTED COMPANIES (2025)
Against the backdrop of a deepening global concept of sustainable development, environmental, social and governance (ESG) elements have gradually risen to become key components of corporate strategic choices. Within the framework of China's ‘dual-carbon’ strategic goal, green investment, as a key path to promote sustainable development, has attracted widespread attention for its intrinsic driving mechanism. This study selects a sample of Chinese A-share listed companies between 2019 and 2023, and systematically analyses the impact of ESG-linked executive compensation on corporate green investment and its mechanism of action. By establishing a multiple regression model and applying the mediation effect and moderating effect analysis method, the following empirical results are obtained: First, ESG-linked executive compensation has a significant positive impact on green investment; Second, Environmental awareness plays a partially mediating role in the relationship between ESG-linked executive compensation and green investment, suggesting that ESG-linked executive compensation not only acts directly on investment decisions, but also indirectly promotes green investment by enhancing corporate environmental awareness; Third, the nature of enterprise ownership and industry characteristics have a significant moderating effect on this effect, compared with private enterprises, ESG-linked executive compensation promotes green investment in state-owned enterprises more obviously; at the same time, the sensitivity of high-pollution industries to ESG-linked executive compensation is higher than that of low-pollution industries, which suggests that ESG-linked executive compensation has a stronger ‘corrective’ effect in industries facing higher environmental risks. To ensure the robustness of the findings, the study was validated by replacing the dependent variable (EPI for environmental investment), replacing the empirical model (Tobit model), and dealing with endogeneity issues (lag analysis and propensity score matching method), all of which yielded results consistent with the underlying research hypotheses.

EXPLORING PERCEPTIONS OF ADOLESCENTS’ MENTAL HEALTH: A QUALITATIVE STUDY WITH EDUCATORS, SOCIAL WORKERS, AND MENTAL HEALTH PROFESSIONALS IN MACAU - Cheong, Wai Teng (2025)
As suicide and medical consultation rates among local adolescents in Macau rise, their mental health becomes increasingly concerning, highlighting a lack of relevant local research. This qualitative study examines the perspectives of adult helping professionals in Macau regarding adolescents' mental health. It involved semi-structured interviews with 12 professionals, including social workers, teachers, counselors, and psychotherapists. The analysis of the interview data revealed six significant themes impacting the mental health of young people: adult sensitivity to adolescents, excessive online information, the influence of peers or significant others, negative self-image and life experiences, and family and socio-cultural factors. The study's findings highlight the protective role of adult sensitivity to adolescents, the prevalence of excessive online information, the influence of peers and significant others, negative self-image and life experiences, and negative socio-cultural factors in Macau. The study underscores the societal demand for success, the need for family-friendly policies, limited public knowledge about mental health, and the protective impact of adult sensitivity on adolescents' mental health. Recommendations include that the government prioritize adolescents' needs, foster multiple abilities, enhance teachers' understanding of mental health and treatment methods, strengthen the workforce, optimize family-friendly policies, value parent-child time, and integrate emotional education courses into the educational system to boost public awareness of mental health. This study provides valuable insights for policymakers and practitioners committed to improving the mental health of Macau's youth.

A PHILOSOPHICAL COMPARISON OF THE AESTHETICS OF FRENCH NOUVELLE CUISINE AND KAISEKI CUISINE - Wong, Lok Io (2025)
This dissertation conducts a comparison of French Nouvelle Cuisine and Japanese Kaiseki Cuisine, exploring the similarities and differences of both cuisines and reflecting how cultural values, philosophical aspects, and historical influences have shaped contemporary dining experiences. In the examination of both cuisines, it takes into consideration aspects such as sensory experience, plating, and their underlying philosophical principles to demonstrate the interaction between aesthetics and culture particularly in relation to the culinary arts. French nouvelle cuisine was influenced by the Enlightenment, and this type of Western cuisine highlights a focus on texture and balance in flavor, emphasizing freshness, innovation, and intellectual artistry. Kaiseki cuisine inherited the tradition of the Japanese tea ceremony and is essentially rooted in Zen Buddhism. Some of the core aesthetic concepts in Kaiseki cuisine include seasonality, simplicity, and the aesthetic concept of wabi-sabi, emphasizing how humans should live in harmony with nature. As these two types of cuisines are compared, there will also be a comparison of Immanuel Kant’s aesthetics and how it is related to French nouvelle cuisine, as representative of a Western philosophical view and this will be compared to Japanese aesthetics in general and, in particular, the views on aesthetics of the Japanese philosopher Daisetsu Teitaro Suzuki, as representative of an Eastern philosophical view and its relation to culinary arts.

L'ORÉAL'S INTERNATIONAL STRATEGY: THE SUCCESS AND CHALLENGES OF LANCÔME BRAND IN THE CHINESE MARKET - Guan, Xin Tong (2025)
his study analyzes the effectiveness of Lancôme's localization strategy in the Chinese market, and explores how international brands can win recognition and achieve sustainable development in a highly competitive market. Against the backdrop of a fast-growing Chinese cosmetics market that is facing the challenges of rising local brands, shifting consumer preferences, and digital marketing, the study employs the Howard Sheth model, combined with in-depth interviews with 16 female consumers, to analyze their purchasing decisions and feedback on localization strategies. The study finds that Lancôme's technological attributes and social media communication have significantly improved brand perception, but the issues of cultural adaptation and price sensitivity still need to be optimized. Consumers generally perceive its high-end technology positioning as contradictory to local needs, and suggest differentiated pricing, deepening of local cultural elements, and emotional marketing to enhance affinity. The conclusion suggests that international brands need to find a balance between ""high-end technology"" and ""local affinity"", and respond to the complex challenges of the market through flexible pricing, in-depth localization and upgrading of the omni-channel experience.

An Empirical Assessment of Public Servants' Integrity in the Public Sector of Macao - Wong, Hio Nam (2025)
This study provides an empirical assessment of public servants’ integrity in Macao’s public sector, exploring how integrity is perceived, practiced, and promoted amid Macao’s unique administrative and socio-cultural context. Drawing on in-depth, semi-structured interviews with ten public servants from diverse departments and hierarchical levels, the research adopts a qualitative approach guided by the Theory of Public Service Motivation (PSM). The findings reveal that integrity fundamentally prioritizes public interest above personal gain, grounded in honesty, self-discipline, and ethical commitment. While organizational missions and formal codes offer guidance, individual values, professional ethics, and personal motivation are central to upholding integrity. Key enablers include mission-driven values, ethical leadership, supportive organizational culture, non-monetary incentives, and recognition. However, integrity is undermined by inconsistent ethics training, weak supervision, ineffective reporting mechanisms, and cultural factors such as close social networks and fear of retaliation. The effectiveness of mechanisms, such as internal regulations, anti-corruption agencies, and ethics training, varies across departments, often hindered by procedural gaps and societal norms. The study concludes that sustaining integrity in Macao’s public sector requires strengthening ethics education, enhancing leadership and culture, improving internal systems, and addressing systemic and societal risks. Limitations include the small, non-generalizable sample and focus on qualitative insights. Recommendations are targeted at policymakers, the supervisory institution, the Commission Against Corruption (CCAC), and institutional leaders for future reforms.

澳門普通學校教師特教專業知能與融合教育態度之關係混合研究 - Lio, Hang Io (2025)
This study investigates the relationship between special education professional competence and inclusive education attitudes among general school teachers in Macao, aiming to understand how these factors influence the development of inclusive education in the region. 310 valid questionnaires were collected from local general school teachers through surveys incorporating 14 background variables, analyzed using statistical methods including independent samples t-tests, one-way ANOVA, and ordinal one-way ANOVA. Qualitative interviews further supplemented the findings. The results show: 1. General school teachers in Macao demonstrated a relateively high level of ""overall special education competence"" and its five dimensions: ""general special education knowledge,"" ""curriculum design competence,"" ""instructional design competence,"" ""assessment competence,"" and ""classroom management competence."" 2. Teachers showed positive ""overall inclusive education attitudes"" across three dimensions: ""cognitive,"" ""emotion,"" and ""behavior."" 3. Nine background variables showed significant differences in special education competence: ""age,"" ""teaching experience,"" ""special education experience,"" ""participation in inclusive education courses offered by the Education and Youth Affairs Bureau (EYAB),"" ""participation in EYAB workshops/seminars,"" ""pre-teaching relevant experience,"" ""level of support from special education professionals,"" ""frequency of colleague communication regarding inclusive students,"" and ""number of inclusive students in the class with the highest inclusion rate."" 4. Five variables show significant differences in attitudes toward inclusive education: ""age,"" ""teaching experience,"" ""special education experience,"" ""pre-teaching relevant experience,"" and ""frequency of colleague communication on inclusive student issues."" Part of the qualitative interview results are consistent with the quantitative results. Additionally, Pearson Correlation Analysis was conducted, revealing a positive correlation between special education professional competence and attitudes toward inclusive education. Qualitative findings revealed additional insights: 1. Teachers identified five influencing variable for special education competence: ""gender,"" ""educational background,"" ""professional specialization,"" ""job position,"" and ""teaching stage."" 2. Teachers identified four variables impacted inclusive education attitudes: ""educational background,"" ""professional specialization,"" ""job roles,"" and ""number of inclusive students in the class with highest inclusion rate."" 3. ""Personality traits"" was a critical factor in teachers’ inclusive education attitudes: teachers with more positive, open, and patient dispositions showed stronger inclusive education attitudes. 4. ""Teacher-student relationship"" positively influenced both competence and attitudes, with better relationships correlating with higher proficiency and more favorable attitudes. Qualitative data primarily served to support and enrich the quantitative findings. 本研究以澳門普通學校教師為研究對象，探討教師在融合教育中的特教專業知能及融合教育態度之相關情況，並瞭解特教專業知能及融合教育態度對澳門融合教育發展之影響，從而由受訪者提供可提升相關因素的建議。研究一共收集了310位本澳普通學校教師的資料，14個背景變項，使用獨立樣本t檢定，單因子變異數分析、單因子等級變異數分析進行統計。結果顯示： 1）本澳普通教師在「整體特教專業知能」及其「一般特教知能」、「課程設計知能」、「教學設計知能」、「課程評核知能」及「班級經營知能」五大層面也屬於較好程度。 2）本澳普通教師在「整體融合教育態度」及其「認知」、「情感」及「行為」三大層面也屬於較好程度。 3）「年齡」、「教學年資」、「特教年資」、「修讀教青局所舉辦融合教育課程進修」、「修讀教青局所舉辦有關的講座/工作坊」、「任教前相關經驗」、「特殊教育專業人員的支援程度」、「就融合生問題而與同事溝通時間頻率」及「任教班級中最多融合生的班級之融合生人數」等九個背景變項在特教專業知能中呈顯著差異。 4）「年齡」、「教學年資」、「特教年資」、「任教前相關經驗」及「就融合生問題而與同事溝通時間頻率」等五個背景變項在融合教育態度中呈顯著差異。 而質性訪談有部分結果與量化結果相似，因此質性能解釋量化的情形。此外，亦通過獨立皮爾遜積差相關分析進行統計。結果顯示：特教專業知能與融合教育態度相互呈正相關。 再者，在質性訪談結果中有不同的發現，結果顯示： 1）本澳普通學校教師認為「性別」、「學歷」、「專業背景」、「擔任職務」、「任教階段」等五個背景變項在特教專業知能中有影響。 2）本澳普通學校教師認為「學歷」、「專業背景」、「擔任職務」、「任教班級中最多融合生的班級之融合生人數」等四個背景變項在融合教育態度中有影響。 3） 「人格特質」是影響教師融合教育態度的其中一個決定性因素，越正面積極、開放性態度越高及越有耐性，在融合教育態度上越正面。 4） 「師生關係」可能是影響教師特教專業知能及融合教育態度的其中一個決定性因素，即師生關係越好，特教專業知能及融合教育態度越好。 而質性所得出之結果主要是用來支撐及補充量化研究的結果之發現。

THE IMPACT OF SOCIAL INNOVATION THROUGH INCUBATION IN CHINA: IMPLEMENTING SDG 8 DECENT JOB AND 17 COLLABORATION NETWORK - Abdullah, Abubakar Sadik (2025)
This study explores the influence of social innovation facilitated through incubation programs on advancing Sustainable Development Goals (SDGs), specifically SDG 8 Decent Work and SDG 17 Partnerships. Employing a qualitative research approach, the investigation involved analyzing the perspectives of 9 participants from Epark Incubation, representing diverse enterprise. Semi-structured interviews were conducted to examine how social innovation within these incubation initiatives contributes to value co creation and supports the achievement of these SDGs. Out of the initial participants, nine were successfully interviewed, providing rich insights that addressed the core research questions. The qualitative data reveal that the provision of cost-reduction platforms to incubators plays a crucial role in fostering sustainability, which subsequently leads to job creation. This underscores the effectiveness of cost-efficient support mechanisms and providing training through a mentorship in driving decent work and economic growth (SDG 8). Findings also emphasize the importance of digital training, including artificial intelligence (AI) skills, and the enhancement of resource pools to strengthen networks among incubates enterprises. Moreover, the research identifies significant challenges such as funding gaps, cultural frictions, and regulatory barriers. To address these issues, it recommends integrating digital training aligned with current technological trends and navigating policy environments to facilitate easier access to funding for the incubatees. Establishing structured communication frameworks-through workshops, seminars, and benchmarking-can also help mitigate cultural frictions. 3 Looking ahead, the study suggests that future research should focus on diversifying funding sources beyond traditional capital, particularly for technology-driven incubator. Exploring impact investment models, developing crowdfunding platforms tailored for social enterprises, and advocating for government incentives to support social innovation are vital strategies. While the training-to-placement model has demonstrated effectiveness, scaling these programs and adapting them to emerging skill gaps is essential to maintain relevance in a rapidly evolving digital economy.

Sustainable Tourism Practices in Macau from Operators Perspective: Challenges and Opportunities - Lok, Pou Ieng (2025)
This dissertation investigates the challenges and opportunities for implementing sustainable tourism practices in Macau from the perspective of tourism operators. With Macau's economy heavily reliant on its vibrant tourism industry, particularly the gaming sector, the rapid growth has led to significant environmental and social impacts, raising concerns about long-term sustainability. This study aims to identify the barriers preventing operators from fully embracing sustainability, such as high implementation costs, a perceived lack of robust governmental support, and insufficient knowledge among stakeholders. Concurrently, it explores the potential avenues for sustainable tourism development, including enhanced collaboration, improved financial incentives, and strengthened environmental legislation. Through qualitative interviews, the research provides a comprehensive understanding of the current landscape. The findings reveal that while operators acknowledge the importance of sustainability, practical and policy-related hurdles persist. The study concludes with actionable recommendations for policymakers and tourism operators to foster a more sustainable and resilient tourism sector in Macau, capable of withstanding global shocks and ensuring long-term prosperity without compromising its unique cultural and natural assets. 本論文調查了實施的挑戰和機遇 從旅遊經營者的角度看澳門的可持續旅遊實踐。 隨著 澳門的經濟嚴重依賴其充滿活力的旅遊業，特別是 遊戲行業的快速增長給環境和社會帶來了重大影響， 引起對長期可持續性的擔憂。 這項研究旨在確定障礙 阻止運營商充分接受可持續性，例如高實施率 成本，被認為缺乏強大的政府支援，以及知識不足 在利益相關者中。 同時，它探索了可持續的潛在途徑 旅遊業發展，包括加強合作，改善財政激勵措施， 並加強了環境立法。 透過定性訪談， 研究提供了對當前格局的全面瞭解。 這 調查結果顯示，雖然運營商承認可持續性的重要性， 實際和政策相關的障礙持續存在。 這項研究以可操作的結論 對決策者和旅遊經營者的建議，以促進更可持續的 澳門有彈性的旅遊業，能夠抵禦全球衝擊和 在不損害其獨特的文化和自然的情況下確保長期繁榮資產

EXPLORING MACAU CULTURAL HERITAGE THROUGH PATUÁ LANGUAGE WITH THEATRE GROUP DÓCI PAPIAÇÁM - Choi, Kit I. (2025)
Macanese Patuá, a Creole language of Macau, also known as "Dóci Língu di Macau", crafted by Macanese people with different cultural backgrounds such as Portuguese, Malay, Cantonese, English, and Spanish, has been forgotten over time and is almost unknown to local new generations. This research aims to explore the historical and social relevance of Patuá, emphasising its rise, evolution, and fall in Macau society. In addition, the study will use a Macanese theatre group as a case study, Dóci Papiaçám di Macau, created by creole Macanese thespians who speak Patuá and wish to continue to use the language and promote their cultural heritage. They offer yearly public performances of Patuá theatre around May. The ensemble integrates multilingual features into performances, humorously interpreting cultural differences and societal themes, earning local acclaim and support, effectively advocating for Macanese Patuá through art.

Application of Deep Learning Techniques for Air Quality Prediction: A Case Study in Macau - Lei, Thomas; Cai, Jianxiu; Cheng, Wan-Hee; Kurniawan, Tonni Agustiono; Molla, Altaf Hossain; Nadzir, Mohd Shahrul Mohd; Kong, Steven Soon-Kai; Chen, L.-W. Antony (Processes, 2025)
To better inform the public about ambient air quality and associated health risks and prevent cardiovascular and chronic respiratory diseases in Macau, the local government authorities apply the Air Quality Index (AQI) for air quality management within its jurisdiction. The application of AQI requires first determining the sub-indices for several pollutants, including respirable suspended particulates (PM10), fine suspended particulates (PM2.5), nitrogen dioxide (NO2), ozone (O3), sulfur dioxide (SO2), and carbon monoxide (CO). Accurate prediction of AQI is crucial in providing early warnings to the public before pollution episodes occur. To improve AQI prediction accuracy, deep learning methods such as artificial neural networks (ANNs) and long short-term memory (LSTM) models were applied to forecast the six pollutants commonly found in the AQI. The data for this study was accessed from the Macau High-Density Residential Air Quality Monitoring Station (AQMS), which is located in an area with high traffic and high population density near a 24 h land border-crossing facility connecting Zhuhai and Macau. The novelty of this work lies in its potential to enhance operational AQI forecasting for Macau. The ANN and LSTM models were run five times, with average pollutant forecasts obtained for each model. Results demonstrated that both models accurately predicted pollutant concentrations of the upcoming 24 h, with PM10 and CO showing the highest predictive accuracy, reflected in high Pearson Correlation Coefficient (PCC) between 0.84 and 0.87 and Kendall’s Tau Coefficient (KTC) between 0.66 and 0.70 values and low Mean Bias (MB) between 0.06 and 0.10, Mean Fractional Bias (MFB) between 0.09 and 0.11, Root Mean Square Error (RMSE) between 0.14 and 0.21, and Mean Absolute Error (MAE) between 0.11 and 0.17. Overall, the LSTM model consistently delivered the highest PCC (0.87) and KTC (0.70) values and the lowest MB (0.06), MFB (0.09), RMSE (0.14), and MAE (0.11) across all six pollutants, with the lowest SD (0.01), indicating greater precision and reliability. As a result, the study concludes that the LSTM model outperforms the ANN model in forecasting air pollutants in Macau, offering a more accurate and consistent prediction tool for local air quality management.

Industrial heritage tourism in Macau: reinventing the Iec Long firecracker factory - Zuev, Denis; Hannam, Kevin; Zhao, Jethro (Tourism Geographies, 2025)
Macau is a Special Administrative Region (SAR) located in the south of the People’s Republic of China (PRC). Settled by the Portuguese it was the last European colony in Asia. Over the centuries as a maritime city Macau saw its fortunes coming as trade boomed in the 16–17th centuries; however, with the establishment of Hong Kong as a port city the importance of Macau decreased. The authorities resorted to gaming and tourism as key sources of tax revenues eventually in 2000s becoming ‘Las Vegas’ of Asia. As the pandemic hit China and the rest of the world, Macau was isolated, gaming revenues declined temporarily and the Macau authorities decided to diversify its offer of tourist attractions. Although Macau has already been recognised as a UNESCO heritage site with a well-preserved historic core since 2005, two new attractions were developed to help reposition Macau as a city with a rich cultural history. The two new sites that opened in 2023 were the long abandoned Iec Long firecracker factory (益隆炮竹厂) in Taipa and dilapidated Lai Chi Vun shipyards in Coloane. Iec Long firecracker factory is unique, as it blends an interface with nature (green space dominated by the century old trees), a public space and interpretative displays of how the industrial activities were performed. In this paper we use mixed methods approach to provide a ‘thick description’ of Iec Long firecracker factory as an interplay of affective and material elements. Drawing on the existing literature we further advance how assemblage thinking can contribute to analysis of industrial heritage sites as tourist attractions. Additionally, drawing on the first-hand empirical data and the context of ongoing urban revitalization in Macau we scrutinise heritage-tourism dichotomy and demonstrate how we can better understand the meanings of heritage co-created from below.

Vasotocin and oxytocin modulation of the endocrine and behavioral response to an aggressive challenge in male Siamese fighting fish - Fusani, Bianca; Ramos, Andreia; Cardoso, Sara D.; Gonçalves, David (Hormones and Behavior, 2025)
Aggressive behavior is an adaptive trait present across all taxa. However, the neuroendocrine mechanisms regulating it, particularly in fish, are not well understood. Oxytocin (OXT) and arginine vasotocin (VT) are known modulators of aggression, but their actions remain controversial. This study tested the possible modulation of endocrine and behavioral responses to an aggression challenge by these nonapeptides in Siamese fighting fish, Betta splendens, a species known for its intrinsic aggressiveness. Male B. splendens were injected with different dosages of either Manning compound or L-368,899, VT and OXT receptor antagonists respectively, and were exposed to a mirror challenge for 30 min. While all fish displayed high levels of aggression toward their mirror image, no differences were observed between control-injected and treatment fish. However, blocking VT inhibited the post-fight increase in plasma levels of the androgen 11-ketotestosterone (KT). To further investigate this result, testis tissue from males was incubated with and without VT and Manning compound, and KT levels were measured after 180 min. Results showed a direct effect of VT on in vitro KT secretion, indicating the presence of VT receptors in the testes of this species. Overall, the study does not support a modulatory role of VT or OXT in aggressive behavior, although VT might be implicated in the regulation of peripheral androgen response to aggression in B. splendens.

PAWMATCHPRO: INTERACTIVE APPLICATION FOR PET ADOPTION IN MACAO - Lin, Wei Hui (2025)
This study systematically analyzes the needs and preferences of pet adopters in Macao through questionnaires, in-depth interviews and data analysis, in view of the problems such as information asymmetry, complex adoption process and lack of knowledge about pet health care. Based on this, a pet adoption app has been designed, integrating pet information display, intelligent matching recommendations, simplified adoption procedures, pet health management, community interaction and sharing, as well as educational resource integration. The app not only provides rich pet adoption information and convenient adoption processes but also uses smart algorithms to recommend the most suitable pets for users, enhancing the accuracy of adoption matches. At the same time, the built-in pet health management module and community interaction features effectively enhance users' awareness and participation in pet health care. Experimental validation shows that this application significantly improves pet adoption efficiency, enhances user satisfaction, and promotes pet welfare. This study not only provides an innovative technical solution for pet adoption in Macao but also offers valuable references for the design and development of pet adoption applications in other regions.

自閉症兒童自傷行為的功能行為評估與行為干預 - Ng Cen, Juana (2025)
The incidence of self-injurious behavior (SIB) in children with Autism Spectrum Disorder (ASD) ranges from 35% to 60%. Common types of SIB include head-banging, hair-pulling, arm-biting, eye-poking, skin-scratching and other behaviors. Functional Behavior Assessment (FBA) and function-based behavioral interventions have been shown to reduce SIB in children with ASD. However, there is limited research on this subject in Macao. This study applies a single-subject alternating treatment design to conduct an FBA on the self-injurious behavior of a child with ASD in Macao, followed by the implementation of a function-based behavioral intervention, aiming to effectively reduce the frequency or intensity of SIB in children with ASD. Based on the results of this study, the conclusions are as follows: a) Based on the Functional Behavior Assessment, the main functions of self-injurious behavior in the child with ASD are identified as escape from task demands and access to tangible items; b) Function-based intervention strategies (such as functional communication training, FCT) significantly reduce the occurrence of SIB in children with ASD. In this case study, the frequency of SIB markedly decreased, and the improvement was maintained even after the intervention was withdrawn; c) Based on the results of FCT, both independent communication behaviors (picture cards and the speech-generating device BigMac) effectively reduced the child’s SIB. However, the child learned to use the BigMac as an alternative communication behavior more quickly, and there was no occurrence of self-injurious behavior while using BigMac, whereas SIB occasionally occurred when using picture cards; d) Function-based intervention strategies demonstrate a good social validity, with the child’s teachers expressing agreement with the research’s implementation process and outcomes. 自閉症譜系障礙（Autism Spectrum Disorder，ASD）兒童自傷行為的發生率高達35%-60%，常見的類型包括撞頭、拉頭髮、咬手臂、戳眼睛及抓皮膚等。功能行為評估和基於功能的行為干預有助於降低自閉症兒童的自傷行為，然而，澳門相關的研究較少。本研究採用單一被試交替處理設計對1名澳門自閉症兒童的自傷行為開展功能行為評估，並制定相應的基於功能的行為干預。研究結果顯示：a) 基於功能行為評估，可以確定該自閉症兒童自傷行為的主要功能為逃避任務及獲得實物；b) 採用基於行為功能的干預策略（即功能性溝通訓練），可以有效降低該自閉症兒童自傷行為的頻率，且在撤銷干預後仍能維持改善效果；c) 根據功能性溝通訓練的結果，學習兩種獨立溝通行為（圖卡和言語生成設備BigMac）均有助於減少該兒童的自傷行為，但相對而言，他更快學會使用BigMac這個替代溝通行為，而且在使用BigMac的實驗時段中完全沒有出現自傷行為，而使用圖卡時會出現自傷行為；d) 基於行為功能的干預策略具有良好的社會效度，該自閉症兒童的教師對研究的實施過程及成效表示認同。

Valuation of Estee Lauder - Huang, Zhi Ting (2025)
The Estée Lauder Companies (EL)is a global leader in prestige beauty. They build consumer-beloved brands that manufacture, market, and sell exemplary skin care, makeup, fragrance, and hair care products, and serve as a steward of luxury and prestige brands globally. Today Estée Lauder's skin care, makeup and fragrance products is sold in more than 150 countries worldwide. But sustaining its competitive advantage represents an everyday challenge, due to the fierce competition that characterizes the beauty and cosmetics industry worldwide. Therefore, the thesis analyzed the financial statements of Estée Lauder Companies for the past five years (2019-2023) and forecast the business performance for the next decade (2024-2033). After that, it will calculate the intrinsic value of Estée Lauder as of December 31, 2023, and compare it with the stock market price on that day. This comparative analysis is helpful for judging whether the market price of the company's stocks truly reflects its actual value. Another objective is to explore and analyze the internal and external factors influencing the company and its future strategic planning, thereby providing important information for the sensitivity analysis of stock prices. Through this analysis, the potential impact that these factors and strategies may have on the future price of stocks can be reflected, providing an important basis for investors' decision-making. 雅诗兰黛公司（EL）是全球高端美妆领域的领导者。他们打造深受消费者喜爱的品牌，生产、营销和销售卓越的护肤品、彩妆、香水和护发产品，并在全球范围内担任奢侈品和高端品牌的守护者。如今，雅诗兰黛的护肤品、彩妆和香水产品在全球 150 多个国家销售。 但要保持其竞争优势是一项日常挑战，因为全球美容和化妆品行业竞争激烈。因此，本文分析了雅诗兰黛公司过去五年（2019 - 2023 年）的财务报表，并预测了未来十年（2024 - 2033 年）的业务表现。之后，将计算截至 2023 年 12 月 31 日雅诗兰黛的内在价值，并将其与当天的股票市场价格进行比较。这种比较分析有助于判断该公司股票的市场价格是否真正反映了其实际价值。另一个目标是探索和分析影响公司及其未来战略规划的内部和外部因素，从而为股票价格的敏感性分析提供重要信息。通过这种分析，可以反映出这些因素和策略可能对股票未来价格产生的潜在影响，为投资者的决策提供重要依据。

CAREGIVERS TO PEOPLE LIVING WITH DEMENTIA IN SINGAPORE: PROCESSES AND EXPERIENCES - Xu, Si Min (2025)
Dementia is a progressive cognitive disease affecting 55 million people worldwide. Each of these 55 million people needs at least one caregiver to support them as dementia progresses. By exploring home-based caregiving as a process, I attempt to highlight how a bioecological approach to study caregivers could shed some light on issues currently unidentified by extant caregiving studies. A bioecological approach also shows the systemic implications to caregivers’ human development due to the proximal processes between the care recipient and the caregiver. Nine Singaporean Chinese caregivers with at least three years of dementia caregiving experience were interviewed and analysed using thematic analysis. Research findings reveal three major themes of (a) human development with subthemes of self-growth and self-preservation, (b) proximal processes between caregiver and care recipient with subthemes of rollercoaster of emotions, meaning-making and adaptive behaviours and (c) bioecological effects of dementia caregiving with subthemes of role engulfment and support from others. By using a bioecological approach, this study moves beyond conventional themes frequently explored in extant caregiver literature, such as caregiver burdens and gains. The findings from these studies extend beyond Singaporean and Asian caregivers with relevance to caregivers worldwide, as dementia is a global healthcare condition with common challenges faced by caregivers worldwide. My research findings shed light on how the caregiver’s systemic interactions with principal persons such as the care recipient’s spouse, siblings and helpers play crucial roles in sustaining the caregiver’s wellbeing and enable them to carry on caregiving. This study advocates that caregivers continue their caregiving journey because of systemic support from principal persons and the relationship with the care recipient. The implications of these research findings are discussed from a microsystemic perspective, focusing on the individual caregiver, and mesosystemic, exosystemic and macrosystemic perspectives, focusing on society, community and government policies. Taking a systemic approach, practical suggestions include counselling support and psychotherapeutic interventions for caregivers throughout their caregiving journey to improve personal happiness, more proactive and microsystemic support from grassroots and public agencies focusing on the early days of a caregiver’s journey to improve caregiver visibility, reduce feelings of isolation and provide support. Increasing the profile of caregivers in the public domain could also promote a sense of visibility and recognition of individual caregivers. By helping caregivers, society could keep people living with dementia in family-level care and reduce public healthcare costs and reliance on formal institutions.

EXPLORATORY ANALYSIS OF STOCK MARKET PREDICTION USING AUTOREGRESSIVE AND MACHINE LEARNING ALGORITHMS - Luo, Wen Hao (2025)
"This study addresses the challenges of multidimensional nonlinearity and multifactorial influences in stock market prediction by proposing a dual-channel deep learning framework based on BERT+BiGRU+Attention (BBA), which integrates investor sentiment analysis with temporal trading data dynamics. Leveraging crawled data from platforms such as East Money Stock Bar, we analyze 30,000 investor comments on Tsingtao Brewery (600600) and corresponding trading records (2010- 2021). Key innovations include: A domain-specific financial sentiment lexicon enhanced by BERT for contextual text vectorization, coupled with BiGRU-based temporal feature extraction and attention-driven keyword focus.Test the rise and fall pages of stocks using stock reviews"

EXPLORING THE FACTORS THAT INFLUENCE CAREER DECISION- MAKING AMONG HIGH SCHOOL STUDENTS: A CASE STUDY COMPARING PUBLIC AND PRIVATE SCHOOLING IN VIETNAM - Ho, Thi Huyen (2025)
The rising number of students working in different fields after graduation has prompted the Ministry of Education and Training in Vietnam to emphasize the establishment of school counselling focused on career orientation to help students make a right career choice and to enhance workforce quality in response to the labor market. Career orientation is crucial for providing guidance, information, and clarity to assist individuals in career decision-making. This research aims to identify factors influencing career decision-making among high school students in Vietnam. This qualitative study uses semi-structured interviews with a convenience sample of grade 12 students from a public high school in Nghe An Province and a private high school in Dak Nong Province, Vietnam, to explore the factors influencing their career decision-making. This study identified how different factors influence the career choice of students, including individual, family, school, peers, and social trends. Two major influencing factors in career decision-making among the grade 12 students are: 1) academic performance and 2) family socioeconomic status. The results also show the differences among the factors between the public and private schooling, in which students in private school tend to have greater autonomy in their career decision-making, influenced by family aspirations, supportive educational resources and share openly with peers about career choices, while in public school students often prioritize job security and financial concerns due to limited exposure and guidance. This study contributed important information for students to make their career decisions seriously, stressing the role of school in career orientation in providing career information, career programs, and school counselling services to avoid the common situation of “too many chiefs, not enough Indians.

EXPLORING ENTREPRENEURIAL PERCEPTION AND CHALLENGES OF AFRICAN STUDENTS ABROAD: THE CASE OF MACAU. - Fati, Mamadu (2025)
This paper explores the entrepreneurial perception and challenges of African students from Portuguese-speaking countries (PSC) in Macau, adopting a qualitative research method and conducting in-depth interviews with ten students from this geographic area to understand their Perceptions and challenges towards the entrepreneurial field. This study is significant because it enriches the theoretical guidance framework. Moreover, it helps future researchers utilize valuable data for their research in the field with many samples. The insights obtained from this paper might inform policymakers and universities about the necessary framework to support international students, especially African students from Portuguese-speaking countries, in a way that can encourage them to pursue entrepreneurial opportunities. In-depth interviewing is the primary method for data collection. The thematic content analysis (TCA) An approach is utilized to analyze the data from interview transcripts. Existing research illustrated students from this geographic area's entrepreneurial perception and challenges, as well as their aspirations and intentions as planned after their study. From the point of view of the researcher's interview with his sources, the researcher discovered that there is no opportunity for them to pursue an entrepreneurial career in Macau, which means that, after their study, they will return to their motherland. III In conclusion, based on the findings, understanding the entrepreneurial perception and challenges Students from this geographic area can help to provide support from the local Government and Universities, based on their field of study in a way they can have the opportunity to explore practical experience in a working environment for their personal and professional development.

THE IMPACT OF ONLINE REVIEWS QUALITY ON TOURISM INTENTION IN THE CONTEXT OF RED BOOK: THE MEDIATING ROLE OF DESTINATION IMAGE IN MACAO - Liu, Cui Feng (2025)
This study focuses on the influence of online review quality on tourism intention, with destination image as a mediating variable, in the context of the rapid rise of internet content platforms like Red Book and Douyin. The platforms like Red Book and Douyin play an important role in shaping travel behavior, as potential travelers frequently rely on user-generated content (UGC) to find information about travel destinations, plan their trips, and form perceptions of destinations. Through a comprehensive review of existing literature and the application of structural equation modeling (SEM), the study reveals that the cognitive and affective image of destination are significantly influenced by the quality of online reviews, which in turn impacts overall destination image and tourism intention. The findings demonstrate that higher-quality online reviews — those that are timely, sufficient，helpful, and credible — not only enhance the cognitive understanding of destinations but also evoke stronger emotional connections, ultimately fostering a higher likelihood of travel intention. Moreover, the study highlights the mediating role of destination image during the process where online review quality influences tourism intention. These results offer critical insights for destination marketing organizations (DMOs) in conducting tourism marketing to attract tourists by strategically enhancing the quality and authenticity of online reviews. The study also identifies limitations in sample selection and mediating variables, providing directions for future research in the fields of online content, destination image, and tourism behavior.

DESIGNING INNOVATIVE APPLICATION INTERFACES FOR CHINESE CULTURAL PRODUCTS: STRATEGIES TO ATTRACT USERS, STREAMLINE ORDERING, AND PROMOTE EXPORTS THROUGH INTERFACE INNOVATION - Yang, Ruo Ting (2025)
Against the backdrop of globalization and thriving cultural trade, the export of Chinese cultural products faces a dual challenge of expanding international markets and enhancing competitiveness. This Dissertation focuses on designing an innovative digital platform interface aimed at effectively integrating cultural connotations with modern technology, meeting the needs of international users, and promoting the dissemination and trading of cultural products. By analyzing the Strategies to Attract Users, Streamline Ordering, and Promote Exports through Interface Innovation, cross-cultural interface design strategies are proposed. The core functions of the platform include cultural product display, online transactions, user interaction, and multilingual support, and the information architecture has been optimized to adapt to different cultural backgrounds. Visual design incorporates traditional Chinese colors and cultural symbols, while also considering the visual adaptability of global users. The study used prototype tools to build interfaces and optimized them through usability testing. The achievements not only provide practical interface design solutions for the export of cultural products, which are expected to improve the display effect and sales conversion rate in the international market, but also provide theoretical references for the development of digital cultural platforms, and help promote the dissemination and exchange of Chinese culture on a global scale.

EXAMINING MENTAL HEALTH, RESILIENCE, AND COPING STRATEGIES AMONG VIETNAMESE MIGRANT WORKERS IN MACAU - Tran, Thi Ha (2025)
Vietnamese migrant workers in Macao encounter numerous difficulties that significantly impact both their mental well-being and overall health. Daily life can be challenging due to language barriers, cultural differences, workplace stress, and financial hardships. Through an exploratory quantitative approach, this study examines these challenges in greater detail, collecting data from 268 participants, the majority of whom—93.7%—are women. Psychological assessment tools were employed to evaluate resilience, coping strategies, coping mechanisms, and levels of stress, anxiety, and depression. The findings indicate that despite working full-time, many participants receive low wages, live in inadequate conditions, and have limited access to healthcare services. A significant portion of Vietnamese migrant workers send money home to support their families, creating substantial financial pressure. Long working hours, difficulties in communication, and job-related insecurities contribute to mental distress. However, rather than seeking professional counselling, most individuals rely on informal social networks for emotional support. In conclusion, the study emphasizes the pressing need for more robust support systems, enhanced mental health resources, and improved workplace policies to aid in the social integration and well-being maintenance of these workers. Furthermore, it encourages future research to incorporate a greater number of male participants and qualitative data in order to gain a more thorough understanding of their experiences.

FACTORS AFFECTING EMPLOYEE RETENTION IN SUPERMARKETS: A CASE STUDY OF THE SUPERMARKET INDUSTRY IN MACAO - Zheng, Mei Hua (2025)
This paper focuses on the Macao supermarket industry as a research subject, employing a qualitative methodology that includes in-depth interviews with human resource managers and operational store managers to identify the factors influencing employee retention. The primary data collection method utilized is in-depth interviewing, complemented by thematic content analysis (TCA) to interpret the insights gathered from the interview transcripts. While existing literature has identified eight key factors affecting employee retention in the supermarket sector, this study uncovers three additional factors that significantly impact retention within the context of Macao's unique market environment. Supermarkets are vital to Macao’s economic development, with 26 distinct brands operating in 175 stores. However, these establishments face profitability challenges attributed to rising voluntary employee turnover. Grounded in Herzberg’s two-factor theory of motivation, this qualitative multiple-case study aims to explore the strategies employed by supermarket managers to mitigate voluntary employee turnover and enhance workforce stability. The findings will contribute to a deeper understanding of retention dynamics in the supermarket industry and provide actionable insights for improving employee engagement and satisfaction.

CUSTOM PROCEDURES ON TRADE IN MACAO CHALLENGES AND OPPORTUNITIES - Cheang, Hon Meng (2025)
This dissertation examines the customs procedures governing trade in Macao, a Special Administrative Region of China, focusing on their role in facilitating trade within the Greater Bay Area. Adopting a qualitative approach, the study conducts in-depth interviews with stakeholders, including local businesses, customs officials, and trade experts, to identify factors affecting the efficiency and transparency of customs processes, such as clearance, licensing, and declarations. The research is significant as it enriches the theoretical framework of trade facilitation in Macao, where literature is scarce, and provides practical insights for customs authorities and traders. Findings reveal bureaucratic complexities, technological gaps, and documentation burdens, particularly impacting small and medium enterprises. Three additional factors influencing trade efficiency—regional integration, stakeholder coordination, and policy alignment—are identified. The study recommends streamlined licensing, enhanced digital systems, and SME-focused training to foster sustainable trade development. These insights offer actionable guidance for policymakers and practitioners to strengthen Macao’s position as a regional trade hub.

CHILDREN AND ADOLESCENTS’ PARTICIPATION IN EXTRACURRICULAR ACTIVITIES IN MACAU: ASSOCIATION WITH ACADEMIC ACHIEVEMENT AND MENTAL HEALTH - Hou, Weng Ka (2025)
This study amid rising academic pressures and youth mental health concerns, this study investigates how extracurricular activities (PECA) shape academic and psychological outcomes in Macau—a high-stakes educational context. Focusing on 6–18-year-olds, it examines two dimensions: activity type (sports, academic, cultural and artistic) and number of activities, addressing gaps in age-specific and cross- informant analyses within East Asian settings. Using the Achenbach System (ASEBA) in Macau, data from parents and adolescents were analyzed via ANOVA and independent t-tests. ANOVA revealed optimal academic performance (F[3, 456] = 12.34, p < 0.001) and fewer behavioral issues in students with 3 PECA. T-tests showed sports reduced adolescent self- reported depression (t[210] = -3.21, p = 0.002), while academic activities boosted parent-reported grades (t[198] = 4.57, p < 0.001). Cultural activities had limited mental health impacts but enhanced language/math skills. This study underscores the importance of extracurricular activities (PECA) in Macau’s unique cultural and academic context, by validating the ""optimal balance"" hypothesis, it suggests that participating in three well-chosen activities—spanning sports, arts, and academics—yields the best outcomes. The findings emphasize the need for culturally sensitive and developmentally appropriate PECA programs tailored to Macau’s students. This research provides valuable insights into optimizing PECA types and quantities, fostering academic success, emotional resilience, and personal growth, while supporting the holistic development of well-rounded young citizens.

CONSUMER PERCEPTIONS OF ELECTRIC AIRCRAFT: INVESTIGATING THE DRIVERS OF ACCEPTANCE AND ADOPTION - Ke, Wanchun (2025)
This study investigates and analyzes the behavioral intentions of consumers in Guangdong region towards All-Electric Aircraft (AEA) within the theoretical framework of the Theory of Planned Behavior (TPB), and uses Structural Equation Modeling (SEM) and SmartPLS to analyze the collected data. According to the existing literature, TPB and SEM have not been used to evaluate the electric aviation market in Guangdong region. The purpose of this study is exploratory, adopting a quantitative research method. Structured questionnaires are distributed to approximately 100 consumers in Guangdong to explore their overall cognition of electric aircraft, the factors influencing such cognition, and their willingness to use electric aircraft. The study finds that consumers’ attitude, subjective norm, and environmental concern have a positive impact on their adoption of the new AEA technology, while perceived behavioral control and perceived risk are found to have no effect on consumers. The results of this study provide valuable insights for airlines, aircraft manufacturers, and policymakers. By understanding consumers’ concerns and preferences, airlines can formulate more effective marketing strategies to promote electric aircraft. Aircraft manufacturers can utilize these findings to improve the design and performance of electric aircraft and address consumers’ concerns. Policymakers can formulate relevant policies to support the development and adoption of electric aircraft and promote the sustainable development of the aviation industry.

EXPLORING CURRENT SITUATION AND CHALLENGES OF THE ANNUAL TRAINING PROFESSIONAL DEVELOPMENT FOR PRIMARY SCHOOL TEACHERS IN MACAO - Lei, Lai Si (2025)
The purpose of this paper is to investigate the discrepancy between the current situation of primary school teachers' participation in ‘professional development activities’ and the professional development objectives in the law in the light of the implementation of the current Private Framework law and the operation of the Cultura n.º 88/2018, and to examine the effectiveness of the Cultura n.º 88/2018. In order to achieve this research objective, this study adopted qualitative interviews with two school managers, six primary school general teachers, and one legislator, and then summarised the findings using thematic analysis. It was found that the respondents generally believed that the number of professional training courses offered by DESJ had increased after the Secretary's Directive was issued, which was helpful to school-based training and to teachers in catching up with the number of hours of training, and that the practicality of the training courses had increased to a certain extent based on the different positions of the workplace. On the other hand, due to the different job positions, there were different views and opinions on the practicality and coverage of the training programmes. It was also found that the general concern of the respondents on ‘Quadro geral do pessoal docente das escolas particulares do ensino não superior’ and ‘Despacho do Secretário para os Assuntos Sociais e Cultura n.º 88/2018’ was more inclined to the situation of the hourly allowances and activity enrolment in the professional development provisions, and they were not concerned about the relevant laws and regulations that support the purpose of professional development. Meanwhile, the study found that the majority of primary school teachers are still at the stage of solving teaching challenges in their ‘professional development process’. The study found that the top-down management decision-making model is not only the key to hindering the ‘professional development process’, but also the cyclical factor that makes it difficult to improve the current situation and the difficulties of teachers in teaching, so this paper tries to summarise the findings and make suggestions on the way forward from different perspectives and ways. Therefore, this paper also tries to summarise and suggest a pathway from different perspectives and approaches. This paper consists of six chapters, which are divided into four parts, namely, Background, Literature, Interviews and Analysis, and Conclusion and Recommendations. It will be researched and investigated at both macro and micro levels, and finally, through the combination of macro and micro perspectives, it will be summarized to give feasible and operational recommendations. In the first part of the development of education in Macau from a more macroscopic viewpoint in the Introduction, Background of the Study, and the law of Macau education introduction. 1. Historical background (Brief historical background of the development of education in Macao)Political perspectives (comparison of the differences between the professions political environments) 2. Industry Views and Reactions (Newspaper) 3. Reality situation (‘Quadro geral do pessoal docente das escolas particulares do ensino não superior’ and ‘Despacho do Secretário para os Assuntos Sociais e Cultura n.º 88/2018’) 4. Legal perspectives (restrictions and impacts on education under the current legal system) The second part explores the definition of professional development in education with different literatures, including the comparison of the differences of the profession in different political environments, as well as the Macao situation in comparison with it, the definition and the development path. It analyses the legislative background of the ‘Quadro geral do pessoal docente das escolas particulares do ensino não superior’ and ‘Despacho do Secretário para os Assuntos Sociais e Cultura n.º 88/2018’, and the comparative analysis of the meaning of the ‘Order of the Secretary for Social Affairs and Culture No. 88/2018’. The third part of the interviews and analyses examines the current situation of the annual professional development training for primary school teachers in Macao after the implementation of ‘Quadro geral do pessoal docente das escolas particulares do ensino não superior’. ‘Despacho do Secretário para os Assuntos Sociais e Cultura n.º 88/2018’ after the introduction of the current situation and challenges to the professional development of frontline stakeholders, and even to the actual teaching or management operations. A qualitative research methodology was adopted and subdivided into three sections: 1. In-depth interviews were conducted with a total of eight stakeholders at different levels, including six serving senior elementary school teachers and two school managers. Also a current member of the Legislative Assembly. 2. Collected and excerpted a total of nine elementary school teacher dissertation studies from St. John's University. 3. Summarize and analyze the interviews and excerpts, presenting in an objective and microcosmic manner and actual situations faced by teachers under the Macao's political system relevant laws and regulations, and to respond to and substantiate the points made in Part I of the literature review. The fourth part, Conclusions and Recommendations, finally combines the literature review, interviews and analysis, and integrates both macro and micro perspectives, as well as borrowing and citing existing legal and philosophical perspectives, to compile legal, feasible and practical suggestions on pathways that may be able to break through the challenges, improve the situation of teachers, and help to promote the professional development of teachers. "本研究旨在探究不同背景的小學教師囿於現行《私框》法律的實施，以及《88/2018司長批示》運作下參與「專業發展活動」的現況與法律中的專業發展目標之差異情形，以及檢視《88/2018司長批示》成效。為達此研究目的，本研究採用質性訪談2位學校管理層、6位小學普通教師、1位立法者，再以主題分析法歸納研究結果，發現受訪者中普遍認為司長批示出台之後，教青局的專業培訓課程數量有所增加，這對於校本培訓以及教師追趕培訓時數上有一定幫助，另一方面，基於工作崗位不同的關係，對培訓課程的實用性、涵蓋範圍等各有不同見解和意見，並發現受訪者中普遍對《私框》和批示的關注點，較為傾向於對專業發展條文中的時數津貼與活動報名的情況，且對於輔助專業發展目的的相關法律法規並不關心。同時透過研究發現，現時大部分小學普通教師在「專業發展進程」中仍停留在解決教學挑戰階段，研究發現由上而下的管理決定模式，既是當前教師認為妨礙「專業發展進程」的重要關鍵，也是難以改善現況，造成教師教學困難的循環因素，故本文亦嘗試以不同之角度和方式給予總結和路徑建議。 本文共六章，主要分為四個部分，分別為背景探討、文獻探討、訪談及分析以及總結和建議。並將會分別透過宏觀和微觀兩個層面去作研究和探討，並最終以宏觀與微觀兩個角度結合，透過總結歸納，給出可行和具操作性的路徑建議。 本文首先會採取以下四種角度，分別在緒論、研究背景、前題導讀中，以較為宏觀視角去剖析本澳教育發展的輪廓： 1. 大致歷史脈落（本澳教育發展歷史背景簡述） 2. 業界意見及反應（新聞報章） 3. 現實狀況 （《基力》、《課框》的影響） 4. 法律觀點（現行法律制度下對教育的限制和影響） 而第二部分則以不同文獻探討教育專業發展之定義，包括不同政治環境下專業的差異對比，以及與之對比澳門狀況，定義和發展路徑。分析《非高等教育私立學校教學人員制度框架》簡稱《私框》的立法背景、《第88/ 2018號社會文化司司長批示》簡稱《88/ 2018司長批示》的內涵對比分析。 第三部分訪談及分析，研究澳門小學教師年度專業發展培訓在《非高等教育私立學校教學人員制度框架》簡稱《私框》實施後的現況，《第88/ 2018號社會文化司司長批示》簡稱《88/ 2018司長批示》出台後對前線持份者的專業發展、乃至實際教學或管理操作的現況和挑戰。則採用質性研究法，並細分為三個環節： 1. 分別對六名現職資深小學教師、兩名學校管理層等共八名不同位階的持份者，以及現任立法會議員作深度訪談。 2. 收集及節錄共九份聖若大學小學教師論文研究。 3. 對訪談及節錄作總結和分析，以客觀和微觀方式呈現教師在澳門的政治體制和相關法律法規下所面臨的實際狀況，對應和證實第一部分文獻探討中所得出的觀點。 第四部分總結和建議，最終結合文獻探討、訪談及分析，結合宏觀與微觀兩個角度，並借用和引用現行法律、哲學等角度，整理出有可能可以突破挑戰、改善教師處境、有助推動教師專業發展的合法、可行和具操作性的路徑建議。"

The impact of providing non-human identity cues about sales agents on consumer responses: the role of social presence and speciesism activation - Cicco, Roberta De; Elmashhara, Maher Georges; Silva, Susana C.; Hammerschmidt, Maik (European Journal of Marketing, 2025)
Purpose – This work investigates how different strategies for providing cues about the non-human identity of a sales agent influence consumers’ perceptions and purchase-related outcomes, and how a social interaction style shapes these responses. Additionally, the authors explore the role of consumers’speciesism against non-human entities in eliciting unfavourable responses to the disclosure of the agent’s artificial nature. Design/methodology/approach – Three experimental studies were conducted using real chatbot interactions. Study 1 investigates how non-human identity cues impact consumer trust and, subsequently, attitude towards the firm and intention to purchase the product offered. Study 2 tests these effects across different levels of social presence. Study 3 examines consumer responses to different non-human identity disclosure strategies, considering speciesism’s moderating role. Findings – Study 1 proves that disclosing (vs not disclosing) the artificial nature of a sales agent leads to a decline in trust towards the firm, which in turn negatively influences both attitude towards the firm and purchase intention. This finding reveals discrimination against disclosed (vs non-disclosed) artificial sales agents despite identical, flawless performance. However, Study 2 proves that the negative effects vanish when perceived social presence is high. Study 3 underlines that high speciesism leads to a trust decline if non-human identity cues are presented during the interaction but not if presented earlier in the journey before the interaction. Research limitations/implications – The study highlights the negative effects of disclosure on important, firm-related outcomes. These insights advance current literature by showing that disclosing cues about the non-human nature of a sales agent can undermine psychological and behavioural responses–even when the disclosed agent performs just as effectively as its undisclosed counterpart. This result is noteworthy, as most prior research has linked aversive reactions to artificial agents with situations in which algorithms underperform, whereas this study examines agents that function flawlessly. Furthermore, the study reveals that these adverse effects are driven by speciesism–prejudices against non-human entities–offering a novel explanation for consumers’ negative responses. Practical implications – The findings stress that transparency about the artificial nature of sales agents is penalised by customers and comes at a high cost for business-relevant outcomes. However, by transforming an artificial agent into a social actor through subtle design modifications, firms can overcome the unfavourable prejudice against artificial agents. By creating a social appearance, firms can harness the potential of automated sales services–even when disclosure of the agent’s artificial identity is required. As firms may soon be obliged to disclose the artificial identity of their sales agents, the critical question shifts from whether to disclose to how to disclose in order to mitigate negative consequences. Finally, we offer guidance on targeting the right consumers with artificial agents–specifically, those with lower levels of speciesism-related prejudices. Originality/value – This work addresses pressing issues for managers concerned with the implementation of artificial sales agents. Results extend knowledge on speciesism towards digital agents, inform which consumers are particularly prone to respond negatively to such agents, and present levers for designing chat-based social interactions that prevent non-human-related prejudices that could undermine the effectiveness of conversational technologies.

Managing Aquaculture Noise: Impacts on Fish Hearing, Welfare, and Mitigation Strategies - Duan, Shanshan; Vasconcelos, Raquel; Wu, Lele; Li, Xin; Sun, Wen; Li, Xian (Reviews in Aquaculture, 2025)
ABSTRACT As intensive aquaculture continues to develop, substantial investments have been made in equipment to sustain high‐density farming. However, this has resulted in elevated noise levels within these aquaculture environments, particularly below 2000 Hz, matching the hearing range of most cultured fish species. Fish under noise conditions may experience hearing loss and physiological stress, which can negatively affect their growth, foraging efficiency, reproductive success, and increase their susceptibility to diseases. These adverse effects compromise the welfare of cultured fish, potentially decreasing production quality and increasing mortality rates. Despite these notable effects, the understanding and management of noise conditions in aquaculture systems lag behind other environmental parameters in terms of recognition and control. In this review, we cover the fundamentals of fish auditory systems, the hearing range of key cultured fish species, and the most common noise sources and levels prevalent in current intensive aquaculture systems. Additionally, we examine recent discoveries on the effects of anthropogenic noise on fish hearing, physiological responses, and behavior. Finally, we provide strategies for noise monitoring and management in the aquaculture industry, while also highlighting open questions for future research. Our goal is to assist researchers and practitioners in comprehending underwater noise and its effects on cultured fish species, providing a valuable resource for promoting the healthy and sustainable development of intensive aquaculture.

FINANCIAL VALUATION OF AMAZON - Deng, Xu Feng (2025)
Amazon is a global leader in e-commerce and cloud computing that has continually proven that it can diversify its business model well beyond being just one of the world's largest online retailers. Study its financial results, strategic initiatives by SWOT Analysis, and access its market positioning in industry by using PESTEL Analysis and Porter’s Five Forces Analysis. In order to ascertain the intrinsic value and assess the future prospects of Amazon, the study then utilizes several financial models, Enterprise Discounted Cash Flow (EDCF), Adjusted Present Value (APV) and Discounted Economic Profit (DEP). The study presents Amazon is potentially overvalued (December 31, 2024).

AN EXPLORATION OF PARENTS' PERSPECTIVES AND REASONS FOR PROVIDING ELECTRONIC DEVICES FOR YOUNG CHILDREN IN MACAO - Chio, Chong Leng (2025)
This qualitative study explores parental perspectives and decision-making processes regarding young children's engagement with electronic devices in Macao. Data was collected through semi- structured, in-depth interviews with 15 parents of young children. The researcher analysed the interview contents and synthesized the findings with relevant literature and theoretical support, resulting in the following key insights: 1. Parental attitudes towards children's use of electronic devices were found to be distinctly polarised. Parents with a more open attitude viewed electronic devices as an inevitable part of modern life, suggesting that excessive restrictions might hinder children's development. In contrast, parents with a more conservative perspective emphasised the developmental risks of early exposure. Three primary factors influenced parental attitudes; the parents’ level of professional knowledge in education, their own usage habits, and their sense of parental self-efficacy. Additionally, parental behaviours had a modelling effect on children's usage patterns, directly correlating with the stringency of their management strategies. 2. Regarding child development, parents generally recognised the educational value of electronic devices, particularly the ability of multimedia interactivity to enhance learning engagement and facilitate knowledge acquisition. However, they also expressed concerns about the potential risks in three developmental domains: physiological development (e.g., visual eye strain, sedentary behaviour), psychological development (e.g., addiction, reduced social interaction), and cognitive development (e.g., diminished attention span, fewer opportunities for practical learning). Parents with professional knowledge of child development tended to adopt more comprehensive assessment perspectives and balanced usage strategies. 3. The study identified three primary contexts in which parents provided electronic devices to their children: first, as a response to parenting stress, where parents used devices to gain brief respite or manage household tasks; second, as behavioural management tools, using devices for reward and punishment mechanisms, such as encouraging good behaviour, boosting learning motivation, or soothing children in specific situations (e.g., during illness or mealtime); and third, as influenced by external environmental factors, including caregiving differences (e.g., grandparents, domestic helpers), the technological emphasis in educational settings, and peer influence on children's social interactions. III 4. In terms of management strategies, parents predominantly employed three approaches: restrictive mediation, focusing on controlling screen time and filtering content; technical mediation, involving the use of device security settings and application restrictions; and alternative activity planning, such as encouraging children to engage in constructive play and artistic activities. However, the study revealed that parents less frequently utilised active educational mediation (e.g., discussing content, sharing experiences) and co-viewing strategies (e.g., joint parent-child usage, interactive learning). Based on these findings, the researcher provides recommendations for parents, schools, educators, and government agencies to establish a more comprehensive and supportive framework for young children's use of electronic devices and related services. 本研究採用質性研究方法，探討澳門家長對幼兒使用電子產品的觀點及決策因由，透過半 結構式深度訪談，收集 15 位育有幼兒之家長的經驗與看法。研究者根據訪談內容進行分析 討論，並輔以相關文獻和理論支持，歸納出以下研究結果: (一) 家長對幼兒使用電子產品的態度呈現明顯的兩極分化:持開放態度的家長視其為時代 趨勢，認為過度限制可能阻礙幼兒發展;持保守態度的家長則強調提早接觸電子產品可能帶 來發展風險。研究發現，家長的態度主要受三個因素影響:教育專業知識水平、個人使用習 慣，以及親職效能感。此外，家長的行為會通過示範效應影響幼兒的使用模式，並直接關係 到其管理策略的嚴格程度。 (二) 在幼兒發展方面，家長普遍認同電子產品的教育價值，尤其是其多媒體互動特性能提 升學習投入度及知識獲取。然而，家長同時關注其潛在風險，這些風險主要集中在三個層 面:生理發展(如視力損害、久坐問題)、心理發展(如沉迷、社交互動)、認知發展(如 專注力、實踐機會)。研究發現，具備幼兒發展專業知識的家長更傾向採取全面的評估視角 和均衡的使用策略。 (三) 家長提供電子產品予幼兒的三個主要情境包括:首先是因應育兒壓力，家長表示會透 過電子產品獲得短暫休息及處理家務的時間。其次是行為管理工具，家長運用電子產品進行 獎懲，包括鼓勵良好行為、提升學習動機，以及在特定情境下(如幼兒不適或進食)作為安 撫工具。第三是受外在環境因素的影響，主要來自三方面:替代照顧者(如祖父母、家傭) 的管教差異、教育環境的科技化趨勢，以及同儕使用經驗對幼兒社交需求的影響。 (四) 在管理策略方面，家長主要採取三種調解方式:限制性調解，著重於使用時間管控與 內容篩選;技術性調解，運用設備安全管理功能與應用程式限制;替代活動規劃，包括引導 幼兒參與建構性遊戲與藝術創作等。研究發現，家長較少採用具教育意義的指導性調解(如 內容討論、經驗分享)和社交共賞(如親子共同使用、互動學習)策略。 基於上述研究發現，研究者分別對家長，學校及教師、以及政府部門提出建議，期望建立 更適切且全面的幼兒電子產品使用框架及相關支援服務。

LOVE, OBSESSION AND DESTRUCTION: THE PHILOSOPHICAL CONNOTATION OF LILIAN LEE’S NOVEL ROUGE - Chan, Siu Mo (2025)
This dissertation focuses on the novel Rouge by the Hong Kong-based writer Lilian Lee, which is a fantasy novel that proclaims feminism by deploying a love tragedy, describing the social context and atmosphere of Hong Kong in the 1930s and 1980s, and the living and afterlife experiences of the courtesan Fleur. Rouge was first published in 1984 and subsequently adapted into a film in 1988, which won several awards at film festivals. The novel Rouge can be regarded as Lilian Lee’s most representative work and a significant cultural symbol of Hong Kong in the 1990s. Love is a universal human experience that has a significant impact on our lives, relationships, and our understanding of ourselves and the world around us. Consequently, philosophers have long sought to gain insight into its nature, origins and role in human existence, which makes the exploration of love a core focus of philosophical inquiry. This research will examine how the novel Rouge explores the interplay between authentic love and ego love, and will also investigate the causes that led to Fleur’s tragedy.

A Phenomenological Study of Social Participation of Men in Female Social Service Organisation - Ho, I. Lam (2025)
Today, gender equality and the empowerment of women and girls have become one of the sustainable development goals jointly regarded by the international community. As society's understanding of gender gradually becomes more diverse and open, more and more people are beginning to pay attention to men's needs. Although society generally recognizes gender equality and pays attention to the development of women, relatively little attention is paid to the development and needs of men. Men also have needs and expectations, and are influenced by society's traditional expectations in their willingness to participate in associations. This study outlines the phenomenon that men’s participation in community services is generally lower than that of women, and cites data from Hong Kong, Taiwan, Macau and other places to support this view. Although gender equality is a global concern, there are relatively few protection policies and services specifically for men in Macau and surrounding areas. In the context of pursuing gender equality, men's rights and needs should not be ignored. Therefore, this study aims to explore men's motivations for participating in women's group social services. It uses qualitative research and a phenomenological approach to 15 invited respondents. Interview samples were collected through in-depth interviews. Different findings were obtained from the research results through the use of description and inductive analysis through the life stories of the interviewees. The research concluded that service can not only meet their personal needs and experience the achievement of development tasks, but also found the key experience factors, that is, the four major motivations for men to participate in clubs, including personal service spirit, personal life needs, maintenance Social relationships and personal interests and preferences and six elements of continuous participation, including contrast in values, tangible experience, feeling changed, having challenges and growth, improving horizons and knowledge, and feeling a sense of belonging. The study also obtained four suggestions from the interviewees for social services and their expected experiences. This study also inspired social workers to formulate comprehensive and targeted men's policies, not only to respond to the diverse needs of the men's group, but also to It is the key to promoting comprehensive, coordinated and sustainable development of society. 現今性別平等與增強婦女和女童的權能，已成為國際社會共同視為持續發展目標之一。隨著社會對兩性的認知逐漸變得多元及開放，越來越多人士開始關注男士的需要。儘管社會普遍認同性別平等並關注婦女發展情況，但對男士的發展和需求關注相對不足。男士同樣有需求和期望，並且受社會傳統的期望影響參與社團的意願。 本研究概述了社團服務中男性參與度普遍低於女性的現象，並引用了香港、臺灣及澳門等地的數據來支撐這一觀點。儘管性別平等是全球關注的議題，但在澳門及周邊地區，專門針對男性的保護政策和服務相對較少。在追求性別平等的背景下，男士的權益和需求不應被忽視，因此本研究旨在探討男士參與婦女團體社會服務的動機，採用質性研究，以現象學方式，向受邀的 15 位受訪樣本，透過深度訪談蒐集資料。藉著受訪者闡述生活故事，運用描述及歸納分析，從研究結果中得到不同的發現。研究結論得出，服務既滿足到他們的個人需要，以及體 驗到發展任務的達成，另外找到了關鍵體驗的因素，即男士參與社團的四個動機，包括個人服務精神、個人生活需要、維繫社會關係、個人興趣與喜好以及六個持續參與元素，包括 價值觀的反差、切實之體驗、感受到改變、.有挑戰和成長、提升視野知識以及感覺歸屬感。 研究也得到了受訪者對社會服務的四個建議，以及他們期望的體驗，這樣研究同時啟發了社會工作者如何制定全面且有針對性的男士政策，不僅是回應男士群體多元化需求，更是推動社會全面、協調、可持續發展的關鍵所在。

ANALYSES OF THE PERCEPTION OF THE IMPACT OF PERSONAL DATA PROTECTION LAW ON SMES OPERATING IN MACAO - Kuan, Su Cheng (2025)
Macao is a small city, and most businesses operating in Macao are small and medium-sized enterprises (SMEs). With personal data protection gaining increasing global attention, what impact does personal data protection law have on the operations of SMEs in Macao? What is the perception of the impact of the Personal Data Protection Law on the operation of Macao's SMEs? This thesis aims to make a corresponding analysis. The article examines Macao's current business environment and enterprise models, integrates data collected from SME surveys, and considers Macao's economic development trajectory before and after its return to China. It analyzes Macao's connections with Portuguese-speaking countries, the European Union, and the cities in the Guangdong-Hong Kong-Macao Greater Bay Area, which the Chinese government is actively developing. By studying the characteristics of personal data protection legal systems in various countries and regions and their influence on Macao, the paper provides recommendations for enhancing SMEs' awareness of personal data protection and leveraging personal data protection laws to improve business operations in Macao. 澳門是一個細小的城市，在澳門做生意的企業大多是中小企業，個人資料保護在全球日益受到重視，究竟個人資料保護法對澳門中小企營運又帶來甚麼影響 ? 澳門中小企營運過程中，對個人資料保護法影響認知有多少? 本篇論文將會作出相應分析，文章透過分析澳門現時具體營商環境及企業模式，結合透過中小企問卷調查搜集獲得之資料，以及澳門在回歸後，前後經濟發展歷程中與葡語系國家、歐盟、以及與現時中國政府大力發展之大灣區城市之聯系，分析各國家及地區的個人資料保護法律制度之特色以及對澳門之影響，最後就澳門中小企未來就加強中小企個人資料保護意識以及善用個人資料保護法律營商作出建議。

Managing the Performance of the Facility Management for Improvement of the Hotel Operations - Kuong, Chi Chun (2025)
Management of people” and “enhancement of the system” are the focused aspects for improvement of the business operations in this thesis. A case study was carried out in the Facility Management department of a five-star hotel. A list of questionnaire was delivered to about 50% employees of the FM department for the purpose of identifying the awareness of the Organizational Culture. The result indicate that the “Work Process” and “Organization Climate” are the higher score elements than the “Leadership Style” and “Organization Value”. The results tell the management that people are reluctant to change the present work process and the leadership is not effective in the organization. The above issues represent the employees’ behavior and attitude which can affect the employees’ performance as well as the company’s operational efficiency. Suitable management techniques are applied to analyze the employees’ needs and group the people into passive and active attitude, then the appropriate motivation schemes are proposed aiming to improve the overall performance of different groups of employees. The latest technologies such as the Internet of Things (IoT) and 5G mobile communications are proposed for enhancement of the current FM systems aiming for the improvement on fast response, operational cost saving , carbon neutralization and comfort to customers. The proposed system enhancement also considers the minimal investment, so the system enhancement is mainly executed by software upgrade on the core system and replacement of the Smart Sensing devices. The hardware of core equipment can be re-used. AI technology is the future trend of operational improvement, it will be considered as the next step when AI become mature and standardized.

Financial Valuation of Caterpillar Inc. - Zeng, Fanxin (2025)
Caterpillar, one of the world's most recognised industrial brands, is a leading global manufacturer of construction and mining equipment, as well as diesel and natural gas engines and industrial gas turbines. Currently, Caterpillar operates in North America, Asia Pacific, EAME region and Latin America, with operations in North America accounting for approximately 47% of the company's net revenue in 2022. Caterpillar has been able to win customers' trust and achieve stable business growth through reliable products, advanced technology, user-friendly services and differentiated service solutions. Post-coronavirus, it can be seen that the industry in which Caterpillar operates is vulnerable to changes in the economic and social environment. In addition, the industry is becoming increasingly competitive, especially with the rise of emerging players, such as construction equipment manufacturers in China, who are entering the markets of developing countries with cost-effective products. In addition to that, such as the traditional machinery manufacturing companies in Europe and Japan, their products are not only highly intelligent, but also motorised equipment technology is quite reliable. It is a tough challenge to maintain a competitive edge. Understanding the impact of these changes on the industry and the company helps in assessing the intrinsic value of Caterpillar and its future positioning. Comparing the intrinsic value derived from the three valuation models to the company's market share price as of 31 December 2022 will provide valuable information to investors.

THE NATURE OF HOLISTIC CONSCIOUSNESS IN HERMETIC PHILOSOPHY - Wong, Enia (2025)
This thesis explores the nature of holistic consciousness in Hermetic philosophy, drawing on the classical text of The Emerald Tablet and The Corpus Hermeticum attributed to Hermes Trismegistus. Central to this ancient philosophy from Hellenistic Alexandria is the “as above, so below” principle, highlighting the interconnectedness of all things. Hermetic philosophy views harmony as the balance and interconnection of all elements in the universe. Sound, tied to the divine word, is vital for this harmony and understanding of creation and divine wisdom. This thesis focuses on the relationship between human, cosmic, and divine consciousness. Through divinization, humans can align with cosmic consciousness, realizing their divine nature by transcending physical limitations. Furthermore, we will review Hermetic philosophy in light of contemporary challenges, such as materialism which has caused environmental, social and mental health crises. Hermetic philosophy’s holistic approach and emphasis on interconnectedness can counteract social atomization caused by digital technology. Hermetic philosophy having a scientific-rational basis, can be aligned with contemporary ideas like the holographic universe theory. Self-reflection, meditation, nature engagement, and inner dialogue are all proven methods for cultivating holistic consciousness, as advocated in Hermetic philosophy. We can better understand the universe by integrating Hermetic wisdom with science. 這篇論文探討赫爾墨斯哲學中整體意識的性質，參考了赫爾墨斯·特里斯梅吉斯圖斯所屬的古典文本《翡翠石板》和《赫爾墨斯文集》。這一源自希臘化亞歷山大的古老哲學的核心原則是「上如是下」，強調所有事物之間的相互連結。 赫爾墨斯哲學視和諧為宇宙中所有元素的平衡與相互關聯。聲音與神聖之語相連，對於這種和諧及對創造與神聖智慧的理解至關重要。這篇論文專注於人類、宇宙與神聖意識之間的關係。透過神化，人類能夠與宇宙意識對齊，超越身體的限制，實現其神聖本質。 此外，我們將審視赫爾墨斯哲學在當代挑戰下的意義，例如物質主義所導致的環境、社會和心理健康危機。赫爾墨斯哲學的整體方法和對相互連結的強調，可以對抗數位科技所造成的社會原子化現象。 赫爾墨斯哲學具科學理性基礎，能與當代觀念如全息宇宙理論相結合。自我反思、冥想、與自然的互動及內心對話，都是培養整體意識的有效方法，正如赫爾墨斯哲學所提倡的。我們可以通過將赫爾墨斯智慧與科學相結合，更深入地理解宇宙。

Chinese Traditional Festival Culture and Customs of Game Design - Xie, Wan Ting (2025)
This board game is designed around China's major traditional festivals (such as the Spring Festival, Dragon Boat Festival, Mid-Autumn Festival, etc.) and their customs, with the aim of allowing players to experience and learn about China's rich cultural traditions through gameplay. The goal of the game is to earn points by completing festival tasks, answering questions about customs, and collecting festival items, with the highest scorer ultimately winning. The gameplay design includes elements like festival task cards, customs quizzes, and festival item collection to enhance interactivity and fun. Players will assume different roles in the game, using cards, maps, and festival-themed objects to gain a deeper understanding of the history and customs of each festival. Educational Value: This board game is not only entertaining but also helps players learn about traditional Chinese culture in a relaxed setting, enhancing cultural identity. It is suitable for family gatherings, friends' meetups, and educational settings, particularly for players interested in Chinese culture.

Modeling PM10 Emissions in Quarry and Mining Operations: Insights from AERMOD Applications in Malaysia - Khan, Md Munir Hayet; Kurniawan, Tonni Agustiono; Chandra, Indra; Lei, Thomas (Atmosphere, 2025)
PM10 emissions have been a significant concern in rock crushing and quarry operations (study site #1) and iron ore mining projects (study site #2) in certain regions of Malaysia, posing fears to the health and well-being of nearby communities with severe air pollution. To address this issue, it is crucial to develop effective mitigation strategies to reduce dust particle emissions like PM10 in the ambient air. The AERMOD model was applied to predict PM10 emissions during quarry operations and iron ore mining projects, both with and without control measures. The results indicated that PM10 emissions were reduced when control measures were implemented. The modeling result shows the mean PM10 concentration with and without control measures in study site #1 is 74.85 µg/m3 and 20,557.69 µg/m3, respectively. In comparison, the average PM10 concentration with and without control measures in study site #2 is 53.95 µg/m3 and 135.69 µg/m3. Therefore, the control measure has successfully reduced the PM10 concentrations by 99.90% and 60.24% in study sites #1 and #2, respectively, and ensures the air quality complies with the Malaysian Ambient Air Quality Guidelines (MAAQG) 24 h threshold limits at 100 µg/m3. In addition, the AERMOD modeling results showed that mitigation measures performed better in rock crushing and quarry operations than in iron ore mining projects in this case study.

NiCo-layered double hydroxide coating on nitrogen/oxygen co-doped carbon nanocage composite for high-performance supercapacitor electrode - Li, Changgang; Tan, Xiang; Hu, Weijie; Tan, Xiaoen; Xie, Wenyu; Liu, Zhisen (Ionics, 2025)
Nickel–cobalt-layered double hydroxide (NiCo-LDH) has received considerable attention in the field of supercapacitor; however, the low conductivity and structural instability limit its practical applications. In this paper, a facile strategy for the fabrication of NiCo-layered double hydroxide (NiCo-LDH) coating on nitrogen/oxygen co-doped carbon nanocages (NOCN) was proposed in this paper. This multicomponent nanocomposite, NiCo-LDH@NOCN, has a high specific capacitance of 1842 F g−1 at 1 A g−1, a remarkable rate capability of 68.1% increasing the current density to 30 A g−1, and excellent cycling stability of 72.1% after 1000 cycles. Furthermore, an asymmetric supercapacitor (ASC) composed of NiCo-LDH@NOCN as a positive electrode and NOCN as a negative electrode was fabricated. The ASC shows a superior energy density of 31.6 Wh kg−1 at a power density of 700 W kg−1, which suggests the great practical application potential of supercapacitor.

Vehicle to Grid: Technology, Charging Station, Power Transmission, Communication Standards, Techno-Economic Analysis, Challenges, and Recommendations - Biswas, Parag; Rashid, Abdur; Habib, A. K. M. Ahasan; Mahmud, Md; Motakabber, S. M. A.; Hossain, Sagar; Rokonuzzaman, Md; Molla, Altaf Hossain; Harun, Zambri; Khan, Md Munir Hayet; Cheng, Wan-Hee; Lei, Thomas (World Electric Vehicle Journal, 2025)
Electric vehicles (EVs) must be used as the primary mode of transportation as part of the gradual transition to more environmentally friendly clean energy technology and cleaner power sources. Vehicle-to-grid (V2G) technology has the potential to improve electricity demand, control load variability, and improve the sustainability of smart grids. The operation and principles of V2G and its varieties, the present classifications and types of EVs sold on the market, applicable policies for V2G and business strategy, implementation challenges, and current problem-solving techniques have not been thoroughly examined. This paper exposes the research gap in the V2G area and more accurately portrays the present difficulties and future potential in V2G deployment globally. The investigation starts by discussing the advantages of the V2G system and the necessary regulations and commercial representations implemented in the last decade, followed by a description of the V2G technology, charging communication standards, issues related to V2G and EV batteries, and potential solutions. A few major issues were brought to light by this investigation, including the lack of a transparent business model for V2G, the absence of stakeholder involvement and government subsidies, the excessive strain that V2G places on EV batteries, the lack of adequate bidirectional charging and standards, the introduction of harmonic voltage and current into the grid, and the potential for unethical and unscheduled V2G practices. The results of recent studies and publications from international organizations were altered to offer potential answers to these research constraints and, in some cases, to highlight the need for further investigation. V2G holds enormous potential, but the plan first needs a lot of financing, teamwork, and technological development.

Understanding virtual influencers as brand endorsers: A conceptual framework for evaluating the traits of virtual influencers and an agenda for future research - Silva, Susana C.; Fernandes, Beatriz Pineda; Dias, Joana Carmo (Journal of Digital & Social Media Marketing, 2025)
Over the last few years, brands have increasingly looked to influencer marketing to promote their products. More recently, a new approach has emerged, leveraging artificial intelligence to create virtual influencers. Despite the growing importance of virtual brand ambassadors, academic research on virtual influencers remains fragmented, with limited discussion regarding the ideal characteristics of such agents. This paper addresses this gap in the literature and identifies the conditions necessary for virtual influencers to deliver positive outcomes. Based on existing literature, we identify eight essential attributes that significantly influence the effectiveness of virtual influencers. We also propose an agenda for future research and present a conceptual model to elucidate virtual influencer dynamics. This research enhances our understanding of virtual influencers’ role and impact in contemporary brand promotion, providing valuable insights for scholars and practitioners.

PERCEPTIONS OF CO-TEACHING AMONG PRIMARY AND SECONDARY SCHOOL TEACHERS: A CASE STUDY OF AN INCLUSIVE SCHOOL IN MACAU - Marinho, Gomes Vasconcelos Pinto Ana Teresa (2025)
The study aimed to analyze teachers' perceptions of co-teaching within an inclusive educational environment, focusing on the challenges they face, the tools and resources available, and how these factors contribute to promoting inclusion. Conducted with 16 primary and secondary school teachers from an inclusive school in Macau, the research utilized in-depth semi- structured interviews to gather qualitative data on their experiences and perceptions. Overall, the findings highlight co-teaching as a powerful strategy in educational settings, particularly for enhancing students’ learning outcomes. Teachers reported positive views on co-teaching, recognizing its potential to promote collaboration and support diverse learners effectively. Nevertheless, cultural factors significantly influenced teachers’ attitudes toward inclusion. The study revealed that teachers varied cultural and professional backgrounds lead to different perspectives on inclusive practices. This complexity highlights the need for culturally responsive approaches in teacher training and professional development. Despite the positive perceptions of co-teaching, teachers encountered several challenges, namely inconsistent school practices, lack of institutional support from school administration and leadership and inadequate training opportunities. This study suggests that addressing these challenges is crucial for the successful implementation of co-teaching approaches, namely policy adjustments by stakeholders to support co-teaching initiatives, effective allocation of resources for teachers, professional development for school leaders to enhance their ability to foster a collaborative environment, and ongoing training focused on co-teaching methodologies for teachers.

Criminal Jurisdiction of Cross-Border Cybercrimes between Macao and China - Ieong, Weng Mui (2025)
With the rapid development of Internet technology and the acceleration of globalization, cross-border cybercrime has become a global challenge, and its complexity and severity are increasingly prominent. Cyberspace is unbounded, anonymous and real-time, which provides unprecedented convenience for criminals, enabling them to easily cross-national borders and commit a series of criminal acts that seriously endanger national security, social stability and citizens' rights and interests, including online fraud, online gambling, online money laundering and infringement of intellectual property rights. These crimes not only destroy the order of cyberspace, but also pose new challenges to the legal system and jurisdiction of the real world. As two closely linked economies, Macao and China enjoy the convenience brought by the Internet, but they are also deeply troubled by cross-border cybercrimes. Although the two places belong to the same sovereign country, there are significant differences in legal systems, judicial systems and law enforcement practice, which may lead to conflicts and differences in the jurisdiction, investigation, prosecution and trial of cases. These legal conflicts not only affect the fairness of cases, but also hinder the effective cooperation between Macao and China in combating cross-border cybercrimes, posing a serious threat to maintain social stability and protecting citizens' rights and interests in the two places. Therefore, it is not only of great theoretical significance, but also of far-reaching practical significance to study the criminal jurisdiction over cross-border cybercrimes between Macao and China. From a theoretical point of view, the criminal jurisdiction of cross-border cybercrime involves many disciplines such as constitutional law, criminal law, criminal procedure law, and also the application of the Basic Law of Macao, which is a complex research topic. With the continuous innovation of Internet technology, the applicability of the traditional criminal jurisdiction principle in cross-border cybercrimes is seriously challenged. How to re-examine and define the criminal jurisdiction of cross-border cybercrimes in the new era and how to coordinate the jurisdiction conflicts between different jurisdictions have become urgent problems in current legal research. From a practical point of view, cross-border cybercrime has seriously endangered the social stability and economic development of Macao and China. Criminals use the Internet to engage in cross-border gambling, cross-border fraud, spread network viruses and other criminal activities, which not only bring huge economic losses and psychological trauma to the victims, but also seriously undermine the social atmosphere and market order. Therefore, it is of great significance to strengthen the crackdown on cross-border cybercrimes and improve the criminal jurisdiction system of cross-border cybercrimes for maintaining the stability of the society and promoting healthy economic development in both places.

Study on User Acceptance of Resident Behavior for E-Government Services in Macao: Macao One Account Study - Kuok, Chi Hou (2025)
This dissertation investigates the key factors influencing citizens to adopt e-government services in Macao, focusing on the Macao One Account platform. Using the Unified Theory of Acceptance and Use of Technology (UTAUT) framework, the study examines factors such as Performance Expectancy, Effort Expectancy, Social Influence, and Facilitating Conditions, with additional factors including Trust and Perceived Risk. This study is essential to provide a guideline for adopting e-government services effectively, helping policymakers and government entities optimize digital platforms for improved service delivery and user engagement. The research employed a quantitative methodology. The survey data was collected through an online survey in Google Forms distributed to Macao residents who use the Macao One Account platform. The responses of the 126 respondents were analyzed using descriptive statistical methods to identify trends and relationships between the key constructs. The findings reflect that performance expectations, effort expectations, trust, and facilitating conditions are the most influential drivers, with social influence playing a more moderate role. Perceived risk is low, indicating minimal concerns about security or privacy. Usability is an important driver, as most respondents find the platform easy to learn and use. Additionally, the users’ attitudes to the e-government platform could be affected by their trust in the government; reducing risk and increasing confidence can improve the platform's reliability to users. This study shows the need to improve the e-government platform by focusing on users. It includes making it easier to use, building trust with strong data protection, and making it accessible to all citizens. These results give ideas for adopting e-government in Macao and offer simple steps for policymakers to create more inclusive digital services.

EXPLORING THE DIFFICULTIES AND CHALLENGES FACED BY REGULAR PRIMARY SCHOOL TEACHERS IN MACAO WHEN DEALING WITH INCLUSIVE STUDENTS IN THE CLASSROOM - Lam, Mei In (2025)
This study aims to explore the difficulties and challenges faced by regular primary school teachers in Macao when dealing with inclusive students in the classroom. As the concept of inclusive education deepens, the number of inclusive students in Macao has been increasing, but the growth of schools participating in inclusive education has been slow, posing more challenges for regular primary school teachers. This research adopts a mixed-method approach, combining classroom observations and in-depth interviews to comprehensively understand the issues teachers face. The study conducted structured observations of 15 lessons, covering 5 grade levels and 5 subjects, and carried out in-depth interviews with 7 teachers. The findings reveal: (1) Inclusive students generally experience difficulties in classroom participation, task completion, and independent learning; (2) Teachers generally lack sufficient professional knowledge and skills to effectively address the needs of inclusive students; (3) Schools lack resources and support, including adaptive curriculum arrangements and assessment methods for inclusive students; (4) There are contradictions between current educational policies and practical needs, such as the no-retention policy for grades 1-4, which may lead to missing the best intervention timing for inclusive students. Based on the research results, this paper proposes recommendations including strengthening teacher professional development, optimizing school resource allocation, improving educational policies, reinforcing early identification and intervention mechanisms, and promoting home-school cooperation. These findings and suggestions provide important references for policy-making and practical improvements in inclusive education in Macao. 本研究旨在探討澳門普通小學教師在課堂應對融合學生時所面臨的困難及挑戰。隨著融合教育理念的普及，澳門融合學生數量不斷增加，但參與融合教育的學校數量增長緩慢，使得普通小學教師面臨更多挑戰。本研究採用混合研究方法，結合課堂觀察和深度訪談，以全面了解教師面臨的問題。 研究對15節課進行了結構化觀察，涵蓋5個年級和5個學科，並對7位教師進行了深度訪談。研究發現：（一、）融合學生在課堂參與、任務完成和自主學習等方面普遍存在困難；（二、）教師普遍缺乏足夠的專業知識和技能來有效應對融合學生；（三、）學校資源和支援不足，缺乏針對融合學生的適應性課程安排和評核方式；（四、）現行教育政策與實際需求之間存在矛盾，如一至四年級不留級制度可能導致錯過融合學生最佳干預時機。 基於研究結果，本文提出了加強教師專業發展、優化學校資源配置、完善教育政策、強化早期識別和干預機制，以及促進家校合作等建議。這些發現和建議為澳門融合教育的政策制定和實踐改進提供了重要參考。

National Competitive Advantage and Ikea's Entry into the China Market - Riquito, Nikola Mullerova (2025)
Ikea’s entry into the China market and how its become successful in the foreign country

TEACHER’S PERCEPTIONS ON DIGITAL TECHNOLOGY IN RELATION TO THE IMPACT OF THE COVID-19 PANDEMIC SITUATION IN MACAU EDUCATION - Chow, Ian U. (2025)
This dissertation investigates the impact of the COVID-19 pandemic on teachers' perceptions of digital technology in education, particularly in the context of Macau. As traditional classrooms transitioned to online and blended learning environments in March 2020, the necessity for teachers to adapt and utilize technology became paramount. This study explores how future educators' experiences with e-learning during this crisis have shaped their views on the benefits and challenges of various instructional methods, including online, face-to-face, and blended learning. Utilizing a quantitative research methodology, data were collected from a sample of 30 primary teachers through structured surveys. Findings reveal a significant shift in attitudes towards digital tools, with many educators reporting increased confidence in their digital literacy and recognizing the importance of technology in modern education. The research further elucidates the factors influencing teachers' preparedness for digital instruction and the effectiveness of their internship experiences during the pandemic. The implications of this study underscore the critical role of teacher training programs in enhancing digital literacy and pedagogical skills, ensuring that future educators are well-equipped to navigate the complexities of contemporary educational environments. This dissertation contributes to the growing body of literature on technology integration in education and emphasizes the need for ongoing professional development to support teachers in leveraging digital tools effectively.

Bioprospecting Bioactive Peptides in Halobatrachus didactylus Body Mucus: From In Silico Insights to Essential In Vitro Validation - Cunha, Marta Fernandez; Coscueta, Ezequiel R.; Brassesco, María Emilia; Almada, Frederico; Gonçalves, David; Pintado, Maria Manuela (Marine Drugs, 2025)
Fish body mucus plays a protective role, especially in Halobatrachus didactylus, which inhabits intertidal zones vulnerable to anthropogenic contaminants. In silico predicted bioactive peptides were identified in its body mucus, namely, EDNSELGQETPTLR (HdKTLR), DPPNPKNL (HdKNL), PAPPPPPP (HdPPP), VYPFPGPLPN (HdVLPN), and PFPGPLPN (HdLPN). These peptides were studied in vitro for bioactivities and aggregation behavior under different ionic strengths and pH values. Size exclusion chromatography revealed significant peptide aggregation at 344 mM and 700 mM ionic strengths at pH 7.0, decreasing at pH 3.0 and pH 5.0. Although none exhibited antimicrobial properties, they inhibited Pseudomonas aeruginosa biofilm formation. Notably, HdVLPN demonstrated potential antioxidant activity (ORAC: 1.560 mu mol TE/mu mol of peptide; ABTS: 1.755 mu mol TE/mu mol of peptide) as well as HdLPN (ORAC: 0.195 mu mol TE/mu mol of peptide; ABTS: 0.128 mu mol TE/mu mol of peptide). Antioxidant activity decreased at pH 5.0 and pH 3.0. Interactions between the peptides and mucus synergistically enhanced antioxidant effects. HdVLPN and HdLPN were non-toxic to Caco-2 and HaCaT cells at 100 mu g of peptide/mL. HdPPP showed potential antihypertensive and antidiabetic effects, with IC50 values of 557 mu g of peptide/mL for ACE inhibition and 1700 mu g of peptide/mL for alpha-glucosidase inhibition. This study highlights the importance of validating peptide bioactivities in vitro, considering their native environment (mucus), and bioprospecting novel bioactive molecules while promoting species conservation.

EXPLORING EXPERIENCES AND PERCEPTIONS OF THE HELPING RELATIONSHIPS IN MACAU - Choi Hoi, Ana (2025)
This study aims to become a conduit of a missing conversation wherein our front line help-givers can express their experiences. Through a series of semi-structured questions, and theoretical analyses, the themes regarding the Experience and Perception of Helping Relationships in Macau. Findings include difficulties and challenges that the helping profession in Macau encounters in different settings related to role ambiguity and public understanding of the profession. Stigma around a person considered to be a “problem” as well as stigma related to nomenclature of mental illnesses. Factors that enable and facilitate a helping relationship were identified. Trust, sincerity, listening and positive regard were mentioned. Due to Macau’s multi-cultural background, an enabling agent to facilitate a helping relationship was identified – language. As a qualitative enquiry medium for reflection and discovery, this study hopes to bring forward the unique experiences of eleven helping professionals with a spectrum of background to provide richness and newness to the current body of literature.

Exploring the Dual Edges of Macao's Economic Diversification A Study of the Strengths and Limitations of the Policy - Lei, Iat Cheong (2025)
This study aims to conduct a comprehensive analysis of the dual effects of Macao's economic diversification policy, with the intention of exploring its role in fostering economic sustainability. By thoroughly examining Macao's economy, which has traditionally been heavily reliant on the gaming and tourism industries, the study uncovers the implementation effects of the economic diversification policy, the challenges it encounters, and its potential influence on the economy's future trajectory. The research utilizes a mixed-methodology approach, integrating extensive quantitative data analysis with qualitative interviews to ensure the comprehensiveness and systematic nature of the findings. The study's outcomes underscore the beneficial effects of Macao's economic diversification policy in stimulating the growth of new industries, bolstering economic resilience, and attracting foreign investment. However, the policy also faces challenges such as skill shortages, uneven resource distribution, and the impact on traditional economic pillar industries. The research indicates that despite certain progress, Macao's economic diversification process still needs to overcome various internal and external obstacles. In response to the research findings, this study proposes a series of targeted recommendations, including strengthening the connection between education and industry, optimizing resource allocation strategies, stimulating innovation and entrepreneurship, and promoting the collaborative development of traditional and emerging industries. These suggestions aim to assist the Macao government in effectively addressing current challenges and laying a solid foundation for the long-term development of Macao's economy.

Study of the Regulatory Framework of Aviation Reform in the Macau Special Administrative Region: Analyzing the Balance between Protection and Liberalization - Melo, Loi da Silva e; Man, I. (2025)
This dissertation studies the regulatory framework of aviation reform in the Macau Special Administrative Region, focus on the balance between protecting local businesses and promoting market liberalization. The study explores how Macau, as a highly autonomous local administrative region in China with a relatively small economy, can effectively reform its aviation industry while safeguarding local interests in the face of open market competition. The importance of this study lies in its analysis of Macau's aviation sector reforms. As Macau seeks to diversify its economy and strengthen its position as a member of the Greater Bay Area initiative, the aviation industry presents both opportunities and challenges. This research contributes to the broader discussion of how small jurisdictions with special political status can participate in regional economic integration while maintaining their distinct advantages and protecting local interests. The research uses Doctrinal Legal Research and Comparative Legal Research methodologies, utilizing documentary analysis and comparative study methods. This research examines the legal framework of the aviation industry in Macau and the challenges it is currently facing. A comprehensive review of international aviation laws, bilateral air service agreements, and domestic regulations provides the foundation for analyze. The study also conducts a comparative analyze with Hong Kong's aviation framework, offering alternative regulatory approaches for a similar Special Administrative Region of China. Several interesting findings emerged from this research. First, the study identified a fundamental tension between Macau's stated open skies policy and its practical implementation, particularly in limitations of its current concession-based system and the underutilization of international traffic rights. Second, the analysis highlights how the current concession-based system has created a monopolistic market structure that hinders competition and innovation, exacerbated by outdated legislation. Third, the comparative analysis with Hong Kong highlights the importance of a clear legal framework and rules in balancing market liberalization with local industry protection, areas where Macau's current regulations show deficiencies. The concluding thought based on these findings is that Macau's aviation industry reform requires a careful approach that gradually introduces competitive elements while maintaining protections for local enterprises. The study suggests that successful reform will depend on establishing a comprehensive legal framework, implementing a flexible multi-tiered licensing system, enhancing regulatory oversight, and developing mechanisms for regional integration. These reforms must be tailored to Macau's unique circumstances, considering its small market size, political status, and strategic position within the Greater Bay Area.

Man in a Hurry: Murray MacLehose and Colonial Autonomy in Hong Kong Ray Yep. Hong Kong: Hong Kong University Press, 2024. xi + 202 pp. HK$295.00 (hbk). ISBN 9898888842926 - Roberts, Priscilla (The China Quarterly, 2025)

Exploring freshwater soundscapes of tropical marshland habitats in Southeast Asia: insights into auditory sensory adaptation of wild Siamese fighting fish Betta splendens - Ramos, Andreia; Gonçalves, David; Vasconcelos, Raquel (PeerJ, 2025)
While soundscapes shape the structure and function of auditory systems over evolutionary timescales, there is limited information regarding the adaptation of wild fish populations to their natural acoustic environments. This is particularly relevant for freshwater ecosystems, which are extremely diverse and face escalating pressures from human activities and associated noise pollution. The Siamese fighting fish Betta splendens is one of the most important cultured species in the global ornamental fish market and is increasingly recognized as a model organism for genetics and behavioural studies. This air-breathing species (Anabantoidei), characterized by the presence of a suprabranchial labyrinth organ that enhances auditory sensitivity, is native to Southeast Asia and inhabits low flow freshwater ecosystems that are increasingly threatened due to habitat destruction and pollution. We characterized the underwater soundscape, along with various ecological parameters, across five marshland habitats of B. splendens, from lentic waterbodies to small canals near a lake in Chiang Rai province (Thailand). All habitats exhibited common traits of low dissolved oxygen and dense herbaceous vegetation. Soundscapes were relatively quiet with Sound Pressure Level (SPL) around 102-105 dB re 1 mu Pa and most spectral energy below 1,000 Hz. Sound recordings captured diverse biological sounds, including potential fish vocalizations, but primarily insect sounds. Hearing thresholds were determined using auditory evoked potential (AEP) recordings, revealing best hearing range within 100-400 Hz. Males exhibited lower hearing thresholds than females at 400 and 600 Hz. This low-frequency tuning highlights the potential susceptibility of B. splendens to anthropogenic noise activities. This study provides first characterization of the auditory sensitivity and natural soundscape of B. splendens, establishing an important ground for future hearing research in this species. The information provided on the auditory sensory adaptation of B. splendens emphasizes the importance of preserving quiet soundscapes from lentic freshwater ecosystems.

Adaptive Block Sparse Backtracking-Based Channel Estimation for Massive MIMO-OTFS Systems - Wang, Han; Chen, Qiulin; Wang, Xianpeng; Du, George; Li, Xingwang; Nallanathan, Arumugam (IEEE Internet of Things Journal, 2025)
—Orthogonal time frequency space (OTFS) modulation, combined with massive multiple-input–multiple-output (MIMO) technology, offers robust performance in high-mobility environments and high-user densities by capturing the full diversity of the wireless channel and effectively utilizing spatial multiplexing. This article introduces an adaptive block sparse backtracking (ABSB) algorithm designed to enhance channel estimation in OTFS with massive MIMO (massive MIMO-OTFS) systems. The proposed ABSB algorithm features dynamic block size adjustment based on the residual signal, improving its adaptability to the varying sparsity structure of the channel. Additionally, the algorithm extends the selection range of related block atoms to increase redundancy, reducing the risk of underfitting. Comprehensive simulation results demonstrate that the ABSB algorithm significantly outperforms traditional pilot-based methods in terms of channel estimation accuracy. It also surpasses the block orthogonal matching pursuit (BOMP) method as well as other classical compressed sensing methods. Specifically, the ABSB algorithm achieves up to a 20% reduction in estimation error compared to some of these traditional methods. The enhanced adaptability and robustness of the ABSB algorithm make it a promising solution for channel estimation in massive MIMO-OTFS systems, paving the way for more reliable and efficient next-generation wireless communications.

The Effectiveness of Dance Movement Therapy on Emotion Identification of Facial Expressions in Adults with Autism Spectrum Disorders: An EEG study - Chui, Ngou Cheng (2025)
Autism Spectrum Disorder (ASD) is receiving growing attention as the number of diagnoses continues to rise. However, there is a lack of resources focused on investigating interventions that could improve the quality of life for individuals with ASD. People with ASD often encounter difficulties in social interactions, and their challenges in recognizing emotions further hinder their ability to understand social cues and build relationships. This emotional recognition deficit is thought to be influenced by observed brain abnormalities in the frontal lobe for people with ASD. Given these significant factors, it is crucial to explore potential interventions. The present study utilized Dance Movement Therapy (DMT) as an intervention for individuals with ASD and assessed their emotional recognition abilities, complemented by EEG recordings to explore the efficacy of DMT. A total of 12 one-hour DMT sessions were conducted with the experimental group (n=6), while the control group (n=5) received no intervention. Participants were presented with the Revised Version of the Averaged Karolinska Directed Emotional Faces (AKDEF), which included 36 images (excluding neutral images and full left and right profiles) at four intervals: pre-therapy (T1), after the 4th session (T2), after the 8th session (T3), and post-therapy (T4), while task for control group was present in two-week intervals. EEG band power for alpha and beta frequencies in the frontal lobe was recorded using the EMOTIV EPOC X at the AF4, F4, F3, and AF3 sites. Results indicated that the experimental group demonstrated a significant improvement in accuracy on emotional recognition tasks compared to the control group, although no significant differences were found between trials. In contrast, EEG signal analysis revealed significant differences between trials in both groups. A comparison of the correlation between emotional recognition tasks and EEG band power highlighted intriguing contrasts, suggesting potential insights into the learning effects. The experimental group exhibited peak performance at T2, followed by a decline at T3 and T4; while the control group showed a decrease at T2, an increase at T3, and another decrease at T4. It is proposed that the learning observed in the experimental group at T2, following four sessions of DMT, enhanced their ability to perform the emotional recognition tasks, resulting a subsequent decrease in alpha and beta power at T3 and T4, suggesting that less effort was needed during image perception and. In contrast, the control group struggled to learn, which may indicate that learning was not occurred for the controls. This relationship has not been explicitly explored in current research, and further investigations are recommended. Nonetheless, the findings indicate that DMT is effective to some extent in enhancing emotional recognition skills among individuals with ASD, suggesting its potential utility for social services to consider in their offerings. Future studies would benefit from incorporating a larger sample size or employing clinical EEG recording devices to further refine the results.

Consumer Responses to Warwashing Amidst the Russia-Ukraine Conflict: A Comparative Study of Portuguese and Danish Perspectives - Silva, Susana C. (2025)

Heavy metal accumulation in paddy plants and health risks: Insights from southern peninsular Malaysia and global research trends - Teoh, Yan Ji; Cheng, Wan Hee; Wider, Walton; Krishnan, Kumar; Yap, Chee Kong; Chen, Qijin; Jiang, Leilei; Lei, Thomas; Tanee, Tawatchai; Sudmoon, Runglawan; Lee, Shiou Yih (Asian Journal of Agriculture and Biology, 2025)
This current study assessed the toxicity of selected heavy metals in paddy and sediments of non-major production sites in Southern Peninsular Malaysia, complemented by bibliometric analysis of research trends and health implications of rice contamination. Paddy (grains, stems, roots) and soil samples were collected from seven selected sites in the Southern parts of Peninsular Malaysia and analyzed for their heavy metals content. The health risk assessments were conducted based on estimated daily intake, and the Web of Science database was used for bibliometric analysis. The results indicated elevated levels of manganese, Mn (0.4 ± 0.07), especially in the roots, compared to other heavy metals. Generally, the heavy metal levels in paddy grains were below FAO/WHO’s tolerable daily intake levels, indicating minimal non-carcinogenic risks to both adults and children. The bibliometric analysis indicated a significant increase in related publications, reflecting growing academic interest. This study highlights the potential of non-major sites to produce rice with lower contamination levels, provides insights into research trends, and identifies future investigation areas, especially for major production sites and post-COVID-19 periods. Therefore, this study offers a robust scientific context, identifies research gaps, benchmarks findings, and guides future research directions, ensuring an in-depth perception on heavy metal contamination and its health risks. © This is an Open Access article distributed under the terms of the Creative Commons Attribution 4.0 License. (https://creativecommons.org/licenses/by/4.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.

FROM ARTISANAL TRADITIONS TO THE DIGITAL EXPERIENCE: REIMAGINING TEXTILES TRADITIONS THROUGH ARTISTIC CREATION AND IMMERSIVE TECHNOLOGIES - Pereira, S. (Pereira; Fernandes-Marcos, Adérito (2025)
This article explores the intersection between traditional textile craftsmanship and digital innovation through the Hands series, a project that integrates tangible and virtual artefacts. Grounded in post-digital aesthetics, Hands examines the rematerialisation of textile heritage by combining traditional techniques with immersive technologies such as augmented reality and digital modelling. The project questions the physical and digital dichotomy, proposing new ways of experiencing textile art beyond its material constraints. By incorporating multisensory elements and interactivity, Hands redefines the engagement between spectators and artefacts, expanding the narrative potential of textile traditions in contemporary artistic practice. This study critically analyses how post-digital textile aesthetics can serve as a bridge between preservation and innovation, fostering an enriched sensory experience. The discussion highlights the challenges and opportunities of integrating emerging technologies into artistic processes, reinforcing the relevance of sensory engagement in digital art contexts.

Study on the Implementation of Low-Carbon Policies in Macao - Wong, Mio San (2025)
As a special administrative region of China, Macau, despite its small size and limited resources, has been actively promoting low-carbon development to address the global climate change challenge. In recent years, Macao has provided important support for achieving the goal of carbon peaking and carbon neutrality by formulating a series of policies, such as energy management, promotion of green buildings and optimization of waste treatment. However, despite the clarity of the policy framework, its actual implementation and effectiveness still need to be systematically reviewed. This study uses a combination of qualitative and quantitative research methods, interviews and questionnaires to gain an in-depth understanding of the social acceptance and public participation of policies, and quantitative data to analyze the implementation effects of policies, with a view to revealing the advantages and disadvantages of low-carbon policies in Macao. The research results will systematically evaluate the effectiveness of low-carbon policies in Macao from multiple levels. On the one hand, quantitative data will provide a clear empirical basis for the progress of low-carbon policies; On the other hand, qualitative research will reveal key social and technological barriers to policy implementation, helping to understand the impact of public attitudes and behaviour on policy effectiveness. These results can not only provide reference for Macao's future low-carbon policy adjustment, but also provide experience for other similar cities to cope with similar challenges in low-carbon development. The importance of this study lies in its dual contribution to academia and practice. At the academic level, this study has enriched the theoretical research on low-carbon city development, especially the special challenges of carbon emission reduction in resource-limited cities. At the practical level, the results of this study can directly provide policy makers with specific suggestions for improving low-carbon policies, such as resource allocation, technology introduction and public awareness. Through these analyses, the study hopes to provide a practical roadmap for Macao to achieve its goal of carbon neutrality, as well as a valuable reference for the low-carbon development of similar cities around the world.

探討澳門普小教師在課堂應對融合學生時所面對的困難及挑戰 - Lam, Mei In (2025)
This study aims to explore the difficulties and challenges faced by regular primary school teachers in Macao when dealing with inclusive students in the classroom. As the concept of inclusive education deepens, the number of inclusive students in Macao has been increasing, but the growth of schools participating in inclusive education has been slow, posing more challenges for regular primary school teachers. This research adopts a mixed-method approach, combining classroom observations and in-depth interviews to comprehensively understand the issues teachers face. The study conducted structured observations of 15 lessons, covering 5 grade levels and 5 subjects, and carried out in-depth interviews with 7 teachers. The findings reveal: (1) Inclusive students generally experience difficulties in classroom participation, task completion, and independent learning; (2) Teachers generally lack sufficient professional knowledge and skills to effectively address the needs of inclusive students; (3) Schools lack resources and support, including adaptive curriculum arrangements and assessment methods for inclusive students; (4) There are contradictions between current educational policies and practical needs, such as the no-retention policy for grades 1-4, which may lead to missing the best intervention timing for inclusive students. Based on the research results, this paper proposes recommendations including strengthening teacher professional development, optimizing school resource allocation, improving educational policies, reinforcing early identification and intervention mechanisms, and promoting home-school cooperation. These findings and suggestions provide important references for policy-making and practical improvements in inclusive education in Macao. 本研究旨在探討澳門普通小學教師在課堂應對融合學生時所面臨的困難及挑戰。隨著融合教育理念的普及，澳門融合學生數量不斷增加，但參與融合教育的學校數量增長緩慢，使得普通小學教師面臨更多挑戰。本研究採用混合研究方法，結合課堂觀察和深度訪談，以全面了解教師面臨的問題。 研究對15節課進行了結構化觀察，涵蓋5個年級和5個學科，並對7位教師進行了深度訪談。研究發現：（一、）融合學生在課堂參與、任務完成和自主學習等方面普遍存在困難；（二、）教師普遍缺乏足夠的專業知識和技能來有效應對融合學生；（三、）學校資源和支援不足，缺乏針對融合學生的適應性課程安排和評核方式；（四、）現行教育政策與實際需求之間存在矛盾，如一至四年級不留級制度可能導致錯過融合學生最佳干預時機。 基於研究結果，本文提出了加強教師專業發展、優化學校資源配置、完善教育政策、強化早期識別和干預機制，以及促進家校合作等建議。這些發現和建議為澳門融合教育的政策制定和實踐改進提供了重要參考。 關鍵詞：融合教育，普通小學教師，融合學生，澳門

Interdisciplinary Teaching Design and Practice Research Combining Mathematics and Programming: A Case Study of Fourth Grade Mathematics Topics - Lao, Si Man (2025)
本研究旨在探討跨學科教學方法在數學教育中的應用效果,特別聚焦於編 程與數學課程的整合。探討結合數學與編程的跨學科教學設計對小學四年級學 生的影響,旨在提升學生的數學和編程學習的成效。研究採用 5E 教學模式, 將 Scratch 3.0 編程活動融入數學課程,並進行實驗以評估其成效。研究對象為 澳門一所學校兩個四年級普通班級(A 班和 B 班)的學生,分為實驗組和對照 組。研究採用交叉設計,進行兩次實驗:實驗一以 A 班為實驗組、B 班為對照 組,進行《旋轉對稱圖形》單元的跨學科教學;實驗二則互換角色,以 B 班為 實驗組、A 班為對照組,進行《可以被 3 整除的數》單元的跨學科教學。研究 使用數學單元測驗卷、數學學習動機量表,以及學生的數學測驗成績和編程學 習動機量表作為評估工具。 研究結果顯示: 一、數學成績提升:實驗組學生的數學成績顯著高於對照組。 二、數學學習動機增強:實驗組學生在數學興趣和自我效能感方面均有顯 著提升。 三、編程學習動機提升:實驗組在編程社會價值、感知編程效用、編程興 趣和自我效能方面均有顯著的提升。 結論指出,實施編程活動融入數學科的跨學科教學,提升學生的數學成 績、數學和編程的學習動機。建議應推廣此類跨學科教學,並加強教師培訓及 教學資源開發,以提高學生的學習動機和成效。未來研究可擴大樣本範圍,探 討長期效果及多學科整合的影響。 This study investigates the impact of interdisciplinary teaching design integrating mathematics and programming on fourth-grade elementary school students, aiming to enhance their learning outcomes in both subjects. The research employs the 5E instructional model, incorporating Scratch 3.0 programming into the mathematics curriculum, and conducts experiments to evaluate its effectiveness. The study subjects are two regular fourth-grade classes (Class A and Class B) from a school in Macau, divided into experimental and control groups. A crossover design is used, conducting two experiments: in Experiment 1, Class A serves as the experimental group and Class B as the control group for the "Rotational Symmetry Figures" unit; in Experiment 2, the roles are reversed, with Class B as the experimental group and Class A as the control group for the "Numbers Divisible by 3" unit. The study uses mathematics learning motivation and programming learning motivation scales as assessment tools. Major research findings are as follows: 1. Improved mathematics performance: The experimental group's mathematics scores were significantly higher than the control group's. 2. Enhanced mathematics learning motivation: The experimental group showed significant improvements in mathematics interest and self-efficacy. 3. Increased programming learning motivation: The experimental group demonstrated significant improvements in programming social value, perceived programming utility, programming interest, and self-efficacy. The conclusion indicates that the 5E instructional model effectively promotes the integration of mathematics and programming, enhancing students' learning outcomes. It is recommended that educational institutions promote such interdisciplinary teaching and strengthen teacher training and teaching resource development to improve students' learning motivation and effectiveness. Future research could expand the sample size to explore long-term effects and the impact of multi-disciplinary integration.

The Impact of the Understanding of Reproductive Rights on Career Planning and Gender Equality Attitudes Among Macau Residents Aged 25-34 - Lou, Weng Si (2025)
本研究旨在探討澳門 25-34 歲年齡層個人對生育權的認知與理解,以及這 些觀點對其生涯規劃和性別平等態度的影響。澳門作為一個快速發展的特別行 政區,關於生殖權的討論仍然較為缺乏,這使得本研究特別重要,因為它有助 於填補這一領域的知識空白。本研究採用質性研究方法,通過有目的抽樣,對 20 名年齡在 25-34 歲之間的澳門居民進行半結構訪談,並以詮釋學方法分析數 據。 研究發現如下: 1. 男性參與者更關注個人角色和責任,並反思社會期望和文化價值觀。 2. 女性參與者則更關注社會期望與個人自主權的衝突,並關心性別平等和 個人權利。 這些差異突顯了性別角色和社會責任在男性和女性身上的不同詮釋,並反映 了社會、文化和個人因素對於性別觀點的塑造作用。研究結果對於推動澳門的 性別平等政策和生殖權利保障具有重要意義,並為後續研究提供了實證基礎。 This study aims to explore the awareness and understanding of reproductive rights among individuals aged 25-34 in Macau, as well as the impact of these views on their career planning and attitudes towards gender equality. As a rapidly developing Special Administrative Region, Macau still lacks extensive discussion on reproductive rights, making this research particularly important as it helps to fill the knowledge gap in this field. The study employs qualitative research methods, using purposive sampling to conduct semi-structured interviews with 20 Macau residents aged 25-34, and analyzes the data using hermeneutic methods. The findings of the study are as follows: 1. Male participants are more concerned with individual roles and responsibilities, and they reflect on societal expectations and cultural values. 2. Female participants are more focused on the conflict between societal expectations and personal autonomy, and they are concerned with gender equality and individual rights. These differences highlight the varying interpretations of gender roles and social responsibilities between men and women and reflect the influence of social, cultural, and personal factors on gender perspectives. The research results have significant implications for promoting gender equality policies and reproductive rights protection in Macau, providing an empirical basis for subsequent studies.

REGIONAL TRADE AGREEMENTS: TOOL TO PROMOTE CLIMATE – SMART AND SUSTAINABLE TRADE - Toshevska-Trpchevska, Katerina; Lei, Weng Chi (Florence); Kocev, Ljuben; Tonovska, Jasna (InterEULawEast: Journal for the International and European Law, Economics and Market Integrations, 2024)

Personal Story and Public Identity as Axis of Value Response: Lessons on Literacy and Morality from John Henry Newman (1801-1890) and Ma Xiangbo (1840-1939) - Law, Cyril (2025)
In the hype of multi-/inter-disciplinarity, is the voi-ce or voices of theistic religions and the attendant philosophical moral awareness (etymologically bet-ter rendered as conscientização in Portuguese) still meant to be heard? Can classical tales of saints and sinners remain part of the canon of public literacy? How existential is the threat of “organised religions” or otherwise established ecclesiastical structures posed to society when they are accused of attempting to fight proxy crusades against humanitarian enlightenment under the guise of religious literature? Are tenets pro-pounded by scholars like Gavin D’Costa in Theology and the Public Square (2005) to be politely bracketed when discussing perennial values? Values that respon-sible media strive to propagate, particularly the value of human dignity eulogised by the life exemplars of great figures in times of existential crises of whatever magnitude. With these questions in mind, this article will hearken back to the stories of two “grandees” in the Roman Catholic tradition who left their marks on the pages of the development of modern English and Chinese literacy. Newman’s Apologia pro vita sua(1865) is just but one of the tactical devises for his defense of creedal integrity, while Ma Xiangbo engaged in catholicising the Chinese national ethos through educational literacy for close to half a century. We shall phenomenologically draw inspirations from their parallel vision and experience on what lends power to the medium of words and deeds in shaping informed public conscience in regard to the core values of truth, good, and beauty.

Assessing critical thinking disposition through text analysis in traditional Chinese: An empirical study of tourism and gaming undergraduates in Macao - Lam, Carlos Siu; Liu, Yong; Zhang, Yinghong; Wu, Hao (Frontiers in Education, 2025)
Critical thinking disposition (CTD) is increasingly recognized as an important trait in education, reflecting the inclination and habits necessary for addressing complex challenges in today's world. This study assessed the CTD of students enrolled in a tourism and gaming management programme, focusing on two key dimensions: Analyticity and Open-Mindedness. This study was conducted at a university in Macao and involved 65 participants. The students were presented with an article relevant to their major, written in Traditional Chinese, and were asked to provide their opinions on each statement in the article. A rubric was designed to analyze their responses and assess their Analyticity and Open-Mindedness within the CTD framework. The results demonstrated high reliability (Cronbach's α = 0.91) and revealed an association between Analyticity and Open-Mindedness. Using Python programming, the study analyzed the frequency of parts of speech (POS) in students' responses, introducing a novel approach for evaluating CTD in Traditional Chinese. Regression modeling showed that parallel and adversative conjunctions significantly predicted Analyticity, while the frequency of conjunction use varied across Open-Mindedness classifications. These findings highlighted an innovative and objective method for assessing CTD through text analysis, offering promising applications for educational research in Traditional Chinese-speaking contexts.

MOND formulation emerging from general relativity - Arraut, Ivan (Modern Physics Letters A, 2025)
In this paper, we demonstrate that the effects of Dark-Matter, partially in the way proposed by the Modified Newtonian Dynamics (MOND), emerge naturally from the standard theory of General Relativity (without any modification) under a new proposed vacuum solution. There is a family of metric solutions able to reproduce the galaxy rotation curves and the relevant scales where the Dark-Matter effects are supposed to appear in a galaxy. This family of solutions deviate from the standard spherically symmetric solution. The proposed formulation, being relativistic by nature, opens the scenario where we can test the relativistic effects attributed to Dark-Matter and having relevance in cosmology. Among such effects, we have gravitational lensing, effects on the CMB scenario and effects on the formation of galaxies.

Unlocking Sustainable Talents 培育永續人才：如何共同建設更好的生態，以滿足日益增長的金齡人士 - Lei, Weng Chi (Florence) (2025)
本書由36 位不同界別的領袖、專家和學者，分享與人口老齡化相關的精闢觀察與洞見，探索創新永續的生活和經濟模式，包括相關的政策、黃金時代經濟的發展、中國安老服務的新視野、醫康養老新發展、智齡科技的應用、永續人才和社區發展等議題，為業界提供參考，亦為45 歲以上的黃金一代應對未來退休生活提供啟發。 「我們的生活越來越受創新技術的影響，我們的社會也更加重視綠色生活和可持續發展。科技和綠色生活方式必須融入智齡產品和服務中。」 —— 陳茂波 香港特別行政區財政司司長 「我們的共同目標是在老齡化世界中不讓任何人掉隊。」 —— 威廉•史密斯博士 聯合國紐約總部老年事務非政府組織委員會主席 「我們深信人口老化為全球帶來嶄新的機遇。中、老年人是唯一正在不斷增長的人力資源，也是創新產品和服務的龐大消費群體。」 —— 容蔡美碧 黃金時代基金會創會主席

The Solution to Hardy’s Paradox - Arraut, Ivan (Condensed Matter, 2025)
By using both the weak-value formulation as well as the standard probabilistic approach, we analyze Hardy’s experiment introducing a complex and dimensionless parameter (ϵ), which eliminates the assumption of complete annihilation when both the electron and the positron departing from a common origin cross the intersection point P. We then find that the paradox does not exist for all the possible values taken by the parameter. The apparent paradox only appears when ϵ=1, which is just a singular value. In this paper we demonstrate that this particular value is forbidden inside the scenario proposed by the experiment.

Electrifying the Skies: Battery Electric Aircraft and Their Role in Advancing Regional Integration - Lampo, Alessandro (INTI Journal, 2025)
The aviation sector is transforming as electrification emerges as a promising technology. Adopting battery-electric aircraft (BEA) - aircraft that solely rely on rechargeable onboard batteries - is a sustainable alternative to conventional aviation that could change short-haul regional travel habits for business and leisure travellers. This study examines the factors influencing individuals’ public acceptance in China's Greater Bay Area (GBA) context. Given the limited research, a qualitative methodology grounded in the Theory of Planned Behaviour (TPB) examines the underlying factors influencing behavioural intentions (attitudes, subjective norms, perceived behavioural control, and perceived risks). The findings indicate that participants recognise the technology's environmental benefits and potential to enhance regional connectivity; however, they still have concerns about safety, infrastructure, and operations. The respondents’ perceived ease of access, information available, and endorsements from reputable sources also have essential roles in influencing broader acceptance. Addressing these factors with appropriate communication efforts is vital for promoting trust and accelerating technology acceptance and use. Although exploratory, this study offers insights to develop strategies for infrastructure readiness, build public confidence, and endorse sustainable aviation. The research is conducted within the GBA context. Still, the findings also apply to regions with fragmented geographies or developing transportation networks, thus contributing to global environmental sustainability and advancing regional integration goals.

Assessing critical thinking disposition through text analysis in traditional Chinese: An empirical study of tourism and gaming undergraduates in Macao - Siu Lam, Carlos; Liu, Yong; Zhang, Yinghong; Wu, Hao (Frontiers in Education, 2025)
Critical thinking disposition (CTD) is increasingly recognized as an important trait in education, reflecting the inclination and habits necessary for addressing complex challenges in today's world. This study assessed the CTD of students enrolled in a tourism and gaming management programme, focusing on two key dimensions: Analyticity and Open-Mindedness. This study was conducted at a university in Macao and involved 65 participants. The students were presented with an article relevant to their major, written in Traditional Chinese, and were asked to provide their opinions on each statement in the article. A rubric was designed to analyze their responses and assess their Analyticity and Open-Mindedness within the CTD framework. The results demonstrated high reliability (Cronbach's α = 0.91) and revealed an association between Analyticity and Open-Mindedness. Using Python programming, the study analyzed the frequency of parts of speech (POS) in students' responses, introducing a novel approach for evaluating CTD in Traditional Chinese. Regression modeling showed that parallel and adversative conjunctions significantly predicted Analyticity, while the frequency of conjunction use varied across Open-Mindedness classifications. These findings highlighted an innovative and objective method for assessing CTD through text analysis, offering promising applications for educational research in Traditional Chinese-speaking contexts.
Keywords: critical thinking disposition; educational assessment; text analysis; tourism and gaming education; traditional Chinese

Solving the dark energy problem via symmetry constraints - Arraut, Ivan (The European Physical Journal C, 2025)
We derive the vacuum energy from the zero-point quantum fluctuations after imposing a natural constraint emerging from the rotational symmetry inside the de-Sitter metric. The constraint imposes a maximum azimuthal angle for each frequency mode emerging from the vacuum. In this way, the shorter the wavelength of the mode, the larger will be its suppression. The same result is derived subsequently by using the Friedmann–Lemaitre–Robertson–Walker (FLRW) metric. We then make a physical interpretation of the physical effects from the perspective of pair creations over the vacuum, where the mentioned constraint emerges, limiting then the maximum angle which each pair generated from the vacuum can rotate with respect to each other during their short existence.

Using Machine Learning CART Decision Trees for Predicting the Causes of Delays in Projects from the Construction Industry - Lobo Marques, Joao Alexandre; Chun, Fung Ka; Riccelli, Bruno (2024)
Construction projects are complex endeavours, with potential obstacles that can cause delays which can have particularly profound implications potentially impacting on company's financial health, business continuity and reputation. It is becoming increasingly recognised that delays are context-specific and multifaceted, requiring more industry-oriented perceptions. This work proposes the exploratory use of Machine Learning based on Classification and Regression Trees (CART) Decision Trees (DT) to assess the predictive analysis of these approaches, considering surveys (primary data) collected from 100 specialists with different backgrounds and experiences in the construction industry. Survey responses are discussed, followed by the CART DTs, which are used as predictor for clarifying underneath relationship among different variables in a project environment. The major issue presented is related to Project Design, with "The firm is not allowed to apply for an extension of contract period", with two possible predictors, firstly, as the main factor it is found "Mistakes, inconsistencies, and ambiguities in specification and drawing", while other aspect highlights "Poor site supervision and management by the contractor". The results indicate that the correct use of Artificial Intelligence techniques with relevant data are potential tools to support the analysis of scenarios and avoidance of project delays in Project Management.

The Future of Digital Banking in Macau: Developing a Theoretical Model of User Willingness for Digital Banking Services - Lin, Jing-ying; Lobo Marques, Joao Alexandre; Neto, Andreia (Proceedings of the 2024 15th International Conference on E-business, Management and Economics, 2024)
In the wave of digital transformation, Chinese banks have prioritized digital banking services as key strategic goals, aiming to revolutionize the mobile banking experience. This study aims to assess the factors influencing the willingness to use the various financial and contextual services offered through digital banking. Specifically, it is proposed a model based on users' perceptions of mobile banking scenarios and examines how the development of digital banking services influences users' willingness to use them. The study involved qualitative in-depth interviews with 12 mobile banking users, with the interview content analyzed using Nvivo qualitative analysis software. The data analysis identified 9 core coding categories: Financial Professionalism, Security, Marketing Stimulation, Innovative Products, Use Experience, Strong Relationship, Trust, Perceived Usefulness, and Willingness to Use. These categories were further refined to construct a theoretical model of user willingness in digital banking services, drawing from the optimized Technology Acceptance Model (TAM). The findings provide valuable insights for the banking industry in Macau, aiding in understanding customer needs and supporting the positive development of mobile finance and contextual digital banking services in the region.

Stock market prediction using artificial intelligence: A systematic review of systematic reviews - Lin, Chin Yang; Lobo Marques, Joao Alexandre (Social Sciences & Humanities Open, 2024)
There are many systematic reviews on predicting stock. However, each reveals a different portion of the hybrid AI analysis and stock prediction puzzle. The principal objective of this research was to systematically review the existing systematic reviews on Artificial Intelligence (AI) models applied to stock market prediction to provide valuable inputs for the development of strategies in stock market investments. Keywords that would fall under the broad headings of AI and stock prediction were looked up in Scopus and Web of Science databases. We screened 69 titles and read 43 systematic reviews, including more than 379 studies, before retaining 10 for the final dataset. This work revealed that support vector machines (SVM), long short-term memory (LSTM), and artificial neural networks (ANN) are the most popular AI methods for stock market prediction. In addition, the time series of historical closing stock prices are the most commonly used data source, and accuracy is the most employed performance metric of the predictive models. We also identified several research gaps and directions for future studies. Specifically, we indicate that future research could benefit from exploring different data sources and combinations, while we also suggest comparing different AI methods and techniques, as each may have specific advantages and applicable scenarios. Lastly, we recommend better evaluating different prediction indicators and standards to reflect prediction models’ actual value and impact.

Predicting consumer ad preferences: Leveraging a machinelearning approach for EDA and FEA neurophysiologicalmetrics - Lobo Marques, Joao Alexandre; Neto, Andreia C.; Silva, Susana C.; Bigne, Enrique (Psychology & Marketing, 2024)
Abstract This research unveils to predict consumer ad preferences by detecting seven basic emotions, attention and engagement triggered by advertising through the analysis of two specific physiological monitoring tools, electrodermal activity (EDA), and Facial Expression Analysis (FEA), applied to video advertising, offering a twofold contribution of significant value. First, to identify the most relevant physiological features for consumer preference prediction. We integrated a statistical module encompassing inferential and exploratory analysis tools, which identified emotions such as Joy, Disgust, and Surprise, enabling the statistical differentiation of preferences concerning various advertisements. Second, we present an artificial intelligence (AI) system founded on machine learning techniques, encompassing k‐Nearest Neighbors, Support Vector Machine, and Random Forest (RF). Our findings show that the RF technique emerged as the top performer, boasting an 81% Accuracy, 84% Precision, 79% Recall, and an F1‐score of 81% in predicting consumer preferences. In addition, our research proposes an eXplainable AI module based on feature importance, which discerned Attention, Engagement, Joy, and Disgust as the four most pivotal features influencing consumer ad preference prediction. The results indicate that computerized intelligent systems based on EDA and FEA data can be used to predict consumer ad preferences based on videos and effectively used as supporting tools for marketing specialists.

Mini-programs in mobile payment to access eGovernment in China’s Greater Bay Area - exploring the determinants and mechanism from self-determination and motivation theory - Patrick, Lai ChiMeng; Lobo Marques, Joao Alexandre (Cogent Social Sciences, 2024)
Government service mini-programs (GSMPs) in mobile payment have become integral to the eGovernment in China’s Greater Bay Area (GBA). The ubiquitous nature of WeChat and Alipay provides excellent flexibility for accessing public e-services. Yet, the determinants and mechanisms of adoption have not been identified. A convenience sample was collected from GBA core cities for statistical and SEM analysis. The findings suggest that service quality, trust in eGovernment, ubiquity, and social influence constitute the determinants. A structural model grounded on Self-Determination and Motivation theory is verified, where perceived value and intention contribute a high explanatory power. Benevolence, integrity, and competence are crucial indicators of trust, while social influence amplifies risk perception. Surprisingly, government support negatively moderates the impact of determinants on intention, indicating that over-intervention leads to inhibition. The mechanism illustrates the beneficial impact of GSMPs as the smart government channel and provides insights into addressing service homogeneity and policy applicability. Relevant theoretical and managerial implications are instructive to policymakers and practitioners of smart city innovation and in-depth integration in GBA.

Integration of Blockchain Technology in Auditing Practices - Bibliometric Analysis - Almeida, Ermelinda Nazaré António de; Lobo Marques, Joao Alexandre (Proceedings of the 2024 15th International Conference on E-business, Management and Economics, 2024)
The potential of blockchain technology extends beyond cryptocurrencies and has the power to transform various sectors, including accounting and auditing. Its integration into auditing practices presents opportunities and challenges, and auditors must navigate new standards and engage with clients effectively. Blockchain technology provides tamper-proof record-keeping and fraud prevention, enhancing efficiency, transparency, and security in domains such as finance, insurance, healthcare, education, e-voting, and supply chain management. This paper conducts a bibliometric analysis of blockchain technology literature to gain insights into the current state and future directions of blockchain technology in auditing. The study identifies significant research themes and trends using keyword and citation analysis. The Vosviewer software was used to analyze the data and visualize the results. Findings reveal significant growth in blockchain research, particularly from 2021 onwards, with China emerging as a leading contributor, followed by the USA, India, and the UK. This study provides valuable insights into current trends, key contributors, and global patterns in blockchain technology research within auditing practices, and future research may explore thematic areas in greater depth.

Enhancing Dynamic Hand Gesture Recognition through Optimized Feature Selection using Double Machine Learning - Yan, Keyue; Lam, Chi Fai; Fong, Simon; Lobo Marques, Joao Alexandre; Song, Qun; Qin, Huafeng (Proceedings of the 2024 8th International Conference on Big Data and Internet of Things, 2024)

Emotion Detection from EEG Signals Using Machine Deep Learning Models - Fernandes, João Vitor Marques Rabelo; Alexandria, Auzuir Ripardo de; Lobo Marques, Joao Alexandre; Assis, Débora Ferreira de; Motta, Pedro Crosara; Silva, Bruno Riccelli dos Santos (Bioengineering, 2024)
Detecting emotions is a growing field aiming to comprehend and interpret human emotions from various data sources, including text, voice, and physiological signals. Electroencephalogram (EEG) is a unique and promising approach among these sources. EEG is a non-invasive monitoring technique that records the brain’s electrical activity through electrodes placed on the scalp’s surface. It is used in clinical and research contexts to explore how the human brain responds to emotions and cognitive stimuli. Recently, its use has gained interest in real-time emotion detection, offering a direct approach independent of facial expressions or voice. This is particularly useful in resource-limited scenarios, such as brain–computer interfaces supporting mental health. The objective of this work is to evaluate the classification of emotions (positive, negative, and neutral) in EEG signals using machine learning and deep learning, focusing on Graph Convolutional Neural Networks (GCNN), based on the analysis of critical attributes of the EEG signal (Differential Entropy (DE), Power Spectral Density (PSD), Differential Asymmetry (DASM), Rational Asymmetry (RASM), Asymmetry (ASM), Differential Causality (DCAU)). The electroencephalography dataset used in the research was the public SEED dataset (SJTU Emotion EEG Dataset), obtained through auditory and visual stimuli in segments from Chinese emotional movies. The experiment employed to evaluate the model results was “subject-dependent”. In this method, the Deep Neural Network (DNN) achieved an accuracy of 86.08%, surpassing SVM, albeit with significant processing time due to the optimization characteristics inherent to the algorithm. The GCNN algorithm achieved an average accuracy of 89.97% in the subject-dependent experiment. This work contributes to emotion detection in EEG, emphasizing the effectiveness of different models and underscoring the importance of selecting appropriate features and the ethical use of these technologies in practical applications. The GCNN emerges as the most promising methodology for future research.

ECG Forecasting System Based on Long Short-Term Memory - Zacarias, Henriques; Marques, João Alexandre Lôbo; Felizardo, Virginie; Pourvahab, Mehran; Garcia, Nuno M. (Bioengineering, 2024)
Worldwide, cardiovascular diseases are some of the primary causes of death; yet the early detection and diagnosis of such diseases have the potential to save many lives. Technological means of detection are becoming increasingly essential and numerous techniques have been created for this purpose, such as forecasting. Of these techniques, the time series forecasting technique seeks to predict future events. The long-term time series forecasting of physiological data could assist medical professionals in predicting and treating patients based on very early diagnosis. This article presents a model that utilizes a deep learning technique to predict long-term ECG signals. The forecasting model can learn signals’ nonlinearity, nonstationarity, and complexity based on a long short-term memory architecture. However, this is not a trivial task as the correct forecasting of a signal that closely resembles the original complex signal’s structure and behavior while minimizing any differences in amplitude continues to pose challenges. To achieve this goal, we used a dataset available on the Physio net database, called MIT-BIH, with 48 ECG recordings of 30 min each. The developed model starts with pre-processing to reduce interference in the original signals, then applies a deep learning algorithm, based on a long short-term memory (LTSM) neural network with two hidden layers. Next, we applied the root mean square error (RMSE) and mean absolute error (MAE) metrics to evaluate the performance of the model and obtained an average RMSE of 0.0070±0.0028 and an average MAE of 0.0522±0.0098 across all simulations. The results indicate that the proposed LSTM model is a promising technique for ECG forecasting, considering the trends of the changes in the original data series, most notably in R-peak amplitude. Given the model’s accuracy and the features of the physiological signals, the system could be used to improve existing predictive healthcare systems for cardiovascular monitoring.

Doctor Bone: treinamento de redes neurais para auxílio na identificação da idade óssea - Barbosa, Rodrigo Lages; Martins, Heitor de Castro Teixeira e; Barbosa, Felipe Cassiano; da Costa, Beatriz Torres; Matela, Rolf Freitas; Neto, José Fernando Rodrigues Ferreira; Fontes, Yuri Nekan Soares; Lobo Marques, Joao Alexandre; Duarte, João Batista Furlan; Neto, Joel Sotero da Cunha (2024)
Objetivo: Explorar a aplicação de inteligência artificial (IA) na predição da idade óssea a partir de imagens de raios-X. Método: Utilizou-se a Metodologia Interdisciplinar para o Desenvolvimento de Tecnologias em Saúde (MIDTS) para desenvolver uma ferramenta de predição. O treinamento foi realizado com redes neurais convolucionais (CNNs) usando um conjunto de dados de 14.036 imagens de raios-X. Resultados: A ferramenta alcançou um coeficiente de determinação (R²) de 0,94807 e um Erro Médio Absoluto (MAE) de 6,97, destacando sua precisão e potencial de aplicação clínica. Conclusão: O projeto demonstrou grande potencial para aprimorar a predição da idade óssea, com possibilidades de evolução conforme a base de dados aumenta e a IA se torna mais sofisticada.

Automl-Based Eeg Signal Analysis in Neuro-Marketing Classification Using Biclustering Method - Albuquerque, Victor; Gois, Francisco Bernardo; Lobo Marques, Joao Alexandre; Silva, Bruno Riccelli dos Santos; Cortez, Paulo Cesar (Elsevier BV, 2024)
Consumer neuroscience analyzes individuals’ preferences through the assessment of physiological data monitoring, considering brain activity or other bioinformation to assess purchase decisions. Traditional marketing tactics include customer surveys, product evaluations, and comments. For product or brand marketing and mass production, it is important to understand consumer neurological responses when seeing an ad or testing a product. In this work, we use the bi-clustering method to reduce EEG noise and automatic machine learning to classify brain responses. We analyze a neuromarketing EEG dataset that contains EEG data from product evaluations from 25 participants, collected with a 14 channel Emotiv Epoch + device, while examining consumer items. Four components comprised the research methodology. Initially, the Welch Transform was used to filter the EEG raw data. Second, the best converted signal biclusterings are used to train different classification models. Each biclustering is evaluated with a separate classifier, considering F1-Score. After that, the H2O.ai AutoML library is used to select the optimal biclustering and models. Instead of traditional procedures, two thresholds are used. First-threshold values indicate customer satisfaction. Low values of the second threshold reflect consumer dissatisfaction. Values between the first and second criteria are classified as uncertain values. We outperform the state of the art with a 0.95 F1-Score value.

Assessment of the post-acute COVID-19 syndrome cardiovascular effect through ECG analysis - Ribeiro, Pedro; de Souza, Clarice Cristina Cunha; Camerino, Cristine Mayara Cavalcante; Pordeus, Daniel; Leite, Camila Ferreira; Lobo Marques, Joao Alexandre; Madeiro, João Paulo; Rodrigues, Pedro Miguel (2024)
Introduction: SARS-CoV-2, a virus responsible for the emergence of the life-threatening disease known as COVID-19, exhibits a diverse range of clinical manifestations. The spectrum of symptoms varies widely, encompassing mild to severe presentations, while a considerable portion of the population remains asymptomatic. COVID-19, primarily a respiratory virus, has been linked to cardiovascular complications in some patients. Notably, cardiac issues can also arise after recovery, contributing to post-acute COVID-19 syndrome, a significant concern for patient health. The present study intends to evaluate the post-acute COVID-19 syndrome cardiovascular effect through ECG by comparing patients affected with cardiac diseases without COVID-19 diagnosis report (class 1) and patients with cardiac pathologies who present post-acute COVID-19 syndrome (class 2). Methods: From 2 body positions, a total of 10 non-linear features, extracted every 1 second under a multi-band analysis performed by Discrete Wavelet Transform (DWT), have been compressed by 6 statistical metrics to serve as inputs for an individual feature analysis by the means of Mann-Whitney U-test and XROC classification. Results and Discussion: 480 Mann-Whitney U-test statistical analyses and XROC discrimination approaches have been done. The percentage of statistical analysis with significant differences (p<0.05) was 30.42% (146 out of 480). The best overall results were obtained by approximating the feature Energy, with the data compressor Kurtosis in the body position Down. Those results were 83.33% of Accuracy, 83.33% of Sensitivity, 83.33% of Specificity and 87.50% of AUC. Conclusions: The results show that the applied methodology can be a way to show changes in cardiac behaviour provoked by post-acute COVID-19 syndrome.

Analysis of deep learning algorithms for emotion classification based on facial expression recognition - Qian, Cheng; Lobo Marques, Joao Alexandre; Fong, Simon James (Proceedings of the 2024 8th International Conference on Big Data and Internet of Things, 2024)
Facial expression recognition (FER) is essential for discerning human emotions and is applied extensively in big data analytics, healthcare, security, and user experience enhancement. This paper presents an empirical study that evaluates four existing deep learning models—VGG16, DenseNet, ResNet50, and GoogLeNet—utilizing the Facial Expression Recognition 2013 (FER2013) dataset. The dataset contains seven distinct emotional expressions: angry, disgust, fear, happy, neutral, sad, and surprise. Each model underwent rigorous assessment based on metrics including test accuracy, training duration, and weight file size to test their effectiveness in FER tasks. ResNet50 emerged as the top performer with a test accuracy of 69.46%, leveraging its residual learning architecture to effectively address challenges inherent in training deep neural networks. Conversely, GoogLeNet exhibited the lowest test accuracy among the models, suggesting potential architectural constraints in FER applications. VGG16, while competitive in accuracy, demonstrated lengthier training times and a larger weight file size (512MB), highlighting the inherent balance between model complexity and computational efficiency.

Real-time emotion recognition based on facial expressions using artificial intelligence techniques - A review and future directions - Cheng, Qian; Lobo Marques, Joao Alexandre; de Alexandria, Auzuir Ripardo (2025)

Application of Multiple Deep Learning Architectures for Emotion Classification Based on Facial Expressions - Qian, Cheng; Lobo Marques, Joao Alexandre; Alexandria, Auzuir Ripardo de; Fong, Simon James (Sensors, 2025)
Facial expression recognition (FER) is essential for discerning human emotions and is applied extensively in big data analytics, healthcare, security, and user experience enhancement. This study presents a comprehensive evaluation of ten state-of-the-art deep learning models—VGG16, VGG19, ResNet50, ResNet101, DenseNet, GoogLeNet V1, MobileNet V1, EfficientNet V2, ShuffleNet V2, and RepVGG—on the task of facial expression recognition using the FER2013 dataset. Key performance metrics, including test accuracy, training time, and weight file size, were analyzed to assess the learning efficiency, generalization capabilities, and architectural innovations of each model. EfficientNet V2 and ResNet50 emerged as top performers, achieving high accuracy and stable convergence using compound scaling and residual connections, enabling them to capture complex emotional features with minimal overfitting. DenseNet, GoogLeNet V1, and RepVGG also demonstrated strong performance, leveraging dense connectivity, inception modules, and re-parameterization techniques, though they exhibited slower initial convergence. In contrast, lightweight models such as MobileNet V1 and ShuffleNet V2, while excelling in computational efficiency, faced limitations in accuracy, particularly in challenging emotion categories like “fear” and “disgust”. The results highlight the critical trade-offs between computational efficiency and predictive accuracy, emphasizing the importance of selecting appropriate architecture based on application-specific requirements. This research contributes to ongoing advancements in deep learning, particularly in domains such as facial expression recognition, where capturing subtle and complex patterns is essential for high-performance outcomes.

A Novel Improvement of Feature Selection for Dynamic Hand Gesture Identification Based on Double Machine Learning - Yan, Keyue; Lam, Chi-Fai; Fong, Simon; Lobo Marques, Joao Alexandre; Millham, Richard Charles; Mohammed, Sabah (Sensors, 2025)
Causal machine learning is an approach that combines causal inference and machine learning to understand and utilize causal relationships in data. In current research and applications, traditional machine learning and deep learning models always focus on prediction and pattern recognition. In contrast, causal machine learning goes a step further by revealing causal relationships between different variables. We explore a novel concept called Double Machine Learning that embraces causal machine learning in this research. The core goal is to select independent variables from a gesture identification problem that are causally related to final gesture results. This selection allows us to classify and analyze gestures more efficiently, thereby improving models’ performance and interpretability. Compared to commonly used feature selection methods such as Variance Threshold, Select From Model, Principal Component Analysis, Least Absolute Shrinkage and Selection Operator, Artificial Neural Network, and TabNet, Double Machine Learning methods focus more on causal relationships between variables rather than correlations. Our research shows that variables selected using the Double Machine Learning method perform well under different classification models, with final results significantly better than those of traditional methods. This novel Double Machine Learning-based approach offers researchers a valuable perspective for feature selection and model construction. It enhances the model’s ability to uncover causal relationships within complex data. Variables with causal significance can be more informative than those with only correlative significance, thus improving overall prediction performance and reliability.

Local Equivalence of the Black–Scholes and Merton–Garman Equations - Arraut, Ivan (2025)
It has been previously demonstrated that stochastic volatility emerges as the gauge field necessary to restore local symmetry under changes in stock prices in the Black–Scholes (BS) equation. When this occurs, a Merton–Garman-like equation emerges. From the perspective of manifolds, this means that the Black–Scholes and Merton–Garman (MG) equations can be considered locally equivalent. In this scenario, the MG Hamiltonian is a special case of a more general Hamiltonian, here referred to as the gauge Hamiltonian. We then show that the gauge character of volatility implies a specific functional relationship between stock prices and volatility. The connection between stock prices and volatility is a powerful tool for improving volatility estimations in the stock market, which is a key ingredient for investors to make good decisions. Finally, we define an extended version of the martingale condition, defined for the gauge Hamiltonian.

The shifting landscape of Chinese student mobility to Thailand - Lertpusit, Sivarin; Ge, Rochelle; Ho, Kong Chong (Asian Population Studies, 2025)
This paper examines the evolving trends in Chinese student mobility to Thailand, highlighting three distinct phases shaped by changes in the higher education: the dominance of Thai language programmes (1990–2010), the rise of business and international programmes (2010–2020), and the increasing preference for graduate studies (2020 onwards). By analysing the economic, cultural, and institutional factors facilitating these shifts, this paper positions Thailand as an emerging alternative study destination for Chinese students. It highlights the significance of this migration within the context of Thailand’s declining fertility rate and labour shortages, focusing on how Thai universities have adapted through active recruitment strategies targeting Chinese students. This paper also addresses the push and pull factors underpinning this migration and the pursuit of alternative educational pathways among Chinese youth. Additionally, it explores the strategic role of Sino-Thai collaborations under the BRI and their broader implications for educational mobility and economic ties.

是來時路，亦是前行燈：澳門教師的使命與歸屬 - Ge, Rochelle (2025)

A grounded theory study of Chinese female spouses of problem gamblers in Hong Kong: emergence of a multiple-paradigm coping model - Kwan, Edward Wood Kai; Jackson, Alun C.; Tse, Samson (Asia Pacific Journal of Counselling and Psychotherapy, 2025)

A razão da intervenção psicológica na deformidade dentofacial - Silva, Susana; Teixeira, Vítor; Pinhão Ferreira, Afonso; Ustrell‐Torrent, Maria Josep (Revista Portuguesa de Estomatologia, Medicina Dentária e Cirurgia Maxilofacial, 2016)

Autoestima e deformidade dentofacial: um estudo comparativo com a escala de autoestima global de Rosenberg - Silva, Susana; Teixeira, Vítor; Pinhão Ferreira, Afonso; Ustrell‐Torrent, Maria Josep (Revista Portuguesa de Estomatologia, Medicina Dentária e Cirurgia Maxilofacial, 2016)

Determining the relationships of employee resilience and organizational culture with levels of employee work engagement - Kuok, Angus; Taormina, Robert (2024)
The objective is to assess whether the extent to which employee resilience and organizational culture would be significantly related to and statistically predict the three facets of employee work engagement. Resilience was measured by four facets (Determination, Endurance, Adaptability, and Recuperability); and Organization Culture was measured for three types (Bureaucratic, Innovative, and Supportive). The dependent measures were the three facets of Work Engagement (Cognitive, Emotional, and Physical). This research by questionnaire was conducted in 2023. The questionnaires completed by 316 full-time workers revealed that all four facets of employee resilience had significant positive correlations with all three types of work engagement. Also, all three facets of work engagement were significantly higher in Innovative and Supportive cultures compared to Bureaucratic cultures. The regression analyses performed showed that the resilience factors of Determination and Adaptability were strong positive predictors of all three facets of work engagement. Furthermore, Innovative culture had additional positive effects on all three facets of work engagement; while Supportive culture had an additional positive effect on Emotional Work Engagement. The implications of the results for management are also discussed in this paper.

THE INTERPLAY BETWEEN A CONFUCIAN-HERITAGE CULTURE AND TEACHERS' SENTIMENTS AND ATTITUDES TOWARDS INCLUSION IN MACAU - Correia, Ana; Forlin, Chris; Santos Teixeira, Vitor; Kuok, A. C. H.; Monteiro, Elisa (2019)
Macau Special Administration Region (Macau SAR) is in the process of revising legislation concerning special and inclusive education. While the institutional discourse revolves around establishing inclusive education, it is unclear as to how the proposed changes will enable or depress this from occurring. This research, therefore, examined teachers attitudes towards inclusion as an indication of how well the new legislation may be received. Specifically, it investigated the interplay between 508 teachers working in private schools in Macau, that identified themselves as being inclusive schools, and teachers sentiments and attitudes towards the acceptance of inclusion and the role that Confucian values might play in shaping these attitudes. Discussion focusses on four key outcomes that need to be addressed if a significant improvement in including all children in regular schools in Macau is to be achieved. These include the need (1) to clarify the concept of inclusion at government, school, and teacher levels as it currently has ambiguous meaning; (2) to provide teachers with more opportunities to have systematic contacts with students with SEN, as this is crucial to improving their sentiments and attitudes toward people with disability; (3) to provide professional learning about inclusive education with better partnerships between teacher education institutions and schools to bridge theory and practice; and (4) to review the hidden influence of the subtle levels of time-honoured Confucian beliefs in Macau, which are not manifest nor easily detected but possibly have a deep impact on day-to-day practices.

Examining the Latent Structure of Gambling Motivation and Its Relationship with Gambling Behavior in Gambling-Exposed Chinese Casino Employees - Mordeno, Imelu G.; Coteriano, Carla; Leong, Sin U. (Psychological Studies, 2017)
Examining why individuals engage in gambling is important in understanding the development of gambling behaviors. Numerous studies have investigated the underlying factor of gambling motivation. However, there is a dearth of evidence showing the latent dimensions of gambling motivation among individuals who are exposed to gambling in daily basis (i.e., casino employees). To address this gap, 817 casino employees were administered the Chinese version of the Gambling Motivation Scale (GMS) and other related measures. Results revealed that of the four models tested, a first-order model with seven factors achieved better fit in contrast to all other models. The seven factors include intrinsic motivation (IM) for knowledge, IM for accomplishment, IM for stimulation, extrinsic motivation (EM) due to identified regulation, EM due to introjected regulation, EM due to external regulation, and amotivation. However, the seven-factor model did not reach the conventional fit indices for good fit. After some post hoc modifications, the revised model achieved adequate fit. Moreover, the revised seven factors were related to frequency of gambling and amount spent for gambling. Generally, results showed that modified GMS with seven factors can be used with Chinese population, more specifically with Chinese casino employees.
Keywords: Casino employees; Gambling; Latent structure

Sharing towards cohesive community: the role of social capital in sharing economy - Lai, Michael (ResearchGate, 2024)
PDF | Purpose Whilst the majority of academic studies have focused on the for-profit business-to-consumer type of sharing economy, the community-based... | Find, read and cite all the research you need on ResearchGate

The use Robotics in the intervention with children with ASD in Macao: a pilot study with Milo - Teixeira, Vitor; Lai, Michael (Revista Portuguesa de Investigação Educacional, 2021)
Robotics are being used in the intervention with children with Autism Spectrum Disorder (ASD) in many places and already for many years. Many robots were developed and different studies are being made in order to evaluate its effectiveness. “Socially Assistive Robotics” is shown to be effective in different areas mainly in social and emotional development. Milo, a robot developed by a team led by Richard Margolin for the Robots4Autism program (RoboKind, 2020), is one of the robots whose use is reported to be successful. In Macao there is no report of studies or experiences on the use of robots in the intervention with children with ASD. In a collaboration between the Macao Science Centre, the Macao Autism Association (MAA) and the University of Saint Joseph, an exploratory study was developed to understand the applicability of Milo to the work with children with ASD in Macao. The study showed that the robot is able to facilitate social and emotional competences of children with ASD. However, several limitations including language, cultural differences, the inexperienced facilitators and the level of sessions are too simple for the participants to be aware of that may affect the effectiveness of the intervention. It is important to show that the adoption of Milo in Macao for intervening children with ASD can be further implemented, with better practical solutions.
Number: 21

Non-Native Raters and Native Speech: Other Perspective for the Research on Comprehensibility of Second Language Input - Simões, Edlia; Martins, Margarida Alves; Figueiredo, Sandra; Silva, Carlos Fernandes da (International Journal of Speech & Language Pathology and Audiology)
This study examines how specific variables such as age, first language, nationality, school grade and socioeconomic status (SES) affect the comprehensibility of second language (L2) speech in 92 second/non-native language learners. Comprehensibility refers to the degree of speech understanding. Fluency, rhythm, grammatical features and word stressing are concurrent factors for the listening comprehension (and the listener comprehensibility) mainly in L2 context. Research evidence focused the quality and differences of speech samples produced by the L2 learners and the comprehensibility rated by native speakers. In reverse scenario there is less evidence on the judgment of L2 learners for speech samples produced by native speakers. In this study we analysed if the comprehensibility ability of 92 young Portuguese L2 learners differ in the following conditions: age, nationality, home language, school grade, proficiency and socioeconomic status. Speech (one text) was recorded by a native speaker and was judged by L2 speakers using 1-5 Likert scale for comprehension difficulty. Main results showed that neither age nor home language had influence for comprehensibility, but socioeconomic, nationality and grades accounted for statistical differences between the groups tested. Also, data suggested that phonetic features are more likely important for the beginner in second language learning compared to the semantic features of speech that heavily depend on vocabulary domain.
Keywords: Aprendizagem; Leitores principiantes; Leitura de palavras; Padrão de erros

A aquisição da leitura em leitores principiantes: erros típicos no português europeu - Simões, Edlia; Martins, Margarida Alves (Educação e Pesquisa, 2018)
O estudo das estratégias que as crianças usam na leitura de palavras e a análise dos erros que tipicamente ocorrem ao longo do processo de aprendizagem numa dada ortografia são da maior importância para a compreensão do processo de aprendizagem da leitura. O objectivo deste trabalho foi perceber como se processa a aquisição da leitura no início do ensino fundamental no português europeu. Procurou-se saber se haveria diferenças na frequência de erros fonológicos e lexicais e no padrão de erros fonológicos entre os dois primeiros anos do ensino fundamental. Participaram 175 crianças do 1º ano e 137 do 2º ano de seis escolas. Foi aplicada uma prova de leitura oral de palavras. Os erros foram categorizados em fonológicos, com diversas subcategorias, e lexicais. Encontraram-se diferenças na frequência dos erros fonológicos e lexicais entre os dois anos, assim como nos subtipos de erros fonológicos que tipicamente ocorreram. Os erros de substituição foram os mais frequentes, tendo ocorrido mais nas consoantes e nos dígrafos. Seguiram-se os erros de adição e de supressão, que ocorreram sobretudo em sílabas complexas. Tais resultados, contribuindo para uma caracterização dos erros típicos nessa fase de aprendizagem, revelam-se um instrumento importante na detecção de dificuldades precoces na aprendizagem da leitura e na adequação de estratégias de ensino-aprendizagem. Este estudo permite uma melhor compreensão dos processos usados pelas crianças na resolução dos problemas que as características da língua portuguesa lhes coloca, assim como poderá permitir uma intervenção educativa que conduza a um maior sucesso na aprendizagem da leitura.Leitores principiantes; Aprendizagem; Leitura de palavras; Padrão de erros
Keywords: Aprendizagem; Leitores principiantes; Leitura de palavras; Padrão de erros

Unveiling retail omnichannel challenges: developing an omnichannel obstacles scale - Radomska, Joanna; Kawa, Arkadiusz; Hajdas, Monika; Klimas, Patrycja; Silva, Susana C. (International Journal of Retail & Distribution Management, 2024)
Purpose Retail omnichannel implementation faces barriers hindering accurate and efficient integration across marketing channels. Our desk examination identified a need for a broader perspective in investigating these barriers, moving away from a dominant, narrow approach. This research aims to develop a comprehensive set of items to measure retail omnichannel obstacles, refine the scale and assess its reliability and validity for a robust measurement tool. Design/methodology/approach Our approach combines quantitative and qualitative methods, using data from primary and secondary sources to create and validate the omnichannel obstacles scale. Findings This study emphasises the inclusive nature of retail functional areas, departing from prior literature that examined them in isolation. Instead of focussing on separate domains where retail omnichannel obstacles may arise, we adopt a holistic perspective by integrating previously disconnected elements. Originality/value We assert that challenges in retail omnichannel operations encompass three distinct dimensions: operational efficiency, channel inefficiency, and strategy and organisational culture within retailing. In our final validated measurement model, we consolidate the channel inefficiency dimension and refine the omnichannel obstacles scale to emphasise two areas of consideration.

Is masculinity ruining the male skincare market? Comprehensive insights on consumer behavior in cosmetics - Duarte, Paulo; Silva, Susana; Carvalho, Maria Joana (Journal of Consumer Marketing, 2025)
This paper aims to investigate the factors influencing men’s purchase intentions for skincare products, particularly focusing on the evolving attitudes toward masculinity, grooming and self-care. The study seeks to identify dimensions such as self-image, health concerns, masculinity and perceptions regarding skincare, along with the impact of social media use on men’s skincare purchase intentions.,The research uses an online questionnaire to gather data from 178 valid responses. The collected data is analyzed using partial least squares structural equation modeling.,The results reveal that men’s skin health concerns significantly impact their purchase intention for skincare products. Self-image concerns and perceptions regarding skincare also emerge as influential determinants in shaping men’s purchasing decisions. Conversely, health concerns and social media platform use do not directly influence skincare purchase intention. Notably, self-image completely mediates the relationship between men’s social media usage and their intention to purchase skincare products.,The data is based on responses from an online questionnaire, which may introduce biases. In addition, the research focuses on specific personal variables and social media use, potentially overlooking other influential factors.,By recognizing the importance of men’s skin health concerns, self-image and perceptions regarding skincare, cosmetic companies can tailor marketing strategies to effectively target key dimensions to enhance sales of skincare products among men.,In a broader societal context, this research contributes to the ongoing evolution of attitudes. By identifying influential factors in men’s skincare purchase intention, the study sheds light on changing societal norms and perceptions. Acknowledging these shifts can lead to a more inclusive understanding of masculinity and contribute to breaking traditional stereotypes related to men’s grooming practices.,This research contributes to the understanding of men’s skincare purchase intention by exploring dimensions such as self-image, health concerns, masculinity and perceptions regarding skincare, in conjunction with the impact of social media use. The findings provide valuable insights, expanding on previous studies on men’s attitudes toward skincare products. The identification of self-image as a complete mediator is a novel contribution.

Unveiling retail omnichannel challenges: developing an omnichannel obstacles scale - Radomska, Joanna; Kawa, Arkadiusz; Hajdas, Monika; Klimas, Patrycja; Silva, Susana C. (International Journal of Retail & Distribution Management, 2024)
Purpose Retail omnichannel implementation faces barriers hindering accurate and efficient integration across marketing channels. Our desk examination identified a need for a broader perspective in investigating these barriers, moving away from a dominant, narrow approach. This research aims to develop a comprehensive set of items to measure retail omnichannel obstacles, refine the scale and assess its reliability and validity for a robust measurement tool. Design/methodology/approach Our approach combines quantitative and qualitative methods, using data from primary and secondary sources to create and validate the omnichannel obstacles scale. Findings This study emphasises the inclusive nature of retail functional areas, departing from prior literature that examined them in isolation. Instead of focussing on separate domains where retail omnichannel obstacles may arise, we adopt a holistic perspective by integrating previously disconnected elements. Originality/value We assert that challenges in retail omnichannel operations encompass three distinct dimensions: operational efficiency, channel inefficiency, and strategy and organisational culture within retailing. In our final validated measurement model, we consolidate the channel inefficiency dimension and refine the omnichannel obstacles scale to emphasise two areas of consideration.

Empowering Luxury: How Cause-Related Marketing Influences Gen Z and Millennials' Post-Purchase Guilt in China's High-End Retail Landscape - Dias, Joana Carmo; Silva, Susana; Martins, Carla; Casais, Beatriz (European Journal of Applied Business and Management, 2024)
Purpose: This study explores the emotional impact of post-purchase guilt on younger consumers in the Chinese luxury retail market, with a specific focus on the role of Cause-related Marketing (CrM) in mitigating negative emotions across luxury and non-luxury product categories.Design/Methodology/Approach: A quantitative experimental design was utilized, involving 326 respondents exposed to different advertising scenarios. The study tested the impact of CrM on post-purchase guilt in both luxury (high-priced) and non-luxury (moderately priced) product conditions, using a 2 × 2 factorial design. The data were analyzed using ANCOVA to assess the effects of CrM campaigns across conditions.Findings: The results demonstrate that CrM effectively reduces post-purchase guilt across both luxury and non-luxury product categories, providing a moral justification for purchases by linking them to a positive social cause. However, contrary to expectations, the impact of CrM was not significantly stronger in the luxury context compared to non-luxury. This suggests that CrM's influence on post-purchase guilt operates uniformly, regardless of product type.Originality: This research enhances understanding Millennial and Gen Z consumer behavior in the Chinese luxury market. The findings offer actionable insights for luxury brands, highlighting the effectiveness of CrM in addressing guilt-related concerns, thereby informing marketing strategies aimed at younger generations.Keywords: post-purchase guilt, Millennials, Gen Z, Chinese luxury retail industry, cause-related marketing.Acknowledgments: The first author would like to thank CEGE – Research Centre in Management and Economics, funded by The Multiannual Funding Programme of R&D Centres of FCT – Fundação para a Ciência e Tecnologia under the project UIDB/00731/2020. The fourth author would like to thank COMEGI funded by FCT – Fundação para a Ciência e Tecnologia under the project UIDB/04005/2020.DOI: https://doi.org/10.58869/EJABM10(3)/06
Number: 3

Trust in AI and Top Management Support in Generative-AI Adoption - Korzyński, Paweł; Silva, Susana Costa E; Górska, Anna Maria; Mazurek, Grzegorz (Journal of Computer Information Systems, 2024)

A Possible Solution to the Black Hole Information Paradox - Arraut, Ivan (AppliedMath, 2025)
The information paradox suggests that the black hole loses information when it emits radiation. In this way, the spectrum of radiation corresponds to a mixed (non-pure) quantum state even if the internal state generating the black hole is expected to be pure in essence. In this paper we propose an argument solving this paradox by developing an understanding of the process by which spontaneous symmetry breaks when a black hole selects one of the many possible ground states and emits radiation as a consequence of it. Here, the particle operator number is the order parameter. This mechanism explains the connection between the density matrix, corresponding to the pure state describing the black hole state, and the density matrix describing the spectrum of radiation (mixed quantum state). From this perspective, we can recover black hole information from the superposition principle, applied to the different possible order parameters (particle number operators).
Number: 1
Keywords: Hawking radiation; black holes; information paradox; spontaneous symmetry breaking

Unveiling the power of supplier-country image on B2B customers' perceptions: Beyond the product’s beauty - Crespo, Cátia Fernandes; Crespo, Nuno Fernandes; Silva, Susana C. (International Business Review, 2025)

基于价格检验的粤港澳大湾区经济一体化实证研究 - CNKI [Empirical Study on the Economic Integration of the Guangdong-Hong Kong-Macao Greater Bay Area Based on Price Assessment] - 王心如; 李颖芝 (产业创新研究, 2024)

Impact of Education on Green Fintech Adoption: Evidence From the New Sub-Center of Beijing - Lei, Weng Chi; An, Boyang (Journal of Global Business Research and Practice, 2024)

Beyond the myth: understanding women's impulsive retail footwear shopping - Duarte, Paulo; Silva, Susana C.; Magro, Margarida; Dias, Joana Carmo (International Journal of Retail & Distribution Management, 2025)
Purpose This research focuses on common misconceptions about the factors driving women to purchase footwear impulsively. Its primary objective is to explore how emotional and social triggers specifically influence women's purchasing decisions, contrasting with the traditionally rational consumer models. Design/methodology/approach An online questionnaire was administered to a sample of women, yielding 199 useable responses. Findings The findings reveal the key determinants of women's impulsive retail footwear purchases, which include self-regulation, hedonic motivations and the influence of the retail store environment. This research challenges the prevailing assumption that women's passion for shopping is driven solely by inherent characteristics and suggests that external factors substantially shape their impulsive buying behaviour. In summary, the stereotypical portrayal of women as compulsive retail footwear shoppers may result more from external stimuli and environmental factors rather than an intrinsic trait. Originality/value This study improves the existing knowledge of women’s impulsive buying behaviour by unveiling the determinants of women's impulsive footwear purchases and assessing whether prevailing stereotypes hold true.

Habermas, Honneth, Critical Theory, and Ideology Critique for Transformative Mixed Methods Research - Morrison, Keith (Journal of Mixed Methods Studies, 2024)
This article sets a theoretical foundation to transformative mixed methods research that is rooted in the critical theory of Habermas and Honneth. This addresses Habermas’s knowledge-constitutive interests and communicative action for redressing societal pathologies, and Honneth’s work on (mis)recognition, (dis)respect, and social justice. In doing so, the article argues for broadening the scope and embrace of mixed methods research, to go beyond being empirical research only or largely, and to include theorisation, critical theoretical discourse and its analysis, and ideology critique, as legitimate methods for (transformative) mixed methods research. The article makes a case for these methods as constituting important research methods in themselves in the portfolio of mixed methods research, moving the boundaries of mixed methods research beyond solely empirical studies, and providing emancipatory lenses and consciousness-raising in recognising that transformation takes many forms.

Employee Motivation in Elderly Care Social Enterprises in Macau - Phillips, Jenny O. L.; Mui, UnKei (Journal of Advanced Management Science, 2024)

Consumer Purchase Intention towards Floral Products: A Study Based on the Five Consumption Values - Lei, Si Nga; Phillips, Jenny O. L. (Journal of Economics, Business and Management, 2024)

Understanding Policy Acceptance Through UTAUT-2: The Case of the Northbound Travel Policy for Macau Vehicles - Lampo, Alessandro; Diakite, Ansoumane D.; Ip, Emil C. H. (Journal of Global Business Research and Practice, 2024)

Waldorf early childhood education: from the West to the East - Ikegami, Kiiko; Morrison, Keith; Sio, Ka I (Compare: A Journal of Comparative and International Education)
The philosophy of Rudolf Steiner’s Anthroposophy, fundamental to Waldorf education, provides an alternative view on education to that in the non-western world. The article illustrates a rhizomatic, informal diffusion of ‘alternative education’ in contrast to ‘policy borrowing’ in education, reporting how Waldorf education and Anthroposophy are regarded and operated in an East Asian context. An initial exploratory study of this provides insider perspectives of ‘knowledgeable’ practitioners in Waldorf early childhood centres in East Asia, regarding their understanding and practices of Anthroposophy and its three key concepts: the Four Temperaments; the Seven-Year [development] cycle; and the Twelve Senses. Participants identified key features of Waldorf education: holistic development of the child; nature relatedness; modelling and imitation; and contextualisation and localisation. Many features of Waldorf education ran counter to significant values and practices in schooling in the local culture. The paper indicates how to reconcile these, and makes recommendations for further research.
_eprint: https://doi.org/10.1080/03057925.2024.2442330
Keywords: Anthroposophy; Rudolf Steiner; Waldorf education; child development; early childhood education

From Overcoming Self to Overcoming Nature: Teaching on Human Nature in Ricci, Pantoja, and Aleni - Cai, Yilun (Logos: A Journal of Catholic Thought and Culture, 2024)
Publisher: Logos: A Journal of Catholic Thought and Culture
Keywords: Catholicism and Confucianism; Intercultural Dialogue; Jesuit Mission to China; Jesuit Theology; Theological Anthropology

Beyond the myth: understanding women's impulsive retail footwear shopping - Duarte, Paulo; Silva, Susana C.; Magro, Margarida; Dias, Joana Carmo (International Journal of Retail & Distribution Management, 2024)
This research focuses on common misconceptions about the factors driving women to purchase footwear impulsively. Its primary objective is to explore how emotional and social triggers specifically influence women's purchasing decisions, contrasting with the traditionally rational consumer models.,An online questionnaire was administered to a sample of women, yielding 199 useable responses.,The findings reveal the key determinants of women's impulsive retail footwear purchases, which include self-regulation, hedonic motivations and the influence of the retail store environment. This research challenges the prevailing assumption that women's passion for shopping is driven solely by inherent characteristics and suggests that external factors substantially shape their impulsive buying behaviour. In summary, the stereotypical portrayal of women as compulsive retail footwear shoppers may result more from external stimuli and environmental factors rather than an intrinsic trait.,This study improves the existing knowledge of women’s impulsive buying behaviour by unveiling the determinants of women's impulsive footwear purchases and assessing whether prevailing stereotypes hold true.

Action research on circular economy strategies in fashion retail - Silva, Susana C.; Neiva, Carolina Rocha; Dias, Joana Carmo (International Journal of Retail & Distribution Management, 2025)
Purpose The aim of this study is to explore the role and impact of action research in the adoption of circular economy strategies by a fashion retail brand. This exploration is motivated by the need to address the underutilization of action research in management studies, despite its potential to foster a deep understanding of organizational processes and to drive positive transformations. The study seeks to illustrate how action research can contribute to the practical implementation of sustainability initiatives, specifically within the context of new environmental legislation and growing demands for sustainable practices in retailing. Design/methodology/approach This research employs an action research methodology, particularly suited to the retail field, where understanding and influencing organizational processes are key. Through a detailed case study of a fashion retail brand, the study illustrates how action research facilitates the adoption of circular economy strategies. Findings The findings of this study underscore the effectiveness of action research in implementing circular economy strategies within the fashion retail industry. Specifically, it highlights how this approach has led to the successful reduction of waste and reintegration of products into their lifecycle. Originality/value The originality of this study lies in its thorough application of action research to measure and refine the outcomes of circular economy strategies in retailing. This novel approach provides substantial insights into the potential of the circular economy to drive practical innovations in business practices within retail.

Understanding the dynamics of customer satisfaction and repurchase intentions in the era of platform service supply chain – a case study of Foodpanda in Pakistan - Choudhary, Waliha; Waqar Haider, Syed; Raza, Aamir; Silva, Susana C.; Carmo Dias, Joana (Journal of Foodservice Business Research, 2024)

Predicting consumer ad preferences: Leveraging a machine learning approach for EDA and FEA neurophysiological metrics - Marques, João Alexandre Lobo; Neto, Andreia C.; Silva, Susana C.; Bigne, Enrique (Psychology & Marketing, 2025)
This research unveils to predict consumer ad preferences by detecting seven basic emotions, attention and engagement triggered by advertising through the analysis of two specific physiological monitoring tools, electrodermal activity (EDA), and Facial Expression Analysis (FEA), applied to video advertising, offering a twofold contribution of significant value. First, to identify the most relevant physiological features for consumer preference prediction. We integrated a statistical module encompassing inferential and exploratory analysis tools, which identified emotions such as Joy, Disgust, and Surprise, enabling the statistical differentiation of preferences concerning various advertisements. Second, we present an artificial intelligence (AI) system founded on machine learning techniques, encompassing k-Nearest Neighbors, Support Vector Machine, and Random Forest (RF). Our findings show that the RF technique emerged as the top performer, boasting an 81% Accuracy, 84% Precision, 79% Recall, and an F1-score of 81% in predicting consumer preferences. In addition, our research proposes an eXplainable AI module based on feature importance, which discerned Attention, Engagement, Joy, and Disgust as the four most pivotal features influencing consumer ad preference prediction. The results indicate that computerized intelligent systems based on EDA and FEA data can be used to predict consumer ad preferences based on videos and effectively used as supporting tools for marketing specialists.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/mar.22118
Keywords: advertising; consumer ad preferences; consumer neuroscience; emotions; explainable artificial intelligence; machine learning

Comparing Online Learning Experiences Between University Students With and Without Special Educational Needs During COVID-19 - Lim, Yun Ting; Nah, Yong-Hwee; Chen, Mo (ISSN: 2758-0962 The Paris Conference on Education 2024: Official Conference Proceedings, 2024)
The aim of this study is to examine the online learning experiences of university students with Special Educational Needs (SEN), and how their experiences might differ from their typically developing peers. Fifty typically developing students (mean age = 22; 29 females) and 31 students with SEN (mean age = 22; 15 females) from a local

Changing professional identities: a qualitative study of how Singapore allied educators managed their own resistance to change - Kit, Phey Ling; Ow Yeong, Wai Mang Elizabeth; Chen, Mo (Teacher Development, 2024)

The cosmological constant emerging from a symmetry invariant - Arraut, Ivan (Modern Physics Letters A, 2024)
The cosmological constant is normally introduced as an additional term entering the Einstein–Hilbert (EH) action. In this letter, we demonstrate that, instead, it appears naturally from the standard EH action as an invariant term emerging from spacetime symmetries. We then demonstrate that the same constraint emerging from this invariant suppresses the short wavelength modes and it favors the long wavelength ones. In this way, inside the proposed formulation, the observed value for the vacuum energy density is obtained naturally from the zero-point quantum fluctuations.
Keywords: Dark energy; cosmological constant; zero point quantum fluctuations

An Evangelical Adrift: The Making of John Henry Newman's Theology by Geertjan Zuijdwegt (review) - Morgan, Stephen (Antiphon: A Journal for Liturgical Renewal, 2023)

Order parameter conditions from mutual information and symmetry conditions - Arraut, Ivan; Yu, Wing Chi (International Journal of Modern Physics B, 2024)
The mutual information method has demonstrated to be very useful for deriving the potential order parameter of a system. Although the method suggests some constraints which help to define this quantity, there is still some freedom in the definition. The method then results inefficient for cases where we have order parameters with a large number of constants in the expansion, which happens when we have many degenerate vacuums. Here, we introduce some additional constraints based on the existence of broken symmetries, which help us to reduce the arbitrariness in the definitions of the order parameter in the proposed mutual information method.
Keywords: Mutual information; order parameter; quantum phase transitions; spontaneous symmetry breaking

Cross-cultural adaptation and validation of the Chinese version of Skills and Needs Inventories in Functional Behavior Assessments and Interventions (SNI-FBAI-CN) - Chen, Mo; Dutt, Anuradha S.; Nair, Rahul (Behavioral Interventions)
Cross-cultural adaptation and validation of measures are necessary to provide evidence-based educational intervention services among children with autism spectrum disorder (ASD) across countries. Language plays an integral role in the cross-cultural adaptation and validation process of measures. Currently, there are limited validated tools in Chinese available to assess special education teachers' skills in functional behavior assessments and interventions in Mainland China to effectively support students with ASD. This study aimed to validate a Chinese version of the Skills and Needs Inventories in Functional Behavior Assessments and Interventions (SNI-FBAI-CN) in mainland China. The SNI-FBAI, originally developed and validated in Singapore, in the English language, was translated, culturally adapted, and then administered to 239 special education teachers in two schools for children with ASD in China. Results show that the SNI-FBAI-CN has a three-factor structure (i.e., skills in behavioral assessment, skills in behavioral interventions, and needs for training) that fits the data well, with good reliability for the overall scale, as well as the three subscales. Partial measurement invariance was established between the Chinese and the original Singapore samples, providing additional construct validity evidence for this tool. Limitations of this study and directions for future research are discussed.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/bin.2038
Keywords: Chinese; SNI-FBAI; autism spectrum disorders; cross-cultural validation; mainland China; special education teachers

Reply to the "Comment on The Tully-Fisher law and dark matter effects derived via modified symmetries" by I. Arraut. - Arraut Guerrero, Ivan (Europhysics Letters, 2024)
It has been claimed in \cite1, that the idea proposed in \cite2 has certain mistakes based on arguments of energy conditions and others. Additionally, some of the key arguments of the paper are criticized. Here we demonstrate that the results obtained in \cite2 are correct and that there is no violation of any energy condition. The statements claimed in \cite1 are based on three things: 1). Misinterpretation of the metric solution. 2). Language issues related to the physical quantities obtained in \cite1, where the authors make wrong interpretations about certain results over the geometry proposed in \cite2. 3). Non-rigorous evaluations of the vacuum condition defined via the result over the Ricci tensor R_\mu\nu=0.

Teaching and learning with older adults: Research ethics, risk analysis, and covert research - Ní Bhroin, Áine; Morrison, Keith (Educational Gerontology, 2024)
This article reports a case study of older adults learning English in China. It indicates how, founded on consequentialist ethics, risk analysis, and safeguarding, it was decided to use covert research, drawing on the confluence of risk analysis, risk evaluation, risk management, safeguarding, research ethics, and important contextual and cultural features. Ethical principles of nonmaleficence, beneficence, safeguarding, and protection were addressed, and account was taken of the strength, likelihood, and consequences of risks, safeguards, and benefits, informed by Chinese cultural contexts, values, behaviors, and features of teaching and learning based on andragogy and geragogy. Implications are drawn for teaching and learning with older adults, advocating significant account to be taken of contextual factors.
_eprint: https://doi.org/10.1080/03601277.2024.2377872

Digital and Sustainable Trade Facilitation in Western Balkans Countries - Toshevska-Trpchevska, Katerina; Lei, Weng Chi (Florence); Stojkoski, Viktor (European Scientific Journal, ESJ, 2024)
After the Covid-19 Pandemic crisis in international economic relations it became evident that climate-smart aspects should be considered when re-establishing a new international trade order. International organizations have proclaimed that this momentum should be used to include climate-smart trade and investment provisions to enable sustainable development. It has been acknowledged that trade has an important role to play in the global response to climate change, providing economies with tools to draw on in their efforts to mitigate climate change and to adapt to its consequences. In this paper we focus the analysis on investigating the digital and sustainable component of trade facilitation measures applied in Western Balkans countries. To evaluate the importance of trade facilitation measures and their digital and sustainable components we apply standard gravity model with the data from UN Global Survey on digital and sustainable trade facilitation. The results show that trade facilitation measures are important for improving and increasing trade among the Western Balkans countries. Especially, measures connected to improving transparency procedures in trade and measures for alleviating trade formalities are most significant for increasing bilateral trade among Western Balkans countries. With a lower level of importance are the measures for improving cross-border paperless trade between these countries.
Keywords: Digital and sustainable trade facilitation; UN Global Survey on Digital and Sustainable Trade Facilitation; Western Balkans countries; gravity model

A Pilot Study for Measuring Complex Problem-Solving in Jordan: Feasibility, Construct Validity, and Behavior Pattern Analyses - Alrababah, Saleh Ahmad; Wu, Hao; Molnár, Gyöngyvér (Sage Open, 2024)
In the 21st century, complex problem-solving (CPS) serves as a key indicator of educational achievement. However, the elements of successful CPS have not yet been fully explored. This study investigates the role of strategic exploration and different problem-solving and test-taking behaviors in CPS success, using logfile data to visualize and quantify students’ problemsolving behavior on 10 CPS problems with different characteristics and levels of difficulty. Additionally, in the present study, we go beyond the limits of most studies that focus on students’ problem-solving behavior pattern analyses in European cultures and education systems to examine Arabic students’ CPS behavior. The results show that computer-based assessments of CPS are feasible and valid in Jordanian higher education. The findings also confirm the structural validity of CPS, indicating that the processes of knowledge acquisition (KAC) and knowledge application (KAP) can be distinguished and separated in the problem-solving process. Large differences were identified in students’ test-taking behavior in terms of the efficacy of their exploration strategy. We identified four latent classes based on the students’ exploration strategy behavior. The study thus leads to a better understanding of how students solve problems and behave during the problem-solving process in uncertain situations.

Matteo Ricci's teaching on the goodness of human nature: its Thomistic and neo‐Confucian sources - Cai, Yilun (The Heythrop Journal, 2024)
Abstract The Jesuit missionary Matteo Ricci's teaching on the goodness of human nature in The True Meaning of the Lord of Heaven represents the fruit of the first encounter between Catholicism and Confucianism. This article will consider the Thomistic and neo‐Confucian sources in Ricci's enunciation of the Catholic doctrine on the goodness of human nature in this Chinese catechism. It will illustrate that Ricci developed his teaching, which is fundamentally Thomistic, with the help of terminology borrowed from the Chinese philosophical tradition. His distinction between the good of nature and the good of virtue leads to prioritising the cultivation of human nature. Ricci's teaching reflects the early modern Jesuits’ appreciation of human freedom. It also displays a Catholic reaction to the sixteenth‐century neo‐Confucian intellectual trend that ignored the importance of moral cultivation.

Hawking Radiation as a Manifestation of Spontaneous Symmetry Breaking - Arraut, Ivan (Symmetry, 2024)
We demonstrate that black hole evaporation can be modeled as a process where one symmetry of the system is spontaneously broken continuously. We then identify three free parameters of the system. The sign of one of the free parameters governs whether the particles emitted by the black hole are fermions or bosons. The present model explains why the black hole evaporation process is so universal. Interestingly, this universality emerges naturally inside certain modifications of gravity.
Number: 5
Keywords: Hawking radiation; black holes; spontaneous symmetry breaking

Fintech Adoption: A Study of Users in the Guangdong-Macao In-Depth Cooperation Zone in Hengqin (China) - Weng, Chi Lei; Lampo, Alessandro (INTI JOURNAL, 2024)
Intended as an economic and development hub, the Hengqin Cooperation Zone aims to foster collaboration and integration between mainland China, Hong Kong, and Macao, serving as a platform for economic development and innovation among the three regions. The zone's development has increased demand for financial services, often offered through fintech. There is, however, a lack of interoperability between the fintech services currently used in Macao and Hengqin. This may hinder Macao users' adoption of the technology. Thus, our research objective is to identify the factors determining Macao residents' adoption of fintech services in the area and provide insights for service providers, developers, and policymakers. A framework based on the Technology Acceptance Model (TAM) and Theory of Planned Behavior (TPB) was used for this purpose. The responses of 103 Macao residents provided evidence that ease of use significantly and positively impacts the usefulness of the technology. This in turn influences attitudes towards fintech usage. Subjective norms and perceived behavioral control positively impact fintech adoption intentions. The fintech industry and the governments of Macao and Hengqin can work on improving technology's ease of use and usefulness. They can also promote them to Macao users, and provide the resources required for better access to fintech in the zone
Number: 02

Impacts of Central Bank Digital Currency on Regional Economic Integration: Evidence from the Greater Bay Area of China - Lei, Weng Chi; Wang, Xinru (The Chinese Economy, 2024)
An increasing number of countries have launched their central bank digital currencies (CBDC) in recent years, but the economic impacts of CBDC adoption are underexplored. To empirically assess how CBDC adoption influences regional economic integration, this paper investigates the Greater Bay Area, where China carried out one of its first digital renminbi pilot programs. The Greater Bay Area provides a good example because the growing acceptance of digital renminbi in the area can potentially mitigate transaction costs and risks due to the exchange rate volatility of the Chinese renminbi, Hong Kong dollar, and Macao pataca. CBDC adoption can lead to greater real and financial integrations by facilitating cross-border trade in goods and services. This paper evaluates deviations from uncovered interest rate parity, purchasing power parity, and real interest rate parity across Guangdong, Hong Kong, and Macao based on monthly interest rate and price data from January 2016 to December 2022. The time series have mean values near zero, which validate the parity conditions and indicate high degrees of financial, real, and economic integrations. The Markov regime-switching regression model identifies three regimes: (1) pre-Covid, (2) post-Covid, and (3) post-CBDC. The Covid-19 outbreak brought lower integration and stability, but the launch of the CBDC restored some of the pre-Covid integration and stability. Regimes 1 and 2 are persistent, and transitions from Regime 3 back to Regime 1 are probable. Hence, this study finds evidence that CBDC adoption improves regional economic integration in the short and long run.
_eprint: https://doi.org/10.1080/10971475.2024.2333124
Keywords: Central bank digital currency; Greater Bay Area; digital renminbi; economic integration; financial integration

Revenue Management in Airlines and External Factors Affecting Decisions: The Harmonic Oscillator Model - Arraut, Ivan; Rosado, Wilson; Leong, Victor (Mathematics, 2024)
The Revenue Management (RM) problem in airlines for a fixed capacity, single resource and two classes has been solved before by using a standard formalism. In this paper we propose a model for RM by using the semi-classical approach of the Quantum Harmonic Oscillator. We then extend the model to include external factors affecting the people’s decisions, particularly those where collective decisions emerge.
Number: 6
Keywords: collective decisions; harmonic oscillator; revenue management; spontaneous symmetry breaking

“To Listen to the Language of Nature and to Act Accordingly” :: Natural Law as Beacon guiding to Human Flourishing and Ecological Civilization - Gassner, Franz (Orientis Aura: Macau Perspectives in Religious Studies, 2021)
The article sets off from a speech given by Benedict XVI in the German Bundestag in 2011, where he requested an ecological learning process to aim at sustainable human development. Appreciating the Ecological Movement, he asked to learn to listen to Nature’s language and act accordingly, which he applies analogically to “human ecology”. The article bridges elements of “Listening to Nature” and the Natural Moral Law Tradition in Benedict’s speech and in Francis’ Encyclical Letter Laudatu Si’ inview of serving human flourishing in an ecological civilization. Keywords: Natural Moral Law; Nature, Laudatu Si’, Benedict XVI, Francis; Ecological Civilization/生態文明, Sustainable Development, Ecology of Man.
Number: 6

Message from Program Chairs - Ma, J.; Du, W.; Lu, W. (Proceedings - 2022 IEEE/ACIS 22nd International Conference on Computer and Information Science, ICIS 2022, 2022)
ISBN: 9781665494632

Foreword - Ma, J.; Du, W.; Lu, W. (Studies in Computational Intelligence, 2023)
ISBN: 9783031121265

Does Romans 2:14 Refer to the Natural Law? - Leong, Chi Hei (Orientis Aura: Macau Perspectives in Religious Studies, 2021)
Whilst after decades of research, exegetes have all agree on the complexity of Paul’s line of thinking in Rom 2:14–16, the ITC in its 2009 document, In Search of a Universal Ethic, still in an oversimplified manner propagates the view that Rom 2:14 presupposes a theory/theology of the natural law. This article makes plain the major disagreements among Pauline exegetes whether such presupposition stands by reviewing some major contributions to the discussion by raising major questions regarding the issue of φύσει in those verses, the nature of the law mentioned by Paul, the identity of the people Paul calls “Gentiles.” This article offers a more nuanced understanding of Rom 2:14. Keywords: Rom 2:14, ITC, Universal Ethic, Natural Law, φύσει, Gentiles
Number: 6

聖多瑪斯思想權威之演變，從1274年至1323年 - 蔡翼倫 (《神學論集》)
本文梳理聖多瑪斯去世至1323年列聖品之間，發生的圍繞其思想權威性的爭議與演變。在這近五十年中，多瑪斯思想的權威性在不斷的爭議與回應中逐漸形成，其中尤其針對他運用亞里士多德的哲學來闡釋天主啟示，及對貧窮勸諭的理解所衍生的論辯。作者指出，以道明會會士為 主的神學家致力於以多瑪斯思想為基點，回應各種反對多瑪斯思想的挑戰，過程中逐漸形成了具有統一性的多瑪斯學派，加以教會內各種歷史性因素，都促成了多瑪斯在1323年7月的亞維農被列入聖品。

Perspectives of Local Communities on the Impact of Chinese Aid: A Case Study of China's Aid Projects in the Education Sector in Guinea - Diakite, Ansoumane Douty (Journal of Globalization Studies, 2023)
China's re-emergence as an aid donor has attracted the attention and criticism from Western donors, academia, and the media. In contrast to traditional donors, China's aid has been portrayed as anti-poverty aid, mainly due to its combination with other instruments, such as investment, and the absence of any political or economic conditions. This paper examines the impact of Chinese aid projects in Guinea's education sector from the perspective of the beneficiaries. The author collected data from both primary (interviews) and secondary (document analysis) sources. The present study concludes that China's aid projects in the education sector have received both positive and negative feedback, mainly because the recipients' needs have not been appropriately targeted. This study contributes to the literature on China's role in Africa. More specifically, it discusses the conditions for aid effectiveness in the field of education. Moreover, in the context of the globalization of aid practices, the study proposes best practices for China to adopt in order to improve the practices of its aid delivery. The novelty of this study lies in the methodology (qualitative method) used to understand China's aid from the perspective of the beneficiaries of its aid.

Static recording apparatus for soundscape analysis in Macau - Estadieu, Gerald; Cheung, Yin Yan; Pestana, Pedro Duarte; Barbosa, Alvaro (INTER-NOISE and NOISE-CON Congress and Conference Proceedings, 2023)
The concept of Soundscape was initially proposed to study the relationship between humans and their sonic environment. It has gathered momentum from academia to environmentalists and policymakers throughout the years. The study and characterisation of Soundscapes can be complex as it tries to take a holistic and qualitative approach rather than simply quantifying sound pressure levels. This paper introduces a comprehensive Soundscape study process in an ongoing research project in Macao (China), a small territory (32.9 km2) and one of the most densely populated areas in the world. The paper seeks to show a first version of a technical solution to systematically capture the local soundscape, analyse it, classify it, and ultimately deliver a dataset library and the intangible qualities of the environmental sound. This implementation, including technical documentation, code, and sound library with strong labelling, is presented under an open-source license to encourage future collaborative research. Finally, the paper offers suggestions on further developing the apparatus to reach a systematic and near real-time soundscape analysis with the development of a machine learning system.

Unsettling Exiles: Chinese Migrants in Hong Kong and the Southern Periphery During the Cold War Angelina Y. Chin. New York: Columbia University Press, 2023. 320 pp., $35.00; £30.00, ISBN 9780231209991. - Roberts, Priscilla (The China Quarterly, 2023)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS0305741023001406/resource/name/firstPage-S0305741023001406a.jpg

Death of a salesman? the new junket regulation and practice in macau - Ho, Hong-Wai; Phillips, Jenny (Gaming Law Review, 2023)
This review article is among the first to examine the new junket regulations in the Macau gaming industry. Particular emphasis is on the legal and regulatory framework governing the junket activity of gaming promoters and their associates. The recent changes to Macau gaming laws have resulted in stronger licensing requirements for local junket participants and precipitated the collapse of the VIP room system in casinos. Furthermore, this article highlights the policy and managerial implications of the current junket environment for the gaming industry in Macau and possibly other regional gaming jurisdictions. The effects of the new legal environment for Macau junkets could also provide insights into the implementation of similar legislation in other jurisdictions.
Keywords: Macao; VIP room; gambling; gaming regulation; international gaming; junket operation

Machine learning-based cardiac activity non-linear analysis for discriminating COVID-19 patients with different degrees of severity - Ribeiro, Pedro; Marques, João Alexandre Lobo; Pordeus, Daniel; Zacarias, Laíla; Leite, Camila Ferreira; Sobreira-Neto, Manoel Alves; Peixoto, Arnaldo Aires; de Oliveira, Adriel; Madeiro, João Paulo do Vale; Rodrigues, Pedro Miguel (Biomedical Signal Processing and Control, 2024)
Objective: This study highlights the potential of an Electrocardiogram (ECG) as a powerful tool for early diagnosis of COVID-19 in critically ill patients with limited access to CT–Scan rooms. Methods: In this investigation, 3 categories of patient status were considered: Low, Moderate, and Severe. For each patient, 2 different body positions have been used to collect 2 ECG signals. Then, from each collected signal, 10 non-linear features (Energy, Approximate Entropy, Logarithmic Entropy, Shannon Entropy, Hurst Exponent, Lyapunov Exponent, Higuchi Fractal Dimension, Katz Fractal Dimension, Correlation Dimension and Detrended Fluctuation Analysis) were extracted every 1s ECG time-series length to serve as entries for 19 Machine learning classifiers within a leave-one-out cross-validation procedure. Four different classification scenarios were tested: Low vs. Moderate, Low vs. Severe, Moderate vs. Severe and one Multi-class comparison (All vs. All). Results: The classification report results were: (1) Low vs. Moderate - 100% of Accuracy and 100% of F1–Score; (2) Low vs. Severe - Accuracy of 91.67% and an F1–Score of 94.92%; (3) Moderate vs. Severe - Accuracy of 94.12% and an F1–Score of 96.43%; and (4) All vs All - 78.57% of Accuracy and 84.75% of F1–Score. Conclusion: The results indicate that the applied methodology could be considered a good tool for distinguishing COVID-19’s different severity stages using ECG signals. Significance: The findings highlight the potential of ECG as a fast and effective tool for COVID-19 examination. In comparison to previous studies using the same database, this study shows a 7.57% improvement in diagnostic accuracy for the All vs All comparison.
Keywords: Accuracy; COVID-19; ECG signals; Machine learning classifiers; Non-linear analysis; –

Aspects that constitute citizens’ trust in e-government - A review and framework development - Lai, Chimeng; Marques, Alexandre Joao Lobo (Multidisciplinary Reviews, 2024)
The extent of citizens' trust in government determines the success or failure of e-government initiatives. Nevertheless, the idiosyncrasies of the concept and the broad spectrum of its approach still present relevant challenges. This work presents a systematic literature review on e-government trust while elaborating and summarizing a conceptual analysis of trust, introducing evaluation methods for government trust, and compiling relevant research on e-government trust and intentional behavior. A total of 26 key factors that constitute trust have been identified and classified into six categories: Government trust, Trust in Internet and technology (TiIT), Trust in e-government (TiEG), Personal Beliefs, Trustworthiness, and Trust of intermediary (ToI). The value added of this work consists of developing a conceptual framework of TiEG to provide a significant reference for future in-depth studies and research on e-government trust.
Keywords: Systematic Literature Review (SLR); framework; trust; trust in e-government

Exploratory Analysis of Project Management Adoption and Maturity Level of IT Companies–A Comparison between Macao and Hengqin - Wong, Ka Seng; Lobo Marques, João Alexandre (Journal of Advanced Management Science, 2023)

Career trajectory and cross-system mobility: Career planning of doctoral students in Macao - Ge, Yun (Higher Education Quarterly, 2024)
This study investigates career trajectory and work locations of doctoral students trained in Macao and analyses how their career paths are shaped by perceived macro-level factors. Respondents from four applied disciplinary areas were selected for semi-structured in-depth interviews. Research results show that doctoral students who graduated from Macao higher education institutions enjoy good career prospects in Mainland China. Their competitiveness in the research-related job market benefits from having a multi-level support system and a training mode that promotes government–university–industry collaboration. Policies and demand from industrial sectors are involved in students' learning experience through channels such as financial support, project collaboration and networks. Doctoral students in Macao are strategic planners and actors in leveraging their human capital. As Macao becomes an emerging destination for cultivating high-level research labour, findings from this study capture a model of human capital formation in China's cross-system context.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/hequ.12474
Keywords: career trajectory; cross-system mobility; doctoral education; employability; human capital formation

LSDA-APF: A Local Obstacle Avoidance Algorithm for Unmanned Surface Vehicles Based on 5G Communication Environment - Li, Xiaoli; Jiao, Tongtong; Ma, Jinfeng; Duan, Dongxing; Liang, Shengbin (Computer Modeling in Engineering & Sciences, 2023)
In view of the complex marine environment of navigation, especially in the case of multiple static and dynamic obstacles, the traditional obstacle avoidance algorithms applied to unmanned surface vehicles (USV) are prone to fall into the trap of local optimization. Therefore, this paper proposes an improved artificial potential field (APF) algorithm, which uses 5G communication technology to communicate between the USV and the control center. The algorithm introduces the USV discrimination mechanism to avoid the USV falling into local optimization when the USV encounter different obstacles in different scenarios. Considering the various scenarios between the USV and other dynamic obstacles such as vessels in the process of performing tasks, the algorithm introduces the concept of dynamic artificial potential field. For the multiple obstacles encountered in the process of USV sailing, based on the International Regulations for Preventing Collisions at Sea (COLREGS), the USV determines whether the next step will fall into local optimization through the discrimination mechanism. The local potential field of the USV will dynamically adjust, and the reverse virtual gravitational potential field will be added to prevent it from falling into the local optimization and avoid collisions. The objective function and cost function are designed at the same time, so that the USV can smoothly switch between the global path and the local obstacle avoidance. The simulation results show that the improved APF algorithm proposed in this paper can successfully avoid various obstacles in the complex marine environment, and take navigation time and economic cost into account.

A Multi-Channel Text Sentiment Analysis Model Integrating Pre-training Mechanism - Liang, Shengbin; Jin, Jiangyong; Du, Wencai; Qu, Shenming (Information Technology and Control, 2023)
The number of tourist attractions reviews, travel notes and other texts has grown exponentially in the Internet age. Effectively mining users’ potential opinions and emotions on tourist attractions, and helping to provide users with better recommendation services, which is of great practical significance. This paper proposes a multi-channel neural network model called Pre-BiLSTM combined with a pre-training mechanism. The model uses a combination of coarse and fine- granularity strategies to extract the features of text information such as reviews and travel notes to improve the performance of text sentiment analysis. First, we construct three channels and use the improved BERT and skip-gram methods with negative sampling to vectorize the word-level and vocabulary-level text, respectively, so as to obtain more abundant textual information. Second, we use the pre-training mechanism of BERT to generate deep bidirectional language representation relationships. Third, the vectors of the three channels are input into the BiLSTM network in parallel to extract global and local features. Finally, the model fuses the text features of the three channels and classifies them using SoftMax classifier. Furthermore, numerical experiments are conducted to demonstrate that Pre-BiLSTM outperforms the baselines by 6.27%, 12.83% and 18.12% in average in terms of accuracy, precision and F1-score.
Number: 2
Keywords: Pre-training mechanism

A medical text classification approach with ZEN and capsule network - Liang, Shengbin; Sun, Fuqi; Sun, Haoran; Chen, Tingting; Du, Wencai (The Journal of Supercomputing, 2023)
Text classification is an important topic in natural language processing, with the development of social network, many question-and-answer pairs regarding health-care and medicine flood social platforms. It is of great social value to mine and classify medical text and provide targeted medical services for patients. The existing algorithms of text classification can deal with simple semantic text, especially in the field of Chinese medical text, the text structure is complex and includes a large number of medical nomenclature and professional terms, which are difficult for patients to understand. We propose a Chinese medical text classification model using a BERT-based Chinese text encoder by N-gram representations (ZEN) and capsule network, which represent feature uses the ZEN model and extract the features by capsule network, we also design a N-gram medical dictionary to enhance medical text representation and feature extraction. The experimental results show that the precision, recall and F1-score of our model are improved by 10.25%, 11.13% and 12.29%, respectively, compared with the baseline models in average, which proves that our model has better performance.
Keywords: Capsule network; Medical text classification; Text mining; ZEN model

Relationship between Student Teachers' Beliefs and Practices on Early Chinese Literacy Instruction - Sun, Chunrong; Ho, Ka Lee Carrie (Universal Journal of Educational Research, 2023)
This study explores the relationship between student teachers' beliefs and practices in early Chinese literacy instruction. Semi-structured interviews, classroom observation, and document analysis were conducted with six student teachers during their teaching practices. Findings indicated that the student teachers believed explicitly teaching literacy skills and imperceptible acquisition of literacy abilities through communication and meaning-making processes are essential in Chinese early literacy learning. However, they mainly taught Chinese literacy skills in their practices, which means the student teachers still needed to practice what they preached fully. The study suggests that possible reasons for the discrepancies include 'direct teaching' and 'rote learning' might be much easier for student teachers to design and conduct a lesson. Student teachers have limited abilities and experiences in conducting an ideal lesson, and the kindergarten curriculum and onsite supervisors highly influenced their teaching practices. The findings from this study suggested that more operational activities (such as designing lesson plans and conducting micro-teaching) should be used during pre-service training. Furthermore, the communication of educational beliefs between the university supervisor and the onsite supervisor should be strengthened.

Relationships among critical thinking disposition components of Chinese undergraduates: A moderated mediating effect analysis - Zhao, Yangyintao; Liu, Yong; Wu, Hao (International Journal of Educational Research, 2024)
Critical thinking (CT), as a form of higher-order thinking, is intended to help individuals form reasonable reflection and judgment to deal with increasingly severe employment situations. As the primary workforce in the labor market, undergraduates must possess a strong critical thinking disposition (CTD) to make better use of CT. Despite extensive research on components of CTD from the perspective of educational practices, there is limited emphasis on investigating the components and their relationships of CTD in the labor market and the impact of gender differences. Therefore, this study presented an analysis of 1535 Chinese undergraduates (Mage = 20.89; SD = 1.43) using the Employer-Employee-Supported Critical Thinking Disposition Inventory (2ES-CTDI), aiming to explore the CTD that undergraduates should possess before entering the labor market. The relationships among the components were examined using SmartPLS4.0 in conjunction with Partial Least Squares Structural Equation Modeling (PLS-SEM). Additionally, a multigroup analysis (PLS-MGA) with a measurement invariance (MI) test was conducted to validate the moderating effects of gender. The findings indicate that (a) self-efficacy has a significant negative effect on habitual truth-digging, and boys are more affected than girls, instant judgment plays a competitive partial mediating role in this relationship; (b) self-efficacy has a significant positive effect on instant judgment, and boys are more likely to make instant judgments than girls; (c) instant judgment significantly positively affects habitual truth-digging. These findings highlight the dynamic equilibrium among the internal components of CTD in the labor market and call for increased attention from educators to the importance of gender differences in the cultivation process.
Keywords: Critical thinking disposition; Labor Market; Moderated mediation; Undergraduates

Higher Education students' perceptions towards Information Literacy: a study in Macau - Sanches, Tatiana; Chan, Emily (Ibersid: revista de sistemas de información y documentación, 2023)
Integrating information literacy into learning improves student performance and, for that reason, academic librarians can play a significant role by collaborating in the design and training programs in these areas. In Macao, there is no known study on the information literacy performance of higher education students, so we seek to diagnose this area. For that purpose, a survey was applied to higher education students to assess students' perception of information literacy and their self-characterization regarding the use of resources and the type of skills needed for academic work. A semi-structured interview was also carried out with teachers about the same reality. Students perceive themselves to have a low level of confidence in the performance of their academic tasks, which affects their fulfilment. Faculty are aligned with this diagnosis, revealing the students’ weaknesses in the information search and presentation. Overall, information needs are evident among students as also is the use of preferred information resources in pursuit of their studies. The training aimed at students in search, retrieval, analysis, and use of information seems to be essential, which is why the construction of a tailormade training program in Information Literacy is anticipated.
Number: 2
Keywords: Macao

Categorization of Foreign Aid Donors: A Critical Review of the Criteria in Light of China's Reemergence as a Donor - Diakite, Ansoumane Douty; Marques, João Alexandre Lobo (Journal of Global South Studies, 2023)
Over the past several decades, the dichotomy between traditional and emerging donors has been based upon the notion that emerging donors (such as China) support authoritarian regimes and use foreign aid to pursue their economic interests at the expense of the poor in the recipient countries. Accordingly, Western donors, media, and scholars portray Chinese aid as non-poverty-focused. This study aims to review and analyze whether the dichotomy between traditional and emerging donors is still relevant in the current aid system and to propose a new and rigorous criterion for recategorizing donors. In terms of methodology, this study relies on secondary data, including scholarly works on traditional and emerging donors and foreign aid policy documents. Conclusions based on the research indicate that the divide between traditional donors and (re)emerging donors is becoming more ambiguous. The literature review indicates that the two donors’ aids had a mixed impact and that their approaches were similar. This paper highlights the importance of developing different recategorization criteria depending on the impact of aid.
Number: 2
Keywords: China and development assistance committee donors; aid policies; categorization of donors; sustainable development goal; traditional and emerging donors

The Role of the Volatility in the Option Market - Arraut, Ivan; Lei, Ka-I. (AppliedMath, 2023)
We review some general aspects about the Black–Scholes equation, which is used for predicting the fair price of an option inside the stock market. Our analysis includes the symmetry properties of the equation and its solutions. We use the Hamiltonian formulation for this purpose. Taking into account that the volatility inside the Black–Scholes equation is a parameter, we then introduce the Merton–Garman equation, where the volatility is stochastic, and then it can be perceived as a field. We then show how the Black–Scholes equation and the Merton–Garman one are locally equivalent by imposing a gauge symmetry under changes in the prices over the Black–Scholes equation. This demonstrates that the stochastic volatility emerges naturally from symmetry arguments. Finally, we analyze the role of the volatility on the decisions taken by the holders of the options when they use the solution of the Black–Scholes equation as a tool for making investment decisions.
Number: 4
Keywords: Black–Scholes equation; Merton–Garman equation; decision theory; option price; stock market; volatility

Comment on ''Generalized James' effective Hamiltonian method'' - Rosado, W.; Arraut, Ivan (Physical Review A, 2023)
In the paper carried out by Wenjun et al. [Phys. Rev. A 95, 032124 (2017)], a generalization of the James effective dynamics theory based on a first version of the James method was presented. However, we contend that this is not a very rigorous way of deriving the effective third-order expansion for an interaction Hamiltonian with harmonic time-dependence. In fact, here we show that the third-order Hamiltonian obtained by Wenjun et al. is not Hermitian for general situations when we consider time dependence. Its non-Hermitian nature arises from the foundation of the theory itself. In this comment paper, the most general expression of the effective Hamiltonian expanded up to third order is obtained. Our derived effective Hamiltonian is Hermitian even in situations where we have time dependence.

Leadership and Neurosciences - The analysis of emotional arousal during decision-making processes with decision-makers exposed to acute stress - Marques, Joao Alexandre Lobo (European Conference on Management Leadership and Governance, 2023)
Corporate leaders are constantly dealing with stress in parallel with continuous decision-making processes. The impact of acute stress on decision-making activities is a relevant area of study to evaluate the impact of the decisions made, and create tools and mechanisms to cope with the inevitable exposure to stress and better manage its impact. The intersection of leadership and neurosciences techniques is called Neuroleadership. In this work, an experiment is proposed to detect and measure the emotional arousal of two groups of business professionals, divided into two groups. The first one is the intervention/stress group, n=30, exposed to stressful conditions, and the control group, n=14, not exposed to stress. The participants are submitted to a sequence of computerized stimuli, such as watching videos, answering survey questions, and making decisions in a realistic office environment. The Galvanic Skin Response (GSR) biosensor monitors emotional arousal in real-time. The experiment design implemented stressors such as visual effects, defacement, unfairness, and time-constraint for the intervention group, followed by decision-making tasks. The results indicate that emotional arousal was statistically significantly higher for the intervention/stress group, considering Shapiro and Mann-Whitney tests. The work indicates that GSR is a reliable stress detector and may be useful to predict negative impacts on executive professionals during decision-making activities.
Number: 1

Neurofinance: Exploratory Analysis Stock Trader's Decision-Making Process by Real-Time Monitoring of Emotional Reactions - Hsu, Hsin-Tzu; Marques, João Alexandre Lobo (European Conference on Management Leadership and Governance, 2023)
Human emotions can be associated with decision-making, and emotions can generate behaviors. Due to the fact that it could be biased and exhaustively complex to examine how human beings make choices, it is necessary to consider relevant groups of study, such as stock traders and non-traders in finance. This work aims to analyze the connection between emotions and the decision-making process of investors and non-investors submitted to the same set of stimuli to understand how emotional arousal might dictate the decision process. Neuroscience monitoring tools such as Real-Time Facial Expression Analysis (AFFDEX), Eye-Tracking, and Galvanic Skin Response (GSR) were adopted to monitor the related experiments of this paper and its accompanying analysis process. Thirty-seven participants attended the study, 24 were classified as stock traders, and 13 were non-traders; the mean age for the groups was 35 and 25, respectively. The designed experiment initially disclosed a thought-provoking result between the two groups under the certainty and risk-seeking prospect theory; there were more risk-takers among non-investors at 75%, while investors were inclined toward certainty at 79.17%. The implication could be that the non-investing individuals were less complex in thought and therefore pursued higher returns besides a high probability of losing the game. In addition, the automatic emotion classification system indicates that when non-investors confronted a stock trending chart beyond their acquaintance or knowledge, they were psychologically exposed to fear, anger, sadness, and surprise. On the contrary, investors were detected with disgust, joy, contempt, engagement, sadness, and surprise, where sadness and surprise overlapped in both parties. Under time pressure conditions, 54.05% of investors or non-investors tend to make decisions after the peak(s) of emotional arousal. Variations were found in the deciding points of the slopes: 2.70% were decided right after the peak(s), 37.84% waited until the emotions turned stable, and 13.51% were determined as the emotional indicators started to slide downwards. Several combinations of emotional responses were associated with decisions. For example, negative emotions could induce passive decision-making, in this case, to sell the stock; nevertheless, it was also examined that as the slope slipped downwards to a particular horizontal point, the individuals became more optimistic and selected the "BUY" option. Future works may consider expanding the study to larger sample size, different demographic groups, and other biometrics for further analysis and conclusions.
Number: 1

Neuromarketing: Evaluating Consumer Emotions and Preferences to Improve Business Marketing Management - Zeng, Ian Mei; Marques, João Alexandre Lobo (European Conference on Management Leadership and Governance, 2023)
The invention of neuroscience has benefited medical practitioners and businesses in improving their management and leadership. Neuromarketing, a field that combines neuroscience and marketing, helps businesses understand consumer behaviour and how they respond to advertising stimuli. This study aims to investigate the consumer purchase intention and preferences to improve the marketing management of the brand, based on neuroscientific tools such as emotional arousal using Galvanic Skin Response (GSR) sensors, eye-tracking, and emotion analysis through facial expressions classification. The stimuli for the experiment are two advertisement videos from the Macau tea brand “Guanding Teahouse” followed by a survey. The experiment was conducted on 40 participants. 76.2% of participants that chose the same product in the first survey responded with the same choice of products in the second survey. The GSR peaks in video ad 1 measured a total of 60. On the other hand, video ad 2 counted a total of 55 GSR peaks. The emotions in ad1 and ad2 have similar responses, with an attention percentage of 76%. The results showed that ad1 has a higher engagement time of 11.1% and ad2 has 9.6%, but only 19 of the respondent’s conducted engagement in video ad1, and 31 showed engagement in video ad2. The results demonstrated that although ad 1 has higher engagement rates, the respondents are more attracted to video ad 2. Therefore, ad2 has better marketing power than ad 1. Overall, this study bridges the gap of no previous research on measuring tea brand advertisements with the neuroscientific method. The results provide valuable insights for marketers to develop better advertisements and marketing campaigns and understand consumer preferences by personalising and targeting advertisements based on consumers' emotional responses and behaviour of consumers' purchase intentions. Future research could explore advertisements targeting different demographics.
Number: 1

The Tully-Fisher law and dark matter effects derived via modified symmetries - Arraut, Ivan (Europhysics Letters, 2023)
In any physical system, when we move from short to large scales, new spacetime symmetries emerge which help us to simplify the dynamics of the system. In this letter we demonstrate that certain variations on the symmetries of general relativity at large scales generate the effects equivalent to dark matter ones. In particular, we reproduce the Tully-Fisher law, consistent with the predictions proposed by MOND. Additionally, we demonstrate that the dark matter effects derived in this way are consistent with the predictions suggested by MOND, without modifying gravity.

Post-disaster Temporary Housing System based on Generative Design Method - Afonso, Filipe G.; Lu, Jun C. (International Journal of Structural and Civil Engineering Research, 2021)

Pathophysiological, cardiovascular and neuroendocrine changes in hypertensive patients during the hemodialysis session - Gutiérrez-Adrianzén, O. A.; Moraes, M. E. A.; Almeida, A. P.; Lima, J. W. O.; Marinho, M. F.; Marques, A. L.; Madeiro, J. P. V.; Nepomuceno, L.; da Silva Jr, J. M. S.; Silva Jr, G. B.; Daher, E. F.; Rodrigues Sobrinho, C. R. M. (Journal of Human Hypertension, 2015)
The pathophysiological mechanisms of arterial hypertension during hemodialysis (HD) in patients with end-stage renal disease (ESRD) are still poorly understood. The aim of this study is to investigate physiological, cardiovascular and neuroendocrine changes in patients with ESRD and its correlation with changes in blood pressure (BP) during the HD session. The present study included 21 patients with ESRD undergoing chronic HD treatment. Group A (study) consisted of patients who had BP increase and group B (control) consisted of those who had BP reduction during HD session. Echocardiograms were performed during the HD session to evaluate cardiac output (CO) and systemic vascular resistance (SVR). Before and after the HD session, blood samples were collected to measure brain natriuretic peptide (BNP), catecholamines, endothelin-1 (ET-1), nitric oxide (NO), electrolytes, hematocrit, albumin and nitrogen substances. The mean age of the studied patients was 43±4.9 years, and 54.6% were males. SVR significantly increased in group A (P<0.001). There were no differences in the values of BNP, NO, adrenalin, dopamin and noradrenalin, before and after dialysis, between the two groups. The mean value of ET-1, post HD, was 25.9 pg ml−1 in group A and 13.3 pg ml−1 in group B (P=<0.001). Patients with ESRD showed different hemodynamic patterns during the HD session, with significant BP increase in group A, caused by an increase in SVR possibly due to endothelial dysfunction, evidenced by an increase in serum ET-1 levels.
Number: 6
Keywords: End-stage renal disease; Haemodialysis; Hypertension

Quality of life during the pandemic: a cross sectional study about attitude, individual perspective and behavior change affecting general population in daily life - Khatoon, F.; Kumar, M.; Khalid, A. A.; Alshammari, A. D.; Khan, F.; Alshammari, R. D.; Balouch, Z.; Verma, D.; Mishra, P.; Abotaleb, M.; Makarovskikh, T.; El-kenawy, E. M.; et al. (IET Digital Library, 2022)
Quality of life in general population before and during pandemic is topic need to be address by researcher in terms of mobility, self-care, usual activities, pain/discomfort and anxiety/depression. The study was carried out among Saudi population. Data were collected from general population using questionnaire during the period from 22 August 2021 to 10th January 2022. As a result, total 214 participants have included in this study. Among them prevalent age group include 40 years (n= 63, 29.4%) shadowed by the age group 25-35 (n= 61, 28.5%) while above 60 years group were least frequent (n= 1, 0.5%). On questioning the applicants whether they were satisfied with their health and how would they rate their quality of life, their answers were as follows: yes, or satisfied (n= 86, 40.2%), very Satisfied (n= 102, 47.7%) Dissatisfied (n= 11, 5.1%) and neither satisfied nor dissatisfied (n= 15, 7%). Due to pandemic, they were rate quality of life very good (n= 94, 43.9%), good (n= 63, 29.4 %) poor (n= 5, 2.3 %) and neither good and nor poor (n= 52, 24.3 %). During pandemic 96 participants feel no change in their weight but 110 participants respond that there is increase in coffee intake during the pandemic. Similarly increased in smoking habits and decrease rate in social activities (n=119,41.4%). The psychosomatic well-being of people has been interrupted by disturbing their social activities during pandemic.

Acceptance of Insects as Food: An Exploratory Study of Young Consumers in Macau - Lampo, Alessandro; Sun, Hou Tong (Indian Journal of Entomology, 2023)
Substitute foods are increasingly popular to reduce our environmental footprint and promote food security. As the world population is expected to grow and food resources become scarce, insects as food have recently gained attention as a viable alternative. In the present study, a model grounded on the Theory of Planned Behavior (TPB) is proposed and analyzed through structural equation modeling software (SmartPLS) to assess consumers intentions toward insects as food. Except for subjective norm, both attitude and perceived behavioral control were key determinants of intention and, in turn, of actual use behaviour. Despite insects being consumed in nearly 1/4 of the sample (for instance in Chinese medicine), the study found that respondents were on average relatively unwilling to use them as a dietary habit. Also, it appeared that men were more likely to consume insects as food than women. The insights of our study have important implications for practitioners and policymakers seeking to promote sustainable nutritional practices among consumers. This study is particularly relevant for Macau, as the city positions itself as a "UNESCO Creative City of Gastronomy" with the aim to develop internationally a unique and sustainable food image.

Pope John Paul II, ‘Memory and Identity: conversations at the dawn of a millennium’ - Morgan, Stephen (Memory and Identity: the proceedings of the 28th ASEACCU Annual Conference, 2023)

The Roman Mass: From Early Christian Origins to Tridentine Reform by Uwe Michael Lang - Morgan, Stephen (Antiphon: A Journal for Liturgical Renewal, 2023)

Influencing Companies’ Green Governance Through the System of Legal Liability for Environmental Infractions in China and Brazil: Lighting the Way Toward BRICS Cooperation - Wei, D.; Rafael, Ângelo Patrício (BRICS Law Journal, 2023)
Peer-rewieved journal
Number: 2

China’s Approach to Sustainable Development in Free Trade Agreements - Wei, Dan; Rafael, Ângelo Patrício (Law and Development Review, 2023)
The question of how to adequately integrate environment and labor provisions in free trade agreements is still a difficult one for both States and academicians. This article explores China’s approach to environment and labor issues in free trade agreements. For reference and comparison, it relies on the European Union’s and the United States’ approaches in their respective FTAs. The article identifies China’s preference for a case-by-case approach to the inclusion of environmental chapters in its FTAs. Additionally, in most FTAs it avoids to include provisions on labor standards. These two preferences represent major divergences from the European Union’s and the United States’ approaches, characterized by inclusion of chapters on environment and labor in all their modern FTAs. The article also finds that China’s FTAs rely solely on consultations and cooperation for the implementation of environmental and labor provisions, within the framework of Joint Committees and avoid the inclusion of civil society mechanisms. Moreover, resolution of disputes relies exclusively on consultations, in a diverse procedure than the one applicable to trade disputes. Despite alignment with the European Union model, this is another major point of divergence with the United States’ model, which applies the same enforcement mechanism for both environment and labor issues and trade issues and includes the possibility of applying sanctions. Finally, the article concludes that China’s options with regards to the treatment of environment and labor concerns in its free trade agreements aligns with both its domestic governance approach and its approach to international cooperation.
Keywords: China; environment and trade; free trade agreements; labor and trade; sustainable development

Gauge symmetries and the Higgs mechanism in Quantum Finance - Arraut, Ivan (Europhysics Letters, 2023)
By using the Hamiltonian formulation, we demonstrate that the Merton-Garman equation emerges naturally from the Black-Scholes equation after imposing invariance (symmetry) under local (gauge) transformations over changes in the stock price. This is the case because imposing gauge symmetry implies the appearance of an additional field, which corresponds to the stochastic volatility. The gauge symmetry then imposes some constraints over the free parameters of the Merton-Garman Hamiltonian. Finally, we analyze how the stochastic volatility gets massive dynamically via Higgs mechanism.

Actio Ecclesiae: The Participation of the Lay Christian Faithful in the Liturgy of the Hours (c. 1174 Sec. 2) - Law, Cyril Jerome (The Jurist: Studies in Church Law and Ministry, 2023)

Enhancing Health and Public Health through Machine Learning: Decision Support for Smarter Choices - Rodrigues, Pedro Miguel; Madeiro, João Paulo; Marques, João Alexandre Lobo (Bioengineering, 2023)
In recent years, the integration of Machine Learning (ML) techniques in the field of healthcare and public health has emerged as a powerful tool for improving decision-making processes [...]
Number: 7
Keywords: n/a

LatinX in AI research - Banda, Juan M.; Ruiz-Garcia, Ariel; Montoya, Laura N.; Arraut, Ivan (Neural Computing and Applications, 2023)
We are delighted to present this special issue editorial for Neural Computing and Applications special issue on LatinX in AI research. This special issue brings together a collection of articles that explore machine learning and artificial intelligence research from various perspectives, aiming to provide a comprehensive and in-depth understanding of what LatinX researchers are working on in the field. In this editorial, we will introduce the overarching theme of the special issue, highlight the significance of the selected papers, and offer insights into the contributions made by the authors. The LatinX in AI organization was launched in 2018, with leaders from organizations in Artificial Intelligence, Education, Research, Engineering, and Social Impact with a purpose to together create a group that would be focused on “Creating Opportunity for LatinX in AI.” The main goal is to increase the representation of LatinX professionals in the AI industry. LatinX in AI Org and programs are volunteer-run and fiscally sponsored by the Accel AI Institute, 501(c)3 Non-Profit.

The Hawking Radiation in Massive Gravity: Path Integral and the Bogoliubov Method - Arraut, Ivan; Segovia, Carlos; Rosado, Wilson (Universe, 2023)
We prove the consistency of the different approaches for deriving the black hole radiation for the spherically symmetric case inside the theory of Massive Gravity. By comparing the results obtained by using the Bogoliubov transformations with those obtained by using the Path Integral formulation, we find that in both cases, the presence of the extra-degrees of freedom creates the effect of extra-particles creation due to the distortions on the definitions of time defined by the different observers at large scales. This, however, does not mean extra-particle creation at the horizon level. Instead, the apparent additional particles perceived at large scales emerge from how distant observers define their time coordinate, which is distorted due to the existence of extra-degrees of freedom.
Number: 5
Keywords: Bogoliubov transformation method; Hawking radiation; Massive Gravity; Path Integral method; extra-degrees of freedom

Book Review: ‘The Catholic Invasion of China: Remaking Chinese Christianity’, by D. E. Mungello (Lanham, MD: Rowman & Littlefield, 2015) - Law, Cyril Jerome (Heythrop Journal, 2018)

Minimising Maximum Illud: Early Resistance to Missionary Inculturation in China - Law, Cyril Jerome (Orientis Aura: Macau Perspectives in Religious Studies, 2022)

Neuromarketing and Global Branding Reaction Analysis Based on Real-Time Monitoring of Multiple Consumer's Biosignals and Emotions - Goncalves, Marcus; Lobo Marques, Joao Alexandre; Silva, Bruno Riccelli Santos; Luther, Valorie; Hayes, Sydney (Journal of International Business and Management, 2023)
Consumers' selections and decision-making processes are some of the most exciting and challenging topics in neuromarketing, sales, and branding. From a global perspective, multicultural influences and societal conditions are crucial to consider. Neuroscience applications in international marketing and consumer behavior is an emergent and multidisciplinary field aiming to understand consumers' thoughts, reactions, and selection processes in branding and sales. This study focuses on real-time monitoring of different physiological signals using eye-tracking, facial expressions recognition, and Galvanic Skin Response (GSR) acquisition methods to analyze consumers' responses, detect emotional arousal, measure attention or relaxation levels, analyze perception, consciousness, memory, learning, motivation, preference, and decision-making. This research aimed to monitor human subjects' reactions to these signals during an experiment designed in three phases consisting of different branding advertisements. The nonadvertisement exposition was also monitored while gathering survey responses at the end of each phase. A feature extraction module with a data analytics module was implemented to calculate statistical metrics and decision-making supporting tools based on Principal Component Analysis (PCA) and Feature Importance (FI) determination based on the Random Forest technique. The results indicate that when compared to image ads, video ads are more effective in attracting consumers' attention and creating more emotional arousal.

From Maximum Illud 1919 to the First National Synod Primum Concilium Sinensis 1924 in Shanghai: Historical & Theological Perspectives - Gassner, Franz (Orientis Aura: Macau Perspectives in Religious Studies, 2022)

Diagnóstico à literacia da informação de estudantes de ensino superior: um estudo de caso em Macau - Chan, Emily; Sanches, Tatiana (Actas do Congresso Nacional de Bibliotecários, Arquivistas e Documentalistas, 2023)
O presente estudo faz parte de uma investigação mais alargada que pretende i) estudar, numa população estudantil de ensino superior, as suas necessidades e comportamento perante a informação e ii) desenvolver um programa de formação em literacia da informação, integrando este conhecimento e os contributos dos diversos intervenientes (estudantes, docentes, bibliotecários). Sabemos hoje que a integração da literacia da informação nas aprendizagens melhora o desempenho dos estudantes e que, por esse motivo, os bibliotecários académicos podem desempenhar um papel importante ao colaborarem no desenho e formação de programas nestas áreas. Esta comunicação apresenta a primeira fase deste estudo. Trata-se da aplicação de um inquérito por questionário a uma população de estudantes de graduação, no ensino superior, em Macau. Os resultados demonstram as perceções dos estudantes relativamente às suas necessidades de informação, bem como o uso dos recursos informativos preferidos na prossecução dos seus estudos. A formação destes estudantes na pesquisa, recuperação, análise e uso da informação parece ser essencial. A construção de programas de formação em literacia da informação deve ser concebida à medida, recorrendo-se a um diagnóstico próximo e efetivo. A par, é importante continuar a desenvolver ambientes físicos e virtuais que disponibilizem informação credível e que deem resposta às necessidades informacionais dos que os utilizam, apoiando a aprendizagem.
Number: 14
Keywords: Estudantes

China’s Aid policy approach to Poverty Alleviation in the recipient country: A Case study of the Republic of Guinea - Diakite, Ansoumane Douty (Journal of Social Studies (JSS), 2023)
This paper examines the extent to which China’s aid policies integrate poverty alleviation as a goal of their aid in general, particularly in Guinea. More specifically, the paper analyzed how aid donors focus on poverty alleviation and which policies and mechanisms are in place to address poverty in the countries receiving aid. Regarding the methodology, the author collected data from secondary sources, including government declarations of donors, policy documents at both the donor and recipient levels, as well as from scholarly publications. The following findings resulted from study: China’s aid policies have progressively incorporated poverty alleviationobjectives and identified sectors for intervention against poverty. However, the limitations of China approach to poverty is that China adopts a top-down approach to poverty reduction and lacks of an impact evaluation mechanism based on poverty alleviation.
Number: 1
Keywords: Aid policy; China; Guinea; Poverty alleviation; Strategy

The role of environmental concern and technology show-off on electric vehicles adoption: the case of Macau - Lampo, Alessandro; Silva, Susana C.; Duarte, Paulo (International Journal of Emerging Markets, 2025)
Purpose Research on battery electric vehicles (BEVs) has typically considered environmental concern a key determinant of behavioral intention that leads individuals to prefer electric vehicles. This paper challenges this assumption and argues that technology frameworks may require new variables to capture consumers' preferences. A UTAUT2-based study has been developed to assess the role of environmental concern in the BEVs context and put forward the technology show-off (TS) concept to explain the technology's acceptance. Design/methodology/approach A quantitative and cross-sectional look at behavioral intention is adopted. The study uses structural equation modeling to analyze a sample of 236 Macau residents to determine the relevance of the factors behind the choice to adopt BEVs. Findings The findings indicate that environmental concern and price may be relevant to explain behavioral intention to adopt the BEVs technology. Furthermore, the UTAUT2 framework seems to benefit from adding new variables, with TS playing a pertinent role in explaining technology acceptance. Social implications The findings show that environmental concern fails to build an argument for the shift to full electric mobility and promote the desired behavioral change toward adopting BEVs. Herein lies the necessity to consider new variables that can better describe the characteristics of modern society. Originality/value This paper proposes the TS construct, combining visibility and trialability as significant determinants of behavioral intention to use technology. The study also stresses the need to reconsider the role of environmental concerns' impact on consumer decision-making.

Occurrence and precipitation mechanism of silver in pyrite from chimney fragments in the Edmond hydrothermal field, Central Indian Ridge - Zhang, Huichao; Chen, Kean; Tao, Chunhui; Alveirinho Dias, Ágata; Liang, Jin; Yang, Weifang; Liao, Shili; An, Fang; Yin, Bohao; Sun, Chuanqiang (Ore Geology Reviews, 2023)

Coral empire: underwater oceans, colonial tropics, visual modernity: by Ann Elias Durham: Duke University Press, 2019, 296 pages ISBN: 9781478003182 (hbk) 99.95 USD, 9781478003823 (pbk) 26.95 USD, 9781478004462 (ebook) 26.95 USD - Zuev, Dennis (Visual Studies, 2023)

Exploratory Research on Key Technology of Human-Computer Interactive 2.5-Minute Fast Digital Early Warning for Mild Cognitive Impairment - Li, Nan; Yang, Xiaotong; Du, Wencai; Ogihara, Atsushi; Zhou, Siyu; Ma, Xiaowen; Wang, Yujia; Li, Shuwu; Li, Kai (Computational Intelligence and Neuroscience, 2022)
Objective. As the preclinical stage of Alzheimer’s disease (AD), Mild Cognitive Impairment (MCI) is characterized by hidden onset, which is difficult to detect early. Traditional neuropsychological scales are main tools used for assessing MCI. However, due to its strong subjectivity and the influence of many factors such as subjects’ educational background, language and hearing ability, and time cost, its accuracy as the standard of early screening is low. Therefore, the purpose of this paper is to propose a new key technology of fast digital early warning for MCI based on eye movement objective data analysis. Methodology. Firstly, four exploratory indexes (test durations, correlation degree, lengths of gaze trajectory, and drift rate) of MCI early warning are determined based on the relevant literature research and semistructured expert interview; secondly, the eye movement state is captured based on the eye tracker to realize the data extraction of four exploratory indexes. On this basis, the human-computer interactive 2.5-minute fast digital early warning paradigm for MCI is designed; thirdly, the rationality of the four early warning indexes proposed in this paper and their early warning effectiveness on MCI are verified. Results. Through the small sample test of human-computer interactive 2.5 fast digital early warning paradigm for MCI conducted by 32 elderly people aged 70–90 in a medical institution in Hangzhou, the two indexes of “correlation degree” and “drift rate” with statistical differences are selected. The experiment results show that AUC of this MCI early warning paradigm is 0.824. Conclusion. The key technology of human-computer interactive 2.5 fast digital early warning for MCI proposed in this paper overcomes the limitations of the existing MCI early warning tools, such as low objectification level, high dependence on professional doctors, long test time, requiring high educational level, and so on. The experiment results show that the early warning technology, as a new generation of objective and effective digital early warning tool, can realize 2.5-minute fast and high-precision preliminary screening and early warning for MCI in the elderly.

Learning dynamics of kernel-based deep neural networks in manifolds - Wu, Wei; Jing, Xiaoyuan; Du, Wencai; Chen, Guoliang (Science China Information Sciences, 2021)

An Improved Dual-Channel Deep Q-Network Model for Tourism Recommendation - Liang, Shengbin; Jin, Jiangyong; Ren, Jia; Du, Wencai; Qu, Shenming (Big Data, 2023)
Keywords: context-aware; deep reinforcement learning; dual-channel; tourism recommendation

Editorial - Castro, Maria Guilhermina; Palinhos, Jorge; Ribas, Daniel; Caires, Carlos Sena (Journal of Science and Technology of the Arts, 2017)
Number: 2

Design for Classroom Units: A Collaborative Multicultural Studio Development with Chinese Students - Caires, C. S.; Barbosa, A.; Hanyou, W. (International Journal of Educational and Pedagogical Sciences, 2020)
Design for Classroom Units: A Collaborative Multicultural Studio Development with Chinese Students

An Attempt to Examine Digital Native and Digital Immigrant Macau Graphic Designers' Perceptions of Adopting Generative Design - Lau, Ching Man; Caires, Carlos Sena (International Journal of Creative Interfaces and Computer Graphics (IJCICG), 2022)
The manifestation of generating digital visuals through an algorithm is gaining worldwide attention in the graphic design industry. It is a new form of computing that visualizes data input by the designer or collected in the physical environment and turns them into artwork. The generative design of...

Editorial Preface - Marcos, Aderito; Caires, Carlos; Estadieu, Gerald; Mendes, Daniel; Rodrigues, Nuno (International Journal of Creative Interfaces and Computer Graphics, 2023)

An Integrated Learning Platform Focusing on STEAM and Collaborative Modules for Macau - Cheng, Un Man; Martins de Abreu, F. (International Journal of Creative Interfaces and Computer Graphics (IJCICG), 2022)
In Macau, the effectiveness of traditional classroom learning is questioned as the problem is discovered by the changes in technology advances, social media, and the varieties of learning methods. Learning experiences, interests, discoveries, and creativity development are considered essential to ac...

Multimodal Game Design Framework for Creativity in Macau's Educational System Through Digital and Tangible Games: Chinese, Portuguese, and English Languages - Martins de Abreu, F.; Barbosa, Álvaro Mendes (International Journal of Creative Interfaces and Computer Graphics (IJCICG), 2022)
Creativity and collaboration are crucial to learning development in today's fast-paced educational environment. New technology can bridge humans and their natural needs through immersion in digital environments with physical objects. As knowledge and information evolve, digital interactive experienc...

The Chinese Diaspora in Mozambique - Morais, Isabel (Singapore: The Chinese Heritage Centre Bulletin, 2005)

Smallpox Vaccinations and the Portuguese in Macao - Morais, Isabel (Review of Culture, 2006)

O Sonho e o Desejo Libertários da "Lusa Macaense" Lee Li-Lyang: O Heterónimo Feminino na poética de Virgílio De Lemos", - Morais, Isabel Maria da Costa (Entre a Desmistificação e a utopia: Indagação sobre as Lusofonias , Macau: University of Saint Joseph.69-95, 2014)
Virgílio de Lemos (1929-2013), poeta de vanguarda, é um dos precursores da modernidade e experimentalismo como criador do “barroco estético” que ele próprio designou como a linguagem poética marcante nas letras moçambicanas no das décadas de 50 e 60

Macao Caught between the "Tropical China" and Oriental-style: An Approach to the Colonial and Post-colonial Contexts/Macau entre a "China Tropical" e a lusofonia a Oriente: Algumas achegas sobre os contextos colonial e pos-colonial/Macao entre la "Chine tropicale" et la lusophonie a l'orientale: contribution a l'etude des contextes colonial et post-colonial. - Morais, Isabel (Portuguese Studies Review, 2018)
Gale OneFile includes Macao Caught between the "Tropical China&q by Isabel Morais. Click to explore.

Negative affect among undergraduates: Why are higher levels reported by Asian students?: Negative affect in Asian undergraduates - Found, Andrew; Cheong, Hoi Ieng; Duarte, Carlos (Asia-Pacific Psychiatry, 2012)

The Emergence of Resources Seeking Chinese Firms’ Specific Advantages in Emerging Market - Ojo, Olukayode Iwaloye; Im, Hong Kei; Adeniyi, Damilola Olarewaju; Gbadamosi, Ayantunji; Alves, Jose; Link to external site, this link will open in a new window; Trimarchi, Michael (Sustainability, 2022)
It is argued that the role of the Chinese government to support the cross-border operations of Chinese firms is to assist these firms in overcoming their limited established brands, and their disadvantages in technology and managerial resources, which were also the reasons why such firms decided to enter emerging markets instead of developed markets. This strategic choice is preferred to avoid direct confrontation with established firms from developed countries endowed with superior ownership advantages. Therefore, Chinese resources seeking firms innovate by increasing investment in developing and emerging markets to develop unique ownership advantages for sustainable market development and competitive advantage. This research investigates the ownership advantages of resources seeking Chinese firms in these markets using the OLI theory. The paper contributes to explaining the specific advantages of Chinese MNEs when entering emerging markets. The study applied a two-stage qualitative methodology to examine Chinese firms operating in Nigeria. The first stage included an exploratory study based on interviews with key informants and experts while the second stage included a case study methodology. The study focused on resources seeking Chinese MNEs operating in Nigeria.
Num Pages: 8345 Place: Basel, Switzerland
Keywords: OLI theory and Chinese firms; emerging markets; ownership advantages; resources seeking MNEs

Application of D-optimal design for determination of the influence of water content on the thermal degradation kinetics of ascorbic acid at low water contents - Frías, Jesús M.; Oliveira, Jorge C.; Cunha, Luís M.; Oliveira, Fernanda A. (Journal of Food Engineering, 1998)
The kinetics of thermal degradation of ascorbic acid was studied in a Maltodextrin matrix at different temperatures between 75 and 140 °C. Isothermal experiments were performed with samples earlier equilibrated in environments of known aw at 4 °C, enclosed in hermetically sealed vials, with water contents (w) between 0.17 and 1.68 g water/g solids. Sampling times were selected according to an optimal experimental design in terms of minimum confidence regions of the parameters estimated, using the Bigelow model and estimates from preliminary experiments. The results showed a quadratic dependence of the reference D-value and linear dependence of the z-value with moisture content: Dr(140 °C) = 150.07 − 290.73w + 269w2 (min); z = 12.14 + 22.99w (°C) and showed the applicability of D-optimal designs for determining kinetic parameters in complex situations, with limited experimental requirements. The dependence of the rate constants with water content could not be described by the WLF model in qualitative terms, although in absolute values this model could be used with constants similar to those expected from glass transition theory. The thermodynamic analysis of the results showed a good application of the compensation theory in the whole range of water contents.

Publishing mathematics on the World Wide Web - Majewski, M. (Journal of Computer Assisted Learning, 1999)
This paper shows how mathematical concepts can be displayed on World Wide Web pages. A few of the most interesting solutions are outlined although a few others are missing and a few more will be invented very soon. It is for authors to decide which system is the most suitable for their purposes.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1046/j.1365-2729.1999.152086.x

Kinetics of the adsorption of bovine serum albumin contained in a model wine solution by non-swelling ion-exchange resins - Sarmento, M. R.; Oliveira, J. C.; Slatner, M.; Boulton, R. B. (Journal of Food Engineering, 1999)
Adsorption of wine proteins is an essential step in the production of white and rosé wines. In order to develop environmentally friendly adsorption processes, non-swelling adsorbents are required. The performance of selected non-swelling ion-exchange resins (Macro-Prep™ 50S and Streamline® SP) was studied by describing the process kinetics of the adsorption of BSA in a model wine solution. The process was assumed to be diffusion controlled and a shrinking core model was applied. Experiments were performed in the 5–35°C temperature range and with different equilibrium partition coefficients. The results obtained with the shrinking core model were theoretically consistent and the apparent diffusivity values correlated very well with theoretically estimated effective diffusivities combined with a linear dependence of porosity with temperature. Separating the temperature effect on porosity, the apparent diffusivity followed an Arrhenius type dependency with temperature with 16.9 kJ/mole activation energy.
Keywords: Diffusion; Mass transfer; Protein adsorption; Wine stability

Influence of pH and high pressure on the thermal inactivation kinetics of horseradish peroxidase - Lemos, Maria Adília; Oliveira, Jorge C.; Hendrickx, Marc E: (Food Biotechnology, 1999)
The inactivation kinetics of horseradish peroxidase were determined at several values of pH (3, 4, 7, 9 and 10), temperature (40 to 70 °C) and pressure (7, 8 and 9 kbar). The data were obtained by taking samples from the moment that pressure inside the hydrostatic high pressure vessels reached the value specified, and therefore relate to isothermal and isobaric conditions. The inactivation kinetics were non‐log linear and could be individually well described by the conventional two‐fraction model, but the overall consistency of the kinetic parameters of this model was poor and the model was clearly not robust. Inversely, the kinetic model based on the Weibull probability distribution function yielded good individual fits and also a good overall consistency of the kinetic parameters. The whole set of 327 data points could be well described by an overall model considering that the shape parameter (ß) varied with pressure but not with temperature and that the rate parameter (1/α) varied with temperature according to an Arrhenius law, with a pressure‐independent activation energy, and varied exponentially with pressure. The activation energy and the pressure‐sensitivity parameter did not vary with pH up to pH 9. The results suggested a discontinuity of the kinetic behaviour at pH 10, with a different inactivation mechanism prevailing.
_eprint: https://doi.org/10.1080/08905439609549959
Keywords: enzyme barostability; enzyme inactivation; kinetic modeling; protein denaturation

Measurement of glass transition in native wheat flour by dynamic mechanical thermal analysis (DMTA) - Pereira, Pedro M.; Oliveira, Jorge C. (International Journal of Food Science & Technology, 2000)
This work describes a method to study glass transition on native starch powders, based on dynamical mechanical thermal analysis using compression tests, and was applied to wheat flour (13.5% water content). This method will allow the determination of Tg in native (unprocessed) starchy materials, with minimal disturbance of the natural structures. The influence of the test conditions (heating rate, frequency and strain) on the glass transition measurements was determined using factorial designs. The values of Tg determined as the maxima of the energy dissipation (peaks in E″) of native flour and of freeze-dried pre-gelatinized flour were not statistically different (around 64 °C). The heating rate did not affect the measurements in the range tested (0.25 to 1 °C min−1). An interactive effect of the strain amplitude and the frequency was detected. The significance of this interaction can be caused by differences in mechanical energy dissipation, which would indicate that not only temperature but also the total energy input may affect this transition. Slight effects of phase separation between gluten and starch were found on native flour.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1046/j.1365-2621.2000.00289.x
Keywords: Phase transitions; starch; viscoelastic properties

Selection of low swelling materials for protein adsorption from white wines - Sarmento, Miguel R.; Oliveira, Jorge C.; Boulton, Roger B. (International Journal of Food Science & Technology, 2000)
The protein adsorption capacity of different materials was evaluated to assess their potential efficacy as alternative adsorbents for the removal of proteins from wines, with the purpose of finding suitable low-swelling materials that could be used in a percolated bed. The adsorbents tested were thermally treated sodium bentonite, low-swelling adsorbing clays, ion exchange resins and other protein adsorbents (silica gel, hydroxyapatite and alumina). The materials were evaluated by analysing both the capacity to stabilize untreated white wines, according to a heat test, and by characterizing the adsorption isotherms of bovine serum albumin (BSA) in a model wine (water, ethanol and K-bitartrate). Breakthrough curves in a packed bed were determined experimentally for some materials, showing the influence of the adsorption isotherm shape. Some ion-exchange resins showed a favourable behaviour and have good potential as alternative adsorbents.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1046/j.1365-2621.2000.00340.x
Keywords: Bentonite; percolated beds; sorption isotherms; wine stability

Burnout and Service Employees' Willingness to Deliver Quality Service - Humborstad, Sut I W; Humborstad, Bjarte; Whitfield, Richard (Journal of Human Resources in Hospitality & Tourism, 2007)
Employees are vital for enhancing customer satisfaction and loyalty in service organizations because their proactive involvement is an essential part of delivering the services offered. With the recent rapid growth of tourism in the Macau SAR, service employee workloads are clearly increasing, and consequently one would expect that the incidence of job burnout is rising. This study uses the well-known Maslach Burnout Inventory (MBI) to investigate the relationship between service employees' burnout and their willingness to deliver quality services. Self-administered questionnaires from 110 operational staff in three hotels in Macau have been analyzed. The results indicate that job burnout reduces staff's willingness to deliver quality services and that this effect is moderated by individual staff's level of affective organizational commitment, and their perceptions of the extent of organizational and supervisor support provided by the organization. Based on these results, practical managerial strategies to improve service performance are identified.
_eprint: https://doi.org/10.1300/J171v07n01_03
Keywords: Job burnout; affective organizational commitment; perceived organizational support; perceived supervisor support; quality service delivery willingness

Implementation of empowerment in Chinese high power-distance organizations - Humborstad, Sut I W.; Humborstad, Bjarte; Whitfield, Richard; Perry, Chad (The International Journal of Human Resource Management, 2008)
The importance of empowerment in service industries is recognized by practitioners and scholars in the West but there has been limited investigation of its impact on the willingness of service personnel in a high power-distance culture. This study examines how empowerment can be facilitated in the high power-distance context of China. Regression and path model analysis using a sample of 290 service employees from six 4-star to 5-star hotels in the Macau SAR China indicate that empowerment positively leads to higher service willingness and this relationship is mediated by performance-based rewards, and organizational and supervisor support. These findings have implications for HR managers considering or using empowerment.
_eprint: https://doi.org/10.1080/09585190802110224
Keywords: empowerment; high power-distance culture; organizational support; performance-based rewards; supervisor support; training

An exploratory study of students' consumption of non‐alcoholic beverages in Nigeria: A qualitative perspective - Gbadamosi, Ayantunji; Olukayode Iwaloye, Ojo; Bamber, David (Nutrition & Food Science, 2009)
Purpose – Given the diversity which exists among various groups of consumers, the purpose of this paper is to explore students' consumption of non‐alcoholic beverages in Nigeria. Design/methodology/approach – Three focus groups and 20 in‐depth interviews were conducted with students in three universities located in Lagos, Nigeria. Findings – Initial findings indicate that these students' consumption of non‐alcoholic beverages is influenced in many ways. Nevertheless, the most striking of these influences are found to be convenience of purchase, along with availability, price, health concerns, and culture/social reasons. Originality/value – The main contribution of the study lies in the relevance of segmentation, targeting, and positioning activities of business organisations in respect of marketing of non‐alcoholic beverages. Based on the findings, the empirical study will serve as a valuable input to marketers in their planning, analysis, and implementation of appropriate marketing strategies to students vis‐à‐vis the highlighted influences on their consumption of this category of food. It will thus serve as a tool for creating competitive advantage in this prevailing volatile business environment.
Keywords: Consumer behaviour; Nigeria; Non‐alcoholic drinks; Students

Use of CALMS to enrich learning in introductory programming courses - Thota, Neena (Proceedings of the 17th International Conference …, 2009)
Use of CALMS to enrich learning in introductory programming courses

Complexities of Languages and Multilingualism - Baragül, Fernando (Educational Challenges in Multilingual Societies, ed. Zubeida Desai et al., 2010)
Complexities of Languages and Multilingualism

Subjective Wellbeing in China: A Review - Davey, Gareth; Rato, Ricardo (Journal of Happiness Studies, 2012)
We critically review studies of subjective wellbeing conducted in China by the International Wellbeing Group, and we evaluate the International Wellbeing Index (IWI), a new instrument they developed. Subjective wellbeing was positive and similar in studies across China, and conformed to the normative range. Its resilience (PWI = 61.2–67.1) mirrors survey findings conducted in Western countries, in agreement with Subjective Wellbeing Homeostasis. Reliability, validity and psychometric analyses support the utility of the IWI as a measure of subjective wellbeing. Our conclusions have implications for research and social development in China, discussed further in this review.
Keywords: China; Happiness; International wellbeing index; Quality of life; Subjective wellbeing

Marian Piety and Ecumenical Convergence: Challenges and Opportunities - Eleutério, JM (Orientis Aura: Macau Perspectives in Religious …, 2017)
In the Catholic world, the year 2017 is marked by the celebration of the 100th anniversary of the Apparitions of Mary in Fátima, Portugal. Although the field of the devotional and popular …

A receção da figura de Melquisedeque na literatura cristã latina - Eleutério, JM (Didaskalia, 2015)
A interpretação da Escritura e das suas diferentes personagens enriquece a Tradição cristã, mas este processo de receção é muitas vezes marcado por debates e polémica …

When the Gospel meets the China Dream: Religious Freedom and the Golden Rule - Chiaretto Yan, Kin Sheung (International Bulletin of Mission Research, 2018)
The issue of religious freedom affects Sino-Vatican relations, but the Roman Catholic Church shares values with Confucianism, which provides common ground for dialogue. Pope Francis is focusing the church outward by promoting a culture of encounter and by working unceasingly for a fraternal dialogue of peace. Chinese president Xi Jinping urges his people to fulfill the China dream, emphasizing the core values of harmony, friendship, and civilization. Many have believed that the Gospel can contribute to China?s spiritual civilization; normalization of relations between China and the Holy See would benefit China and the Catholic Church and contribute to world peace and harmony.

The influence of SAR government performance on people’s trust toward Central government: Implications for Hong Kong and Macau civic education - Chris Cheung, Hin Wah; So, Man Yum Larry; Choi, Chi U. Francis; Chow, Chin Fung Philip (Asian Education and Development Studies, 2018)
Purpose The purpose of this paper is to explore the influence of Special Administrative Region (SAR) performance on the “trust” of Hong Kong and Macau people, who “live” under similar context of “one country, two systems,” toward Beijing Central Government. The different perceptions, relating to the abovementioned issue, of the young peoples’ are also investigated. Implication for civic education in these two societies will be brought to light. Design/methodology/approach This study adopts secondary data analysis on the captioned topic. To further illustrate the said issue, this study reviews and analyzes data from protest campaigns in both societies. Findings This paper finds that the performance of Hong Kong and Macau SAR Governments has different impacts on the peoples’ “trust” toward Central Government. It may attribute to the different perceptions about the role of Central Government and levels of democratization in these societies. Civic education emphasizing the “core spirit” of “One country, two systems,” roles of SAR and Central Governments could enable young people better comprehend their relationship with Mainland China and their role as SAR–Chinese citizens. Originality/value This paper is an exploratory study for providing implications for further research on this topic.
Keywords: Civic education; Political trust

Artificial selection for male winners in the Siamese fighting fish Betta splendens correlates with high female aggression - Ramos, A.; Gonçalves, D. (Frontiers in Zoology, 2019)
In Southeast Asia, males of the Siamese fighting fish Betta splendens have been selected across centuries for paired-staged fights. During the selection process, matched for size males fight in a small tank until the contest is resolved. Breeders discard losing batches and reproduce winner batches with the aim of increasing fight performance. We assessed the results of this long-term selection process by comparing under standard laboratory conditions male and female aggressive behaviour of one strain selected for staged fights (“fighters”) and one strain of wild-types. The aggressive response of adult fish was tested against their mirror image or a size-matched conspecific. Fighter males were more aggressive than wild-type males for all measured behaviours. Differences were not only quantitative but the pattern of fight display was also divergent. Fighter males had an overall higher swimming activity, performing frequent fast strikes in the direction of the intruder and displaying from a distance. Wild-type males were less active and exhibited aggressive displays mostly in close proximity to the stimuli. Females of the fighter strain, which are not used for fights, were also more aggressive than wild-type females. Aggressive behaviours were correlated across male and female fighter siblings, suggesting common genetic and physiological mechanisms to male and female aggression in this species. The study further shows that results were largely independent of the stimulus type, with the mirror test inducing similar and less variable responses than the live conspecific presentation. These results suggest that selection for male winners co-selected for high-frequency and metabolic demanding aggressive display in males and also enhanced female aggression, opening a wide range of testable hypothesis about the ultimate and proximate mechanisms of male and female aggression in B. splendens.
Keywords: Aggression; Artificial selection; Domestication; Mirror test; Sexual conflict

Reawakening Macanese identity: the impact of Chinese outbound tourism - Lou, Lai-Chu Ivy; Xie, Philip Feifan (Journal of Policy Research in Tourism, Leisure and Events, 2020)
The purpose of this paper examines the potential role of Chinese outbound tourism as a catalyst of change for the Macanese identity. There is an emerging trend to have a new identity amongst Macanese residents to valorize cultural and heritage assets. By using Bourdieu’s concept of habitus, it proposes that the social media space is built to voice concerns of language, place attachment and induced public participation. The study utilizes a mixed method approach comprising a survey for netizens and content analysis of online discussions, in order to fully understand changes due to Chinese outbound tourism.
_eprint: https://doi.org/10.1080/19407963.2018.1505106
Keywords: China; Identity; Macau; linguistic sensitivity; place attachment; public participation

Enhancing Student Learning and Teacher Development: Does “Assessment for Learning” Matter? - Ng, Shun Wing; Kwan, Yee Wan; Huey Lei, Ka Hio (International Journal of Educational Reform, 2020)
This paper aims to report a case study of exploring the effect of ?assessment for learning? on improving student learning and facilitating teachers? professional development in the examination-oriented context of Hong Kong. By adopting Variation Theory of the Lesson Study approach, data were collected through pre- and post-tests, interviews with students and teacher participants and observation field-notes in order to help diagnose students? learning difficulties and provide evidence for teachers to refine their teaching strategies to enhance students? learning effectiveness. The students? improvement in learning performance informed the teacher participants of the usefulness of ?assessment for learning? in the classroom.

Mary and Fátima: A Modest C-Inductive Argument for Catholicism - Mcnabb, Tyler Dalton; Blado, Joseph E. (Perichoresis, 2020)
AbstractC-Inductive arguments are arguments that increase the probability of a hypothesis. In this paper, we offer a C-Inductive argument for the Roman Catholic hypothesis. We specifically argue that one would expect the Miracle of Fátima on Roman Catholicism more so than on alternative hypotheses. Since our argument draws on confirmation theory, we first give a primer for how confirmation theory works. We then, provide the historical facts surrounding the Miracle of Fátima. We offer up two competing naturalistic explanations that attempt to explain the historical facts, but then, argue that a supernatural explanation is superior. Having established that something miraculous likely occurred at Fátima, we move to argue for the overall thesis of the paper. Finally, we engage several objections to our argument.

Who has the power? A reflection on teaching drama improvisation with young children - Ho, Ka Lee Carrie (Journal of Early Childhood Research, 2020)
The following study reflects and explores the dynamics of aesthetic experiences within drama improvisations. This arts-based research was carried out in Hong Kong with six Cantonese children who were aged 3?5?years. Data were collected from the video transcripts of five workshops and the researcher?s own research journal. Two significant milieus were observed: switching in-between roles and intuitive creativity is not talkback. I argue that because each of these two milieus provide the foreground for the complex ? and at times contradictory ? nature of children?s aesthetic experiences where Deleuzian power is at play, opportunities arise for both, challenging the traditional adult?child power relations, and in so doing, educators can be able to reconfigure and reconceptualise teaching goals and practices, both generally and specifically, within the context of early childhood education.

Psychometric properties of a Chinese version of the Constructivist Learning Environment Survey among secondary-school students in Hong Kong - Kwan, Yee Wan (Learning Environments Research, 2020)
The study examined the factor structure, reliability and validity of a Chinese version of the Constructivist Learning Environment Survey (C-CLES), an instrument for assessing students’ perceptions of the extent of constructivist approaches prevalent in classrooms. A convenience sample of 967 students in Secondary Three (Grade 9) in Hong Kong participated in this study by completing a self-administered questionnaire in their class time. Exploratory and confirmatory factor analyses supported the hypothesised factor structure, indicating five theoretical constructivist environment dimensions that showed goodness-of-fit to 25 items: Personal Relevance, Uncertainty, Critical Voice, Shared Control, and Student Negotiation. Criterion-related validity, involving evidence based on relations to other variables, was assessed by correlations between the constructivist environment dimensions and cognitive strategies and academic ability. Most correlations were statistically significant and in the positive direction. The C-CLES with 25 items provides a useful measure for educational practice and research among school students.
Keywords: Cognitive outcomes; Constructivist learning environment; Secondary schools; Validation

Inclusive Education Teachers—Strategies of Working Collaboratively With Parents of Children With Special Educational Needs in Macau - Ng, Shun Wing; Kwan, Yee Wan (International Journal of Educational Reform, 2020)
Education for learners with special education needs has become one of the major concerns of education policies in every corner of the world. In Macau, however, the transformation of schools into inclusive environments is reported to be slow because many teachers in Macau have not accepted the key values of inclusive education and possess little knowledge of their responsibilities as inclusive education teachers. Despite being nonempirical, the aim of this article is twofold: to inform inclusive education teachers, especially those in Macau and other developing regions, of the necessary knowledge, skills and strategies of working collaboratively with parents of children with SEN and provide policy makers concerned with practical ideas of designing effective professional development programmes for teachers working in the inclusive environment. The ultimate aim is to ensure that children with SEN benefit from an education process that includes quality learning opportunities.

Unravelling potentials and limitations of sharing economy in reducing unnecessary consumption: A social science perspective - Lai, Michael K. W.; Ho, Amy P. Y. (Resources, Conservation and Recycling, 2020)
Hyper-consumption in capitalist economies has had a severe impact on the environment that no one can escape. In recent year, there has been a high degree of optimism in sharing economy with regard to coping with the environmental problems caused by consumption. However, most of the current literature focuses on business perspectives in which a sharing economy is portrayed as a new business model, but not as a way to curb environmental degradation. This paper, based on a social science perspective, investigates the potentials and limitations of the strategies adopted in sharing economy projects towards social transformation (especially coping with environmental degradation and hyper-consumption), with the adoption of Erik Olin Wright’s concept of real utopia. A case study approach has been adopted in terms of a sharing economy project named ‘Waste-no-mall (Yuen Long)’ in Hong Kong. The project founder embraces ideological-led strategies based on collective responsibility, self-determination and reflexivity, encouraging the participants to reflect on their consumption behaviours, and thus increasing the level of awareness of the need to reduce unnecessary consumption. However, it is a double-edge sword that limits its impact to those who are active participants, without spreading to others the need for change. It is also limited for their interstitial strategies within the project, and is unable to call for a concrete symbiotic transformation when it comes to policy. The significance of this paper is two-fold. First, it adopts a social science perspective that centres on exploring the proclaimed social implications of sharing economy, an aspect which is under-studied given that most of current studies are from a business perspective; second, it extends Wright’s concept to an operational level by showing an important pathway aiming to solve environmental problems through the simultaneous achievement of both horizontal and vertical balancing strategies, based on Wright’s concept of real utopia.
Keywords: Hong Kong; Mindful consumption; Real utopia; Sharing economy; Social transformation

Malacca Portuguese Creole - Pillai, Stefanie; Baxter, Alan N.; Soh, Wen-Yi (Journal of the International Phonetic Association, 2021)
Malacca Portuguese Creole (MPC) (ISO 639-3; code: mcm), popularly known as Malacca Portuguese or locally as (Papiá) Cristang, belongs to the group of Portuguese-lexified creoles of (South)east Asia, which includes the extinct varieties of Batavia/Tugu (Maurer 2013) and Bidau, East Timor (Baxter 1990), and the moribund variety of Macau (Baxter 2009). MPC has its origins in the Portuguese presence in Malacca, and like the other creoles in this subset, it is genetically related to the Portuguese Creoles of South Asia (Holm 1988, Cardoso, Baxter & Nunes 2012).

International collaboration for mutual benefit: a Southwest China and Southeast United States partnership - Jackson, M. Sebrena; Gardell, Debra Nelson; Williams, Javonda; Tang, Ning; Yang, Fan (China Journal of Social Work, 2021)
China’s return to social work education, after a nearly 35-year absence, opened the door for partnerships like the 2012 China Collaborative partnership between the Council on Social Work Education’s (CSWE) Katherine A. Kendall Institute, the China Association of Social Work Education (CASWE) and the International Association of Schools of Social Work (IASSW). The University of Alabama School of Social Work (UA SSW) was selected to participate in the collaborative and was connected to the Southwest China Region, specifically partnered with Yunnan University. This manuscript will share the strategies used to engage faculty and students from each partnering institution. Data collected by UA SSW over the five-year partnership will be utilised to contribute to the discussion of the extent to which Western knowledge and theory about social work education might usefully be applied to the Chinese context.
_eprint: https://doi.org/10.1080/17525098.2021.1909237
Keywords: China collaborative; International social work; University of Alabama; Yunnan University; social work education

A Preliminary Psychometric Investigation of a Chinese Version of the Engaged Teachers Scale (C-ETS) - Ho, Sammy K.; Chan, Hang; Chan, Edmund Sze-Shing; Fung, Kwok-Kin; Hung, Shirley Suet-Lin (Frontiers in Education, 2021)
This study examines the psychometric properties of a Chinese version of the Engaged Teacher Scale (C-ETS). A translated questionnaire with 16 items was administered to a sample of 341 primary and secondary school teachers in Hong Kong. A series of confirmatory factor analyses were performed to assess the construct, convergent, and discriminant validity of the scale in alternative models. Results provide support for a second-order model with teacher engagement as an overarching construct with four hypothesized dimensions: emotional engagement, cognitive engagement, social engagement (students), and social engagement (colleagues). The C-ETS provides a useful measure for teacher engagement in Chinese societies. Contributions and limitations of the study are discussed.

Androgens and corticosteroids increase in response to mirror images and interacting conspecifics in males of the Siamese fighting fish Betta splendens - Ramos, Andreia; Alex, Deepa; Cardoso, Sara D.; Gonçalves, David (Hormones and Behavior, 2021)
The role of hormones as modulators of aggressive behavior in fish remains poorly understood. Androgens and corticosteroids, in particular, have been associated with aggressive behavior in fish but it is still not clear if animals adjust the secretion of these hormones to regulate behavior during ongoing fights, in response to fight outcomes in order to adjust aggressive behavior in subsequent fights, or both. With its stereotyped displays and high aggression levels, the Siamese fighting fish Betta splendens is an excellent model to investigate this question. Here, we compared the behavioral and endocrine response of male B. splendens to fights where there is no winner or loser by presenting them with a size-matched live interacting conspecific behind a transparent partition or with a mirror image. The aggressive response started with threat displays that were overall similar in frequency and duration towards both types of stimuli. Fights transitioned to overt attacks and interacting with a live conspecific elicited a higher frequency of attempted bites and head hits, as compared with the mirror image. There was a pronounced increase in plasma androgens (11-ketotestosterone and testosterone) and corticosteroids (cortisol) levels in response to the aggression challenge, independent of stimulus type. Post-fight intra-group levels of these hormones did not correlate with measures of physical activity or aggressive behavior. A linear discriminant analysis including all behavioral and endocrine data was a poor classifier of fish from the conspecific and mirror trials, showing that overall the behavioral and endocrine response to mirror images and conspecifics was similar. The results show that fight resolution is not necessary to induce an evident increase in peripheral levels of androgens and corticosteroids in B. splendens. However, the function of these hormones during present and future aggressive contests remains to be clarified.
Keywords: Aggression; Androgens; Corticosteroids; Live conspecific test; Mirror test

Sediments in the mangrove areas contribute to the removal of endocrine disrupting chemicals in coastal sediments of Macau SAR, China, and harbour microbial communities capable of degrading E2, EE2, BPA and BPS - Moreira, Irina S.; Lebel, Alexandre; Peng, Xianzhi; Castro, Paula M. L.; Gonçalves, David (Biodegradation, 2021)
The occurrence of endocrine disrupting chemicals (EDCs) is a major issue for marine and coastal environments in the proximity of urban areas. The occurrence of EDCs in the Pearl River Delta region is well documented but specific data related to Macao is unavailable. The levels of bisphenol-A (BPA), estrone (E1), 17α-estradiol (αE2), 17β-estradiol (E2), estriol (E3), and 17α-ethynylestradiol (EE2) were measured in sediment samples collected along the coastline of Macao. BPA was found in all 45 collected samples with lower BPA concentrations associated to the presence of mangrove trees. Biodegradation assays were performed to evaluate the capacity of the microbial communities of the surveyed ecosystems to degrade BPA and its analogue BPS. Using sediments collected at a WWTP discharge point as inoculum, at a concentration of 2 mg l−1 complete removal of BPA was observed within 6 days, whereas for the same concentration BPS removal was of 95% after 10 days, which is particularly interesting since this compound is considered recalcitrant to biodegradation and likely to accumulate in the environment. Supplementation with BPA improved the degradation of bisphenol-S (BPS). Aiming at the isolation of EDCs-degrading bacteria, enrichments were established with sediments supplied with BPA, BPS, E2 and EE2, which led to the isolation of a bacterial strain, identified as Rhodoccoccus sp. ED55, able to degrade the four compounds at different extents. The isolated strain represents a valuable candidate for bioremediation of contaminated soils and waters.
Keywords: Biodegradation; Bisphenols; EDCs-degrading bacteria; Endocrine disrupting chemicals (EDCs); Estrogens; Mangrove

Occurrence and remobilization of gold in the Dayingezhuang deposit in Jiaodong, North China Craton: Evidence from textural and geochemical features of pyrite - Yuan, Zhong-Zheng; Li, Zhan-Ke; Li, Jian-Wei; Zhao, Xin-Fu; Wu, Ya-Fei; Xu, Hai-Jun; Sun, Hua-Shan (Ore Geology Reviews, 2021)
The Dayingezhuang gold deposit in the Jiaodong district, eastern margin of the North China Craton is hosted in Mesozoic granitic rocks and consists of quartz-sulfide veins/veinlets and sulfide disseminations in alteration envelopes. Previous studies mainly focused on the geochronology, sources of ore-forming fluids and metals to investigate the ore genesis. However, enrichment mechanism of Au and other associated trace metals remain unclear. In this study, we present detailed textures and in-situ LA-ICP-MS trace-element compositions of different generations of pyrite, as well as EMP analysis of Au-bearing minerals to discuss the occurrence and enrichment mechanism of Au at this deposit. Three generations of pyrite (Py1, Py2 and Py3) formed during three hydrothermal ore stages (I, II, and III) at Dayingezhuang. Py1 occurs as disseminations in sericitic alteration assemblages and is characterized by low Au (mean 0.15 ppm), Ag, As and Te contents. The time-resolved depth-concentration profiles indicate that Au in Py1 mainly occurs as nanoparticles and/or micron-sized inclusions. Py2 can be further divided into the early undeformed Py2a and later Py2b, which is the product of deformed Py2a with different degrees of brittle to plastic deformation and recrystallization. Py2a in pyrite-siderite-quartz veins is relatively enriched in invisible Au (mean 0.41 ppm), Ag, As, and Te compared to Py1, and contains numerous micron-sized Au inclusions. In contrast, Py2b contains lesser invisible Au (0.21 ppm) and host abundant gold minerals along the grain boundaries and microfractures. Py3 in polymetallic sulfide veins has little Au. As a whole, Au in pyrite is positively correlated with Ag and Te, which is consistent with the results of EMP analysis showing the occurrence of Au as electrum, native gold and minor petzite in pyrite. Such evidences show that the deformation and recrystallization of auriferous Py2a potentially caused local remobilization of Au (mainly as micron-sized inclusion Au) via solid-state ductile flow and subsequent reconcentration of Au in microfractures of Py2b. The pyrite deformation and Au remobilization events were suggested to be related to the continuous reactivation of the regional Zhaoping Fault contemporaneous with gold mineralization. Our study highlights the importance of remobilization and reconcentration of Au triggered by syn-ore tectonic activities at Dayingezhuang and possibly other Au deposits in the Jiaodong district.
Keywords: Dayingezhuang; EBSD; Gold remobilization; Jiaodong; Pyrite deformation

COVID-19: Psychological and Psychosocial Impact, Fear, and Passion - Dey, Nilanjan; Mishra, Rishabh; Fong, Simon James; Santosh, K. C.; Tan, Stanna; Crespo, Rubén González (Digital Government: Research and Practice, 2021)

Personal Care and Cosmetic Products as a Potential Source of Environmental Contamination by Microplastics in a Densely Populated Asian City - Bashir, Saidu M.; Kimiko, Sam; Mak, Chu-Wa; Fang, James Kar-Hei; Gonçalves, David (Frontiers in Marine Science, 2021)
The prevalence of microplastics in the environment has become a major global conservation issue. One primary source of environmental microplastics is personal care and cosmetic products (PCCPs) containing microbeads. The market availability of PCCPs containing microbeads and the level of contamination of coastal sediments by microplastics was studied in one of the most densely populated cities in the world, Macao in China. We found that PCCPs containing microbeads are still widely available for sale in the region, with over 70% of surveyed PCCPs containing at least one type of microbeads as an ingredient, with polyethylene (PE) being the most common one. In an estimate, the use of PCCPs in the territory may release over 37 billion microbeads per year into the environment via wastewater treatment plants. The density of microplastics in coastal sediments varied between 259 and 1,743 items/L of sediment, amongst the highest reported in the world. The fraction of < 1 mm was the most abundant, representing an average of 98.6% of the total, and correlated positively with the abundance of larger sized fragments. The results show that although environmental pollution with microplastics released from PCCPs usage is significant, other sources, namely fragmentation of larger plastic debris, likely contribute more to the issue. The study highlights the magnitude of the problem at a local level and suggests possible mitigating strategies.

A touristic habitation: automobilities of Chinese driving tourists - Yang, Peng; Xu, Honggang; Hannam, Kevin (Tourism Geographies, 2022)
As an emergent tourism sector, driving tourism connects car use and touristic activities intimately. Following the notion of the ‘inhabited car’, this article explores how and why Chinese tourists inhabit a travelling car for drivers/passengers in the leisure automobility and driving tourism context. Through three different road trips and ‘mobile methods’, it was found that Chinese tourists inhabit the car in four ways: driving, gazing, listening, and communicating. Through this embodied habitation, the car is turned into a ‘touristic inhabitation’ space for protecting the tourists generating touristic emotions、social interactions, and tourism meanings. The study contributes to automobility and tourism literature and provides implications for driving tourism development in China.
_eprint: https://doi.org/10.1080/14616688.2022.2046148
Keywords: Automobilities; China; cars; driving tourism; habitation

CCAAT/Enhancer-Binding Protein Alpha Is a Novel Regulator of Vascular Smooth Muscle Cell Osteochondrogenic Transition and Vascular Calcification - Chen, Pengyuan; Hong, Wanzi; Chen, Ziying; Gordillo-Martinez, Flora; Wang, Siying; Fan, Hualin; Liu, Yuanhui; Dai, Yining; Wang, Bo; Jiang, Lei; Yu, Hongjiao; He, PengCheng (Frontiers in Physiology, 2022)
AimsVascular calcification is a common clinical complication of chronic kidney disease (CKD), atherosclerosis (AS), and diabetes, which is associated with increased cardiovascular morbidity and mortality in patients. The transdifferentiation of vascular smooth muscle cells (VSMCs) to an osteochondrogenic phenotype is a crucial step during vascular calcification. The transcription factor CCAAT/enhancer-binding protein alpha (C/EBPα) plays an important role in regulating cell proliferation and differentiation, but whether it regulates the calcification of arteries and VSMCs remains unclear. Therefore, this study aims to understand the role of C/EBPα in the regulation of vascular calcification.Methods and ResultsBoth mRNA and protein expression levels of C/EBPα were significantly increased in calcified arteries from mice treated with a high dose of vitamin D3 (vD3). Upregulation of C/EBPα was also observed in the high phosphate- and calcium-induced VSMC calcification process. The siRNA-mediated knockdown of C/EBPα significantly attenuated VSMC calcification in vitro. Moreover, C/EBPα depletion in VSMCs significantly reduced the mRNA expression of the osteochondrogenic genes, e.g., sex-determining region Y-box 9 (Sox9). C/EBPα overexpression can induce SOX9 overexpression. Similar changes in the protein expression of SOX9 were also observed in VSMCs after C/EBPα depletion or overexpression. In addition, silencing of Sox9 expression significantly inhibited the phosphate- and calcium-induced VSMC calcification in vitro.ConclusionFindings in this study indicate that C/EBPα is a key regulator of the osteochondrogenic transdifferentiation of VSMCs and vascular calcification, which may represent a novel therapeutic target for vascular calcification.

An exploration of building up the quality of parent-child relationship in residential childcare in Macao - Leong, On Na Ribeiro; Liu, Shu-Wen (Asian Social Work and Policy Review, 2022)
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/aswp.12252

Trying a board game intervention on children with autism spectrum disorder in Macau: how do they react? - Lok, Ka Ieong; Chiang, Hsu-Min; Lin, Yueh-Hsien; Jiang, Chunlian (International Journal of Developmental Disabilities, 2022)
Limited special education and related services are available for children with autism spectrum disorder (ASD) in Macau, especially those who are educated in general education classrooms. No intervention study has been conducted on these children. This study was conducted to explore the relationship between a board game play intervention and board game play behaviors and social communication of children with ASD educated in general education classrooms in Macau. A repeated measures design was used and the results of this study showed the mean occurrence of unprompted board game play behaviors per session during intervention was not significantly different from that during pre- or post-intervention. The mean occurrence of social communication per session during intervention was significantly higher than that during pre- and post-intervention. These findings suggest a positive relationship existed between the board game intervention used in this study and social communication of children with ASD.
_eprint: https://doi.org/10.1080/20473869.2022.2095861
Keywords: Autism Spectrum Disorder; Macau; board game; play; social communication

Attentive recurrent adversarial domain adaptation with Top-k pseudo-labeling for time series classification - He, Qi-Qiao; Siu, Shirley Weng In; Si, Yain-Whar (Applied Intelligence, 2022)
The key challenge of Unsupervised Domain Adaptation (UDA) for analyzing time series data is to learn domain-invariant representations by capturing complex temporal dependencies. In addition, existing unsupervised domain adaptation methods for time series data are designed to align marginal distribution between source and target domains. However, existing UDA methods (e.g. R-DANN Purushotham et al. (2017), VRADA Purushotham et al. (2017), CoDATS Wilson et al. (2020)) neglect the conditional distribution discrepancy between two domains, leading to misclassification of the target domain. Therefore, to learn domain-invariant representations by capturing the temporal dependencies and to reduce the conditional distribution discrepancy between two domains, a novel Attentive Recurrent Adversarial Domain Adaptation with Top-k time series pseudo-labeling method called ARADA-TK is proposed in this paper. In the experiments, our proposed method was compared with the state-of-the-art UDA methods (R-DANN, VRADA and CoDATS). Experimental results on four benchmark datasets revealed that ARADA-TK achieves superior classification accuracy when it is compared to the competing methods.
Keywords: Adversarial training; Attentive; Domain adaptation; Pseudo-labeling; Time series classification

Modulações em português de imagens, experiências e estesias orientais: revisão das razões do fascínio de alguma dicção poética chinesa e japonesa como utopia da poesia - Borges, Vera (Alea: Estudos Neolatinos, 2022)
Resumo O fascínio do Ocidente pela dicção poética oriental está atestado em várias latitudes e línguas, e resultou numa profícua produção na área da poesia. Sabe-se que a reinvenção da poesia chinesa da autoria de Pound, em grande medida na origem da sua proposta de revolução do idioma poético, nas primeiras décadas do séc. XX, assentou, na verdade, numa falácia; numa concepção errada da natureza da escrita chinesa (e japonesa) como essencialmente pictográfica e ideogramática, na base de propriedades expressivas reconhecidas na poesia que resultariam numa particular eficácia na apreensão e tradução do real. Pessanha enaltece, em termos similares aos da exaltação poundiana, a escrita da poesia chinesa clássica. Interessa-nos rever alguns inventários dos traços da dicção poética chinesa e japonesa que explicam que ela seja tomada como metonímia e metáfora da poesia, ou como meta e utopia da poesia, para perceber o que terá levado autores muito díspares a tentar a mão nos haikus, processo em que sondaremos algumas formulações poéticas em língua portuguesa. Consideramos também que esse fascínio por uma (sonhada) origem da dicção poética, quando cruzada com o habitar (não metafórico, neste caso) do pequenino enclave de Macau, de autores que nele lançaram raízes, resultou em alguns exercícios poéticos particularmente felizes e singulares. Serão trazidos à colação nesta abordagem poemas de Eugénio de Andrade, Sophia de Mello Breyner Andresen, José Tolentino Mendonça, Yao Feng, Fernanda Dias e Fernando Sales Lopes.
Keywords: Macau; Pound; falácia; haiku; poesia; poesia chinesa; trocar de voz

Constructing an aesthetic discourse: Aesthetic education where Daoism meets postmodernism - Ho, Ka Lee Carrie (Education Inquiry, 2022)
Despite the prevalence of aesthetic education as one of the main developmental objectives in curricular worldwide, the mainstream philosophical discourse on its definition is predominately framed by western philosophy due to a paucity of cross-cultural studies on the subject. The article aims to achieve a contemporary understanding of aesthetic education from both the Chinese and Western aesthetic perspectives. Through the lens of postmodernism, the relationship between Daoist aesthetics and the western postmodern aesthetic perspectives, particularly the Deleuzian concept of rhizome, is identified. Both aesthetic perspectives concern de-authorship and promote self-consciousness/self-awareness. The study reconceptualises the functions of aesthetic education with the Chinese aesthetic philosophy that promotes the nurture of better people through benevolence.
_eprint: https://doi.org/10.1080/20004508.2020.1831286
Keywords: Aesthetic experiences; Daoism; Deleuze; aesthetic environments; rhizome

Understanding of base-10 concept and its application: a cross-cultural comparison between Japan and Singapore - Marcruz, Ong Yew Lee; Carrie, Ho Ka Lee; Manabu, Kawata; Mayumi, Takahashi; Kumpei, Mizuno (International Journal of Early Years Education, 2022)
It has become increasingly clear that the early use of decomposition for addition is associated with later mathematical achievement. This study examined how younger children execute a base-10 decomposition strategy to solve complex arithmetic (e.g. two-digit addition). 24 addition problems in two modalities (WA: Written Arithmetic; OA: Oral Arithmetic) with sums less than 100 were administered to 22 Japanese and 22 Singaporean 6-year-old kindergarteners. Our findings reveal that they were able to solve complex addition. For instance, Japanese kindergarteners tended to solve complex arithmetic using base-10 decomposition across the modality, whereas Singaporean kindergarteners used standard algorithms and basic counting to solve complex WA and OA problems, respectively. We speculate that Japanese kindergarteners might have a clearer understanding of the base-10 concept and were able to use this knowledge more readily than Singaporean kindergarteners. Mathematical experiences in kindergarten and number-naming systems have been put forward as two of the crucial contributors for such cross-cultural differences. This study also provides new directions for future research on the understanding of the base-10 concept and its application among young children.
_eprint: https://doi.org/10.1080/09669760.2020.1848525
Keywords: Base-10 concept; decomposition strategy; kindergarten; mathematical experiences; number-naming system

Exploring the participation and agency of students with special education needs in a Macau-Chinese secondary school - Correia, Ana M.; Forlin, Chris; Sio, Eva (Journal of Research in Special Educational Needs, 2022)
The research explores the perceptions of five secondary school students with special education needs (SEN) about their participation in learning, group membership, and agency within an inclusive school in Macau SAR. This goal is achieved by using students' voices documented in open-ended interviews and is underpinned by the conceptual framework of heutagogy. The aim is to shed light on students' perceptions on school effectiveness in supporting their needs through successful participation and agentic possibilities. Findings showed that students were more prone to social rejection and being isolated or bullied than their peers. They were struggling to feel included or participate, their needs were only partially being met, and they had few opportunities to exert influence on their educational trajectories. Recommendations are provided to assist educators and schools in enhancing students with SEN to connect to the learning process and community, with the provision of appropriate learning adjustments and more active approaches to ensure their acceptance by mainstream students, including the formation of coaching peers to assist in developing social and academic skills under teacher's scaffolding practices. This study highlights the contribution of the heutagogical perspective to advance research on the participation and agency of students with SEN in mainstream schools.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/1471-3802.12566
Keywords: Macau SAR; Special education needs; agency; disability; inclusive education; participation; students' voice

A contribution to Paulo Freire’s theory and practice: The ‘Cultural Extension Service/University of Recife’ (1962–64) - Gerhardt, Heinz Peter (Educational Philosophy and Theory, 2022)
This contribution to the special issue is an historical account of Paulo Freire’s pedagogical and administrative praxis before his forced exile in 1964. It relies on interviews collected during a field trip in 1976, a conversation with Paulo Freire in Geneva one year later and on the secondary literature up to date. Being the head of the first Extension Service of a major Brazilian university in the early 1960s gave Freire and his collaborators the space and time to experiment with the today world famous literacy method bearing his name. The concept of ‘Field of Cultural Production’ (Bourdieu) is used to elucidate better Freire and his team’s avant-gardist production within the spaces opened up by Brazil’s popular movements in the early sixties. The contribution shows how the ‘Paulo Freire System’ developed in the praxis of a cultural movement and received its academic consecration in an incremental and eclectic style.
_eprint: https://doi.org/10.1080/00131857.2022.2129007
Keywords: Bourdieu; Brazil; Paulo Freire; University of Recife; extension service; literacy

A metamorphic devolatilization model for the genesis of the Baiyun gold deposit in the North China Craton: A novel Fe-S isotopes perspective - Liu, Shuaijie; Chen, Bin; Zheng, Jiahao; Wu, Yafei; Bao, Chuang; Zhao, Guochun (Gondwana Research, 2022)
The Mesozoic gold deposits in the North China Craton (NCC) were hosted by the Precambrian basement and Mesozoic intrusions. Thus, most researchers consider that these gold deposits were genetically linked to the Mesozoic intrusions. However, we suggest that a metamorphic devolatilization model provides an alternative based on a combined Fe and in-situ S isotopes study on auriferous pyrites from the Baiyun gold deposit in the NCC. The Triassic Baiyun gold deposit contains the quartz vein and altered rock ores that were developed in the Paleoproterozoic metavolcanic-sedimentary rocks (the Liaohe Group). Our in-situ S isotopic analyses show that pyrites from the quartz vein ores are characterized by negative δ34S values (-10.7 ∼ -5.5‰), while those from the altered rock ores have two distinct groups of δ34S values, one being positive (+13.5 ∼ +16.2‰) and the other negative (-10.6 ∼ -3.0‰). We suggest that pyrite grains with positive δ34S values should be relicts from the host rocks, because they show comparable δ34S values with those from the host rocks schists (+3.3 ∼ +16.1‰). Thus, only the negative δ34S values of pyrites in ores (-10.7 ∼ -3.0‰) and the Fe isotopes of the quartz vein ores (δ56Fe = +0.30 ∼ +0.48‰) can represent the isotopic characteristics of ore-forming fluids at Baiyun. Our study shows that the sulfur were probably from the pyritic volcanic-sedimentary sequences of the Liaohe Group, rather than from magmas. The calculated δ56Fe values of the ore-forming fluids (-0.78 ∼ -0.37‰; pyrite-fluid isotope fractionation) could be modelled in a metamorphic devolatilization model with Fe-species (pyrite&magnetite) of the Liaohe Group as sources. Therefore, our combined S- and Fe- isotope data indicate that the metamorphic devolatilization of the Liaohe Group could account for the genesis of the Baiyun gold deposit.
Keywords: Baiyun gold deposit; Fe isotope; Metamorphic devolatilization model; Orogenic gold deposits; S isotope

How Immigrant Parents and Local Parents Were Involved in Children's Education in Macau - Ng, Shun W.; Cheong, Ka W. (International Journal of Educational Reform, 2023)
The objective of this case study is to analyze how two groups of parents, a group who have newly arrived in Macau from Mainland China and the other who have resided in Macau for more than three decades, interact with the class teachers at the levels of ?two-way communication,? ?supervision of children at home,? and ?participating in decision making? in a secondary school. The findings will redound to the benefits of school leaders, teachers, and indirectly the parents in a sense that looking closely at the ethnic and cultural differences between parents can promote effective cooperation between parents and teachers.

A model of integrating convolution and BiGRU dual-channel mechanism for Chinese medical text classifications - Li, Xiaoli; Zhang, Yuying; Jin, Jiangyong; Sun, Fuqi; Li, Na; Liang, Shengbin (PLOS ONE, 2023)
Recently, a lot of Chinese patients consult treatment plans through social networking platforms, but the Chinese medical text contains rich information, including a large number of medical nomenclatures and symptom descriptions. How to build an intelligence model to automatically classify the text information consulted by patients and recommend the correct department for patients is very important. In order to address the problem of insufficient feature extraction from Chinese medical text and low accuracy, this paper proposes a dual channel Chinese medical text classification model. The model extracts feature of Chinese medical text at different granularity, comprehensively and accurately obtains effective feature information, and finally recommends departments for patients according to text classification. One channel of the model focuses on medical nomenclatures, symptoms and other words related to hospital departments, gives different weights, calculates corresponding feature vectors with convolution kernels of different sizes, and then obtains local text representation. The other channel uses the BiGRU network and attention mechanism to obtain text representation, highlighting the important information of the whole sentence, that is, global text representation. Finally, the model uses full connection layer to combine the representation vectors of the two channels, and uses Softmax classifier for classification. The experimental results show that the accuracy, recall and F1-score of the model are improved by 10.65%, 8.94% and 11.62% respectively compared with the baseline models in average, which proves that our model has better performance and robustness.
Keywords: Convolution; Deep learning; Machine learning; Memory recall; Neural networks; Recurrent neural networks; Semantics; Syntax

Spatial modulation of the hydrological risk at Praia, Cape Verde - Silva, José Lino; Neves, Ana Cristina; Negreiros, João Garrott Marques (IOP Conference Series: Earth and Environmental Science, 2016)
Hydrology modeling became a relevant topic for the Cidade da Praia, Cabo Verde, Africa, due to negative impact risk to local population and its assets. The modeling via Geographical Information Systems (GIS) can help the decision-making process of space occupation and characterization for this type of risk. Under the municipalities of Praia, the phenomenon of flash flood is common, causing soil erosion and landslide. This constitutes a risk for the local habitat, particularly in districts with a lack of strong human infrastructures. To simulate, analyze and generate risk maps using GIS to help this county governance authorities for decision-making, thus, becomes the main aim of this article.

Learning Computer Science: Dimensions of Variation Within What Chinese Students Learn - Thota, Neena; Berglund, Anders (ACM Transactions on Computing Education, 2016)
We know from research that there is an intimate relationship between student learning and the context of learning. What is not known or understood well enough is the relationship of the students’ background and previous studies to the understanding and learning of the subject area—here, computer science (CS). To show the contextual influences on learning CS, we present empirical data from a qualitative investigation of the experiences of Chinese students studying for a master degree at Sweden's Uppsala University. Data were collected of the students’ understanding and learning of CS, their experience of the teaching and their own studies, and of their personal development in Sweden. Using an analysis framework grounded in phenomenography, we analytically separated the what and how aspects of learning. In this article, we describe the what, or the content of the students’ learning, and identify dimensions of variation in the experiences of students. These dimensions relate to the foci of the CS programs, the learning outcomes, and the impact of the studies. The findings from the analyses indicate pedagogical and pragmatic implications for teaching and learning CS in higher education institutions. The study extends the traditional use of phenomenography through the discussion of the dimensions of variation in the experiences and the values within the dimensions. It opens the way for understanding the relational nature of learning in computing education.
Keywords: Computer science education; context; phenomenography; qualitative research; variation theory

What students are saying on Facebook about their schools? - Kio, Su Iong (Webology, 2015)

The seminars of the Macao forum: An illustration of China’s soft-power diplomacy towards the Portuguese-speaking countries - Tran, Emilie; Dos Santos, Jose Carlos Matias (China: An International Journal, 2015)
This article reviews the role that the Macao Special Administrative Region (SAR) plays in China’s cultural and public diplomacy through training programmes organised by the Macao Forum and tailored for the elite of the world’s Portuguese-speaking countries (PSCs). It begins with a review of China’s approach to key instruments of its soft-power offensive and strategy towards the developing world, followed by an overview of Beijing’s linkages with each PSC. Formulated as an expression of China’s cultural diplomacy towards the PSCs, the seminars of the Macao Forum serve as a kind of cooperation in which the provider party—rather than delivering tangible goods and services such as food, money, loans or infrastructure—actually offers grey matter in the form of ideas for initiatives in public policies and reforms, in order to foster further economic development and administrative rationalisation. Adding to an intense debate and substantial literature that discuss quantitatively and qualitatively China’s role in and aid provision to Africa, the authors argue that China, through the Macao Forum’s training programmes, courts the developing PSCs by building the capacity of their human capital, targeting in particular those in the public and private sectors who are in a position to implement their ideas.

Personality and learning styles surrounded by W3 software: The Macao Portuguese school case - Negreiros, João; Baptista, Zelia; Lee, Leanda (Education and Information Technologies, 2014)
One of the purposes of this study is to evaluate how the choice of teaching method can be assisted by knowledge of a student’s personality type and learning style. The present research is undertaken in the context of Web 2.0 tools use within the Portuguese literature subject at Escola Portuguesa de Macao (EPM). The Felder-Soloman index of learning style (ILS) and the Myers-Briggs Type Indicator (MBTI) based upon Jung’s theory of psychological nature were used as measures of learning style and personality type with 8th grade EPM students. Descriptive and chi-squared correlation statistical results of the associations between personality and learners types are presented. These results are discussed positing that the knowledge of student’s personality traits and learning styles together may have a notable implication for teaching methods.
Keywords: Escola Portuguesa de Macao (EPM); Felder and Soloman; ILS; MBTI; Myers and Briggs; Web 2.0

Implementation of Enterprise Resource Planning for the Supply Chain Management of the Food and Beverage Department at Macao Entertainment Corp - Vai, Fong Tou; Lee, Leanda; Negreiros, Joao (Information Resources Management Journal (IRMJ), 2014)
One of the six gaming concession holders in Macao, Macao Entertainment Corp (MEC)1, undertook to centralize three casino/entertainment properties through utilization of a centralized Enterprise Resource Planning (ERP) in April 2010. The Supply Chain (SC) department was the first to apply the ERP in...

Connectivism and the Use of Technology/Media in Collaborative Teaching and Learning - Thota, Neena (New Directions for Teaching and Learning, 2015)
This chapter explores the ways in which a relational understanding of the education process and the use of collaborative technologies in the connectivist tradition might inform and transform university teaching.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/tl.20131

The Internet in China’s state–society relations: Will Goliath prevail in the chiaroscuro? - Sautedé, Eric (China Information, 2013)
This article explores how state and society relations have been affected by the development of information technology in China over the past 20 years. It argues that despite all the transformative changes that such technology has helped bring about, ?benefits? have to be weighed in terms of both empowerment of society and strengthening of state capacity. Ultimately, the digital challenge has not translated into a weakening of the authoritarian state, and this can be explained by the very nature of the party-state in China and how it has managed to make use of communication tools that prove to be both constructive and divisive.

Potential Ecological Risk of Heavy Metal Distribution in Cemetery Soils - Amuno, S. A. (Water, Air, & Soil Pollution, 2013)
In this paper, preliminary investigation was conducted to evaluate the potential ecological risk of heavy metals contamination in cemetery soils. Necrosol samples were collected from within and around the vicinity of the largest mass grave in Rwanda and analyzed for heavy metal concentrations using total digestion–inductively coupled plasma mass spectrometry and instrumental neutron activation analysis. Based on the concentrations of As, Cu, Cr, Pb, and Zn, the overall contamination degree (Cdeg) and potential ecological risks status (RI) of the necrosols were determined. The preliminary results revealed that the associated cemetery soils are only contaminated to a low degree. On the other hand, assessment of the potential ecological risk index (RI) revealed that cumulative heavy metal content of the soil do not pose any significant ecological risks. These findings, therefore, suggest that, while cemetery soils may be toxic due to the accumulation of certain heavy metals, their overall ecological risks may be minimal and insignificant.
Keywords: Cemetery soils; Environmental management; Heavy metals; Mass graves

Message from general chairs - Berglund, A. (Proceedings - 2013 Learning and Teaching in Computing and Engineering, LaTiCE 2013, 2013)

廣州會議（1667-1668）四十二條條文的意義 - Ip, Ka Kei (道風：基督教文化評論, 2012)
Canton Conference (1667-1668) is regarded as an important event in the history of Christianity in China. The Conference was held by missionaries from three religious orders, namely, the Jesuits, Dominicans and Franciscans. Together they tried to achieve something common to strive for the prosperity of the China mission. It is true that the background and atmosphere of the Conference was influenced and overwhelmed by the Rites controversy. However, another significant part that the conference covered, in a large portion, dealt with wide pastoral issues in the context of Chinese society. The forty two articles in this Conference demonstrate the open-mindedness and a fairly positive knowledge of an approach to Chinese custom. In addition, some recommendations remain open to further inquires, in the sense that they were still finding a better way to cope with the indigenous affairs. Analysis of the articles as a whole gives light to various aspects of missionary work at that time beyond the controversial article forty-first.
Keywords: Canton Conference; Christianity in China; Missionary Activity; 中國基督宗教史; 傳教士活動; 廣州會議

The Development of the Gaming Industry and Its Impact on Land Use - Wan, Yim King Penny; Pinheiro, Francisco (Gaming, Governance and Public Policy in Macao, 2011)
Over the past few years, the gaming industry has changed the face of Macao and the lives of its citizens. The liberalisation of casino licensing in 2002 and the implementation of the Chinese government's new visa regulations in 2003, which permitted many mainland Chinese to travel to Hong Kong and Macao on an individual basis, triggered an economic boom. Foreign investment increased dramatically as international companies began to build casinos and hotels. By 2006, gaming revenues had reached a record annual high of US$10.33 billion, far exceeding the US$6.6 billion made on the Las Vegas strip (Gaming Inspection and Coordination Bureau, 2008). Tourist numbers more than doubled from 11 million in 2002 to 21.7 million in 2009 (Statistics and Census Service, 2009a). Rapid economic growth has come at a price, however. There have been many social dislocations and challenges for public policy that can be attributed to the expansion of the gaming industry. A particular issue is land, a fundamental factor of production and an essential component of the gaming industry's success but in short supply in Macao. The tension between casino requirements for land and public needs spills over into debates on matters as diverse as building height restrictions, heritage protection, green space, the opaqueness of government decisions and its lack of consultative mechanisms. © 2011 by The Hong Kong University Press, HKU. All rights reserved.

Relationship between Traditional Chinese Beliefs about Aetiology of Mental Disorders and Help Seeking: A Survey of the Elderly in Macao - Found, A. (East Asian Archives of Psychiatry: Official Journal of the Hong Kong College of Psychiatrists = Dong Ya Jing Shen Ke Xue Zhi: Xianggang Jing Shen Ke Yi Xue Yuan Qi Kan, 2016)
OBJECTIVE: A wide range of factors can influence help-seeking attitudes when individuals experience a mental disorder. The current study investigated the relationship between traditional Chinese beliefs related to the aetiology of mental disorders and help-seeking attitudes among elderly participants in Macao. METHODS: In order to ensure the suitability of participants for inclusion in this study, the participants were required to complete an initial screening test using the Short Portable Mental Status Questionnaire (SPMSQ). Participants who successfully passed the test (n = 183) completed a questionnaire that included the Inventory of Attitudes Toward Seeking Mental Health Services (IASMHS), a set of 9 items related to traditional Chinese beliefs about aetiology of mental disorders and demographic items. RESULTS: The IASMHS scores were higher for female participants and for participants who had completed high school compared with those who had never attended school or who had only completed primary education. Endorsement of traditional Chinese beliefs about the aetiology of mental disorders was higher for male participants. There was a negative correlation between traditional Chinese aetiology beliefs related to mental disorders and help-seeking attitudes. CONCLUSION: Traditional Chinese beliefs related to the aetiology of mental disorders are a negative factor that inhibits help seeking. Implications for efforts to increase the utilisation of mental health services by the elderly are discussed.
Keywords: Aged; Asian People; Asian continental ancestry group; Cultural Characteristics; Female; Health Knowledge; Attitudes; Practice; Help-seeking behavior; Humans; Macau; Male; Mental Disorders; Mental disorders / etiology; Patient Acceptance of Health Care

Attitudes to mental illness: the effects of labels and symptoms - Found, Andrew; Duarte, Carlos (East Asian Archives of Psychiatry: Official Journal of the Hong Kong College of Psychiatrists = Dong Ya Jing Shen Ke Xue Zhi: Xianggang Jing Shen Ke Yi Xue Yuan Qi Kan, 2011)
OBJECTIVES: To investigate the effects of different Chinese terms for mental illness and related symptoms on the attitudes of adolescents towards sufferers of a mental illness. METHODS: A survey of 578 secondary school students attending 4 schools in Macao was conducted. Each student read a short passage about a new student with a mental illness joining their class. Different versions used different labels to refer to the illness of the new student. The symptoms describing the new student also varied: either describing positive symptoms of schizophrenia or mild negative symptoms only. The attitudes of participants to the new student described were measured. RESULTS: There were significantly more negative attitudes towards the sufferer of a mental illness referred to with a psychiatric label, compared with a general label 'illness'. Participants also expressed significantly more negative attitudes when positive symptoms of schizophrenia were used to describe the new student. The results are discussed in terms of the influence of labels and symptoms on attitudes towards mental illness. CONCLUSIONS: These results supported the existence of 2 additive costs in terms of negative attitudes towards sufferers of mental illness, one associated with the label and the other associated with the symptoms.
Keywords: Adolescent; Adolescent Behavior; Asian People; Attitude to Health; Female; Humans; Male; Mental Disorders; Stereotyping; Students; Surveys and Questionnaires; Young Adult

Editorial: On Cinema - Ribas, Daniel; Crespo, Nuno; Caires, Carlos Sena (Journal of Science and Technology of the Arts, 2020)
In the past decades, the field of cinema has undergone several transformations. The digital turn increasingly called for new forms of production, distribution, and exhibition, which imply different ways of thinking, doing, and experimenting cinema. These new forms also reduced the gap between cinema to other so-called visual arts. If cinema and visual arts were already in the process of merging, the last years forced the naturalization of thinking in similar theoretical grounds. This special issue aims to be a forum for the discussion of new practices of researching cinema, and the changes in cinema’s forms of experience and production.
Number: 2
Keywords: Art and cinema; Cinema; Contemporary cinema; Digital turn; Visual Arts

Selection for winners impacts the endocrine system in the Siamese fighting fish - Ramos, A.; Gonçalves, D. (General and Comparative Endocrinology, 2022)
In southeast Asia, males of the Siamese fighting fish, Betta splendens, have been selected across centuries for winning paired staged fights and previous work has shown that males from fighter strains are more aggressive than wild-types. This strong directional selection for winners is likely to have targeted aggression-related endocrine systems, and a comparison between fighter and wild-type strains can bring into evidence the key hormones implicated in aggression. Here, we compared the plasma levels of the androgen 11-ketotestosterone (KT) and of the corticosteroid cortisol (F) in F2 males of a fighter and a wild-type strain raised under similar laboratory conditions. We show that F was generally lower in fighter as compared with wild-type males, while no overall differences in KT levels were detected between strains. When presented with a mirror-induced aggressive challenge, post-fight levels of F increased but more significantly so in wild-type males, while KT increased in males of both strains. After the challenge, fighter males had higher levels of KT as compared with wild-type males, while the pattern for F was opposite. As compared with animals in social groups, wild-type males placed under social isolation had lower F levels, while KT decreased for fighters. Taken together, this data suggests that while wild-type males responded to aggression with an increase in circulating levels of both androgens and corticosteroids, males selected for winning fights maintained a blunt F response, increasing only KT levels. These data agree with the hypothesis that a combination of high levels of androgens and low levels of corticosteroids is associated with high aggression. Overall, these results seem to indicate that selection for winning had a stronger impact in the hypothalamus-pituitary-interrenal axis than in the hypothalamus-pituitary–gonadal axis in B. splendens.

Effects of a High-Fat Diet on Intestinal and Gonadal Metabolism in Female and Male Sea Cucumber Apostichopus japonicus - Zhang, Shuangyan; Ru, Xiaoshang; Zhang, Libin; Gonçalves, David; Yang, Hongsheng; Xu, Jialei (Biology, 2023)
Parental nutrient reserves are directly related to reproductive performance in sea cucumbers. This study focused on the lipid requirements of male and female sea cucumbers Apostichopus japonicus during the reproductive stage and analyzed their physiological responses to a high-fat diet (HFD). The intestinal lipid metabolites and microbiome profile changed significantly in animals fed with the HFD, as given by an upregulation of metabolites related to lipid metabolism and an increase in the predominance of Proteobacteria in the microbiome, respectively. The metabolic responses of male and female sea cucumbers to the HFD differed, which in turn could have triggered sex-related differences in the intestinal microbiome. These results suggest that the lipid content in diets can be differentially adjusted for male and female sea cucumbers to improve nutrition and promote reproduction. This data contributes to a better understanding of the reproductive biology and sex differences of sea cucumbers.
Number: 2
Keywords: high-fat diet; intestinal microbes; physiological metabolic responses; sea cucumber; sex differences

Application of ANN, XGBoost, and Other ML Methods to Forecast Air Quality in Macau - Lei, Thomas M. T.; Ng, Stanley C. W.; Siu, Shirley W. I. (Sustainability, 2023)
Air pollution in Macau has become a serious problem following the Pearl River Delta’s (PRD) rapid industrialization that began in the 1990s. With this in mind, Macau needs an air quality forecast system that accurately predicts pollutant concentration during the occurrence of pollution episodes to warn the public ahead of time. Five different state-of-the-art machine learning (ML) algorithms were applied to create predictive models to forecast PM2.5, PM10, and CO concentrations for the next 24 and 48 h, which included artificial neural networks (ANN), random forest (RF), extreme gradient boosting (XGBoost), support vector machine (SVM), and multiple linear regression (MLR), to determine the best ML algorithms for the respective pollutants and time scale. The diurnal measurements of air quality data in Macau from 2016 to 2021 were obtained for this work. The 2020 and 2021 datasets were used for model testing, while the four-year data before 2020 and 2021 were used to build and train the ML models. Results show that the ANN, RF, XGBoost, SVM, and MLR models were able to provide good performance in building up a 24-h forecast with a higher coefficient of determination (R2) and lower root mean square error (RMSE), mean absolute error (MAE), and biases (BIAS). Meanwhile, all the ML models in the 48-h forecasting performance were satisfactory enough to be accepted as a two-day continuous forecast even if the R2 value was lower than the 24-h forecast. The 48-h forecasting model could be further improved by proper feature selection based on the 24-h dataset, using the Shapley Additive Explanations (SHAP) value test and the adjusted R2 value of the 48-h forecasting model. In conclusion, the above five ML algorithms were able to successfully forecast the 24 and 48 h of pollutant concentration in Macau, with the RF and SVM models performing the best in the prediction of PM2.5 and PM10, and CO in both 24 and 48-h forecasts.
Number: 6
Keywords: Macau; air pollution; air quality; air quality forecast; machine learning

Monitoring PM2.5 at a Large Shopping Mall: A Case Study in Macao - Lei, Thomas M. T.; Chan, Yan W. I.; Mohd Nadzir, Mohd Shahrul (Processes, 2023)
Employees work long hours in an environment where the ambient air quality is poor, directly affecting their work efficiency. The concentration of particulate matters (PM) produced by the interior renovation of shopping malls has not received particular attention in Macao. Therefore, this study will investigate the indoor air quality (IAQ), in particular of PM2.5, in large-scale shopping mall renovation projects. This study collected on-site PM data with low-cost portable monitoring equipment placed temporarily at specific locations to examine whether the current control measures are appropriate and propose some improvements. Prior to this study, there were no measures being implemented, and on-site monitoring to assess the levels of PM2.5 concentrations was non-existent. The results show the highest level of PM2.5 recorded in this study was 559.00 μg/m3. Moreover, this study may provide a reference for decision-makers, management, construction teams, design consultant teams, and renovation teams of large-scale projects. In addition, the monitoring of IAQ can ensure a comfortable environment for employees and customers. This study concluded that the levels of PM2.5 concentration have no correlation with the number of on-site workers, but rather were largely influenced by the processes being performed on-site.
Number: 3
Keywords: air pollution; construction dust; health exposure; indoor air quality; particulate matter

Diversity and Variation in China's Yao Ancient Wood Frame Structures Through Genetic Algorithms: - Afonso, Filipe; Jedenov, Kirill; Januário, Pedro Gomes; Almeida, Paulo (International Journal of Creative Interfaces and Computer Graphics, 2022)
This study, focusing on the China's Yao minority community, investigates the feasibility to create a generative computational method to replicate the diversity of the existing Yao traditional wood buildings, addressing the critical issues currently facing computational design methods, in the attempt to adapt genetic-generative algorithms to the study of local ancient architecture. The project develops a computational tool to generate a network of three-dimensional prototypes, or building structures, derived from traditional wood frame village houses. It studies possible housing structures that illustrate some of the key working methods available in digital systems such as ‘generating' and ‘compositing' taking as a starting point computational strategies oriented towards geometry and where a set of local variables play a decisive role: available local technologies, use of raw materials, and the dimensioning of timber components based on data collected from Yao architecture.

Can mangroves work as an effective phytoremediation tool for pesticide contamination? An interlinked analysis between surface water, sediments and biota - Ivorra, Lucia; Cardoso, Patricia G.; Chan, Shek Kiu; Cruzeiro, Catarina; Tagulao, Karen Arano (Journal of Cleaner Production, 2021)
Mangroves are a unique group of plants growing along tropical and sub-tropical coastlines, with the ability to remove several types of contaminants such as heavy metals and other persistent organic compounds in coastal waters. However, little attention has been given to the possible role of mangroves in the removal of organochlorinated pesticides (OCPs) from the environment. Used worldwide, these pesticides were banned in the late 80s, withal they can still be quantified in aquatic environments due to their high stability. Moreover, as persistent and lipophilic compounds, OCPs are known for their tendency to bioaccumulate and biomagnify through the food chain, affecting local ecosystems, and potentially human health. This work aimed to investigate the potential benefits of mangrove ecosystems as OCP phytoremediators. For this purpose, a total of seventy-three articles from non-mangrove and mangrove areas around the world were gathered, integrated and re-analysed as a whole. These data include information from four different matrices (water, sediment, benthic fauna and mangrove plants). A common trend of less pesticide contamination in mangrove areas was observed for all the selected matrices. As a complement, average concentrations were discussed considering International Directives, such as the European legislation 2013/39/EU for water policy and the Dutch List together with the International Sediment Quality Guideline, for sediments. Additionally, theoretical risk assessments were also included. Since information regarding OCPs in mangroves ecosystem is very scarce compared to non-mangrove areas, this review provides valuable insights regarding these environments, and the importance of preserving them as a relevant remediation unit.
Keywords: Benthic fauna; Intertidal environments; Organochlorinated pesticides; Persistent organic compounds; Toxicological assessment

How can environmental conditions influence dicofol genotoxicity on the edible Asiatic clam, Meretrix meretrix? - Ivorra, Lucia; Cruzeiro, Catarina; Ramos, Alice; Tagulao, Karen; Cardoso, Patricia G. (Environmental Pollution, 2022)
Genotoxic effects of dicofol on the edible clam Meretrix meretrix were investigated through a mesocosm experiment. Individuals of M. meretrix, were exposed to environmental concentration (D1 = 50 ng/L) and supra-environmental concentration (D2 = 500 ng/L) of dicofol for 15 days, followed by the same depuration period. DNA damage (i.e., strand breaks and alkali-labile sites) was evaluated at day 1, 7 and 15, during uptake and depuration, using Comet assay (alkaline version) and nuclear abnormalities (NAs) as genotoxicity biomarkers. The protective effects of dicofol against DNA damage induced by ex vivo hydrogen peroxide (H2O2) exposure were also assessed. Comet assay results revealed no significant DNA damages under dicofol exposure, indicating 1) apparent lack of genotoxicity of dicofol to the tested conditions and/or 2) resistance of the animals due to optimal adaptation to stress conditions. Moreover, ex vivo H2O2 exposure showed an increase in the DNA damage in all the treatments without significant differences between them. However, considering only the DNA damage induced by H2O2 during uptake phase, D1 animals had significantly lower DNA damage than those from other treatments, revealing higher protection against a second stressor. NAs data showed a decrease in the % of cells with polymorphic, kidney shape, notched or lobbed nucleus, along the experiment. The combination of these results supports the idea that the clams used in the experiment were probably collected from a stressful environment (in this case Pearl River Delta region) which could have triggered some degree of adaptation to those environmental conditions, explaining the lack of DNA damages and highlighting the importance of organisms’ origin and the conditions that they were exposed during their lives.
Keywords: Bivalves; Comet assay; DNA damage; Nuclear abnormalities; Organochlorine pesticides

Quantification of insecticides in commercial seafood sold in East Asian markets: risk assessment for consumers - Ivorra, Lucia; Cardoso, Patricia G.; Chan, Shek Kiu; Cruzeiro, Catarina; Tagulao, Karen (Environmental Science and Pollution Research, 2023)
The extraction of 21 insecticides and 5 metabolites was performed using an optimized and validated QuEChERS protocol that was further used for the quantification (GC–MS/MS) in several seafood matrices (crustaceans, bivalves, and fish-mudskippers). Seven species, acquired from Hong Kong and Macao wet markets (a region so far poorly monitored), were selected based on their commercial importance in the Indo-Pacific region, market abundance, and affordable price. Among them, mussels from Hong Kong, together with mudskippers from Macao, presented the highest insecticide concentrations (median values of 30.33 and 23.90 ng/g WW, respectively). Residual levels of fenobucarb, DDTs, HCHs, and heptachlors were above the established threshold (10 ng/g WW) for human consumption according to the European and Chinese legislations: for example, in fish-mudskippers, DDTs, fenobucarb, and heptachlors (5-, 20- and tenfold, respectively), and in bivalves, HCHs (fourfold) had higher levels than the threshold. Risk assessment revealed potential human health effects (e.g., neurotoxicity), especially through fish and bivalve consumption (non-carcinogenic risk; ΣHQLT > 1), and a potential concern of lifetime cancer risk development through the consumption of fish, bivalves, and crustaceans collected from these markets (carcinogenic risk; ΣTCR > 10–4). Since these results indicate polluted regions, where the seafood is collected/produced, a strict monitoring framework should be implemented in those areas to improve food quality and safety of seafood products.
Keywords: Bivalves; Crustaceans; Health risk assessment; Mudskippers; Organochlorine pesticides

Lugares da Memória, Representações e Poderes - Simões, José Manuel da Silva (Rizoma, 2014)
No seguimento de uma série de contactos estreitos com uma comunidade social situada nos municípios de Baía da Traição, Rio Tinto, Marcação e Mataraca, a 85 quilómetros de distância de João Pessoa, capital do Estado da Paraíba, decidi, desde 2006, levar a efeito um intenso trabalho de campo nestas aldeias indígenas com o objectivo de concretizar um projeto de investigação que englobasse em obrigatória interdisciplinaridade os campos tantas vezes excessivamente singulares da História, da Sociologia, da Política, da Antropologia Cultural e das Teorias da Comunicação, acompanhando e refletindo sobre características e organização social, rituais, manifestações de carácter religioso, evolução histórica, usos e costumes de uma tribo que se abriu quase rendida ao exterior, mas porfiando em manter, todavia, traços e, sobretudo, um discurso narrativo de representações culturais ancestrais. Esta propositada interdisciplinaridade persegue um objectivo epistemológico bem preciso: transformar a investigação empírica em contribuição para uma nova teoria da história da comunicação – a comunicação antropo-histórica entre comunidades ditas tradicionais e o “outro” – a área por mim privilegiada em investigações anteriores, nomeadamente ao nível da licenciatura e do mestrado. Os Potiguara, cuja sociedade ainda não é alfabetizada e, na sua maioria, baseiam a sua cultura na tradição oral, transmitindo os seus lugares da memória sobretudo através do poder do português do Brasil, mesmo quando adornado por escassas palavras tupi, é graças à mensagem e à representação que algumas das suas manifestações culturais reinventam continuadamente a sua identidade Potiguara. É, assim, a mensagem e a representação que inventam o real social e reinventam dinamicamente a sua identidade cultural.
Number: 2
Keywords: Lugares de Memória

Etnografia, lugares da memória e o discurso dos poderes na aldeia dos índios potiguara - Simões, José Manuel (e-hum, 2013)
eoi/doi Deposit-Electronic Object Identifierhttp://eoi.citefactor.org/10.11248/ehum.v6i2.1385RESUMO: A aldeia dos índios Potiguara não é somente um aglomerado de casas e pessoas. Trata-se de um espaço social muito mais complexo, somando ao habitat modelos de parentesco, cruzando práticas culturais e economicas, juntando aos humanos bichos e plantas, rotinas de trabalhos e “libertações” de lazeres. A aldeia Potiguara embora se apresente como singular, ela comunicava e continua a comunicar hoje com redes mais amplas de aldeias rurais e indígenas, gerando transformações culturais e sociais profundas. Embora as alterações marquem as mudanças nos habitos da aldeia Potiguara acredita-se que as práticas culturais que se estendem das festas ao turismo das suas aldeias são tão tradicionais como singulares.PALAVRAS-CHAVES: Aldeia indígena – Espaço social – Práticas culturais – TransformaçõesABSTRACT:The village of Potiguara Indians is not only a cluster of houses and people. This is a social space much more complex, adding to habitat kinship models, crossing cultural and economic practices, joining human animals and plants, work routines and "releases" of leisure.The Potiguara village despite presenting as singular, she communicated and continues to communicate today with wider networks of rural and indigenous villages, generating deep cultural and social transformations. Although the changes mark the changes in the habits of the village Potiguara is believed that cultural practices that extend parties to tourism from their villages are so traditional and unique.KEYWORDS: Indian Village - social area - Cultural practices - TransformationsRecebido: 31/08/2014 Aceito: 01/10/2014
Number: 2
Keywords: Aldeia indígena; Espaço social; Práticas culturais; Transformações

The other side of creative industries in Hong Kong and Macau - Mendes, Carla de Utra; Simoes, José Manuel (International Journal of Cultural and Creative Industries, 2014)

Festas e lugares da memória dos índios Potiguara – a invenção das tradições locais - Simoes, José Manuel (Tokyo University of Foreign Studies, 2015)

Espaço, história e memória: os potiguara na paraíba - Simoes, José Manuel (Sæculum – Revista de História, 2016)
últimos assumidos remanescentes provavelmente de um território cultural antes bem mais vasto vivem atualmente nos municípios de Baía da Traição, Marcação e Rio Tinto, no litoral setentrional da Paraíba - nem sobre s seus espaços, culturas e gentes. É preciso dobrar a primeira metade do século XX para se encontrar nos títulos gerais de histórias da Paraíba alguma atenção pelos Potiguara e a sua movimentação histórica no processo longo e contraditório de formação da capitania e da instalação portuguesa na região, enfrentando primeiro a concorrência comercial e militar francesa, depois no século XVII a ocupação holandesa e sempre, até quase meados de seiscentos, a oposição muitas vezes feroz e brutal de vários grupos e milícias potiguaras. A arqueologia confirma um processo recente de formação histórica dos espaços atualmente reivindicados como originais e tradicionais pelos Potiguara. Os estudos linguísticos disponíveis sobre os Potiguara também não destacam a memória rigorosa de um espaço cultural arcano e pré-colonial. Os espaços Potiguara de hoje com este sistema de organização agrícola quase binário são tudo menos naturais. Trata-se, antes, de um espaço em recorrentes transformações históricas, demográficas, económicas e sociais que desafia qualquer ideia de um espaço ‘natural’, ‘original’ ou ‘essencial’ dos Potiguara. Seja como for, estas polarizações estruturais são historicamente aquelas que presidiram à exata produção dos espaços que atualmente os Potiguara apresentam como seus, originais, antigos e tradicionais seguindo, afinal, um modelo colonial de ocupação de espaços e especialização das gentes do Brasil.
Keywords: História colonial

O papel da imprensa em língua portuguesa de Macau: a ética, a ideologia do proissionalismo e o Código Deontológico dos Jornalistas - Simões, José Manuel (Estudos em Jornalismo e Mídia, 2019)
In Macao, Special Autonomous Region of China, there are two professional codes of journalists: one by the Portuguese and English Press Association of Macao and the other by the Macao Journalists’ Association, and there is no regulator in the territory or anyone who administers the rules or sanctions the journalists activity. here’s also no cases of known or reported censorship. However, according to the latest human rights report for this small region of Asia, “the Government has taken steps to limit the coverage of unfavorable news”, admitting the practice of self-censorship by the media.

The Political and Economic Dependence of the Press in Macao under Portuguese and Chinese Rule: Continuity and Change - Costa-Ribeiro, Nelson; Simões, José Manuel (Communication & Society, 2021)
The article analyses the media system in Macao, a special administrative region of China that transitioned from Portuguese to Chinese sovereignty in 1999, becoming one of cities in the world with the largest number of published newspapers per capita. Combining historical research with the analysis of contemporary empirical data collected through interviews with journalists working on the ground, the research demonstrates how there is a long tradition of state control that goes back to the colonial era and that has assumed different forms, ranging from outright censorship to physical intimidation of journalists and economic dependence on the government. Limitations and control strategies imposed on news reporting during the Portuguese administration continue to be practiced today by the Chinese authorities. Even so, journalists operating on the Macao media market tend to overstate the level of freedom they are given, which can be attributed to media outlets being economically dependent on the state. Nevertheless, the level of freedom attributed to the press is today higher than it had been during the colonial period with some critical voices being allowed to reach the media. This needs to be understood in the context of what has been defined as the Chinese safety valve strategy.
Number: 1
Keywords: Censorship; Journalism Practice; Media Systems; Press Freedom; Press Subsidies

Multilingual freedom of the press in Macau - Simões, José Manuel; Mayes, Lee ([RMd] RevistaMultidisciplinar, 2020)
There can be no conclusive determining regarding true press freedom in Macau, and perhaps this statement can be applied elsewhere as well. Issues of self-censorship, partisanship, or cultural loyalty exist in cities and countries around the world, and most of the time there is simply no reliable measurement to determine their impact. The Special Administrative Region (SAR) of Macau is separate and distinct from mainland China, but that does not mean that it is entirely without question regarding its freedom of the press, ethical journalistic practices, and interference by non-authorized agencies at the three languages local newspapers.
Number: 1
Keywords: autocensura; ingerência; liberdade de imprensa; partidarismo; práticas éticas

La terre des autochtones potiguara du brésil: une construction sociale et politique - Simões, José Manuel (E-Journal of Intercultural Studies, 2022)
The land of the potiguara indians of Brazil: a social and political construction The space in which the potiguaras of Brazil live is, today as in the past, the result of a longterm process, many negotiations and well-managed refuges. Paradoxically, despite their recurrent discourse invoking the ancestry of their lands of origin, the Potiguara fight and continue to fight politically for the return to the spaces where their colonial refuge took place.

A reserva territorial dos aborígenes potiguaras do Brasil: um locus simbólico - Simões, José Manuel (Revista Internacional em Língua Portuguesa, 2023)
The various volumes coordinated by Pierre Nora to pursue a history of the places of memory in France have become a multidisciplinary theoretical reference for those who, like us, seek to reconstruct the memories with which the land of the Potiguara aborigines of Brazil is organized today. In the introduction to the voluminous work that he directed for eight years, Nora explained his epistemic understanding of the notion of “places of memory”, stressing that a “lieu de mémoire” is any significant entity that, material or immaterial in nature, through a human will or the wear and tear of time, has become a symbolic element of a community's memorial heritage. The French historian also added that, since memory is the fundamental structure of this generally lengthy process, it was convenient to understand it as a phenomenon of emotions and magic that only accommodates the facts that feed it. Strictly speaking, memory is always vague, and reminiscent, stirring both general impressions and fine symbolic details. Furthermore, memory is always vulnerable to transference, repressed and imagined memories, censorship, and all kinds of projections. (Nora, 1984). In this article, we try to understand that the places of memory are also almost always what comes to us, stays, and selects the past. The reserve where they live appears as a symbolic locus to which the Potiguara aborigines cling with all their strength to preserve what remains of their past.
Keywords: aborígenes Potiguara; censuras; locus simbólico; lugares de memória; preservar o passado; reconstrução das memórias

To follow or overcome our nature? - Cai, Yulin (GREGORIANUM, 2022)
The doctrine of original sin gives people the impression that the goodness of human nature is under-evaluated in the Christian theological tradition. The Chinese philosopher Mencius is famous for his teaching on the goodness of human nature. Reading Mencius and Thomas Aquinas side by side, this article argues that the Mencian teaching on human nature brings us to affirm the goodness of human nature by recovering the significance of the image of God for the Christian doctrine of human nature. If we seek the goodness of human nature in the possibilities to become good, it is natural to see that even in the fallen state the possibilities of becoming like God remain in human nature imprinted with the image of God. It is open to the culmination of a gradual progression to its perfection.

Learning God’s Mercy: Spiritual Transformation According to Hos 11:8 - Gassner, Franz (The Journal of the Macau Ricci Institute, 2022)
A growing focus on God’s mercy and forgiveness emerged in the wake of the recent Pontificates of John Paul II, Benedict XVI, and Francis. Our time with its multiple crises cries for healing, forgiveness, and the experience of God’s mercy. In social, political, and global terms, humanity craves for “lasting peace, born of the marriage of justice and mercy” (John Paul II, 2001, no. 15). The experience of God’s forgiveness, merciful healing and new life has been expressed many times in the Bible. But, theologically, it has never been formulated as directly as in Hosea 11:8, when God’s own heart becomes “turned over”, “converted” following the blaze of his own overwhelming compassion, paving the way for a fundamental spiritual transformation, rooted in forgiveness and mercy, that opens wellsprings of dignity, healing, and new life for all.

The Anglican Patrimony in Catholic Communion ed. by Tracey Rowland (review) - Morgan, Stephen (Antiphon: A Journal for Liturgical Renewal, 2021)

Transforming struggling reform implementers into effectual reform agents: Hong Kong preschool teachers’ voices on process drama - Tam, Po Chi; Sun, C. R. (Youth Theatre Journal, 2021)

Modelling the barriers that are preventing e-commerce to thrive – a case study from Portugal, international journal of business excellence - Silva, Susana Costa e; Machado, Joana Costa; Martins, Carla; Duarte, Paulo; Marques, João Alexandre Lobo (International Journal of Business Excellence, 2021)
The identification of barriers for e-commerce to thrive in specific countries is a topic of great interest. This work proposes two models to study the barriers to B2C e-commerce adoption in Portugal, highlighting obstacles less exploited by previous research: the impact of offline shopping pleasure and the influence of the distance to shopping malls on online shopping intent. An online survey was conducted based on different constructs. A multivariate OLS hierarchical regression was used to analyse the proposed models regarding the intention to buy online and the number of online purchases. The results revealed that customer satisfaction is a strong predictor of intent to buy online and that perceived product risk remains a barrier to e-commerce. Consumers living in high urbanised areas have more propensity to buy online. Helpful information is provided regarding the impact of context, culture, product, and individual barriers, showing that multichannel strategies are best suited for success.
Keywords: E-commerce barriers; Online shopping; Portugal; Retail

The transformation of government employees’ behavioural intention towards the adoption of E-government services: An empirical study - Iong, Kit Yeng; Phillips, Jenny O. L. (Social Sciences & Humanities Open, 2023)
Electronic government is increasingly dominant in the study of public administration. In analysing people's behavioural factors towards the adoption of e-services, most previous studies targeted the adult population, while those on government employees are minimal. Government employees have an essential function in the process of government operation; they can be regarded as the principal medium of communication between the service provider (government) and the end-users (citizens). This study was designed to understand the government employees' behavioural factors on their intentions towards adopting e-government services. A set of semi-structured interview questions was developed based on the prior literature on the Theory of Planned Behaviour (TPB) and e-government studies. Ten in-depth interviews were conducted in Macao SAR (Special Administrative Region). In addition to analysing the three primary constructs of TPB, the factor of Trust and some enablers and hindrances were identified. Significant findings were yielded while investigating how the government employees perceived the e-services and how they regarded the general public's perception of this issue. This contextualisation would help policymakers look at this issue from different perspectives and design feasible interventions according to group alignment strategies.
Keywords: Electronic government; Government employees; In-depth interviews; The Theory of Planned Behaviour

Macau 2.0: New Gaming Law and its Implications for Casino Market - Ho, Hong-Wai; Phillips, Jenny (Gaming Law Review, 2023)
This article discusses the new gaming law in Macau with emphasis on the critical aspects concerning the gaming operators, concession regime, and other regulatory obligations.1 Thanks to the gaming liberalization commenced in 2001,2 Macau has experienced tremendous economic growth. The past two decades have seen the rapid development of large-scale integrated resorts, and Macau now ranks among the world's major gaming jurisdictions.3 Policy and regulatory challenges have also emerged along with the growth of the junket-driven VIP business in casinos.4 With the recent amendment of Law No. 16/2001 and the subsequent enactment of Law No. 16/2022, Macau has strengthened the legal underpinnings of its system of gaming regulation to oversee various groups involved in casinos and their industry practices. The present study is among the first to review the scope and impact of the revised gaming law, and associated managerial and operational implications for Macau casinos. Topics covered include policy directions, concession requirements, industry participants, gaming taxes, and fair business practices. This study could provide insights into the “Macau 2.0” project and how casinos are to be operated and managed over the next decade. This article could also provide practical guidance for policy makers charged with formulating gaming policy and regulation in other jurisdictions.
Keywords: Macao; concession; economic diversification; gaming regulation; junket; operation

EFFECTIVENESS ANALYSIS OF WATERFALL AND AGILE PROJECT MANAGEMENT METHODOLOGIES – A CASE STUDY FROM MACAU'S CONSTRUCTION INDUSTRY - Marques, Joao Alexandre Lobo; Morais, João José Bragança dos Reis; Alves, José; Gonçalves, Marcus (Revista Gestão em Análise, 2023)
The adoption of project management techniques is a crucial decision for corporate governance in construction companies since the management of areas such as risk, cost, and communications is essential for the success or failure of an endeavor. Nevertheless, different frameworks based on traditional or agile methodologies are available with several approaches, which may create several ways to manage projects. The primary purpose of this work is to investigate the adequate project management methodology for the construction industry from a general perspective and consider a case study from Macau. The methodology considered semi-structured interviews and a survey comparing international and local project managers from the construction industry. The interviews indicate that most construction project managers still follow empirical methods with no specific methodology but consider the adoption of traditional waterfall approaches. In contrast, according to the survey, most project managers and construction managers agree that the project's efficacy needs to increase, namely in planning, waste minimization, communication increase, and focus on the Client's feedback. In addition, there seems to be a clear indication that agile methodology could be implemented in several types of projects, including hospitality development projects. A hybrid development approach based on the Waterfall and Agile methodologies as a tool for the project management area may provide a more suitable methodology for project managers to follow.
Number: 1
Keywords: PMBOK; agile; construction industry; project management methodologies

A Heart Rate Variability-based Smart Approach to Analyze Frailty in Older Adults - Paulo do Vale Madeiro, João; César Cortez, Arnaldo Aires Peixoto Júnior, Paulo; Alexandre Lôbo Marques, João; Alisson Pessoa Guimarães, Antônio; Hebert da Silva Felix, John (The Smart Computing Review, 2015)
This paper presents an algorithm that applies metrics derived from automatic QRS detection and segmentation in electrocardiogram signals for analyzing Heart Rate Variability to study the evolution of metrics in the frequency domain of a clinical procedure. The analysis was performed on three sets of elderly people, who are categorized according to frailty phenotype. The first set was comprised of frail elderly, the second pre-frail elderly, and the third robust elderly. Investigators from many disciplines have been encouraged to contribute to the understanding of molecular and physiological changes in multiple systems that may increase the vulnerability of frail elderly. In this work, the frailty phenotype can be characterized by unintentional weight loss, as self-reported, fatigue assessed by self-report, grip strength (measured directly), physical activity level assessed by self-report and gait speed (measured). The results obtained demonstrate the existence of significant differences between Heart Rate Variability metrics for the three groups, especially considering a higher preponderance for sympathetic nervous system for the group of robust patients in response to postural maneuver.

Sudden cardiac death multiparametric classification system for Chagas heart disease's patients based on clinical data and 24-hours ECG monitoring - Cavalcante, Carlos H. L.; Primo, Pedro E. O.; Sales, Carlos A. F.; Caldas, Weslley L.; Silva, João H. M.; Souza, Amauri H.; Marinho, Emmanuel S.; Pedrosa, Roberto C.; Marques, João A. L.; Santos, Hélcio S.; Madeiro, João P. V.; Cavalcante, Carlos H. L.; et al. (Mathematical Biosciences and Engineering, 2023)
About 6.5 million people are infected with Chagas disease (CD) globally, and WHO estimates that $ > million people worldwide suffer from ChHD. Sudden cardiac death (SCD) represents one of the leading causes of death worldwide and affects approximately 65% of ChHD patients at a rate of 24 per 1000 patient-years, much greater than the SCD rate in the general population. Its occurrence in the specific context of ChHD needs to be better exploited. This paper provides the first evidence supporting the use of machine learning (ML) methods within non-invasive tests: patients' clinical data and cardiac restitution metrics (CRM) features extracted from ECG-Holter recordings as an adjunct in the SCD risk assessment in ChHD. The feature selection (FS) flows evaluated 5 different groups of attributes formed from patients' clinical and physiological data to identify relevant attributes among 57 features reported by 315 patients at HUCFF-UFRJ. The FS flow with FS techniques (variance, ANOVA, and recursive feature elimination) and Naive Bayes (NB) model achieved the best classification performance with 90.63% recall (sensitivity) and 80.55% AUC. The initial feature set is reduced to a subset of 13 features (4 Classification; 1 Treatment; 1 CRM; and 7 Heart Tests). The proposed method represents an intelligent diagnostic support system that predicts the high risk of SCD in ChHD patients and highlights the clinical and CRM data that most strongly impact the final outcome.
Cc_license_type: cc_by Number: mbe-20-05-402 Primary_atype: Mathematical Biosciences and Engineering Subject_term: Research article Subject_term_id: Research article

A review on multimodal machine learning in medical diagnostics - Yan, Keyue; Li, Tengyue; Marques, João Alexandre Lobo; Gao, Juntao; Fong, Simon James; Yan, Keyue; Li, Tengyue; Marques, João Alexandre Lobo; Gao, Juntao; Fong, Simon James (Mathematical Biosciences and Engineering, 2023)
Nowadays, the increasing number of medical diagnostic data and clinical data provide more complementary references for doctors to make diagnosis to patients. For example, with medical data, such as electrocardiography (ECG), machine learning algorithms can be used to identify and diagnose heart disease to reduce the workload of doctors. However, ECG data is always exposed to various kinds of noise and interference in reality, and medical diagnostics only based on one-dimensional ECG data is not trustable enough. By extracting new features from other types of medical data, we can implement enhanced recognition methods, called multimodal learning. Multimodal learning helps models to process data from a range of different sources, eliminate the requirement for training each single learning modality, and improve the robustness of models with the diversity of data. Growing number of articles in recent years have been devoted to investigating how to extract data from different sources and build accurate multimodal machine learning models, or deep learning models for medical diagnostics. This paper reviews and summarizes several recent papers that dealing with multimodal machine learning in disease detection, and identify topics for future research.
Cc_license_type: cc_by Number: mbe-20-05-382 Primary_atype: Mathematical Biosciences and Engineering Subject_term: Review Subject_term_id: Review

COVID-19 Detection by Means of ECG, Voice, and X-ray Computerized Systems: A Review - Ribeiro, Pedro; Marques, João Alexandre Lobo; Rodrigues, Pedro Miguel (Bioengineering, 2023)
Since the beginning of 2020, Coronavirus Disease 19 (COVID-19) has attracted the attention of the World Health Organization (WHO). This paper looks into the infection mechanism, patient symptoms, and laboratory diagnosis, followed by an extensive assessment of different technologies and computerized models (based on Electrocardiographic signals (ECG), Voice, and X-ray techniques) proposed as a diagnostic tool for the accurate detection of COVID-19. The found papers showed high accuracy rate results, ranging between 85.70% and 100%, and F1-Scores from 89.52% to 100%. With this state-of-the-art, we concluded that the models proposed for the detection of COVID-19 already have significant results, but the area still has room for improvement, given the vast symptomatology and the better comprehension of individuals’ evolution of the disease.
Number: 2
Keywords: COVID-19; artificial intelligence; computerized diagnostic systems; image processing; signal processing

The use Robotics in the intervention with children with ASD in Macao: a pilot study with Milo - Teixeira, Vitor; Lai, Michael (Revista Portuguesa de Investigação Educacional, 2021)
Robotics are being used in the intervention with children with Autism Spectrum Disorder (ASD) in many places and already for many years. Many robots were developed and different studies are being made in order to evaluate its effectiveness. “Socially Assistive Robotics” is shown to be effective in different areas mainly in social and emotional development. Milo, a robot developed by a team led by Richard Margolin for the Robots4Autism program (RoboKind, 2020), is one of the robots whose use is reported to be successful. In Macao there is no report of studies or experiences on the use of robots in the intervention with children with ASD. In a collaboration between the Macao Science Centre, the Macao Autism Association (MAA) and the University of Saint Joseph, an exploratory study was developed to understand the applicability of Milo to the work with children with ASD in Macao. The study showed that the robot is able to facilitate social and emotional competences of children with ASD. However, several limitations including language, cultural differences, the inexperienced facilitators and the level of sessions are too simple for the participants to be aware of that may affect the effectiveness of the intervention. It is important to show that the adoption of Milo in Macao for intervening children with ASD can be further implemented, with better practical solutions.
Number: 21

Análise multimodal de estratégias discursivas: debate sobre o “bailout” entre Hillary Clinton e Bernie Sanders - Rocha, Nuno (ElingUP : Revista eletrónica de Linguística dos Estudantes da Universidade do Porto, 2019)
Este trabalho consiste numa análise multimodal das estratégias discursivas de Bernie Sanders e Hillary Clinton num excerto de um debate sobre as benesses dadas pela senadora norte americana aos bancos no pós-crise económica global de 2008. Bernie Sanders e Hillary Clinton evidenciaram uma linguagem corporal diferente, tanto na posição de locutor como na de interlocutor. No entanto, mesmo utilizando estratégias de comunicação verbal e física diferentes, os gestos utilizados enquadram-se no campo dos gestos recorrentemente observados em figuras políticas em estudos feitos por outros autores. Reforça-se assim a ideia de que os gestos em questão são regularmente utilizados por figuras políticas.
Number: 2

How social media affects the purchase intentions of female consumers in Macao - watching beauty and cosmetics product experience videos on YouTube - Chan, Velda; Silva, Susana C.; Lampo, Alessandro (Revista Gestão em Análise, 2022)
YouTube has become increasingly popular for marketing purposes. As corporate and user-generated content is widely available on this platform, beauty-related professionals need to understand how to create videos that make their products more appealing and stand out from the clutter. In this study, we examine four factors (i.e., perceived usefulness of the information, perceived credibility of the information, attitude toward the purchase, and perceived video characteristics) that affect the purchase intentions of female consumers. After viewing beauty-related videos, a sample of 204 female consumers was analyzed by structural equation modeling. The findings showed that videos with more views, likes, and comments tend to have a greater effect on the respondents' intentions to purchase. Also, the factors of perceived usefulness of the information, perceived credibility of the information, and attitude toward the purchase exhibited a significant effect on the intention to buy beauty-related products. The result showed that perceived video characteristics (such as quality and visuals) did not significantly influence the purchase intention, however, there is evidence that this factor should not be ignored by content creators. Finally, our research provides insights, strategies, and future directions for industry practitioners and marketers.
Number: 3
Keywords: YouTube beauty products; YouTube marketing; beauty and cosmetics marketing; purchase intention

AN ANALYSIS OF CRITICAL MANAGERIAL CHALLENGES IN MACAU - Lampo, Alessandro (Revista Gestão em Análise, 2023)
Macau has long been considered to be an example of remarkable economic growth. With the opening of the gaming sector in 2002, the casino and hospitality sector flourished, creating employment opportunities but also imposing several challenges on managers. Since Macau endeavors to be positioned as the center for international business with Portuguese-speaking countries and a platform for trading with China’s Greater Bay Area (GBA), it becomes essential for international enterprises to understand the local dynamics. In light of the limited research available, this study aims to identify management challenges from the perspectives of senior executives in different industries based in Macau. Our findings point out that managers must contend with several issues, such as the lack of a skilled local talent pool, high turnover rates, employees' work attitudes, and a tightly controlled immigration policy. It is also imperative for international managers to nurture relationships and pay attention to the local culture. Our results suggest that Macau has to develop a highly skilled local workforce to attract international companies, while local organizations also have to create an attractive working environment to compete in the marketplace.
Number: 1
Keywords: Macau; casinos; greater bay area; management; managerial challenges

The Influence of Society on the Behavioral Intention to Use a Technology: Evidence from the Battery Electric Vehicles Domain - Lampo, Alessandro; Silva, Susana C.; Duarte, Paulo (International Journal of Business Excellence, 2022)

A Critical Look at Blockchain-Interactive Generative Art - Farinha, Daniel Filipe (International Journal of Creative Interfaces and Computer Graphics, 2022)
Artists are increasingly using blockchain as a tool for trading digital artwork as non-fungible tokens (NFTs); however, some are also beginning to experiment with the blockchain as a medium for generative art, using it as a seed for a generative process or to continuously modify an evolving piece. This paper surveys, reviews, and classifies the state-of-the-art in blockchain-interactive NFTs and presents a liberal-arts critique of the opportunities and threats posed by this technology, whilst addressing existing criticism on the broader topic of art-related NFTs. The paper examines some of the most experimental pieces minted on the Hic et Nunc (HEN) and Teia NFT marketplaces, for which a purpose-built research tool was developed. The survey reveals some reliance on centralised infrastructure, namely blockchain indexers, placing undesired trust on third parties which undermines the potential longevity of the artwork. The paper concludes with recommendations for artists and NFT platform designers for developing more resilient and economically sustainable architectures.
Keywords: Art Preservation; Blockchain; Crypto Art; Dynamic NFT; Generative Art; Non-Fungible Token; Provenance

Analysis of reading errors in Portuguese : digraphs and complex syllabic structures - Simões, Edlia; Martins, Margarida Alves (Análise Psicológica, 2020)
Abstract: The Portuguese language poses several challenges for children in the initial phase of learning how to read, particularly in the case of letters that may correspond to more than one phoneme, two letters that correspond to a single phoneme and in the case of words containing complex syllabic structures. The objective of this study was to perform a psycholinguistic analysis of the reading errors of children, attending the 1st (n=175) and 2nd year (n=137) of schooling, specifically in the case of words containing digraphs or complex syllabic structures and to analyse the differences between children’s reading errors in these two years. An oral reading test was used for data collection. A quantitative and qualitative analysis of the type of reading errors was conducted using words with consonant digraphs (ch, nh, lh, gu, rr, ss), and words with complex syllables <CVC and CCV>. This analysis showed that children presented greater difficulties in some specific digraphs and tended to simplify complex syllables, either by adding or deleting phonemes. The quantity and quality of the reading errors of children attending both grades were discussed in light of reading acquisition theories and children’s phonological development.
0 citations (Crossref) [2023-03-15] Accepted: 2021-01-20T11:46:39Z

Mangrove Conservation in Macao SAR, China: The Role of Environmental Education among School Students - Tagulao, Karen Araño; Bernardo, Allan B. I.; Kei, Loi Hoi; Calheiros, Cristina Sousa Coutinho (International Journal of Environmental Research and Public Health, 2022)
Mangrove forests are one of the most ecologically valuable ecosystems in the world and provide a wide variety of ecosystem services to coastal communities, including cities. Macao, a highly urbanized coastal city located on the southern coast of China west of the Pearl River, is home to several species of mangroves with many associated flora and fauna. Mangrove forests in Macao are vulnerable to threats due to pressure from rapid and massive urban developments in the area, which led to mangrove loss in the past decades. To address this issue, the local authorities established special Ecological Zones for the management of the local mangroves. To reinforce local conservation efforts, educating the local population about the value of mangroves, especially school students, is of utmost importance. To evaluate the impact of environmental education activities on the environmental orientation, knowledge, and values of students toward mangrove conservation in Macao, a quasi-experimental study was undertaken. The effectiveness of a mangroves exhibition and field visit were evaluated using the New Environmental Paradigm (NEP) Scale—Macao version in a group of local school students who participated in the activities. Overall, the results provided consistently positive evaluations of the impact of the environmental education program. The strongest improvements were found in the students’ pro-environmental orientations, knowledge about mangroves, and value for environmental protection.
0 citations (Crossref) [2023-03-15] Number: 6
Keywords: NEP-New Ecological Paradigm; conservation; environmental orientation; environmental protection; urban mangroves

Religious Vows in their Mystic and Prophetic Dimensions - Gallares, Judette (Religious Life Asia, 2022)

An Exploratory Study of Macao's Role as an Arbitration Seat and Venue for Sino-Luso Commercial Disputes - Si, Leung Cheok; Diakite, Ansoumane Douty (Revista Opinião Jurídica (Fortaleza), 2023)
Objective: Over the past decade, arbitration has grown in popularity as a method of resolving commercial disputes worldwide. However, this practice is relatively new in Macao SAR. Recently, official plans were announced to make Macao as a seat of arbitration for commercial disputes between China and Portuguese-speaking countries (Hereinafter PSCs). This article is dedicated to explores the possibility of Macao undertaking and implementing such a role. Accordingly, this article addresses the following issues: What are the strengths and weaknesses of Macao as a seat and eventually as venue for hosting international commercial arbitration between Chinese and PSCs entrepreneurs?Methodology: A mixed-method approach of legal doctrinal and empirical research was used in this article. We first included a thorough study of the concept of arbitration followed by analysis of various legal journals and legislations, including Macao, China, and PSCs’ arbitration laws. An empirical research was then used to collect data by surveying and interviewing with both lawyers and arbitration practitioners from Macao, China and PSCs.Results: This article argues that the strength of Macao resides in the similarities between its legal system and that of the China and PSCs and the languages advantage (Chinese and Portuguese both official languages). In spite of this, arbitration is still relatively underutilized in the region, and there is a limited number of arbitrators and legal professionals with bilingual proficiency.Contributions: This article contributes to the identification of the opportunities and challenges that Macao faces in its potential future development as a seat/venue of arbitration between China and the PSCs.
0 citations (Crossref) [2023-02-08] Number: 36
Keywords: China; Macao; arbitraje internacional comercial; international commercial arbitration; participante y anfitrión de arbitraje; países de habla portuguesa; portuguese-speaking countries; seat and venue of arbitration

Ceremonies of the Sarum Missal: A Careful Conjecture by R. J. Urquhart (review) - Morgan, Stephen (Antiphon: A Journal for Liturgical Renewal, 2021)
0 citations (Crossref) [2023-01-27]

Going to Church in Medieval England by Nicholas Orme (review) - Morgan, Stephen (Antiphon: A Journal for Liturgical Renewal, 2022)
0 citations (Crossref) [2023-01-27]

The Fire “Once Kindled on Moriah”: Wojtyła and Newman on the Conditions for the Proposal of Christ - Morgan, Stephen (Newman Studies Journal, 2022)
0 citations (Crossref) [2023-01-27]

Serpentinization and its implications for ultramafic-hosted sulfide mineralization: A case study at the Tianzuo hydrothermal field, 63.5°E, Southwest Indian Ridge - Ding, Teng; Dias, Ágata Alveirinho; Wang, Jia; Tan, Tingting; Liang, Jin; Wu, Bin; Tao, Chunhui (Marine Geology, 2023)
Reaction of ultramafic rocks with seawater and subsequent serpentinization has been considered one of the most important factors controlling the formation of ultramafic-hosted seafloor massive sulfide (UM-SMS) deposits. However, the mineralization processes responsible for these deposits remain poorly understood, in particular because they are less abundant as compared with their basaltic counterparts. In this work, serpentinites with different alteration grades collected at the Tianzuo hydrothermal field (THF), Southwest Indian Ridge, were studied. Mineralogical and chemical analyses were performed in the secondary opaque minerals resulting from serpentinization to understand the role of this process during the formation of UM-SMS deposits. Our results show that these opaque minerals mainly consist of magnetite, hematite, pentlandite, and minor pyrite, suggestive of high but varying oxygen and sulfur fugacities. The hematite is characterized by an enrichment in Mg, Si, Ni, and Co as compared with magnetite. Pentlandite associated with hematite has elevated and consistent Ni contents as compared with that associated with magnetite. These results indicate that breakdown and decomposition of primary silicate and sulfide minerals during serpentinization has controlled the sources of ore-forming materials. Concentrations of Te are variable and show a positive correlation with Ni in pentlandite associated with magnetite or hematite, suggesting that gabbroic intrusions provided additional material to the hydrothermal system. Oxidation and sulfidation conditions are ideal for the formation of trisulfur ion S3− in THF, which can significantly improve the capability of hydrothermal fluids for leaching ore-forming metals from the wall rocks, promoting the formation of THF. In addition of reduced systems, hydrothermal fluids with high oxygen and sulfur fugacities triggered by extensive seawater infiltration can most likely also develop in ultramafic-hosted systems. These results suggest that the areas with well-developed fractures are promising candidates for further exploration of UM-SMS deposits along mid-oceanic ridges.
0 citations (Crossref) [2022-12-25]
Keywords: Opaque minerals; Oxidation and sulfidation; Sulfide mineralization; Tianzuo hydrothermal field; Ultramafic rocks

Uptake and depuration kinetics of dicofol metabolite 4,4′-dichlorobenzophenone, in the edible Asiatic clam Meretrix meretrix - Ivorra, Lucia; Cruzeiro, Catarina; Chan, Shek Kiu; Tagulao, Karen Araño; Cardoso, Patricia G. (Chemosphere, 2019)
Uptake and depuration kinetics of 4,4′-dichlorobenzophenone (main metabolite of dicofol) in the edible clam Meretrix meretrix were evaluated through a mesocosm experiment. M. meretrix was exposed to different dicofol concentrations (environmental concentration, D1 = 50 ng/L; supra-environmental concentration, D2 = 500 ng/L) for 15 days, followed by the same depuration period. To accomplish this goal, an analytical method was successfully optimized for 4,4′-DCBP using QuEChERS as extraction method with a range of concentrations 0.3–76.8 ng/g ww quantified by gas chromatography coupled to tandem mass spectrometry. Our results demonstrated different kinetics of accumulation depending on the two dicofol treatments. For D1, the uptake kinetic was best fitted using a plateau followed by one phase association kinetic model, while for D2 a one phase association kinetic model suited better. Similar bioconcentration factors were obtained for both concentrations but only animals exposed to D2, showed 4,4′-DCBP levels above the limits of quantification after 24 h exposure. These animals also showed lower uptake rate (ku) than organisms exposed to D1. During the depuration period, only organisms exposed to D1 successfully depurated after 24 h. On the other hand, although animals exposed to D2 presented higher elimination factor, they did not reach the original levels after depuration. Moreover, values detected in these clams were higher than the Maximum Residue Level (10 ng/g) established by the European legislation. This indicates that longer periods of depuration time than the ones used in this study, may be needed in order to reach safe levels for human consumption. This work also demonstrated that studies on metabolite kinetics during uptake/depuration experiments, could be a new alternative to understand the impact and metabolism of pesticides in the marine environment.
1 citations (Crossref) [2022-11-10]
Keywords: Bivalves; GC-MS/MS; Organochlorine pesticides; QuEChERS bioconcentration; Seafood

Environmental characterization of 4,4′-dichlorobenzophenone in surface waters from Macao and Hong Kong coastal areas (Pearl River Delta) and its toxicity on two biological models: Artemia salina and Daphnia magna - Ivorra, Lucia; Cardoso, Patricia G.; Chan, Shek Kiu; Tagulao, Karen; Cruzeiro, Catarina (Ecotoxicology and Environmental Safety, 2019)
8 citations (Crossref) [2022-11-10]

Temporary transnational labour mobility and gendered individualization in Europe - Harsløf, Ivan; Zuev, Dennis (Mobilities, 2022)
In a context of a new transnational division of labour, temporary international labour mobility is on the rise in Europe. In particular, recent decades have seen considerably more women seeking work experience abroad. Observers have been concerned with how such mobility is related to individualization, and in particular how it may challenge collective institutions, communities and families. The aim of this study is to explore such issues among women and men with international work experience. Using data from European Social Survey, the paper investigates previously mobile workers in terms of their current working and living conditions. Across genders, we consider different forms of individualization that may be associated with transnational labour mobility. While both women and men with transnational work experience generally feature strong strategic individualization, this is most pronounced among men. Hence, men's mobility is among other things associated with increased autonomy in working life, while – in contrast to women – it does not seem to hamper their integration in the sphere of social reproduction.
0 citations (Crossref) [2022-11-10] _eprint: https://doi.org/10.1080/17450101.2022.2092417
Keywords: Europe; Temporary labour mobility; individualization; sphere of production; sphere of social reproduction; transnational division of labour

Behavioural and endocrine responses to non-interactive live and video conspecifics in males of the Siamese fighting fish - Alex, Deepa; Cardoso, Sara D; Ramos, Andreia; Gonçalves, David (Current Zoology, 2022)
The physiological mechanisms underlying variation in aggression in fish remain poorly understood. One possibly confounding variable is the lack of standardization in the type of stimuli used to elicit aggression. The presentation of controlled stimuli in videos, a.k.a. video playback, can provide better control of the fight components. However, this technique has produced conflicting results in animal behaviour studies and needs to be carefully validated. For this, a similar response to the video and an equivalent live stimulus needs to be demonstrated. Further, different physiological responses may be triggered by live and video stimuli and it is important to demonstrate that video images elicit appropriate physiological reactions. Here, the behavioural and endocrine response of male Siamese fighting fish Betta splendens to a matched for size conspecific fighting behind a one-way mirror, presented live or through video playback, was compared. The video playback and live stimulus elicited a strong and similar aggressive response by the focal fish, with a fight structure that started with stereotypical threat displays and progressed to overt attacks. Post-fight plasma levels of the androgen 11-ketotestosterone were elevated as compared to controls, regardless of the type of stimuli. Cortisol also increased in response to the video images, as previously described for live fights in this species. These results show that the interactive component of a fight, and its resolution, are not needed to trigger an endocrine response to aggression in this species. The study also demonstrates for the first time in a fish a robust endocrine response to video stimuli and supports the use of this technique for researching aggressive behaviour in B. splendens.

Examination of sex-related differences in intestinal and gonadal lipid metabolism in the sea cucumber Apostichopus japonicus - Zhang, Shuangyan; Ru, Xiaoshang; Zhang, Libin; Gonçalves, David; Yang, Hongsheng (Aquaculture, 2023)
Reproduction of the sea cucumber Apostichopus japonicus is critical for aquaculture production. Gonadal development is the basis of reproduction, and lipids, which are among the main nutrients required for gonadal development, directly affect reproduction. We investigated whether gonadal and intestinal lipid metabolism differed between male and female A. japonicus. Transcriptome analysis of the intestines of sexually mature male and female wild-caught individuals revealed differences in gene expression, with 27 and 39 genes being up-regulated in females and males, respectively. In particular, the expression of the fatty acid synthase gene was higher in males than in females. Metabolome analysis of the gonads identified 141 metabolites that were up-regulated and 175 metabolites that were down-regulated in the testes compared with the ovaries in the positive/negative mode of an LC-MS/MS analysis. A variety of polyunsaturated fatty acids were found at higher concentrations in the testes than in the ovaries. 16 s rDNA sequencing analysis showed that the composition and structure of the intestinal microbiota were similar between males and females. These results suggest that sex differences in intestinal metabolism of A. japonicus are not due to differences in the microbiota, and we speculate that gonadal metabolism may be related to intestinal morphology. This information might be useful in improving the reproductive efficiency of sea cucumbers in captivity.
Keywords: Gonads; Intestines; Lipid metabolism; Sea cucumber; Sex differences

Recent Progress in the Discovery and Design of Antimicrobial Peptides Using Traditional Machine Learning and Deep Learning - Yan, Jielu; Cai, Jianxiu; Zhang, Bob; Wang, Yapeng; Wong, Derek F.; Siu, Shirley W. I. (Antibiotics, 2022)
Antimicrobial resistance has become a critical global health problem due to the abuse of conventional antibiotics and the rise of multi-drug-resistant microbes. Antimicrobial peptides (AMPs) are a group of natural peptides that show promise as next-generation antibiotics due to their low toxicity to the host, broad spectrum of biological activity, including antibacterial, antifungal, antiviral, and anti-parasitic activities, and great therapeutic potential, such as anticancer, anti-inflammatory, etc. Most importantly, AMPs kill bacteria by damaging cell membranes using multiple mechanisms of action rather than targeting a single molecule or pathway, making it difficult for bacterial drug resistance to develop. However, experimental approaches used to discover and design new AMPs are very expensive and time-consuming. In recent years, there has been considerable interest in using in silico methods, including traditional machine learning (ML) and deep learning (DL) approaches, to drug discovery. While there are a few papers summarizing computational AMP prediction methods, none of them focused on DL methods. In this review, we aim to survey the latest AMP prediction methods achieved by DL approaches. First, the biology background of AMP is introduced, then various feature encoding methods used to represent the features of peptide sequences are presented. We explain the most popular DL techniques and highlight the recent works based on them to classify AMPs and design novel peptide sequences. Finally, we discuss the limitations and challenges of AMP prediction.
Number: 10
Keywords: antimicrobial peptide; classification; deep learning; machine learning; medicine; regression; therapeutic peptide

In Memorial and Serenity: Introducing VR Grave Mourning in the Chapel of St. Michael in Macao - Olga Ng Ka Man, Sandra; Caires, Carlos Sena (International Journal of Creative Interfaces and Computer Graphics, 2022)
Macao inhabit a population of 683,100. The birth rate has been dropping while the death rate has risen compared to two years ago. Cemeteries are becoming crowded, and burial spots are demanding. In this case, video calls and social media can be the solution. How about our beloved ancestors? Can we video call them on their memorial days? This paper presents a VR experience of immersing oneself in the 3D VR of the Chapel of St. Michael of Macao to create a peaceful atmosphere for grave mourning. The chapel is also a personal space where we can be truly isolated in serenity. It is a retreat to pray, disconnect, and reconnect to the beloved deaths that may not be buried in an easily accessible location. The authors propose a possible future of mourning our loved ones through virtual reality and telepresence: an immersive experience connected with Macao's extraordinary and cultural unicity.

An Exploratory Study on the Possibility of Harmonizing Investment Protection Regimes within the OHADA Zone - Diakité, A. D.; Thiam, A. B. (Transnational Dispute Management (TDM), 2022)
Abstract With its large population and natural resources, Africa needs investors who can sustain its development. At the same time, foreign investors expect returns on their investments. In ...

Conflict between affective versus continuance commitment among casino dealers - Kuok, A. C. H; Taormina, Robert J. (Evidence-based HRM: a Global Forum for Empirical Scholarship, 2015)
Purpose – The purpose of this paper is to empirically investigate the extent of the reported low affective commitment compared to continuance commitment of Chinese casino dealers, to discern if there is a significant difference between the two types of commitment, and to identify factors that could explain the difference between them. Design/methodology/approach – Questionnaire data were obtained from 247 Chinese casino dealers working for the three major casino groups in Macau. Correlations and regressions were used to analyze the data. Findings – Dealers’ affective commitment was significantly lower than their continuance commitment, suggesting dealers do not like their jobs but do not leave them, which indicates they have cognitive dissonance about their jobs. Organizational socialization, organizational support, and supervisor integrity were positively correlated with affective commitment; while value of money, pay satisfaction, and neuroticism, were positively correlated with continuance commitment. Organizational support was the strongest predictor of affective commitment, while the value they place on money was the strongest predictor of continuance commitment. Practical implications – Casino managers could improve dealers’ affective commitment by facilitating their organizational socialization, especially training and rewards for their work, providing greater organizational support, and fair and supportive treatment from their supervisors. Originality/value – This is the first study to provide evidence of the difference between affective and continuance commitment in Chinese society, and identifies factors that influence each type of commitment, and may help resolve the employees’ dilemma about their jobs, which is an important concern for Chinese managers.
8 citations (Crossref) [2022-11-01]

Insights for management among non-gaming industries: Employees’ dissonance in a casino dominant economy - Kuok, A.C.H. (Revista de Psicología del Trabajo y de las Organizaciones, 2017)
2 citations (Crossref) [2022-11-01]

The antecedents of In-service teachers’ burnout in a casino dominant economy - Kuok, A. C. H.; Lam, S. M. I (KEDI Journal of Educational Policy, 2018)

College Students’ Attitudes Toward Counseling for Mental Health Issues in Two Developing Asian Countries - Kuok, A. C. H; Rashidnia, J (Spritual Psychology and Counseling, 2019)

THE INTERPLAY BETWEEN A CONFUCIAN-HERITAGE CULTURE AND TEACHERS' SENTIMENTS AND ATTITUDES TOWARDS INCLUSION IN MACAU - Correia, Ana; Forlin, Chris; Teixeira, Vitor Manuel dos Santos; Kuok, A. C. H.; Monteiro, Elisa (Zenodo, 2019)
Macau Special Administration Region (Macau SAR) is in the process of revising legislation concerning special and inclusive education. While the institutional discourse revolves around establishing inclusive education, it is unclear as to how the proposed changes will enable or depress this from occurring. This research, therefore, examined teachers’ attitudes towards inclusion as an indication of how well the new legislation may be received. Specifically, it investigated the interplay between 508 teachers working in private schools in Macau, that identified themselves as being inclusive schools, and teachers’ sentiments and attitudes towards the acceptance of inclusion and the role that Confucian values might play in shaping these attitudes. Discussion focusses on four key outcomes that need to be addressed if a significant improvement in including all children in regular schools in Macau is to be achieved. These include the need (1) to clarify the concept of inclusion at government, school, and teacher levels as it currently has ambiguous meaning; (2) to provide teachers with more opportunities to have systematic contacts with students with SEN, as this is crucial to improving their sentiments and attitudes toward people with disability; (3) to provide professional learning about inclusive education with better partnerships between teacher education institutions and schools to bridge theory and practice; and (4) to review the hidden influence of the subtle levels of time-honoured Confucian beliefs in Macau, which are not manifest nor easily detected but possibly have a deep impact on day-to-day practices.

Elite athletes’ mental well-being and life satisfaction: a study of elite athletes’ resilience and social support from an Asian unrecognisedNational Olympic Committee - Kuok, A. C. H; K. I. Chio, David; C. H. Pun, Alan (Health Psychology Report, 2021)
Introduction This study aimed to investigate elite athletes’ mental well-being, and to ascertain whether the personal factor resilience and the social factor social support can play a role in promoting mental well-being and life satisfaction. In addition, this is one of the first studies to investigate well-being among elite athletes who are from a region belonging to an unrecognised National Olympic Committee and are not eligible to join the Olympic Games. Material and methods Eighty-four full-time elite athletes (37 males, 47 females) with mean age of 22.36 years old participated in this quantitative research study. Formal letters describing the purpose and organiser of the study were sent to the sport entities in Macao asking their permission for the researchers to contact the elite athletes to participate in this study. After gaining the permission, the elite athletes belonging to these entities were approached individually, to inform them of the purpose of the study and receive their consent. Results Regression revealed that emotional support and adaptability of resilience were strong positive predictors of mental well-being. Additionally, mental well-being was found to be a strong positive predictor of life satisfaction. The results reflected that in elite athletes possessing high adaptability and receiving more emotional support could help to maintain their mental well-being. Conclusions Implications (based on the findings) are discussed in order to provide insights for policy makers or coaches how to promote elite athletes’ mental well-being.
0 citations (Crossref) [2022-10-30]

Measuring Specific Traditional Chinese Values in Relation to Satisfaction of the Five Maslow Needs - Taormina, Robert J.; Gao, Jennifer H.; Kuok, A. C.H. (Psychological Thought, 2022)
To determine whether living according to specific traditional Chinese cultural values was associated with satisfaction of the five needs in Maslow’s motivational hierarchy and overall life satisfaction, a mixed-method approach was employed, with an empirical questionnaire and supplemental interviews. The questionnaire assessed the hypothesized relationships that traditional Chinese values had with personal life outcomes, including health, employment, satisfaction of the five needs from Maslow’s hierarchy, and life satisfaction. The interviews examined the relationships that several demographic variables had with living by traditional Chinese values. The results of the empirical data revealed that most Chinese people today are still living according to the traditional Chinese cultural values, and that living by those traditional values are strongly associated with satisfaction of all five of the human needs in the Maslow hierarchy, as well as with overall life satisfaction. Additionally, the results of the qualitative interviews readily supported the empirical findings, and also revealed that the time during which inter-generational transmission of the Chinese cultural values occurs is when parents teach those values to their children at a very early age, that is, between 3 and 8 years old, before the children start primary school.
0 citations (Crossref) [2022-10-30]

A positivist approach to work engagement: moderating effects of perceived organizational support - Kuok, A. C. H; Taormina, Robert J. (Dynamic Relationships Management Journal, 2022)
0 citations (Crossref) [2022-10-30]

Self-Efficacy, Stress and Job Satisfaction among Pre-Service, Novice and Experienced English Teachers: A Study of their Occupational Health - Lam, Stacy; Kuok, A. C. H.; Sze, Tat Ming (Health Psychology Report, 2022)
Background This study aimed to investigate English teachers’ self-efficacy for student engagement, classroom management, instructional strategies and literacy instruction, as well as to discover teacher stress and job satisfaction can play a role in interfering their occupational health (in terms of self-efficacy). In addition, this is one of the first studies to understand the differences in self-efficacy among pre-service, novice and experienced in-service teachers in a Chinese society, where English is positioned as a foreign language. Participants and procedure 271 English teachers (90 pre-service, 181 in-service) with mean teaching experience of 5.57 months for per-service, and 98.51 months for in-service were participated in this quantitative research study, as the targets were not be able to approach randomly, the English teachers were approaching individually though referral sampling, informing that the purpose of the study and receive their consent. Results It discovered both pre-service and novice in-service teachers posses lowest self-efficacy. Moreover, teachers’ stress from classroom predicted their self-efficacy for student engagement and classroom management negatively. On the other hand, teachers’ job satisfaction predicts their self-efficacy for student engagement, instructional strategies and literacy instruction positively. Conclusions Implications (based on the findings) are discussed in order to provide insights for for schools and education departments to strengthen the teachers’ capability of teaching and their occupational health.
0 citations (Crossref) [2022-10-30]

Emotional Intelligence, Work Satisfaction, and Affective Commitment: An Occupational Health Study of Social Workers - Kuok, A. C. H. (Journal of Work and Organizational Psychology, 2022)
Social workers’ work engagement and burnout were tested in relation to (a) personal variable, i.e., emotional intelligence; (b) organizational variables, i.e., work satisfaction and affective commitment. Regressions revealed emotional intelligence - controlling self – negatively predicted depersonalization and reduced personal accomplishment and positively predicted three facets of work engagement. Emotional intelligence - understanding others – was a negative predictor of reduced personal accomplishment. In addition, work satisfaction negatively predicted three components of burnout and positively predicted emotional work engagement. Affective commitment was a positive predictor of three facets of work engagement and negatively predicted reduced personal accomplishment. Implications for management are discussed.
Company: Colegio Oficial de Psicologos de Madrid (copmadrid) Distributor: Colegio Oficial de Psicologos de Madrid (copmadrid) Institution: Colegio Oficial de Psicologos de Madrid (copmadrid) Label: Colegio Oficial de Psicologos de Madrid (copmadrid)

Design Explorations for 3D-Printed Modular Markers for eXtended-Reality Tangible User Interfaces: - Iok Fong, Chau; Cardoso, Jorge C. S.; Estadieu, Gerald Vincent (International Journal of Creative Interfaces and Computer Graphics, 2022)
Various materials, objects, and sensors have been explored earlier for creating tangible user interfaces (TUIs). However, there is little work on 3D-printed TUIs based on visual markers for smartphone-based extended reality (XR) experiences. The combination of visual markers and smartphones results in cheap, accessible XR systems within reach of many people. Combined with 3D printing, it could foster do-it-yourself (DIY) projects for XR experiences, which may further expand and open-up possibilities for accessible and tangible interaction. This work explores the design space of modular 3D-printed tangibles for smartphone-based XR. The authors report the design exploration process, provide several interactive 3D-printed markers, and reflect on the resulting possibilities.
0 citations (Crossref) [2022-10-27]

Trace-element compositions of sulfides from inactive Tianzuo hydrothermal field, Southwest Indian Ridge: Implications for ultramafic rocks hosting mineralization - Ding, Teng; Wang, Jia; Tao, Chunhui; Dias, Ágata Alveirinho; Liang, Jin; Wang, Yuan; Chen, Jie; Wu, Bin; Huang, Hui (Ore Geology Reviews, 2022)
The recently explored inactive Tianzuo hydrothermal field, in the amagmatic segment of the ultraslow-spreading Southwest Indian Ridge (SWIR), is closely associated with detachment faults. In this site, sulfide minerals are hosted by serpentine-bearing ultramafic rocks and include high-temperature (isocubanite, sphalerite, and minor pyrrhotite) and low-temperature (pyrite I, marcasite, pyrite II, and covellite) phases. In this study, trace-element concentrations of isocubanite and pyrite II were used to elucidate mineralization processes in ultramafic rocks hosting sulfides. Results show that isocubanite is enriched in metals such as Cu, Co, Sn, Te, Zn, Se, Pb, Bi, Cd, Ag, In, and Mn, and pyrite II is enriched in Mo and Tl. The marked enrichment in Te, Cu, Co, and In in isocubanite (compared with Se, Zn, Ni, and Sn, respectively) is most likely due to the contribution of magmatic fluids from gabbroic intrusions beneath the hydrothermal field. The intrusion of gabbroic magmas would have enhanced serpentinization reactions and provided a relatively oxidizing environment through the dissolution of anhydrite precipitated previously in the reaction zone, within high temperature and low pH conditions. This might have facilitated the extraction of metals by initial hydrothermal fluids, leading to the general enrichment of most metals in isocubanite. Metals in pyrite II have compositions similar to those of isocubanite, except for strong depletion in magmatically derived Te, Cu, Co, and In. This means that serpentinization processes had a dominating role in pyrite II precipitation as well. The enrichment of pyrite II in Mo and Tl is also indicative of seawater contribution in its composition. The study concludes that serpentinization reactions contribute effectively both to high- and low-temperature sulfide mineralization at Tianzuo hydrothermal field, with gabbroic intrusions further promoting high-temperature sulfide mineralization, providing additional metals, fluids and heat. In contrast, low-temperature sulfide mineralization occurred during the cooling of gabbroic intrusions, with decreasing rates of serpentinization reactions and a significant influence of seawater.
Keywords: SWIR; Serpentinization; Sulfide; Tianzuo; Trace-element; Ultramafic rocks

Geochemistry, sulfur and lead isotopic composition of hydrothermal sulfide from the Duanqiao hydrothermal field on the Southwest Indian Ridge: implications for ore genesis - Yang, Weifang; Liao, Shili; Alveirinho Dias, Ágata; Liang, Jin; Li, Wei; Ding, Teng; Tao, Chunhui (International Geology Review, 2022)
Hydrothermal activities on ultraslow-spreading ridges exhibit diverse characteristics, long histories with multiple participants, and might form large-scale, high-grade sulfide deposits. The Duanqiao hydrothermal field (DHF) is located at the segment with the thickest oceanic crust and a large axial magma chamber on the Southwest Indian Ridge, providing unique perspective of sulfide metallogenesis on ultraslow-spreading ridges. Previous studies revealed that DHF sulfide exhibits distinct features of enrichment of ore-forming elements in comparison with those of hydrothermal fields on sediment-starved mid-ocean ridges. However, the genesis and processes responsible for such differences remain poorly constrained. In this study, mineralogical, geochemical and S and Pb isotopic analyses were performed on relict sulfide mound samples to characterize DHF formation. The samples show clear concentric mineral zonation from the interior to the exterior wall. Assemblages of chalcopyrite, sphalerite, and pyrite are distributed mainly in the interior wall, whereas pyrite and marcasite are distributed mainly in the exterior wall. The low Cu content and Pb isotopic composition of the sulfide indicate that the metals are derived mainly from basement basalts. The δ34S values exhibit positive values distributed over a reasonably narrow range (2.42‰–7.97‰), which suggests approximately 62.1%–88.5% of S with basaltic origin. Compared with most hydrothermal fields along the sediment starved mid-ocean ridges, the DHF sulfide shows particularly high contents of Pb (263–2630 ppm), As (234–726 ppm), Sb (7.32–44.3 ppm), and Ag (35.2 to >100 ppm). The δ34S values exhibit an increasing tendency from the sample exterior to the interior. We propose that these features probably reflect the existence of a subsurface zone refining process. Our results provide new insight into the sulfide formation process and contribute to understanding the metallogenic mechanism of hydrothermal sulfides on ultraslow-spreading ridges.
_eprint: https://doi.org/10.1080/00206814.2022.2081937
Keywords: Hydrothermal sulfide; geochemistry; southwest Indian ridge; sulfur isotope; zone refining

Material Source of Sediments from West Clarion–Clipperton Zone (Pacific): Evidence from Rare Earth Element Geochemistry and Clay Minerals Compositions - Qiu, Zhongrong; Tao, Chunhui; Ma, Weilin; Dias, Ágata Alveirinho; Hu, Siyi; Shao, Yuexiao; Yang, Kehong; Zhang, Weiyan (Journal of Marine Science and Engineering, 2022)
The geochemistry and mineralogy of sediments provide relevant information for the understanding of the origin and metallogenic mechanism of ferromanganese nodules and crusts. At present, there are still few studies on the sediment origin of the Clarion–Clipperton Zone (CCZ) of the east Pacific, particularly on the systematic origin of sediments with a longer history/length. Here, bulk sediment geochemistry and clay mineral compositions were analyzed on a 5.7 m gravity core (GC04) obtained at the CCZ, an area rich in polymetallic nodules. The results indicate that the average total content of rare earth elements (REE), including yttrium (REY), in sediments is 454.7 ppm and the REEs distribution patterns normalized by the North American Shale Composite of samples are highly consistent, with all showing negative Ce anomalies and more obvious enrichment in heavy REE (HREE) than that of light REE (LREE). Montmorillonite/illite ratio, discriminant functions and smear slide identification indicate multiple origins for the material, and are strongly influenced by contributions from marine biomass, while terrestrial materials, seamount basalts and their alteration products and authigenic source also make certain contributions. The REY characteristics of the sediments in the study area are different from those of marginal oceanic and back-arc basins, and more similar to pelagic deep-sea sediments. Based on LREE/HREE-1/δCe and LREE/HREE-Y/Ho diagrams, we conclude that samples from the study area had pelagic sedimentary properties which suffered from a strong “seawater effect”.
Number: 8
Keywords: Clarion–Clipperton Zone; material source; rare earth elements; sediments geochemistry

Hydrothermal remobilization of subseafloor sulfide mineralization along mid-ocean ridges contributes to the global oceanic zinc isotopic mass balance - Liao, Shili; Tao, Chunhui; Wen, Hanjie; Yang, Weifang; Liu, Jia; Jamieson, John W.; Dias, Ágata Alveirinho; Zhu, Chuanwei; Liang, Jin; Li, Wei; Ding, Teng; Li, Xiaohu; et al. (Geochimica et Cosmochimica Acta, 2022)
Hydrothermal activity on mid-ocean ridges is an important mechanism for the delivery of Zn from the mantle to the surface environment. Zinc isotopic fractionation during hydrothermal activity is mainly controlled by the precipitation of Zn-bearing sulfide minerals, in which isotopically light Zn is preferentially retained in solid phases rather than in solution during mineral precipitation. Thus, seafloor hydrothermal activity is expected to supply isotopically heavy Zn to the ocean. Here, we studied sulfide-rich samples from the Duanqiao-1 hydrothermal field, located on the Southwest Indian Ridge. We report that, at the hand-specimen scale, late-stage conduit sulfide material has lower δ66Zn values (−0.05 ± 0.15 ‰; n = 19) than early-stage material (+0.13 ± 0.15 ‰; n = 10). These lower values correlate with enrichments in Pb, As, Cd, and Ag, and elevated δ34S values. We attribute the low δ66Zn values to the remobilization of earlier sub-seafloor Zn-rich mineralization. Based on endmember mass balance calculations, and an assumption of a fractionation factor (αZnS-Sol.) of about 0.9997 between sphalerite and its parent solution, the remobilized Zn was found consist of about 1/3 to 2/3 of the total Zn in the fluid that formed the conduit samples. Our study suggests that late-stage subsurface hydrothermal remobilization may release isotopically-light Zn to the ocean, and that this process may be common along mid-ocean ridges, thus increasing the size of the previously identified isotopically light Zn sink in the ocean.
Keywords: Hydrothermal activity; Mid ocean ridge; Subsurface remobilization; Zinc isotopic mass balance

Macao air quality forecast using statistical methods - Lei, Man Tat; Monjardino, Joana; Mendes, Luisa; Ferreira, Francisco (International Journal of Environmental Impacts: Management, Mitigation and Recovery, 2019)
0 citations (Crossref) [2022-09-21]

Macao air quality forecast using statistical methods - Lei, Man Tat; Monjardino, Joana; Mendes, Luisa; Gonçalves, David; Ferreira, Francisco (Air Quality, Atmosphere & Health, 2019)
The levels of air pollution in Macao often exceeded the levels recommended by WHO. In order for the population to take precautionary measures and avoid further health risks under high pollutant exposure, it is important to develop a reliable air quality forecast. Statistical models based on linear multiple regression (MR) and classification and regression trees (CART) analysis were developed successfully, for Macao, to predict the next day concentrations of NO2, PM10, PM2.5, and O3. All the developed models were statistically significantly valid with a 95% confidence level with high coefficients of determination (from 0.78 to 0.93) for all pollutants. The models utilized meteorological and air quality variables based on 5 years of historical data, from 2013 to 2017. Data from 2013 to 2016 were used to develop the statistical models and data from 2017 was used for validation purposes. A wide range of meteorological and air quality variables was identified, and only some were selected as significant independent variables. Meteorological variables were selected from an extensive list of variables, including geopotential height, relative humidity, atmospheric stability, and air temperature at different vertical levels. Air quality variables translate the resilience of the recent past concentrations of each pollutant and usually are maximum and/or the average of latest 24-h levels. The models were applied in forecasting the next day average daily concentrations for NO2 and PM and maximum hourly O3 levels for five air quality monitoring stations. The results are expected to be an operational air quality forecast for Macao.
24 citations (Crossref) [2022-09-21]
Keywords: Macao; NO2; O3; PM10; PM2.5; Particulate matter

Statistical Forecast of Pollution Episodes in Macao during National Holiday and COVID-19 - Lei, Man Tat; Monjardino, Joana; Mendes, Luisa; Gonçalves, David; Ferreira, Francisco (International Journal of Environmental Research and Public Health, 2020)
Statistical methods such as multiple linear regression (MLR) and classification and regression tree (CART) analysis were used to build prediction models for the levels of pollutant concentrations in Macao using meteorological and air quality historical data to three periods: (i) from 2013 to 2016, (ii) from 2015 to 2018, and (iii) from 2013 to 2018. The variables retained by the models were identical for nitrogen dioxide (NO2), particulate matter (PM10), PM2.5, but not for ozone (O3) Air pollution data from 2019 was used for validation purposes. The model for the 2013 to 2018 period was the one that performed best in prediction of the next-day concentrations levels in 2019, with high coefficient of determination (R2), between predicted and observed daily average concentrations (between 0.78 and 0.89 for all pollutants), and low root mean square error (RMSE), mean absolute error (MAE), and biases (BIAS). To understand if the prediction model was robust to extreme variations in pollutants concentration, a test was performed under the circumstances of a high pollution episode for PM2.5 and O3 during 2019, and the low pollution episode during the period of implementation of the preventive measures for COVID-19 pandemic. Regarding the high pollution episode, the period of the Chinese National Holiday of 2019 was selected, in which high concentration levels were identified for PM2.5 and O3, with peaks of daily concentration exceeding 55 μg/m3 and 400 μg/m3, respectively. The 2013 to 2018 model successfully predicted this high pollution episode with high coefficients of determination (of 0.92 for PM2.5 and 0.82 for O3). The low pollution episode for PM2.5 and O3 was identified during the 2020 COVID-19 pandemic period, with a low record of daily concentration for PM2.5 levels at 2 μg/m3 and O3 levels at 50 μg/m3, respectively. The 2013 to 2018 model successfully predicted the low pollution episode for PM2.5 and O3 with a high coefficient of determination (0.86 and 0.84, respectively). Overall, the results demonstrate that the statistical forecast model is robust and able to correctly reproduce extreme air pollution events of both high and low concentration levels.
8 citations (Crossref) [2022-09-21] Number: 14
Keywords: COVID-19; air pollution; air quality forecast; modelling; national holiday; pollution episodes

Statistical Forecast Applied to Two Macao Air Monitoring Stations - Lei, M.; Monjardino, J.; Mendes, L.; Gonçalves, D.; Ferreira, F. (IOP Conference Series: Earth and Environmental Science, 2020)
The levels of air pollution in Macao often exceeded the levels recommended by WHO. In order for the population to take precautionary measures and avoid further health risks under high pollutant exposure, it is important to develop a reliable air quality forecast. Statistical models based on multiple regression (MR) analysis were developed successfully for Macao to predict the next day concentrations of PM10, PM2.5, and NO2. All the developed models were statistically significantly valid with a 95% confidence level with high coefficients of determination (from 0.89 to 0.92) for all pollutants. The models utilized meteorological and air quality variables based on five years of historical data, from 2013 to 2017. The data from 2013 to 2016 were used to develop the statistical models and data from 2017 were used for validation purposes. A wide range of meteorological and air quality variables were identified, and only some were selected as significant dependent variables. Meteorological variables were selected from an extensive list of variables, including geopotential height, relative humidity, atmospheric stability, and air temperature at different vertical levels. Air quality variables translate the resilience of the recent past concentrations of each pollutant and usually are maximum and/or the average of latest 24-hour levels. The models were applied in forecasting the next day average daily concentrations for PM10, PM2.5, and NO2 for the air quality monitoring stations. The results are expected to be an operational air quality forecast for Macao.
0 citations (Crossref) [2022-09-21]

Vocal differentiation parallels development of auditory saccular sensitivity in a highly soniferous fish - Vasconcelos, Raquel O.; Alderks, Peter W.; Ramos, Andreia; Fonseca, Paulo J.; Amorim, M. Clara P.; Sisneros, Joseph A. (Journal of Experimental Biology, 2015)
Vocal differentiation is widely documented in birds and mammals but has been poorly investigated in other vertebrates, including fish, which represent the oldest extant vertebrate group. Neural circuitry controlling vocal behaviour is thought to have evolved from conserved brain areas that originated in fish, making this taxon key to understanding the evolution and development of the vertebrate vocal-auditory systems. This study examines ontogenetic changes in the vocal repertoire and whether vocal differentiation parallels auditory development in the Lusitanian toadfish Halobatrachus didactylus (Batrachoididae). This species exhibits a complex acoustic repertoire and is vocally active during early development. Vocalisations were recorded during social interactions for four size groups (fry: <2 cm; small juveniles: 2–4 cm; large juveniles: 5–7 cm; adults >25 cm, standard length). Auditory sensitivity of juveniles and adults was determined based on evoked potentials recorded from the inner ear saccule in response to pure tones of 75–945 Hz. We show an ontogenetic increment in the vocal repertoire from simple broadband-pulsed ‘grunts’ that later differentiate into four distinct vocalisations, including low-frequency amplitude-modulated ‘boatwhistles’. Whereas fry emitted mostly single grunts, large juveniles exhibited vocalisations similar to the adult vocal repertoire. Saccular sensitivity revealed a three-fold enhancement at most frequencies tested from small to large juveniles; however, large juveniles were similar in sensitivity to adults. We provide the first clear evidence of ontogenetic vocal differentiation in fish, as previously described for higher vertebrates. Our results suggest a parallel development between the vocal motor pathway and the peripheral auditory system for acoustic social communication in fish.
11 citations (Crossref) [2022-09-21]

Noise-induced hearing loss in zebrafish: investigating structural and functional inner ear damage and recovery - Breitzler, Lukas; Lau, Ieng Hou; Fonseca, Paulo J.; Vasconcelos, Raquel O. (Hearing Research, 2020)
Exposure to continuous moderate noise levels is known to impair the auditory system leading to Noise-Induced Hearing Loss (NIHL) in animals including humans. The mechanism underlying noise-dependent auditory Temporary Threshold Shifts (TTS) is not fully understood. In fact, only limited information is available on vertebrates such as fishes, which share homologous inner ear structures to mammals and have the ability to regenerate hair cells. The zebrafish Danio rerio is a well-established model in hearing research providing an unmatched opportunity to investigate the molecular and physiological mechanisms of NIHL at the sensory receptor level. Here we investigated for the first time the effects of noise exposure on TTS and functional recovery in zebrafish, as well as the associated morphological damage and regeneration of the inner ear saccular hair cells. Adult specimens were exposed for 24h to white noise at various amplitudes (130, 140 and 150 dB re. 1 μPa) and their auditory sensitivity was subsequently measured with the Auditory Evoked Potential (AEP) recording technique. Sensory recovery was tested at different times post-treatment (after 3, 7 and 14 days) and compared to individuals kept under quiet lab conditions. Results revealed noise level-dependent TTS up to 33 dB and increase in response latency. Recovery of hearing function occurred within 7 days for fish exposed to 130 and 140 dB noise levels, while fish subject to 150 dB only returned to baseline thresholds after 14 days. Hearing impairment was accompanied by significant loss of hair cells only at the highest noise treatment. Full regeneration of the sensory tissue (number of hair cell receptors) occurred within 7 days, which was prior to functional recovery. We provide first baseline data of NIHL in zebrafish and validate this species as an effective vertebrate model to investigate the impact of noise exposure on the structure and function of the adult inner ear and its recovery process.
14 citations (Crossref) [2022-09-21]
Keywords: Fish; Hair cells; Hearing sensitivity; Noise; Sound pressure level; Temporary threshold shift

Impact of noise on development, physiological stress and behavioural patterns in larval zebrafish - Lara, Rafael A.; Vasconcelos, Raquel O. (Scientific Reports, 2021)
Noise pollution is increasingly present in aquatic ecosystems, causing detrimental effects on growth, physiology and behaviour of organisms. However, limited information exists on how this stressor affects animals in early ontogeny, a critical period for development and establishment of phenotypic traits. We tested the effects of chronic noise exposure to increasing levels (130 and 150 dB re 1 μPa, continuous white noise) and different temporal regimes on larval zebrafish (Danio rerio), an important vertebrate model in ecotoxicology. The acoustic treatments did not affect general development or hatching but higher noise levels led to increased mortality. The cardiac rate, yolk sac consumption and cortisol levels increased significantly with increasing noise level at both 3 and 5 dpf (days post fertilization). Variation in noise temporal patterns (different random noise periods to simulate shipping activity) suggested that the time regime is more important than the total duration of noise exposure to down-regulate physiological stress. Moreover, 5 dpf larvae exposed to 150 dB continuous noise displayed increased dark avoidance in anxiety-related dark/light preference test and impaired spontaneous alternation behaviour. We provide first evidence of noise-induced physiological stress and behavioural disturbance in larval zebrafish, showing that both noise amplitude and timing negatively impact key developmental endpoints in early ontogeny.
7 citations (Crossref) [2022-09-21] Number: 1
Keywords: Embryology; Environmental impact; Freshwater ecology

Noise-induced hearing loss correlates with inner ear hair cell decrease in larval zebrafish - Lara, Rafael A.; Breitzler, Lukas; Lau, Ieng Hou; Gordillo-Martinez, Flora; Chen, Fangyi; Fonseca, Paulo J.; Bass, Andrew H.; Vasconcelos, Raquel O. (Journal of Experimental Biology, 2022)
Anthropogenic noise can be hazardous for the auditory system and wellbeing of animals, including humans. However, very limited information is known on how this global environmental pollutant affects auditory function and inner ear sensory receptors in early ontogeny. The zebrafish (Danio rerio) is a valuable model in hearing research, including investigations of developmental processes of the vertebrate inner ear. We tested the effects of chronic exposure to white noise in larval zebrafish on inner ear saccular sensitivity and morphology at 3 and 5 days post-fertilization (dpf), as well as on auditory-evoked swimming responses using the prepulse inhibition (PPI) paradigm at 5 dpf. Noise-exposed larvae showed a significant increase in microphonic potential thresholds at low frequencies, 100 and 200 Hz, while the PPI revealed a hypersensitization effect and a similar threshold shift at 200 Hz. Auditory sensitivity changes were accompanied by a decrease in saccular hair cell number and epithelium area. In aggregate, the results reveal noise-induced effects on inner ear structure–function in a larval fish paralleled by a decrease in auditory-evoked sensorimotor responses. More broadly, this study highlights the importance of investigating the impact of environmental noise on early development of sensory and behavioural responsiveness to acoustic stimuli.
2 citations (Crossref) [2022-09-21]

The effect of time regime in noise exposure on the auditory system and behavioural stress in the zebrafish - Wong, Man Ieng; Lau, Ieng Hou; Gordillo-Martinez, Flora; Vasconcelos, Raquel O. (Scientific Reports, 2022)
Anthropogenic noise of variable temporal patterns is increasing in aquatic environments, causing physiological stress and sensory impairment. However, scarce information exists on exposure effects to continuous versus intermittent disturbances, which is critical for noise sustainable management. We tested the effects of different noise regimes on the auditory system and behaviour in the zebrafish (Danio rerio). Adult zebrafish were exposed for 24 h to either white noise (150 ± 10 dB re 1 μPa) or silent control. Acoustic playbacks varied in temporal patterns—continuous, fast and slow regular intermittent, and irregular intermittent. Auditory sensitivity was assessed with Auditory Evoked Potential recordings, revealing hearing loss and increased response latency in all noise-treated groups. The highest mean threshold shifts (c. 13 dB) were registered in continuous and fast intermittent treatments, and no differences were found between regular and irregular regimes. Inner ear saccule did not reveal significant hair cell loss but showed a decrease in presynaptic Ribeye b protein especially after continuous exposure. Behavioural assessment using the standardized Novel Tank Diving assay showed that all noise-treated fish spent > 98% time in the bottom within the first minute compared to 82% in control, indicating noise-induced anxiety/stress. We provide first data on how different noise time regimes impact a reference fish model, suggesting that overall acoustic energy is more important than regularity when predicting noise effects.
0 citations (Crossref) [2022-09-21] Number: 1
Keywords: Ecology; Neuroscience; Physiology; Zoology

Instance-based deep transfer learning with attention for stock movement prediction - He, Qi-Qiao; Siu, Shirley Weng In; Si, Yain-Whar (Applied Intelligence, 2022)
Stock movement prediction is one of the most challenging problems in time series analysis due to the stochastic nature of financial markets. In recent years, a plethora of statistical methods and machine learning algorithms were proposed for stock movement prediction. Specifically, deep learning models are increasingly applied for the prediction of stock movement. The success of deep learning models relies on the assumption that massive training data are available. However, this assumption is impractical for stock movement prediction. In stock markets, a large number of stocks do not have enough historical data, especially for the companies which underwent initial public offering in recent years. In these situations, the accuracy of deep learning models to predict the stock movement could be affected. To address this problem, in this paper, we propose novel instance-based deep transfer learning models with attention mechanism. In the experiments, we compare our proposed methods with state-of-the-art prediction models. Experimental results on three public datasets reveal that our proposed methods significantly improve the performance of deep learning models when limited training data are available.
0 citations (Crossref) [2022-09-21]
Keywords: Attention mechanism; Deep transfer learning; Instance-based; Stock movement prediction

Chemical toxicity prediction based on semi-supervised learning and graph convolutional neural network - Chen, Jiarui; Si, Yain-Whar; Un, Chon-Wai; Siu, Shirley W. I. (Journal of Cheminformatics, 2021)
As safety is one of the most important properties of drugs, chemical toxicology prediction has received increasing attentions in the drug discovery research. Traditionally, researchers rely on in vitro and in vivo experiments to test the toxicity of chemical compounds. However, not only are these experiments time consuming and costly, but experiments that involve animal testing are increasingly subject to ethical concerns. While traditional machine learning (ML) methods have been used in the field with some success, the limited availability of annotated toxicity data is the major hurdle for further improving model performance. Inspired by the success of semi-supervised learning (SSL) algorithms, we propose a Graph Convolution Neural Network (GCN) to predict chemical toxicity and trained the network by the Mean Teacher (MT) SSL algorithm. Using the Tox21 data, our optimal SSL-GCN models for predicting the twelve toxicological endpoints achieve an average ROC-AUC score of 0.757 in the test set, which is a 6% improvement over GCN models trained by supervised learning and conventional ML methods. Our SSL-GCN models also exhibit superior performance when compared to models constructed using the built-in DeepChem ML methods. This study demonstrates that SSL can increase the prediction power of models by learning from unannotated data. The optimal unannotated to annotated data ratio ranges between 1:1 and 4:1. This study demonstrates the success of SSL in chemical toxicity prediction; the same technique is expected to be beneficial to other chemical property prediction tasks by utilizing existing large chemical databases. Our optimal model SSL-GCN is hosted on an online server accessible through: https://app.cbbio.online/ssl-gcn/home.
1 citations (Crossref) [2022-09-21]
Keywords: ADMET; Chemical toxicity; Deep learning; Graph convolutional neural network; Mean teacher; Semi-supervised learning; Tox21

Anti-epileptic Kunitz-like peptides discovered in the branching coral Acropora digitifera through transcriptomic analysis - Chen, Hanbin; Siu, Shirley Weng In; Wong, Clarence Tsun Ting; Qiu, Jianwen; Cheung, Alex Kwok-Kuen; Lee, Simon Ming Yuen (Archives of Toxicology, 2022)
Approximately 50 million people are suffering from epilepsy worldwide. Corals have been used for treating epilepsy in traditional Chinese medicine, but the mechanism of this treatment is unknown. In this study, we analyzed the transcriptome of the branching coral Acropora digitifera and obtained its Kyoto Encyclopedia of Genes and Genomes (KEGG), EuKaryotic Orthologous Groups (KOG) and Gene Ontology (GO) annotation. Combined with multiple sequence alignment and phylogenetic analysis, we discovered three polypeptides, we named them AdKuz1, AdKuz2 and AdKuz3, from A. digitifera that showed a close relationship to Kunitz-type peptides. Molecular docking and molecular dynamics simulation indicated that AdKuz1 to 3 could interact with GABAA receptor but AdKuz2–GABAA remained more stable than others. The biological experiments showed that AdKuz1 and AdKuz2 exhibited an anti-inflammatory effect by decreasing the aberrant level of nitric oxide (NO), IL-6, TNF-α and IL-1β induced by LPS in BV-2 cells. In addition, the pentylenetetrazol (PTZ)-induced epileptic effect on zebrafish was remarkably suppressed by AdKuz1 and AdKuz2. AdKuz2 particularly showed superior anti-epileptic effects compared to the other two peptides. Furthermore, AdKuz2 significantly decreased the expression of c-fos and npas4a, which were up-regulated by PTZ treatment. In addition, AdKuz2 reduced the synthesis of glutamate and enhanced the biosynthesis of gamma-aminobutyric acid (GABA). In conclusion, the results indicated that AdKuz2 may affect the synthesis of glutamate and GABA and enhance the activity of the GABAA receptor to inhibit the symptoms of epilepsy. We believe, AdKuz2 could be a promising anti-epileptic agent and its mechanism of action should be further investigated.
0 citations (Crossref) [2022-09-21]
Keywords: Anti-epileptic; GABAA; Kunitz peptide; Transcriptome

A Neuropeptide Y/F-like Polypeptide Derived from the Transcriptome of Turbinaria peltata Suppresses LPS-Induced Astrocytic Inflammation - Chen, Qian; Liang, Zirong; Yue, Qian; Wang, Xiufen; Siu, Shirley Weng In; Pui-Man Hoi, Maggie; Lee, Simon Ming-Yuen (Journal of Natural Products, 2022)
Neuropeptides are a group of neuronal signaling molecules that regulate physiological and behavioral processes in animals. Here, we used in silico mining to predict the polypeptide composition of available transcriptomic data of Turbinaria peltata. In total, 118 transcripts encoding putative peptide precursors were discovered. One neuropeptide Y/F-like peptide, named TpNPY, was identified and selected for in silico structural, in silico binding, and pharmacological studies. In our study, the anti-inflammation effect of TpNPY was evaluated using an LPS-stimulated C8-D1A astrocyte cell model. Our results demonstrated that TpNPY, at 0.75–3 μM, inhibited LPS-induced NO production and reduced the expression of iNOS in a dose-dependent manner. Furthermore, TpNPY reduced the secretion of proinflammatory cytokines. Additionally, treatment with TpNPY reduced LPS-mediated elevation of ROS production and the intracellular calcium concentration. Further investigation revealed that TpNPY downregulated the IKK/IκB/NF-κB signaling pathway and inhibited expression of the NLRP3 inflammasome. Through molecular docking and using an NPY receptor antagonist, TpNPY was shown to have the ability to interact with the NPY Y1 receptor. On the basis of these findings, we concluded that TpNPY might prevent LPS-induced injury in astrocytes through activation of the NPY-Y1R.
0 citations (Crossref) [2022-09-21]

Multi-Branch-CNN: Classification of ion channel interacting peptides using multi-branch convolutional neural network - Yan, Jielu; Zhang, Bob; Zhou, Mingliang; Kwok, Hang Fai; Siu, Shirley W. I. (Computers in Biology and Medicine, 2022)
Ligand peptides that have high affinity for ion channels are critical for regulating ion flux across the plasma membrane. These peptides are now being considered as potential drug candidates for many diseases, such as cardiovascular disease and cancers. In this work, we developed Multi-Branch-CNN, a CNN method with multiple input branches for identifying three types of ion channel peptide binders (sodium, potassium, and calcium) from intra- and inter-feature types. As for its real-world applications, prediction models that are able to recognize novel sequences having high or low similarities to training sequences are required. To this end, we tested our models on two test sets: a general test set including sequences spanning different similarity levels to those of the training set, and a novel-test set consisting of only sequences that bear little resemblance to sequences from the training set. Our experiments showed that the Multi-Branch-CNN method performs better than thirteen traditional ML algorithms (TML13), yielding an improvement in accuracy of 3.2%, 1.2%, and 2.3% on the test sets as well as 8.8%, 14.3%, and 14.6% on the novel-test sets for sodium, potassium, and calcium ion channels, respectively. We confirmed the effectiveness of Multi-Branch-CNN by comparing it to the standard CNN method with one input branch (Single-Branch-CNN) and an ensemble method (TML13-Stack). The data sets, script files to reproduce the experiments, and the final predictive models are freely available at https://github.com/jieluyan/Multi-Branch-CNN.
3 citations (Crossref) [2022-09-21]
Keywords: Classification; Deep learning; Drug discovery; Ion channel; Multi-Branch-CNN; Peptides

Using Machine Learning Methods to Forecast Air Quality: A Case Study in Macao - Lei, Thomas M. T.; Siu, Shirley W. I.; Monjardino, Joana; Mendes, Luisa; Ferreira, Francisco (Atmosphere, 2022)
Despite the levels of air pollution in Macao continuing to improve over recent years, there are still days with high-pollution episodes that cause great health concerns to the local community. Therefore, it is very important to accurately forecast air quality in Macao. Machine learning methods such as random forest (RF), gradient boosting (GB), support vector regression (SVR), and multiple linear regression (MLR) were applied to predict the levels of particulate matter (PM10 and PM2.5) concentrations in Macao. The forecast models were built and trained using the meteorological and air quality data from 2013 to 2018, and the air quality data from 2019 to 2021 were used for validation. Our results show that there is no significant difference between the performance of the four methods in predicting the air quality data for 2019 (before the COVID-19 pandemic) and 2021 (the new normal period). However, RF performed significantly better than the other methods for 2020 (amid the pandemic) with a higher coefficient of determination (R2) and lower RMSE, MAE, and BIAS. The reduced performance of the statistical MLR and other ML models was presumably due to the unprecedented low levels of PM10 and PM2.5 concentrations in 2020. Therefore, this study suggests that RF is the most reliable prediction method for pollutant concentrations, especially in the event of drastic air quality changes due to unexpected circumstances, such as a lockdown caused by a widespread infectious disease.
0 citations (Crossref) [2022-09-21] Number: 9
Keywords: COVID-19; air pollution; air quality; air quality forecast; gradient boosting; multiple linear regression; random forest; support vector regression

Evaluation of mathematical models for QRS feature extraction and QRS morphology classification in ECG signals - do Vale Madeiro, João Paulo; Lobo Marques, João Alexandre; Han, Tao; Coury Pedrosa, Roberto (Measurement, 2020)
It is plausible to assume that the component waves in ECG signals constitute a unique human characteristic because morphology and amplitudes of recorded beats are governed by multiple individual factors. According to the best of our knowledge, the issue of automatically classifying different ’identities’ of QRS morphology has not been explored within the literature. This work proposes five alternative mathematical models for representing different QRS morphologies providing the extraction of a set of features related to QRS shape. The technique incorporates mechanisms of combining the mathematical functions Gaussian, Mexican-Hat and Rayleigh probability density function and also a mechanism for clipping the waveform of those functions. The searching for the optimal parameters which minimize the normalized RMS error between each mathematical model and a given QRS search window enables to find an optimal model. Such modeling behaves as a robust alternative for delineating heartbeats, classifying beat morphologies, detecting subtle and anomalous changes, compression of QRS complex windows among others. The validation process evaluates the ability of each model to represent different QRS morphology classes within 159 full ECG signal records from QT database and 584 QRS search windows from MIT-BIH Arrhythmia database. From the experimental results, we rank the winning rates for which each mathematical model best models and also discriminates the most predominant QRS morphologies Rs, rS, RS, qR, qRs, R, rR’s and QS. Furthermore, the average time errors computed for QRS onset and offset locations when using the corresponding winner mathematical models for delineation purposes were, respectively, 12.87±8.5 ms and 1.47±10.06 ms.
13 citations (Crossref) [2022-09-21]
Keywords: ECG feature extraction; Mathematical modeling; Morphology classification; QRS complex delineation

Crowdsensing-Based Gamification for Collective Assistance for Post-Era of Coronavirus Epidemic in Community Living - Luo, Renfei; Marques, João Alexandre Lôbo; Ong, Kok-Leong; Fong, Simon (International Journal of Extreme Automation and Connectivity in Healthcare (IJEACH), 2020)
Crowdsensing exploits the sensing abilities offered by smart phones and users' mobility. Users can mutually help each other as a community with the aid of crowdsensing. The potential of crowdsensing has yet to be fully realized for improving public health. A protocol based on gamification to encoura...
0 citations (Crossref) [2022-09-21]

Health and Well-Being Education: Extending the SCARF Learning Analytics Model for Identifying the Learner Happiness Indicators - Li, Tengyue; Marques, Joao Alexandre Lobo; Fong, Simon (International Journal of Extreme Automation and Connectivity in Healthcare (IJEACH), 2020)
The use of learning analytics (LA) in real-world educational applications is growing very fast as academic institutions realize the positive potential that is possible if LA is integrated in decision making. Education in schools on public health need to evolve in response to the new knowledge and th...
0 citations (Crossref) [2022-09-21]

IoT-Based Smart Health System for Ambulatory Maternal and Fetal Monitoring - Marques, João Alexandre Lobo; Han, Tao; Wu, Wanqing; Madeiro, João Paulo do Vale; Neto, Aloísio Vieira Lira; Gravina, Raffaele; Fortino, Giancarlo; de Albuquerque, Victor Hugo C. (IEEE Internet of Things Journal, 2021)
The adoption of IoT for smart health applications is a relevant tool for distributed and intelligent automatic diagnostic systems. This work proposes the development of an integrated solution to monitor maternal and fetal signals for high-risk pregnancies based on IoT sensors, feature extraction based on data analytics, and an intelligent diagnostic aid system based on a 1-D convolutional neural network (CNN) classifier. The fetal heart rate and a group of maternal clinical indicators, such as the uterine tonus activity, blood pressure, heart rate, temperature, and oxygen saturation are monitored. Multiple data sources generate a significant amount of data in different formats and rates. An emergency diagnostic subsystem is proposed based on a fog computing layer and the best accuracy was 92.59% for both maternal and fetal emergency. A smart health analytics system is proposed for multiple feature extraction and the calculation of linear and nonlinear measures. Finally, a classification technique is proposed as a prediction system for maternal, fetal, and simultaneous health status classification, considering six possible outputs. Different classifiers are evaluated and a proposed CNN presented the best results, with the F1-score ranging from 0.74 to 0.91. The results are validated based on the diagnosis provided by two specialists. The results show that the proposed system is a viable solution for maternal and fetal ambulatory monitoring based on IoT.
9 citations (Crossref) [2022-09-21] Conference Name: IEEE Internet of Things Journal
Keywords: Artificial intelligence (AI); Biomedical monitoring; Cloud computing; Feature extraction; Fetal heart rate; Internet of Things; Medical diagnostic imaging; Monitoring; convolutional neural networks (CNNs); feature extraction; fetal monitoring; health analytics; maternal monitoring

The Importance of Readiness for Change, a Leadership Perspective Based on a Case Study in Macau, SAR China - Marques, João; Reis, Joana; Phillips, Jenny O. L.; Diakite, Ansoumane (Journal of Advanced Management Science, 2020)
0 citations (Crossref) [2022-09-21]

Identification of Latent Risk Clinical Attributes for Children Born Under IUGR Condition Using Machine Learning Techniques - Nguyen Van, Sau; Lobo Marques, J. A.; Biala, T. A.; Li, Ye (Computer Methods and Programs in Biomedicine, 2021)
Background and objective Intrauterine Growth Restriction (IUGR) is a condition in which a fetus does not grow to the expected weight during pregnancy. There are several well documented causes in the literature for this issue, such as maternal disorder, and genetic influences. Nevertheless, besides the risk during pregnancy and labour periods, in a long term perspective, the impact of IUGR condition during the child development is an area of research itself. The main objective of this work is to propose a machine learning solution to identify the most significant features of importance based on physiological, clinical or socioeconomic factors correlated with previous IUGR condition after 10 years of birth. Methods In this work, 41 IUGR (18 male) and 34 Non-IUGR (22 male) children were followed up 9 years after the birth, in average (9.1786 ± 0.6784 years old). A group of machine learning algorithms is proposed to classify children previously identified as born under IUGR condition based on 24-hours monitoring of ECG (Holter) and blood pressure (ABPM), and other clinical and socioeconomic attributes. In additional, an algorithm of relevance determination based on the classifier is also proposed, to determine the level of importance of the considered features. Results The proposed classification solution achieved accuracy up to 94.73%, and better performance than seven state-of-the-art machine learning algorithms. Also, relevant latent factors related to HRV and BP monitoring are proposed, such as: day-time heart rate (day-time HR), day-night systolic blood pressure (day-night SBP), 24-hour standard deviation (SD) of SBP, dropped, morning cortisol creatinine, 24-hour mean of SDs of all NN intervals for each 5 minutes segment (24-hour SDNNi), among others. Conclusion With outstanding accuracy of our proposed solutions, the classification system and the indication of relevant attributes may support medical teams on the clinical monitoring of IUGR children during their childhood development.
2 citations (Crossref) [2022-09-21]
Keywords: ABPM (Ambulatory Blood Pressure Monitoring); HRV (Heart Rate Variability); IUGR (Intrauterine Growth Restriction); Machine Learning

Towards an efficient prognostic model for fetal state assessment - Silva Neto, Manuel Gonçalves da; Madeiro, João Paulo do Vale; Marques, João Alexandre Lobo; Gomes, Danielo G. (Measurement, 2021)
Monitoring signals such as fetal heart rate (FHR) are important indicators of fetal well-being. Computer-assisted analysis of FHR patterns has been successfully used as a decision support tool. However, the absence of a gold standard for the building blocks decision-making in the systems design process impairs the development of new solutions. Here we propose a prognostic model based on advanced signal processing techniques and machine learning algorithms for the fetal state assessment within a comprehensive evaluation process. Feature-engineering-based and time-series-based machine learning classifiers were modeled into three data segmentation schemas for CTU-UHB, HUFA, and DB-TRIUM datasets and the generalization performance was assessed by a two-way cross-dataset evaluation. It has been shown that the feature-based algorithms outperformed the time-series ones on data-limited scenarios. The Support Vector Machines (SVM) obtained the best results on the datasets individually: specificity (85.6% ) and sensitivity (67.5%). On the other hand, the most effective generalization results were achieved by the Multi-layer perceptron (MLP) with a specificity of 71.6% and sensitivity of 61.7%. The overall process provided a combination of techniques and methods that increased the final prognostic model performance, achieving relevant results and requiring a smaller amount of data when compared to the state-of-the-art fetal status assessment solutions.
1 citations (Crossref) [2022-09-21]
Keywords: Cardiotocography; Classification; Fetal state assessment; Prognostic model; System design

The Probability Flow in the Stock Market and Spontaneous Symmetry Breaking in Quantum Finance - Arraut, Ivan; Lobo Marques, João Alexandre; Gomes, Sergio (Mathematics, 2021)
The spontaneous symmetry breaking phenomena applied to Quantum Finance considers that the martingale state in the stock market corresponds to a ground (vacuum) state if we express the financial equations in the Hamiltonian form. The original analysis for this phenomena completely ignores the kinetic terms in the neighborhood of the minimal of the potential terms. This is correct in most of the cases. However, when we deal with the martingale condition, it comes out that the kinetic terms can also behave as potential terms and then reproduce a shift on the effective location of the vacuum (martingale). In this paper, we analyze the effective symmetry breaking patterns and the connected vacuum degeneracy for these special circumstances. Within the same scenario, we analyze the connection between the flow of information and the multiplicity of martingale states, providing in this way powerful tools for analyzing the dynamic of the stock markets.
Number: 21
Keywords: Hermiticity; conservation of the information; degenerate vacuum; flow of information; martingale condition; random fluctuations; spontaneous symmetry breaking; vacuum condition

Education and human capital management in a world city: the case of Singapore - Ho, K. C.; Ge, Yun (Asia Pacific Journal of Education, 2011)
There is considerable evidence to suggest that the human capital needs of the world city differ from what Robinson calls “ordinary cities” or what Markusen and associates term as “second tier cities”. This path is blazed most notably in the field of world cities and the flow of skilled labour, in the work by Sassen and with case examples (finance, law, accountancy) provided in the work by Beaverstock and his associates. This focuses on producer services and migration flows needs to be matched by an accompanying look at city-based strategies. This paper represents an attempt to provide this by providing a case history analysis of Singapore in three stages of growth – as port city, industrial city and as world city – in order to show how the evolving infrastructure associated with human capital (education, immigration and labour policies) allows human capital to be developed, attracted, harnessed, deployed, released and retained.
15 citations (Crossref) [2022-09-21] _eprint: https://doi.org/10.1080/02188791.2011.595058
Keywords: Singapore; human capital; migration

Researching international student migration in Asia: research design and project management issues - Ge, Yun; Ho, Kong Chong (Journal of Population Research, 2014)
In the context of Asia, the changing dynamics of higher education has increased the visibility and significance of the group of intraregional education migrants. There are several methodological issues which need to be addressed in conducting research for this group of migrants. First, how does the particular type of migrant group and Asian context influence the research design? Second, in order to capture the scale and diversity of this migrant group, how should research be conducted across multiple sites? Third, how does a mixed method design allow researchers to learn more about the behaviour, practice and orientations of education migrants? Our paper aims to make contributions to the discussions on the methods of education migration research in Asia through answering these questions. We use research experiences and preliminary data from a multinational project to illustrate the issues involved in the selection of methods, research design and project management.
2 citations (Crossref) [2022-09-21]
Keywords: Asia; Higher education; International student migrants; Mixed methods; Multi-site design; Multicultural research

Belt and Road Initiatives: implications for China’s internationalisation of tertiary-level education - Ge, Yun; Ho, Kong Chong (Educational Research and Evaluation, 2022)
Since the launch of the One Belt and One Road Initiative (BRI) in 2013, the internationalisation of China’s tertiary education has entered a new stage. Central to the BRI is investment and strategic planning for talent cultivation, knowledge production, and transmission. This paper explains how the BRI redirects, reinforces, and intensifies China’s strategic planning and actions for internationalising its education. It adopts a policy analysis approach and reviews three key aspects of development and shifting emphasis of internationalisation under the impact of the BRI: international education networks along the Six BRI Economic Corridors, vocational colleges as new players in international education, and promotion of the Chinese language as a new global language. The analysis captures an important moment in which international education processes are being visibly altered through China’s strategies to take the lead in economic globalisation and to compete for a central place in the world via the BRI.
0 citations (Crossref) [2022-09-21] _eprint: https://doi.org/10.1080/13803611.2022.2041858
Keywords: Belt and Road Initiatives; Chinese language; Internationalisation of higher education; vocational education

Internationalisation of higher education: new players in a changing scene - Ge, Yun (Educational Research and Evaluation, 2022)
0 citations (Crossref) [2022-09-21] _eprint: https://doi.org/10.1080/13803611.2022.2041850

Examining the impact of behavioral factors on the intention of adopting E-government services: An empirical study on the hard-to-reach groups in Macao SAR, China - Iong, Kit Yeng; Phillips, Jenny O. L. (Technology in Society, 2022)
In government studies, electronic government has become a hot topic in recent decades. Many scholars believe that soon, the government might not be able to operate smoothly without the help of ICTs as the Internet has been overwhelming people's daily lives already. In analyzing people's behavioral factors towards adopting e-government services, most studies targeted the adult population, while those in the hard-to-reach groups are minimal. This study was designed especially to understand the behavioral factors of the younger generation aged between 18 and 24 and the senior citizens above 60 on their adoption of e-government services in Macao SAR. Sixteen in-depth interviews were conducted based on the semi-structured interview questions developed from the prior literature on the Theory of Planned Behavior and e-government studies. Six significant findings are yielded, which could serve as an important reference for policymakers designing e-government policy and promoting its implementation strategy. These behavioral factors also contribute empirical data to support the theoretical framework of TPB in the context of Macao SAR e-government services.
0 citations (Crossref) [2022-09-21]
Keywords: Electronic government; Hard-to-reach groups; In-depth interviews; The theory of planned behavior

A performance académica como ritual de criação e ativismo na era pós-digital - Pérez, P; Pereira, S; Fernandes-Marcos, A (AVANCA CINEMA, 2021)

Relações entre o pós-digital e o complexo industrial do capitalismo: reformulações sobre a tecnologia como ideologia e lixo digital na arte - Paquete, Hugo; Fernandes-Marcos, Adérito; Bastos, Paulo Bernardino (AVANCA | CINEMA, 2021)
This essay presents a mapping of the historical concepts that contributed to the emergence of post-digital aesthetics and their connections to the concept of post-media in historical terms. It also analyzes the transition from techno-positivism to discourse of resistance against the effects of the capital technological industrial complex and how these advances in technology influence artistic discourses, practices and are the leverage of art and technology which is nothing more than a representation of the aesthetics of capital. Following art and capitalism as an ideology of innovation. Is proposed an unstinting theory about technology, geology, and the importance of these conditions to the post-digital aesthetics in terms of material disponible and conceptual articulation. Producing a reconfiguration of the post-digital conceptual approach as I propose beyond the dysfunctional aesthetics and connected with the concept of radical ecology centered in the usability of electronic garbage and technical obsolescent technologies in the arts.
0 citations (Crossref) [2022-09-21]

Post-Digital Fashion: The Evolution and Creation Cycle - Pereira, Selma; Fernandes-Marcos, Adérito (ZoneModa Journal, 2021)
In the face of the Covid-19 pandemic, the fashion industry was surprised and quickly had to adapt to digital media. However, the relationship between fashion and the multiplicity of screens is not new. Fashion emerged and took its first steps with Cinema, in Modernity. Although there are times when these two systems are further apart from each other, the alliance survived. To analyse contemporaneity, we take as main reference the studies of Gilles Lipovetsky, and his reflections on aesthetic capitalism. The fashion system has many Western fields of life, including art and technology. In this article we discuss how this relationship of fashion adapts and develops with aesthetic capitalism and post-digital art while we analyse representative artefacts from/about fashion. We propose to put the recent digital fashion artefacts in dialogue with post-digital aesthetics theories, discussing the blurred boundaries between the digital and the post-digital, and proposing the instantiation of a post-digital creation cycle applied to fashion artefacts.
Artwork Size: 71-89 Pages

Climate Alarmism or Lukewarming? How So-Called American Conservatives Should Think About Climate Change - McNabb, T. D; Devito, M (Ethics & the Environment, 2022)
In this essay we argue that, based on current scientific data, the most prudential course of future actions that an American conservative can take, is one that assumes what we call climate change alarmism. In order to establish this thesis, we first provide a basic overview of the relevant climate change science, as well as give an analysis of the alarmist and lukewarming dialectic (the two primary interpretations of the data). We then move to develop our environmental wager. Finally, following Roger Scruton, we end this work by proposing what sort of policies conservatives should endorse going further.

Ockham on the Side of the Angels: Why a Classical Theist Shouldn't be Moved by Oppy's Argument from Simplicity - McNabb, Tyler; DeVito, Michael (New Blackfriars, 2022)
0 citations (Crossref) [2022-09-21]

Papal Bull: A Response to Contemporary Papal Scholarship - McNabb, Tyler Dalton (Journal of Biblical and Theological Studies, 2021)

The evolutionary argument against naturalism: a Wittgensteinian response - DeVito, Michael; McNabb, Tyler (International Journal for Philosophy of Religion, 2022)
In this essay, we put forth a novel solution to Plantinga’s Evolutionary Argument Against Naturalism, utilizing recent work done by Duncan Pritchard on radical skepticism. Key to the success of Plantinga’s argument is the doubting of the reliability of one’s cognitive faculties. We argue (viz. Pritchard and Wittgenstein) that the reliability of one’s cognitive faculties constitutes a hinge commitment, thus is exempt from rational evaluation. In turn, the naturalist who endorses hinge epistemology can deny the key premise in Plantinga’s argument and avoid the dilemma posed on belief in the conjunction of naturalism and evolution.
0 citations (Crossref) [2022-09-21]

An Improved Double Channel Long Short-Term Memory Model for Medical Text Classification - Liang, Shengbin; Chen, Xinan; Ma, Jixin; Du, Wencai; Ma, Huawei (Journal of Healthcare Engineering, 2021)
There are a large number of symptom consultation texts in medical and healthcare Internet communities, and Chinese health segmentation is more complex, which leads to the low accuracy of the existing algorithms for medical text classification. The deep learning model has advantages in extracting abstract features of text effectively. However, for a large number of samples of complex text data, especially for words with ambiguous meanings in the field of Chinese medical diagnosis, the word-level neural network model is insufficient. Therefore, in order to solve the triage and precise treatment of patients, we present an improved Double Channel (DC) mechanism as a significant enhancement to Long Short-Term Memory (LSTM). In this DC mechanism, two channels are used to receive word-level and char-level embedding, respectively, at the same time. Hybrid attention is proposed to combine the current time output with the current time unit state and then using attention to calculate the weight. By calculating the probability distribution of each timestep input data weight, the weight score is obtained, and then weighted summation is performed. At last, the data input by each timestep is subjected to trade-off learning to improve the generalization ability of the model learning. Moreover, we conduct an extensive performance evaluation on two different datasets: cMedQA and Sentiment140. The experimental results show that the DC-LSTM model proposed in this paper has significantly superior accuracy and ROC compared with the basic CNN-LSTM model.
1 citations (Crossref) [2022-09-21]

An improved ant colony optimization algorithm based on context for tourism route planning - Liang, Shengbin; Jiao, Tongtong; Du, Wencai; Qu, Shenming (PLOS ONE, 2021)
To solve the problem of one-sided pursuit of the shortest distance but ignoring the tourist experience in the process of tourism route planning, an improved ant colony optimization algorithm is proposed for tourism route planning. Contextual information of scenic spots significantly effect people’s choice of tourism destination, so the pheromone update strategy is combined with the contextual information such as weather and comfort degree of the scenic spot in the process of searching the global optimal route, so that the pheromone update tends to the path suitable for tourists. At the same time, in order to avoid falling into local optimization, the sub-path support degree is introduced. The experimental results show that the optimized tourism route has greatly improved the tourist experience, the route distance is shortened by 20.5% and the convergence speed is increased by 21.2% compared with the basic algorithm, which proves that the improved algorithm is notably effective.
3 citations (Crossref) [2022-09-21]

Power Allocation for 5G Mobile Multiuser Cooperative Networks - Yin, Fagen; Du, Wencai (Journal of Advanced Transportation, 2021)
With the fifth generation (5G) communication technology, the mobile multiuser networks have developed rapidly. In this paper, the performance analysis of mobile multiuser networks which utilize decode-and-forward (DF) relaying is considered. We derive novel outage probability (OP) expressions. To improve the OP performance, we study the power allocation optimization problem. To solve the optimization problem, we propose an intelligent power allocation optimization algorithm based on grey wolf optimization (GWO). We compare the proposed GWO approach with three existing algorithms. The experimental results reveal that the proposed GWO algorithm can achieve a smaller OP, thus improving system efficiency. Also, compared with other channel models, the OP values of the 2-Rayleigh model are increased by 81.2% and 66.6%, respectively.
1 citations (Crossref) [2022-09-21]

Data Augmentation for Deep Neural Networks Model in EEG Classification Task: A Review - He, Chao; Liu, Jialu; Zhu, Yuesheng; Du, Wencai (Frontiers in Human Neuroscience, 2021)
Classification of electroencephalogram (EEG) is a key approach to measure the rhythmic oscillations of neural activity, which is one of the core technologies of brain-computer interface systems (BCIs). However, extraction of the features from non-linear and non-stationary EEG signals is still a challenging task in current algorithms. With the development of artificial intelligence, various advanced algorithms have been proposed for signal classification in recent years. Among them, deep neural networks (DNNs) have become the most attractive type of method due to their end-to-end structure and powerful ability of automatic feature extraction. However, it is difficult to collect large-scale datasets in practical applications of BCIs, which may lead to overfitting or weak generalizability of the classifier. To address these issues, a promising technique has been proposed to improve the performance of the decoding model based on data augmentation (DA). In this article, we investigate recent studies and development of various DA strategies for EEG classification based on DNNs. The review consists of three parts: what kind of paradigms of EEG-based on BCIs are used, what types of DA methods are adopted to improve the DNN models, and what kind of accuracy can be obtained. Our survey summarizes the current practices and performance outcomes that aim to promote or guide the deployment of DA to EEG classification in future research and development.
4 citations (Crossref) [2022-09-21]

A Deep Neural Network Based on Circular Representation for Target Detection - Lin, Cong; Chen, Zhoujian; Huang, Yiquan; Jiang, Haoyu; Du, Wencai; Chen, Qiong (Journal of Sensors, 2022)
Convolutional neural network (CNN) model based on deep learning has excellent performance for target detection. However, the detection effect is poor when the object is circular or tubular because most of the existing object detection methods are based on the traditional rectangular box to detect and recognize objects. To solve the problem, we propose the circular representation structure and RepVGG module on the basis of CenterNet and expand the network prediction structure, thus proposing a high-precision and high-efficiency lightweight circular object detection method RebarDet. Specifically, circular tubular type objects will be optimized by replacing the traditional rectangular box with a circular box. Second, we improve the resolution of the network feature map and the upper limit of the number of objects detected in a single detect to achieve the expansion of the network prediction structure, optimized for the dense phenomenon that often occurs in circular tubular objects. Finally, the multibranch topology of RepVGG is introduced to sum the feature information extracted by different convolution modules, which improves the ability of the convolution module to extract information. We conducted extensive experiments on rebar datasets and used AB-Score as a new evaluation method to evaluate RebarDet. The experimental results show that RebarDet can achieve a detection accuracy of up to 0.8114 and a model inference speed of 6.9 fps while maintaining a moderate amount of parameters, which is superior to other mainstream object detection models and verifies the effectiveness of our proposed method. At the same time, RebarDet’s high precision detection of round tubular objects facilitates enterprise intelligent manufacturing processes.
0 citations (Crossref) [2022-09-21]

The scalpel model of educational research - Morrison, Keith; van der Werf, Greetje (Educational Research and Evaluation, 2020)
0 citations (Crossref) [2022-09-21]

The truth, the whole truth, and nothing but the truth - Morrison, Keith; van der Werf, Greetje (Educational Research and Evaluation, 2020)
0 citations (Crossref) [2022-09-21]

Methods, understandings, and expressions of causality in educational research - Morrison, Keith; van der Werf, Greetje (Educational Research and Evaluation, 2020)
0 citations (Crossref) [2022-09-21]

Review of Gorard, S. (2020) Getting evidence into education: evaluating the routes to policy and practice - Morrison, Keith (Educational Research and Evaluation, 2020)

Conceptual replications, research, and the “what works” agenda in education - Morrison, Keith (Educational Research and Evaluation, 2022)
2 citations (Crossref) [2022-09-21]

Review of Biesta. G. (2020) Educational research: an unorthodox introduction, Educational Research and Evaluation - Morrison, Keith (Educational Research and Evaluation, 2020)
0 citations (Crossref) [2022-09-21]

Ideology, Linguistic Capital and the Medium of Instruction in Hong Kong - Morrison, Keith; Lui, Icy (Journal of Multilingual and Multicultural Development, 2000)
55 citations (Crossref) [2022-09-21]

Testing to Destruction: A problem in a small state - Morrison, Keith; Joan, Tang Fun Hei (Assessment in Education: Principles, Policy & Practice, 2002)
21 citations (Crossref) [2022-09-21]

Undergraduate students in part‐time employment in China - Tam Oi I, Betty; Morrison, Keith (Educational Studies, 2005)
13 citations (Crossref) [2022-09-21]

Measuring and Targeting Internal Conditions for School Effectiveness in the Free State of South Africa - Kgaile, Abraham; Morrison, Keith (Educational Management Administration & Leadership, 2006)
A questionnaire-based methodology for constructing an overall index of school effectiveness is reported, focusing on within-school conditions of schools, which is currently being used in the Free State of South Africa. The article reports the construction and use of a straightforward instrument for measuring the effectiveness of key aspects of the conditions for school effectiveness in the Free State, using a variety of dimensions. It indicates how this instrument can identify where to intervene in improving schools in order to gain the maximum return on investment of time, effort, development activity and support. The instrument provides aggregated and disaggregated data for individual schools, groups of schools and whole districts, both at a single point in time and over time, thereby enabling the most economical and beneficial development to be planned for targeted individual schools and groups of schools. It enables users to identify the key drivers of the internal school conditions for effectiveness, development and change in schools.
2 citations (Crossref) [2022-09-21]

Does repeating a year improve performance? The case of teaching English - Morrison, Keith; Ieong On No, Anna (Educational Studies, 2007)
10 citations (Crossref) [2022-09-21]

Group work and cultural characteristics in a Chinese school - Morrison, Keith; Garcia, Alejandro Salcedo; Wong, Sin Teng (Educational Research and Evaluation, 2020)
0 citations (Crossref) [2022-09-21]

Randomised Controlled Trials for Evidence-based Education: Some Problems in Judging 'What Works' - Morrison, Keith (Evaluation & Research in Education, 2001)
58 citations (Crossref) [2022-09-21]

Simplicity and Complexity in Contemporary School Leadership: A Response to Grace - Morrison, Keith (British Journal of Educational Studies, 2001)
0 citations (Crossref) [2022-09-21]

Toward an educational agenda for Macau at the start of the new millennium - Morrison, Keith (China Perspectives, 2003)

Improving Teaching and Learning in Higher Education: Metaphors and Models for Partnership Consultancy - Morrison, Keith (Evaluation & Research in Education, 2003)
3 citations (Crossref) [2022-09-21]

Complexity theory and curriculum reforms in Hong Kong - Morrison, Keith (Pedagogy, Culture & Society, 2003)
21 citations (Crossref) [2022-09-21]

The poverty of curriculum theory: a critique of Wraga and Hlebowitsh - Morrison, Keith R. B. (Journal of Curriculum Studies, 2004)
16 citations (Crossref) [2022-09-21]

Structuration theory, habitus and complexity theory: elective affinities or old wine in new bottles? - Morrison, Keith (British Journal of Sociology of Education, 2005)
36 citations (Crossref) [2022-09-21]

Pedagogy in higher education - Morrison, Keith (Chinese Cross Currents, 2005)

Sensitive educational research in small states and territories: the case of Macau - Morrison, Keith (Compare: A Journal of Comparative and International Education, 2006)
15 citations (Crossref) [2022-09-21]

Paradox Lost: Toward a Robust Test of the Chinese Learner - Morrison, Keith (Education Journal, 2006)
This article suggests that attempts to date to unravel the paradox of the Chinese learner are incomplete and inadequately modeled, and that the complexities of the paradox have not yet been fittingly operationalized or alternative explanations of research data investigated. It contends that attempts either to state or to unravel the paradox are chimerical, as they risk oversimplifying a complex phenomenon, the extent and nature of which are insufficiently understood to date. The article argues that investigating the phenomenon of Chinese learners' strong performance in international measures of achievement requires researchers to operate more rigorously in their search for alternative and multiple explanations of results in terms of causality, sampling, and representing heterogeneity. Several explanations of data on the paradox are presented, and alternative explanations which might be more usefully explored are provided. The article also questions the extent to which research on the Chinese learner, with a search for a unitary set of characteristics, is not, itself, prey to totalizing, collectivist ideologies cast in unrealistic meta-narratives. Recommendations are made for further research.

Lone parents' experiences as higher education students: learning to juggle - Morrison, Keith (Educational Research and Evaluation, 2013)
0 citations (Crossref) [2022-09-21]

Educational Philosophy and the Challenge of Complexity Theory - Morrison, Keith (Educational Philosophy and Theory, 2008)
89 citations (Crossref) [2022-09-21]

School inspection in small states and territories: an overview and case study of Macau - Morrison, Keith (Compare: A Journal of Comparative and International Education, 2009)
5 citations (Crossref) [2022-09-21]

Men and women in employment in Macau: A longitudinal survey of inequality. - Morrison, Keith (Journal of Macau University of Science and Technology, 2009)

Complexity Theory, School Leadership and Management: Questions for Theory and Practice - Morrison, Keith (Educational Management Administration & Leadership, 2010)
Complexity theory (CT) has had a meteoric rise in management literature and the social sciences. Its fledgling importation into school leadership and management raises several questions and concerns. This article takes one view of CT and argues that, though its key elements have much to offer school leadership and management, caution has to be exercised in accepting CT too readily, as it: (1) is unclear on its own novelty, nature and status; (2) can be regarded as disguised ideology in conflating description and prescription; (3) confuses explanation with prediction; (4) is relativist, undermining its own status; (5) contains problems in its advocacy of self-organization; (6) neglects the ethical and emotional dimensions of leadership and management; and (7) risks exonerating school leaders and managers from reasonable expectations of accountability and responsibility. The article concludes that there are questions to CT at the levels of theory, ontology, deontology and ethics, but that it offers useful challenges for school leadership and management.
39 citations (Crossref) [2022-09-21]

Leadership for self-organisation: complexity theory and communicative action - Morrison, Keith (International Journal of Complexity in Leadership and Management, 2011)

Searching for causality in the wrong places - Morrison, Keith (International Journal of Social Research Methodology, 2012)
15 citations (Crossref) [2022-09-21]

Interviewing children in uncomfortable settings: 10 lessons for effective practice - Morrison, Keith (Educational Studies, 2013)
5 citations (Crossref) [2022-09-21]

Online and paper evaluations of courses: a literature review and case study - Morrison, Keith (Educational Research and Evaluation, 2013)
11 citations (Crossref) [2022-09-21]

The academic and intellectual life of Macau - Morrison, Keith (Review of Culture (Revista de Cultura), 2014)

The Colonization of Lifeworlds of Education by Work: Restoration and Recoupling of Lifeworld and System in the Inner Self - Morrison, Keith (Horizons of Education, 2015)
The argument is raised that, in an age of the networked, connected society in an information-rich environment with communication possibilities as never before experienced or made possible, the displacement of educational virtues of morality, ethics and the development of all-round human beings, by those of money, labour, power and work are speeding apace, and the disconnect between system and lifeworld is increasing. Drawing initially on the work of Habermas, in which the colonization of the lifeworld occurs by system imperatives of rationalization, labour, money and power, the paper argues that such moves are manifested starkly in discourses of the relation between education and work, and five areas are introduced in which the links operate. The marketization and commodification of education, together with its incorporation into the service of capital and labour, are attested through a short worked example of one small territory within the larger context of China. Then, taking a lead from Sertillanges and Habermas’s later work, the paper argues for: (a) a reaffirmation of the importance of moral, ethical and spiritual dimensions of education; (b) the breaking of a narrowly instrumental, capital-acquisitive view of education as serving the jobs market and social control and towards a liberating view of education as communicative action and the development of being rather than simply behaving; (c) the importance of transcendence and immanence; and, thereby, (d) moves towards the re-integration of system and lifeworld in participating subjects.

Realizing the promises of replication studies in education - Morrison, Keith (Educational Research and Evaluation, 2019)
5 citations (Crossref) [2022-09-21]

Quality of Life in Macau, China - Rato, Ricardo; Davey, Gareth (Social Indicators Research, 2012)
We report the initial findings of an ongoing, long-term investigation into subjective quality of life in Macau, a Special Administrative Region of China. Data were collected via quarterly public surveys (2007 to 2009; n = 8,230), as part of the Macau Quality of Life Report. The main aims of the study were to: (a) ascertain the public’s satisfaction with life and with the regional situation in Macau; (b) confirm the utility of the International Wellbeing Index (IWI) as a measure of subjective life quality; and (c) contribute to ongoing discussion in the literature on quality of life in China. The data indicated moderate levels of personal (PWI = 64.4; range 63–66.7) and national (NWI = 59.7; 57.4–63.7) wellbeing across the study period, which implies that residents in Macau are generally satisfied with life. The lowest scores were reported in the first quarter of 2009, a period of great economic uncertainty in Macau and the world, but were positioned within the normative range. The IWI demonstrated good psychometric performance, consistent with previous studies in China and the West, which confirmed its utility. These findings are discussed in relation to the IWI’s theoretical underpinnings and the literature.
12 citations (Crossref) [2022-09-21]
Keywords: China; International Wellbeing index; Macau; Quality of life

Cognitive Science of Religion and Classical Theism: A Synthesis - McNabb, Tyler Dalton; DeVito, Michael (Religions, 2022)
Launonen and Mullins argue that if Classical Theism is true, human cognition is likely not theism-tracking, at least, given what we know from cognitive science of religion. In this essay, we develop a model for how classical theists can make sense of the findings from cognitive science, without abandoning their Classical Theist commitments. We also provide an argument for how our model aligns well with the Christian doctrine of general revelation.
0 citations (Crossref) [2022-09-21]

Conceptualizing the Second Education Circuit for China’s Doctoral Students in Asia - Ge, Yun; Ho, Kong Chong (International Journal of Chinese Education, 2019)
The quest to become research universities of international repute has led flagship universities in East and Southeast Asia to develop a new focus on attracting international doctoral students. This paper aims to understand Chinese doctoral students’ mobility in the immediate region and their education to work perceptions. The study draws from a sample of 301 doctoral students from China who were studying at five universities in Japan, South Korea, and Singapore. Analysis on students’ decision making and after-study pathways highlights the regional exchange in related areas. We argue that this regional mobility of doctoral students, characterized as the second education circuit, is facilitated by a higher education migration infrastructure with three interactively weaved dimensions: commercial, social, and regulatory. The research findings suggest the growing importance of Asia as a regional second circuit of doctoral training for students from China.
1 citations (Crossref) [2022-09-21]

Constraints of Fe-S-C stable isotopes on hydrothermal and microbial activities during formation of sediment-hosted stratiform sulfide deposits - Qiu, Wenhong Johnson; Zhou, Mei-Fu; Li, Xiaochun; Huang, Fang; Malpas, John (Geochimica et Cosmochimica Acta, 2021)
Microbial and hydrothermal venting activities on the seafloor are important for the formation of sediment-hosted stratiform sulfide (SHSS) deposits. Fe isotopic compositions are sensitive to both microbial and hydrothermal activities and may be used to investigate the formation of these deposits. However, to the best of our knowledge, no Fe isotopic studies have been conducted on SHSS deposits. In the Devonian Dajiangping SHSS-type pyrite deposit (389 Ma), South China, laminated pyrite ores were precipitated from exhalative hydrothermal fluids, whereas black shales were deposited during intervals with no exhalation. Pyrite grains from black shales mostly display positive δ56Fe-py (0.01–0.73‰), higher than marine sediments (ca. 0‰), due to pyrite deriving Fe from basinal shuttled Fe(III) (hydr-)oxides and slowly crystallizing in pores of sediments with equilibrium fractionation, except for negative δ56Fe-py (−0.17‰ to −0.24‰) of two samples caused by mixing of Fe from underlain laminated ores. The positive δ34S-py (3.50–24.5‰) of black shales reflect that sulfur of pyrite originated from quantitative reduction of sulfate in closed pores of sediments. In contrast, pyrite grains of laminated ores have negative δ56Fe-py (−0.60‰ to −0.21‰), which were not only inherited from the negative δ56Fe of hydrothermal fluids but also caused by kinetic fractionation during rapid precipitation of a pyrite precursor (FeS) in hydrothermal plumes. These ores have negative δ34S-py (−28.7‰ to −1.82‰), because H2S for pyrite mineralization was produced by bacterial sulfate reduction (BSR) in a sulfate-rich seawater column or shallow sediments. The δ56Fe-py values of laminated ores co-vary positively with δ34S-py and δ13C-carbonate along the ore stratigraphy, with δ13C-carbonate values ranging from −12.0‰ to −2.50‰. However, they correlate negatively with aluminum-normalized total organic carbon (TOC/Al2O3). Organic carbon is thus considered to enhance the production of H2S by BSR activities, increase pyrite precipitation rates and promote the expression of kinetic fractionation of Fe isotopes. Intriguingly, in the ore units with vigorous hydrothermal venting activities, δ56Fe-py, δ34S-py and δ13C-carbonate values display a consistently increasing trend. Such results suggest that venting hydrothermal fluids significantly inhibited the H2S production of BSR, which then reduced the pyrite crystallization rate and decreased the kinetic fractionation of Fe isotopes. Our study reveals that the formation of SHSS deposits relies on H2S from microbial activities and metals from hydrothermal exhalation on the seafloor, but that vigorous exhalation can inhibit microbial activities and thus sulfide precipitation rates. The integrated use of Fe, S, and C isotopes can effectively elucidate these dynamic interactions between hydrothermal venting and microbial activities during the formation of SHSS deposits.
Keywords: Iron isotope; Isotope fractionation; Sediment-hosted stratiform sulfide deposit; Sulfur isotope

‘Navigation for an ocean of interminable scepticism’ revisited: John Henry Newman and the place of theology in the university - Morgan, Stephen (International Journal for the Study of the Christian Church, 2021)
The place of theology is under threat in the modern university. It is denied a place, except insofar as it is useful in the training of religious professionals or as a phenomenon in its own right, on the grounds that relate to an unscientific scientism that both makes metaphysical assumptions it itself does not recognise as scientific or denies its own epistemological commitments. This article argues that the notion of education in ‘liberal knowledge’ or ‘universal knowledge’, the idea at the heart of John Henry Newman’s The Idea of a University provides a sufficiently robust counter to these assaults on the place of theology proper in the modern university and that refusing such a place to it undermines the claim of universities to use the name at all. It is precisely the uselessness of theology that guarantees its place in the university committed to universal knowledge and universal enquiry.
0 citations (Crossref) [2022-09-21] https://doi.org/10.1080/1474225X.2021.1997030
Keywords: Derrida; Newman; education; liberal education; religious studies; secularisation; theology; university

Basic Beliefs, the Embryo Rescue Case, and Single-Issue Voting: A Response to Dustin Crummett - McNabb, Tyler; DeVito, Michael (The National Catholic Bioethics Quarterly, 2021)
In this essay, we respond to Dustin Crummett’s argument that one cannot consistently appeal to body count reasoning to justify being a single-issue pro-life voter if one is also committed to the usual response to the embryo rescue case. Specifically, we argue that a modified version of BCR we call BCR* is consistent with the usual response. We then move to address concerns about the relevance of BCR* to Crummett’s original thesis.
GSCC: 0000000

Houston, Do We Have a Problem?: Extraterrestrial Intelligent Life and Christian Belief - McIntosh, C. A.; McNabb, Tyler Dalton (Philosophia Christi, 2021)
Would the existence of extraterrestrial intelligent life (ETI) conflict in any way with Christian belief? We identify six areas of potential conflict. If there be no conflict in any of these areas—and we argue ultimately there is not—we are confident in declaring that there is no conflict, period. This conclusion underwrites the integrity of theological explorations into the existence of ETI, which has become a topic of increasing interest among theologians in recent years.

Divine foreknowledge and human free will: Embracing the paradox - DeVito, Michael; McNabb, Tyler Dalton (International Journal for Philosophy of Religion, 2021)
0 citations (Crossref) [2022-09-21] GSCC: 0000000

Parental stress and parenting in Chinese immigrant families: The mediating role of social support - Liu, Shu-Wen; Zhai, Fuhua; Gao, Qin (Child & Family Social Work, 2020)
Abstract As the population of Chinese immigrants has been growing rapidly in the United States, it has been understudied on the parenting behaviours as well as the roles parental stress and social support playing in parenting in this group. This study investigated whether parental stress was associated with parenting and whether this relationship was mediated by social support in a sample of 255 Chinese immigrant parents from the Survey of Asian American Families in New York City. Regression analyses with a rich array of control variables found that a higher level of parental stress and the presence of one or more stressors such as unemployment, low income, and low education were positively associated with the use of harsh discipline and parent?child conflicts and negatively associated with positive parenting practices. Social support functioned as a significant mediator in the relationships between parental stress and positive parenting practices but not in the relationships of parental stress with parent?child conflict or the use of harsh discipline.
8 citations (Crossref) [2022-09-21]
Keywords: Chinese immigrants; harsh discipline; parental stress; parenting practices; parent–child conflict; social support

Home–School Collaboration in Assessment, Placement, and Individual Education Plan Development for Children With Special Education Needs in Macao: The Views of Parents - Correia, Ana; Teixeira, Vitor; Forlin, Chris (School Community Journal, 2021)
The aim of this study was to explore home–school collaboration in the areas of assessment, placement, and Individual Education Plan (IEP) development for children identified with disabilities or special educational needs (SEN) in Macao. Despite the noted benefits of parent–school partnerships from prior research, minimal research has been conducted from the perspective of parents of children with SEN to examine whether these partnerships materialize in the context of Macao. Participants included 115 parents of school-aged children diagnosed with SEN. They provided demographic information and completed a 36-item questionnaire derived from two validated instruments. The research identified a range of factors which hinder parental involvement in decision-making and in the inclusion of children with SEN in optimal ways in Macao schools. Parents indicated they were not receiving relevant information and assessment feedback from the teachers; they were minimally involved in the IEP process, and their children were not receiving one-to-one support, regardless of the type of placement. Parents also underlined issues related to the timing of assessment procedures. Parents of children attending special classes in regular schools voiced more satisfaction with support provision than parents of children following the full inclusion model. Recommendations about how services could be improved for greater parental involvement are discussed. Key Words: parental involvement, school–family collaboration, inclusion, special educational needs, Macao, Individual Education Plans, IEP

Triggering a Change of The Economic Paradigm - Rothlin, Stephan (The Journal of the Macau Ricci Institute, 2021)

Aristotle, Lubich And Ratzinger On A New Economic Paradigm - Eh, Edmond (The Journal of the Macau Ricci Institute, 2021)
GSCC: 0000000

Ethical Investment’s Visible Hand: Methods And Transformative Potentials - Gassner, Franz (The Journal of the Macau Ricci Institute, 2021)

A network analysis investigation of the comorbidity between sleep dysfunction and PTSD symptomatology among Filipino domestic workers in Macao (SAR) China- ClinicalKey - Wang, Siyuan; Sit, Hao Fong; Garabiles, Melissa R.; Blum, Daniel; Hannam, Kevin; Armour, Chérie; Hall, Brian J. (Journal of Psychiatric Research, 2021)

Origin of the Qiyugou gold deposit in the southern margin of the North China Craton: Insights from trace elements of pyrite and mineralogy of Bi-minerals - Wu, Qiang; Zhao, Tai-Ping; Chen, Wei Terry; Gao, Xin-Yu; Meng, Lei; Qiu, Wenhong Johnson (Ore Geology Reviews, 2021)
The Qiyugou gold deposit, located in the Xiong’ ershan area of the North China Craton, contains abundant bismuth-sulfosalts that are closely associated with gold mineralization. Pyrite is the dominant Au-hosted mineral, and has been formed in three generations (Py1, Py2, and Py3). Py1 grains, generally intergrown with milky quartz, are coarse (>1 mm), euhedral in shape, and Au-depleted in composition. In contrast, subhedral Py2 grains, associated with light gray quartz, are medium to coarse (0.2–3 mm) and are enriched in gold that is both invisible and visible. Py3 grains (0.1–0.5 mm), intergrown with abundant sulfide minerals, are relatively fine and Au-depleted. The time-resolved LA-ICP-MS depth profiles of the Py2 grains indicate that invisible gold occurs as either solid solution or nano-particles of native gold and electrum. Visible gold occurs as small blebs in the Py2 grains where inclusions of native bismuth, galenobismutite, lillianite homologs, tetradymite, and galena are also present. In addition, it is common that electrum in microfracture infillings or along grain boundaries of the Py1 and Py2, are intergrown with bismuthinite derivatives, Bi-Cu sulfosalts, emplectite, tetradymite, chalcopyrite, galena, and Py3. Based on textural relationships and mineral assemblages, calculation of physicochemical conditions show that gold was formed in conditions of fTe2 = ~10−11 and fS2 = ~10−11 to 10−12 for Py2, and fTe2 = ~10−9 to 10-11and fS2 = ~10−10 to 10−11 for Py3. We thus proposed that such physicochemical conditions may have triggered the precipitation of Bi melt, and sulfidation driven by cooling or increase in sulfur content results in the transformation of the Au-Bi liquid into a stable assemblage of native gold and bismuthinite. These bismuth minerals are associated with native gold/Au-bearing minerals, indicating that the Au mineralization of the Qiyugou gold deposit might be genetically associated with Bi melt. The present study highlights the role of Bi as important gold scavengers in arsenic-deficient ore-forming fluid.
Keywords: Bi melts scavenging Au; Bismuth minerals; Qiyugou gold deposit; The southern margin of the North China craton; Trace element of pyrite

A análise da cultura organizacional escolar através dos seus artefactos - Correia, Ana; Costa, Adelino (Revista do Fórum Português de Administração Educacional,, 2003)

Liderança feminina nas escolas de Macau: uma abordagem exploratória - Correia, Ana; Costa, Jorge (Revista Portuguesa de Investigação Educacional, 2004)
Number: 3

Da aptidão à aspiração: um caminho por percorrer - Correia, Ana (CECS - Publicações / eBooks, 2015)
Number: 0

Classroom management into learning: using phenomenography to analyse student teachers’ conceptions of classroom management - Correia, Ana Maria (Revista Portuguesa de Investigação Educacional, 2019)
Classroom management is a critical area in the curriculum of teacher education programs. Student teachers’ conceptions of the role of the teacher as a class leader are frequently backed by their intuition and experience as students and socio-cultural context rather than evidence-based. This paper examines the conceptions of classroom management held by a multicultural group of forty-four student teachers attending a teacher education program at a higher education institute in Macao. The study aims at understanding the patterns of variation expressed by student teachers regarding the purpose and relevance of the object of learning. It compares a) the patterns of variation in students’ views of classroom management, and b) the students’ learning progress based on the pre-and post-test. The phenomenographic approach was adopted as the conceptual framework. Participants handwritten transcripts from student teachers at the first and last sessions of the course are the primary type of data collection. The findings show that changes in student teachers’ understanding of the conceptions of classroom management occurred during the course. The initial preferences for disciplinary approaches to classroom leadership have given way to conceptions of promoting the integration of classroom management into learning. The participants expressed increasing adherence to classroom management systems targeting and providing behavioural and academic supports and interventions to children and adolescents with and without special needs.
Artwork Size: 257-280 Páginas

Perceived competence and social acceptance of preschool children in Macao: a case study - Teixeira, Vitor; Correia, Ana (International Journal of Learning and Teaching, 2017)
0 citations (Crossref) [2022-09-21]

Catholic Orders as Efficient Institutions - Rothlin, Stephan; Frey, B. S (Lumen: A Journal of Catholic Studies, 2015)

Un nuovo paradigma economico.(“Ideas for a New Economic Paradigm”) - Rothlin, Stephan (La Civiltà Cattolica, 2021)
La crisi del Covid-19 ha evidenziato il disagio e il divario sempre più ampio tra ricchi e poveri. La crisi finanziaria del 2007-2009 era già risuonata come un campanello d'allarme sulla necessità di

Resource estimation of the sulfide-rich deposits of the Yuhuang-1 hydrothermal field on the ultraslow-spreading Southwest Indian Ridge - Yu, Junyu; Tao, Chunhui; Liao, Shili; Dias, Ágata; Liang, Jin; Yang, Weifang; Zhu, Chuanwei (Ore Geology Reviews, 2021)
Seafloor massive sulfide (SMS) deposits are important deep-sea mineral resources expected to occur predominantly on slow- and ultraslow-spreading mid-ocean ridges. Resource estimates are already available for some of the largest SMS deposits on slow-spreading ridges but not on ultraslow-spreading ridges. Based on geological mapping and sampling, this study investigates the distribution and content of sulfide-rich deposits in the Yuhuang-1 hydrothermal field (YHF), located on the ultraslow-spreading Southwest Indian Ridge. The sulfide-rich deposits in the YHF are composed of two areas ∼500 m apart: the southwest sulfide area (SWS) and the northeast sulfide area (NES). We calculated the volume of sulfide-rich mounds in the YHF and arrived at a total accumulation of ∼10.6 × 106 tons, including at least ∼7.5 × 105 tons of copper and zinc and ∼18 tons of gold. Furthermore, considering the coverage of layered hydrothermal sediment mixed with sulfide-rich breccias, which may have underlying massive sulfide deposits, the maximum total mass was estimated at ∼45.1 × 106 tons. This suggests that the YHF is one of the largest SMS deposits worldwide and confirm that ultraslow-spreading ridges have the greatest potential to form large-scale SMS deposits.
3 citations (Crossref) [2022-09-21]
Keywords: Resource estimate; Seafloor massive sulfide deposits; Southwest Indian Ridge; Yuhuang-1 hydrothermal field

Anticipare il Futuro della Cina. L’eredità del vescovo gesuita Jin Luxian SJ (“Anticipating the Future of China. The Heritage of the Jesuit Bishop Jin Luxian SJ”) - Rothlin, Stephan (La Civiltà Cattolica, 2020)

The Long March toward Moral Leadership in Business - Rothlin, Stephan; McCann, D (Silliman Journal, 2018)

Professional Ethics as Training in Civic Education - Rothlin, Stephan (Hong Kong Journal of Catholic Studies, 2018)

Transparency: A Necessary First Step Toward an Ethic of Finance - Rothlin, Stephan; McCann, D; Myers, T (Silliman Journal, 2017)

Magmatic Evolution of Garnet-Bearing Highly Fractionated Granitic Rocks from Macao, Southeast China: Implications for Granite-Related Mineralization Processes - Quelhas, Pedro; Mata, João; Dias, Ágata (Journal of Earth Science, 2021)
The widespread W-(Mo)-Sn-Nb-Ta polymetallic mineralization in Southeast (SE) China is genetically associated with Mesozoic highly fractionated granitic rocks. Such rocks have enigmatic mineralogical and geochemical features, making its petrogenesis an intensely debated topic. To better understand the underlying magma evolution processes, petrography, garnet chemistry and whole-rock major and trace element data are reported for Jurassic highly fractionated granitic rocks and associated microgranite and aplitepegmatite dikes from Macao and compared with coeval similar granitic rocks from nearby areas in SE China. Despite the fact that the most evolved rocks in Macao are garnet-bearing aplite-pegmatite dikes, the existence of coeval two-mica and garnet-bearing biotite and muscovite granites displaying more evolved compositions (e.g, lower Zr/Hf ratios) indicates that the differentiation sequence reached higher degrees of fractionation at a regional scale. Although crystal fractionation played an important role, late-stage fluid/melt interactions, involving F-rich fluids, imparted specific geochemical characteristics to Macao and SE China highly fractionated granitic rocks such as the non-CHARAC (CHArge-and-RAdius-Controlled) behavior of trace elements, leading, for example, to non-chondritic Zr/Hf ratios, Rare Earth Elements (REE) tetrad effects and Nb-Ta enrichment and fractionation. Such process contributed to the late-stage crystallization of accessory phases only found in these highly evolved facies. Among the latter, two populations of garnet were identified in MGI (Macao Group I) highly fractionated granitic rocks: small grossular-poor euhedral grains and large grossular-rich skeletal garnet grains with quartz inclusions. The first group was mainly formed through precipitation from highly evolved Mn-rich slightly peraluminous melts under low-pressure and relatively low temperature (∼700 °C) conditions. Assimilation of upper crust metasedimentary materials may have contributed as a source of Mn and Al to the formation of garnet. The second group has a metasomatic origin related to the interaction of magmatic fluids with previously crystallized mineral phases and, possibly, with assimilated metasedimentary enclaves or surrounding metasedimentary strata. The highly fractionated granitic rocks in Macao represent the first stage in the development of granite-related W-(Mo)-Sn-Nb-Ta mineralization associated with coeval more evolved lithotypes in SE China.
1 citations (Crossref) [2022-09-21]

Geology of the Macao Special Administrative Region (China) - Quelhas, Pedro; Borges, Ricardo; Dias, Ágata Alveirinho; Ribeiro, Maria Luísa; Costa, Pedro; Mata, João (Journal of Maps, 2021)
A 1:12,000 geological map of the Macao Special Administrative Region has been produced through detailed field work supported by petrographic, mineralogical, geochronological and geochemical data obtained in previous studies. This map aims to represent a reliable tool to understand the geological evolution of the region and for management of the territory. The geology of Macao is dominated by two groups of Jurassic granitic rocks belonging to an intrusive suite located along the coast of Southeast China: Macao Group I (MGI: 164.5 ± 0.6 to 162.9 ± 0.7 Ma) and Macao Group II (MGII: 156.6 ± 0.2 to 155.5 ± 0.8 Ma), including the associated microgranite, aplite and pegmatite dikes and quartz veins. Remnants of the metasedimentary wall-rock are present as Devonian xenoliths enclosed within the granites. Younger Jurassic to Cretaceous andesite to dacite dikes (150.6 ± 0.6 to <120 Ma) intrude the granitic rocks. Additionally, Quaternary sedimentary deposits cover the older lithologies.
0 citations (Crossref) [2022-09-21] _eprint: https://doi.org/10.1080/17445647.2021.1906340
Keywords: Jurassic; Macao (South China); Mesozoic; geological map; granites; magmatic rocks

Acculturative stress and coping among migrant workers: A global mixed-methods systematic review - Liem, Andrian; Renzaho, Andre M. N.; Hannam, Kevin; Lam, Agnes I. F.; Hall, Brian J. (Applied Psychology: Health and Well-Being, 2021)
No existing review has synthesized key questions about acculturation experiences among international migrant workers. This review aimed to explore (1) What are global migrant workers’ experiences with acculturation and acculturative stress? (2) What are acculturative stress coping strategies used by migrant workers? And (3) how effective are these strategies for migrant workers in assisting their acculturation in the host countries? Peer-reviewed and gray literature, without time limitation, were searched in six databases and included if the study: focused on acculturative stress and coping strategies; was conducted with international migrant workers; was published in English; and was empirical. Eleven studies met the inclusion criteria. Three-layered themes of acculturation process and acculturative stress were identified as: individual layer; work-related layer; and social layer. Three key coping strategies were identified: emotion-focused; problem-focused; and appraisal-focused. These coping strategies were used flexibly to increase coping effectiveness and evidence emerged that a particular type of acculturative stress might be solved more effectively by a specific coping strategy. Migrant workers faced numerous challenges in their acculturative process. Understanding this process and their coping strategies could be used in developing research and interventions to improve the well-being of migrant workers.
6 citations (Crossref) [2022-09-21] GSCC: 0000004
Keywords: acculturation; cultural adaptation; global mental health; health disparities; healthcare access; migrant health

Geological Map of the Macao Special Administrative Region (China) - Quelhas, P; Borgens, R; Dias, Ágata; Ribeiro, L; Costa, P; Mata, J (Journal of Maps, 2021)
0 citations (Crossref) [2022-09-21]

Mesozoic Granitic Magmatism in Macao, Southeast China - Quelhas, P. M.; Mata, J.; Lou, U. T.; Ribeiro, M. L.; Dias, Ágata (AGU Fall Meeting Abstracts, 2016)
Macao ( 30 Km2) is a territory characterized by small granitic intrusions, located along the coastal region of Southeast China (Cathaysia Block). Granitoids occur as different facies, including microgranite dykes, with distinct textural, mineralogical and geochemical features, for which a middle-upper Jurassic age ( 164 Ma) has been proposed. New data suggest that these granitoids are mostly high-K calc-alkaline metaluminous (A/CNK = 0.8 - 1.1) biotite granites, consistent with total absence of primary muscovite. They show variable amounts of SiO2 (67-77%), reflecting different degrees of magmatic evolution. There is also variability in terms of trace elements, particularly Rare Earth Elements (REEs), evidenced by decreasing (La/Sm)N, (Gd/Lu)N, (Ce/Yb)N and (Eu/Eu*)N towards the more evolved samples, which can be partly attributed to fractional crystallization processes. Most of the granitoids are characterized by (La/Yb)N = 3 - 10.8, showing negative Ba, Nb, Sr, Zr, P, Ti and Eu anomalies. On the other hand, microgranite dykes, along with a few more evolved granites, show an opposite tendency, being usually enriched in HREEs relatively to LREEs with (La/Yb)N = 0.4 - 1.1. Our data suggests intermediate genetic affinities between I-type and A-type granites. Although these granitoids are mostly metaluminous (characteristic of I-types), Ga/Al ratios, usually used to identify A-types, are close to the accepted boundary between A-type and other granite types. The affinities with A-type granites are more marked for the more evolved facies, which depict higher values of FeOt/MgO (14 - 60) and K2O/MgO (60 - 250). Their trace element characteristics are also transitional between WPG (Within-plate granites) and Syn-COLG (Collision Granites). We interpret those transitional characteristics (A/I and WPG/Syn-COLG) of Macao granitoids as reflecting an origin by melting of infracrustal sources over a period of high heat transfer from mantle to crust during an extensional tectonic setting probably contemporaneous with the subduction of the paleo-Pacific plate beneath the Eurasia, whose paleo-suture is thought to be located in the east flank of the Central Range, Taiwan.
Keywords: 8499 General or miscellaneous; VOLCANOLOGY

Geochemistry and stable isotope constraints on high-temperature activity from sediment cores of the Saldanha hydrothermal field - Dias, Ágata; Früh-Green, G.L.; Bernasconi, S.M.; Barriga, F.J.A.S. (Marine Geology, 2011)
24 citations (Crossref) [2022-09-21]

Surface sediment composition and distribution of hydrothermal derived elements at the Duanqiao-1 hydrothermal field, Southwest Indian Ridge - Dias, Ágata; Liao, Shili; Tao, Chunhui; Su, Xin; Yang, Zhen; Ni, Jianyu; Liang, Jin; Yang, Weifang; Liu, Jia; Li, Wei; Dong, Chuanwan (Marine Geology, 2019)
9 citations (Crossref) [2022-09-21]

High-precision geochronology of Mesozoic magmatism in Macao, Southeast China: Evidence for multistage granite emplacement - Quelhas, Pedro; Dias, Ágata; Mata, João; Davis, Donald Wayne; Ribeiro, Maria Luísa (Geoscience Frontiers, 2020)
5 citations (Crossref) [2022-09-21]

XRD Identification of Ore Minerals during Cruises: Refinement of Extraction Procedure with Sodium Acetate Buffer - Milinovic, Jelena; Dias, Ágata; Janeiro, Ana I.; Pereira, Manuel F. C.; Martins, Sofia; Petersen, Sven; Barriga, Fernando J. A. S. (Minerals, 2020)
The on-board identification of ore minerals during a cruise is often postponed until long after the cruise is over. During the M127 cruise, 21 cores with deep-seafloor sediments were recovered in the Trans-Atlantic Geotraverse (TAG) field along the Mid Atlantic Ridge (MAR). Sediments were analyzed on-board for physicochemical properties such as lightness (L*), pH and Eh. Selected samples were studied for mineral composition by X-ray powder diffraction (XRD). Based on XRD data, sediment samples were separated into high-, low- and non-carbonated. Removal of carbonates is a common technique in mineralogical studies in which HCl is used as the extraction agent. In the present study, sequential extraction was performed with sodium acetate buffer (pH 5.0) to remove carbonates. The ratio between the highest calcite XRD reflection in the original samples (Iorig) vs its XRD-reflection in samples after their treatment with the buffer (Itreat) was used as a quantitative parameter of calcite removal, as well as to identify minor minerals in carbonated samples (when Iorig/Itreat > 24). It was found that the lightness parameter (L*) showed a positive correlation with calcite XRD reflection in selected TAG samples, and this could be applied to the preliminary on-board determination of extraction steps with acetate buffer (pH 5.0) in carbonated sediment samples. The most abundant minerals detected in carbonated samples were quartz and Al- and Fe-rich clays. Other silicates were also detected (e.g., calcic plagioclase, montmorillonite, nontronite). In non-carbonated samples, Fe oxides and hydroxides (goethite and hematite, respectively) were detected. Pyrite was the dominant hydrothermal mineral and Cu sulfides (chalcopyrite, covellite) and hydrothermal Mn oxides (birnessite and todorokite) were mineral phases identified in few samples, whereas paratacamite was detected in the top 20 cm of the core. The present study demonstrates that portable XRD analysis makes it possible to characterize mineralogy at cored sites, in particular in both low- and high-carbonated samples, before the end of most cruises, thus enabling the quick modification of exploration strategies in light of new information as it becomes available in near-real time.
7 citations (Crossref) [2022-09-21]

Sulfur isotopic compositions of sulfides along the Southwest Indian Ridge: implications for mineralization in ultramafic rocks - Dias, Ágata; Ding, Teng; Tao, Chunhui; Liang, Jin; Chen, Jie; Wu, Bin; Ma, Dongsheng; Zhang, Rongqing; Wang, Jia; Liao, Shili; Wang, Yuan; Yang, Weifang; et al. (Mineralium Deposita, 2020)
11 citations (Crossref) [2022-09-21]

Evidence for mixed contribution of mantle and lower and upper crust to the genesis of Jurassic I-type granites from Macao, SE China - Quelhas, Pedro; Mata, João; Dias, Ágata (GSA Bulletin, 2021)
Abstract Much controversy has occurred in the past few decades regarding the nature of the sources, the petrogenetic processes, and the tectonic regime(s) of the Jurassic magmatism within the Southeast China magmatic belt. This study aims to contribute to the discussion with mineral chemistry, and whole-rock element and Sr-Nd-Hf-Pb isotopic geochemical data from granitic rocks and microgranular mafic enclaves from Macao, where two discrete groups of I-type biotite granites have been identified (referred to as Macao Group I [MGI] and Macao Group II [MGII]). It is proposed that the granitic magmas were generated by partial melting of infracrustal medium- to high-K, basaltic Paleoproterozoic to Mesoproterozoic protoliths (Nd depleted mantle model age [TDM2] = 1.7–1.6 Ga and Hf TDM2 = 1.8–1.6 Ga), triggered by underplating of hot mantle-derived magmas in an extensional setting related to the foundering of a previously flat slab (paleo–Pacific plate) beneath the SE China continent. The main differences between the two groups of Macao granites are attributed to assimilation and fractional crystallization processes, during which upper-crustal Paleozoic metasediments were variably assimilated by MGI magmas. This is evidenced by an increase in initial 87Sr/86Sr ratios with degree of evolution, presence of metasedimentary enclaves, and high percentage of zircon xenocrysts with Paleozoic ages. In addition, other processes like late-stage fluid/melt interaction and magma mixing also left some imprints on granite compositions (rare earth element tetrad effect plus non–charge-and-radius-controlled behavior of trace elements and decoupling between different isotope systems, respectively). The distribution of isotopically distinct granites in SE China reflects the nature of the two Cathaysia crustal blocks juxtaposed along the Zhenghe-Dapu fault.
7 citations (Crossref) [2022-09-21]

‘Em Procissão Solene a Deus Orando, para os Batéis Viemos Caminhando’—The Long Ebb-Tide of Catholic Public Piety in the Former-Portuguese Enclave of Macao - Morgan, Stephen (Religions, 2021)
When the City of the Name of God of Macao marked 400 years of Portuguese administration in 1956, the Catholic community’s participation was marked by a wide range of activities that included liturgical celebrations, public processions and other devotions that involved large numbers of the lay faithful, members of confraternities, in addition to the clergy and religious of the enclave. Twenty-one years later the Diocese of Macao celebrated its own quatercentenary with celebrations of a decidedly more sober character and at the retrocession of Macao to Chinese control in December 1999, other than a few liturgical events and hierarchical presence at civic ceremonies, the Church was all but invisible. As the Diocese of Macao plans for its 450th anniversary, some of the former richness has begun to return. This paper outlines the long ebb tide and now-nascent flow of the tide of Catholic public piety in Macao over this period by reference to the Catholic religious processions of the City and seeks to offer tentative explanations grounded in the theological, ecclesial, political and cultural winds that have blown across the Pearl River Delta since the end of the Second World War.
0 citations (Crossref) [2022-09-21] GSCC: 0000000
Keywords: Catholic Church; China; Macao; Portugal; Vatican II; confrarias; processions; public piety

The interplay between a Confucian-heritage culture and teachers’ sentiments and attitudes towards inclusion in Macao - Correia, Ana; Monteiro, Elisa; Kuok, Angus; Forlin, Christine; Teixeira, Vitor (European Journal of Special Education Research, 2019)

Wrestling with God - Flores, Randolf (Orientis Aura: Macau Perspectives In Religious Studies, 2016)
This study will discuss the following Old Testament texts: Gen 32:23-32; Jon 1:17; Tob 6:1-9; and Exod 4:24-26 and will argue that these are about the initiation of a person to do a divine mission. Some parallels from Asia—Epic Gilgamesh, texts from Tibetan Buddhism, Hinduism, and the Philippine epic, Biag ni Lam-ang will also be taken into consideration to shed light on them. It will also present their interpretation as typoi of the sacraments of initiations found in early Christian literature and art.

Vatican II - Gomez, Fausto (Orientis Aura: Macau Perspectives In Religious Studies, 2016)
From a reason-faith perspective, I reflect on “Vatican II: Gaudium et Spes Fifty Years Later.” In the introduction, I speak briefly on the Second Vatican Council, and on its Pastoral Constitution Gaudium et Spes (“Joy and Hope”) and its ethical and social teachings.

The Film Sound Analysis Framework: A Conceptual tool to Interpret the Cinematic Experience - Barbosa, Álvaro; Dizon, Kristine (Journal of Science and Technology of the Arts, 2020)
GSCC: 0000001
Keywords: Analysis framework; Film studies; Sound and music design

Pandemic (Im)mobilities - Adey, Peter; Hannam, Kevin; Sheller, Mimi; Tyfield, David (Mobilities, 2021)
33 citations (Crossref) [2022-09-21] GSCC: 0000029

Tourist’s mobilities: Walking, cycling, driving and waiting - Hannam, Kevin; Butler, Gareth; Witte, Alexandra; Zuev, Dennis (Tourist Studies, 2021)
This commentary reviews recent research in terms of tourist’s mobilities in terms practices of walking, cycling and driving. It concludes by reflecting on the contemporary lock down of travel in terms of the global pandemic and its consequences for waiting, stillness and immobility – particularly in terms of flying.
4 citations (Crossref) [2022-09-21] GSCC: 0000003

Hydrological Risk Assessment at Praia, Cape Verde - Silva, Jose Lino; Negreiros, Joao Garrott Marques (International Journal of Environment, Agriculture and Biotechnology, 2017)
Hydrology modeling became a relevant topic for the Cidade da Praia, Cabo Verde, Africa, due to negative impact risk to local population and its assets. The modeling via Geographical Information Systems (GIS) can help the decision-making process of space occupation and characterization for this type of risk. Under the municipalities of Praia, the phenomenon of flash flood is common, causing soil erosion and landslide. This constitutes a risk for the local habitat, particularly in districts with a lack of strong human infrastructures. To simulate, analyze and generate risk maps using GIS to help this county governance authorities for decision-making, thus, becomes the main aim of this article.
Number: 2

Pestilent Popes or a Pestilent Church? Judaism, Catholicism, and Skeptical Theism - McNabb, Tyler Dalton (The Heythrop Journal, 2020)
0 citations (Crossref) [2022-09-21] GSCC: 0000000

Has Oppy Done Away with the Aristotelian Proof? - McNabb, Tyler; DeVito, Michael (The Heythrop Journal, 2020)
0 citations (Crossref) [2022-09-21] GSCC: 0000000

Education in Religious Freedom - Gassner, Franz (Orientis Aura: Macau Perspectives in Religious Studies, 2016)
The author emphasizes the crucial relevance of religious liberty and freedom of expression for a harmonious and peaceful development of modern societies. He follows the prophetic Declaration of Religious Freedom of Second Vatican Council (1965) with its constitutional limitation of governmental powers in matters of religion. The high value of religious freedom is judged as bulwark of all human rights and true capstone of sound human and societal developments, which have to be guarded against any form of infringements. In this regard, a reasonable education in religious freedom and liberty is indispensable for young people of the twenty-first century. Education in religious freedom in the context of moral and religious formation is based on the dignity of every human person and promotes a deeper mutual and cultural understanding by respecting the conscience of every human person. It thus carries the potential to diminish conflicts and clashes in a sustainable way. Educational reforms in countries have to include the high value of religious liberty and freedom as a main element and condition for human dignity and a peaceful global development.

Is the Belt and Road Initiative in Africa Sustainable? - Nwachukwu, Francis C. (The Journal of the Macau Ricci Institute, 2019)
In 2000, the China-Africa relationship was further strengthened with the establishment of the Forum on China-Africa Cooperation (FOCAC). The FOCAC offers a platform for consultation and cooperation mechanisms aimed at deepening diplomatic, security, trade and investment relations between China and African countries. Later came the Belt and Road Initiative (BRI) in 2013, an international trade network initiated by China that connects the three continents of Asia, Europe and Africa. The BRI focuses on the following key areas: cultural exchange; policy coordination; facilities connectivity; trade and investment; and financial integration. The BRI shares development objectives similar to those of the United Nations’ Sustainable Development Goals (SDGs). In fact, the BRI implements part of the SDGs and provides a practical mechanism to strengthen the Sino-Africa relationship, which Africa can leverage to meet its Sustainable Goals. Africa is linked through the “Road” of the BRI plan and has received infrastructural projects funded by China to facilitate trade and integration of the national economies along the trading route. Through the establishment of Economic and Trade Zones which attracts investments from Chinese companies, and building infrastructures such as sea ports and railways, China through the BRI framework is helping Africa meet UN SGD Goal 9 concerning industry, innovation and infrastructure. A practical effect is that the BRI is helping African countries overcome the infrastructure gap, create jobs, acquire skills and promote integration between countries.

“China Wahala”: the Tribulations of Nigerian “Bushfallers” in a Chinese Territory” - Morais, Isabel (Transtext(e)s Transcultures 跨文本跨文化. Journal of Global Cultural Studies, 2009)
Recent scholarly studies and media coverage have primarily focused on China’s increasing presence and sometimes asymmetrical engagement with Africa in tandem with the new trend of Chinese migration to that continent. Yet, the inverse flux of Africans to China and the emergence of African communities in Southern China over the last decades is influencing some areas of the Pearl River Delta Region, and changing the fabric of cities like Guangzhou, Macau and Hong Kong, in a way without precedent. There are representations or exotic descriptions from some mass circulation magazines and newspapers on the infamous Chungking Mansions in Hong Kong or the so-called “Chocolate-city,”an area centered aroundHongqiao, the village-district and Canaan market in the city of Guangzhou, with its arcades and strip malls filled with ethnic businesses and transnational migrants. In Macau, significant concentrations of African population of different origins are also seen in the “Papa pun” commercial center or in downtown areas. Despite many studies devoted to the “ethnoburbs” in other latitudes, only very recently, these entrepreneurial African communities in Mainland China are starting to become worthy of serious scholarly attention. Yet,there is total absence of studies dealing with the presence of more and more African students and the cultural manifestations of African communities well portrayed in the new African cinema, in music produced by Afro-Chinese bands or even singers.Besides a continuing inward flow of transient Africans who come to China for business on a regular basis, a significant number of settler African traders, particularly Nigerians, have already married local Chinese women, set up families, autonomously run their businesses without recourse to Chinese intermediaries, and established a web of informal and formal committees representing their home nations and states, to solve disputes while maintaining personal and business links with Africa. Besides, those emigrant ‘bushfallers’ who are coming to China solely for business purposes, a new form of “silent” migration of Nigerians comprising students from different backgrounds is enrolling in higher education institutions in the Macau Special Administrative Region of China. These students are coming to pursue their studies or to seek a job to pay their student fees at the margin of the PRC scholarship and stipendprograms for visiting African students that were popular in China in the 1960s and mid-1970s as part of CCP’s foreign policy for Third World aiming friendly relations with Africa. Today, these “transnational” Nigerian students are in their own way affirming their identity and difference, in southern China, in particularly in Macau SAR, thanks to their network of multiple interrelations across nation-states from Africa to Asia and to a combination of perseverance, zeal, and gentleness without subservience. Although they have not been targets for the hostility and even violence like the Shanghai incident of July 1979 or the Nanjing protests in December 1988 at Hehai University targeting African students, today these Nigerian students are facing more subtle forms of ethnocentrism and legal discrimination from immigration laws to daily practices, which always try to associate their citizenship to problematic or easy stereotypes of scam or colour. Yet, at the same time, everything seems to indicate that these newcomers are quick adapting and finding new forms of negotiating their social integration in the Chinese local society which in turn is offering more opportunities.This paper is part of a more ambitious project which aims to assess the new forms of migration from Africa to China and from China to Africa as well as their impact and contribution of globalization. First, this paper considers why and how Macau has evolved from a Portuguese outpost where slavery was a an institutionalized commodity to special administrative region of China where a new urban African community, mostly composed by Nigerian students, is in formation due to opportunities and rapid changes occurring in the region in the first years of the twenty-first century, by comparing the new to old African communities of students and business people/migrant workers from former Portuguese colonies (Angola, Cape Verde, São Tomé and Príncipe, Guinea-Bissau, and Mozambique).Finally, borrowing the title from a sequel movie with the same title of the promising New African cinema, the paper focus on the “China Wahala”or the troubles of these Nigerian students through their tales of their experiences of racism(s) and their negotiations and responses which radically contradicts not only the slogans of cultural diversity propagated by the official discourse and tourist channels as these Nigerians are confronted daily with often dramatic situations ranging from indifference and ostracism to exclusion.
1 citations (Crossref) [2022-09-21] Number: 5

Macau entre a “China Tropical” e a lusofonia a Oriente: Algumas achegas sobre os contextos colonial e pós-colonial - Morais, Isabel (Portuguese Studies Review, 2018)

Science and Laudato Si’ on the Paradigm Shift towards Sustainable Development - Gassner, Franz (The Journal of the Macau Ricci Institute, 2018)
For sustainability researchers and global policy makers it is lucid clear that a radical turnaround of modern societies is needed to approach sustainable development paths. Pope Francis takes his stand on a basic paradigm shift in his Encyclical Letter Laudato Si’: Care for our Common Home (2015). He calls for a radical shift of mindsets and ecological and cultural conversion which are needed for sustainability and a life in dignity for all. The author compares aspects from sustainability research and Laudato Si’ and shows how science and Francis spiritual-theological take converge. Both call for the need of new mindsets and spiritual resources to nourish just life-styles and sustainable societies.

Plasticity in reproductive behaviour in two populations of the peacock blenny - Oliveira, Rui F.; Simões, Mariana G.; Gonçalves, David; Saraiva, João L. (Behaviour, 2011)
3 citations (Crossref) [2022-09-21]

Social cues in the expression of sequential alternative reproductive tactics in young males of the peacock blenny, Salaria pavo - Fagundes, Teresa; Simões, Mariana G.; Gonçalves, David; Oliveira, Rui F. (Physiology & Behavior, 2012)
4 citations (Crossref) [2022-09-21]

Interpopulational variation of the mating system in the peacock blenny Salaria pavo - Saraiva, João L.; Pignolo, Giulia; Gonçalves, David; Oliveira, Rui F. (acta ethologica, 2012)
12 citations (Crossref) [2022-09-21]

Efficient isolation of polymorphic microsatellites from high-throughput sequence data based on number of repeats - Cardoso, Sara D.; Gonçalves, David; Robalo, Joana I.; Almada, Vitor C.; Canário, Adelino V.M.; Oliveira, Rui F. (Marine Genomics, 2013)
8 citations (Crossref) [2022-09-21]

Ecological modulation of reproductive behaviour in the peacock blenny: a mini-review - Saraiva, J. L.; Gonçalves, David; Oliveira, R. F. (Fish Physiology and Biochemistry, 2013)
6 citations (Crossref) [2022-09-21]

Birth date predicts alternative life‐history pathways in a fish with sequential reproductive tactics - Fagundes, Teresa; Simões, Mariana G.; Saraiva, João L.; Ros, Albert F. H.; Gonçalves, David; Oliveira, Rui F. (Functional Ecology, 2015)
10 citations (Crossref) [2022-09-21]

Chromosome-level reference genome of the Siamese fighting fish Betta splendens, a model species for the study of aggression - Fan, Guangyi; Chan, Judy; Ma, Kailong; Yang, Binrui; Zhang, He; Yang, Xianwei; Shi, Chengcheng; Law, Henry; Ren, Zhitao; Xu, Qiwu; Liu, Qun; Wang, Jiahao; et al. (GigaScience, 2018)
9 citations (Crossref) [2022-09-21]

Desafios à unidade geopolítica da lusofonia - Leandro, Francisco da Silva (IDNBrief, 2017)
info:eu-repo/semantics/publishedVersion
Accepted: 2018-05-07T15:45:27Z

Impacts of Public Support and Voices Pluralism in Macao Newspapers - Simões, José Manuel; Faustino, Paulo (Journalism and Mass Communication, 2017)
0 citations (Crossref) [2022-09-21]

Shequ construction and service development in urban China: an examination of the Shenzhen model - Tang, Ning; Sun, Fei (Community Development Journal, 2017)
3 citations (Crossref) [2022-09-21]

Placement, inclusion, law and teachers’ perceptions in Macao’s schools - Teixeira, Vitor; Correia, Ana; Monteiro, Elisa; Kuok, A. C. H.; Forlin, Chris (International Journal of Inclusive Education, 2018)
In Macao, the government has initiated a debate regarding revisions in the Decree Law in order to promote a more inclusive schooling system. In this Special Administrative Region of China, inclusive education is one of three possible types of special education that are likely be legislated in the future. The way the teachers perceive the different aspects related to inclusive education, namely the principles, concepts and law, is essential for its full implementation. The aim of this study is to understand teachers’ perceptions about the proposed amendments in the consultation document for changes in the special education regime. In particular, we focus on teachers’ acceptance of the recommended role of parents, the proposed placement models and expectations for teacher training. A mixed-methods approach with a survey of a sample of 500 teachers in private schools and interviews to a sub-sample of 20 provide the data. While agreeing in principle with the majority of the proposed changes in the Decree Law, there were several reservations made by the teachers, especially regarding the extent of parental choice, placement decisions and teacher training. Recommendations to continue the pathway for a more inclusive education system in Macao and for further research are made.
7 citations (Crossref) [2022-09-21] _eprint: https://doi.org/10.1080/13603116.2017.1414318
Keywords: Disability; education policy; inclusive education; special education; special education needs

The Cultivation of Research Labor in Pacific Asia with Special Reference to Singapore - Ge, Yun; Ho, K. C. (Asia Pacific Education Review, 2018)
This paper adopts a political economy perspective in understanding how the country context frames the development of higher education doctoral science, technology, engineering, and mathematics (STEM) programs. We argue that a country's commitment to research and development spending as a strategy to maintain its economic competitiveness creates the market for research labor. This embeddedness of STEM doctoral training programs in the country's science and technology system enlarges differences between STEM and non-STEM doctoral programs. This argument is validated from a survey of doctoral students in leading Pacific Asian universities which shows that STEM doctoral programs have stronger research networks, are better financed, use better facilities, and incorporate a variety of research placements. The embeddedness of STEM programs is further illustrated from the case of Singapore. Singapore-based STEM doctoral students mention enjoying better financial support and receiving better career advice from their supervisors. They depend on collaborative peer learning and cite more varied employment options when asked about their career plans.
9 citations (Crossref) [2022-09-21]
Keywords: Career Counseling; Cooperative Learning; Doctoral Programs; Educational Facilities; Employment Opportunities; Financial Support; Foreign Countries; Graduate Students; Networks; STEM Education; Student Attitudes; Student Placement; Student Research; Student Surveys; Supervisor Supervisee Relationship; Universities

Perceived efficacy of teachers in Macao and their alacrity to engage with inclusive education - Monteiro, Elisa; Kuok, A. C. H.; Correia, Ana; Forlin, Chris; Teixeira, Vitor (International Journal of Inclusive Education, 2019)
This paper reports findings of a mixed methods study examining private school teachers’ perceptions of efficacy in dealing with the challenges presented by inclusive education in Macao. This is highly pertinent after the Government invited consultation to propose changes to amendments of the Decree Law of 1996 concerning the education of students with Special Education Needs (SEN) which will likely see private schools being required to accept these students in the future. Within the context of teacher preparedness for inclusive education, the study found that a number of teachers felt that they were not at all prepared to teach students with SEN. Whilst some teachers suggested that they lacked skills and knowledge in teaching in inclusive classrooms, some felt overwhelmed with the challenges. The teachers proposed that they would need to know how to provide instructional adaptations and modifications to support students with SEN. Implications for continuous development of teacher training and education are discussed within the context of improving teacher efficacy and how private school teachers could better respond to the challenges of inclusive education in Macao.
9 citations (Crossref) [2022-09-21] _eprint: https://doi.org/10.1080/13603116.2018.1514762
Keywords: Inclusive education; Macao; teacher education; teacher efficacy

Entre a tradição e a modernidade, os Potiguara. Estudo etno-histórico, narrativas de memórias e rituais, a revisitação e o turismo - Simões, José Manuel (História, histórias, 2017)
0 citations (Crossref) [2022-09-21] Number: 10
Keywords: transformações

O Espaço ao Espaço Público e ao Sentido dos Fatos que os Media nos Oferecem - Simões, José Manuel (Revista GEMInIS, 2018)
Comunicar é tornar comum e informar é dar forma à comunicação. Entre um e outro vai frequentemente uma distancia que nem sempre é possível eliminar. O objetivo deste artigo é mostrar que tanto a comunicação como a informação são um espaço ao sentido da vida. Pese embora as contrariedades e obstáculos, a conivência com os poderes, os imperativos de rentabilidade, a pressão do tempo e a aceleração, os media oferecem um espaço ao espaço público, ao sentido dos fatos, à interpelação; um espaço ao sentido da vida.
0 citations (Crossref) [2022-09-21] Number: 1

Reading acquisition in beginner readers: Typical errors in European Portuguese - Simões, Edlia; Martins, Margarida Alves (Educação e Pesquisa, 2018)
0 citations (Crossref) [2022-09-21]

Acoustic communication in marine shallow waters: testing the acoustic adaptive hypothesis in sand gobies - Amorim, Maria Clara P.; Vasconcelos, Raquel O.; Bolgan, Marta; Pedroso, Silvia S.; Fonseca, Paulo J. (Journal of Experimental Biology, 2018)
Skip to Next Section Acoustic communication is an important part of social behaviour of fish species that live or breed in shallow noisy waters. Previous studies have shown that some fish species exploit a quiet window in the background noise for communication. However, it remains to be examined whether hearing abilities and sound production of fish are adapted to marine habitats presenting high hydrodynamism. Here, we investigated whether the communication system of the painted (Pomatoschistus pictus) and the marbled (Pomatoschistus marmoratus) gobies is adapted to enhance sound transmission and reception in Atlantic shallow water environments. We recorded and measured the sound pressure levels of social vocalisations of both species, as well as snapshots of ambient noise of habitats characterised by different hydrodynamics. Hearing thresholds (in terms of both sound pressure and particle acceleration) and responses to conspecific signals were determined using the auditory evoked potential recording technique. We found that the peak frequency range (100–300 Hz) of acoustic signals matched the best hearing sensitivity in both species and appeared well adapted for short-range communication in Atlantic habitats. Sandy/rocky exposed beaches presented a quiet window, observable even during the breaking of moderate waves, coincident with the main sound frequencies and best hearing sensitivities of both species. Our data demonstrate that the hearing abilities of these gobies are well suited to detect conspecific sounds within typical interacting distances (a few body lengths) in Atlantic shallow waters. These findings lend support to the acoustic adaptive hypothesis, under the sensory drive framework, proposing that signals and perception systems coevolve to be effective within local environment constraints.
8 citations (Crossref) [2022-09-21]

Neurogenomic mechanisms of social plasticity - Cardoso, Sara D.; Teles, Magda C.; Oliveira, Rui F. (Journal of Experimental Biology, 2015)
Skip to Next Section Group-living animals must adjust the expression of their social behaviour to changes in their social environment and to transitions between life-history stages, and this social plasticity can be seen as an adaptive trait that can be under positive selection when changes in the environment outpace the rate of genetic evolutionary change. Here, we propose a conceptual framework for understanding the neuromolecular mechanisms of social plasticity. According to this framework, social plasticity is achieved by rewiring or by biochemically switching nodes of a neural network underlying social behaviour in response to perceived social information. Therefore, at the molecular level, it depends on the social regulation of gene expression, so that different genomic and epigenetic states of this brain network correspond to different behavioural states, and the switches between states are orchestrated by signalling pathways that interface the social environment and the genotype. Different types of social plasticity can be recognized based on the observed patterns of inter- versus intra-individual occurrence, time scale and reversibility. It is proposed that these different types of social plasticity rely on different proximate mechanisms at the physiological, neural and genomic level.
81 citations (Crossref) [2022-09-21]

Temporal variation in brain transcriptome is associated with the expression of female mimicry as a sequential male alternative reproductive tactic in fish - Cardoso, Sara D.; Gonçalves, David; Goesmann, Alexander; Canário, Adelino V. M.; Oliveira, Rui F. (Molecular Ecology, 2018)
Distinct patterns of gene expression often underlie intra- and intersexual differences, and the study of this set of coregulated genes is essential to understand the emergence of complex behavioural phenotypes. Here, we describe the development of a de novo transcriptome and brain gene expression profiles of wild-caught peacock blenny, Salaria pavo, an intertidal fish with sex-role reversal in courtship behaviour (i.e., females are the courting sex) and sequential alternative reproductive tactics in males (i.e., larger and older nest-holder males and smaller and younger sneaker males occur). Sneakers mimic both female's courtship behaviour and nuptial coloration to get access to nests and sneak fertilizations, and later in life transition into nest-holder males. Thus, this species offers the unique opportunity to study how the regulation of gene expression can contribute to intersex phenotypes and to the sequential expression of male and female behavioural phenotypes by the same individual. We found that at the whole brain level, expression of the sneaker tactic was paralleled by broader and divergent gene expression when compared to either females or nest-holder males, which were more similar between themselves. When looking at sex-biased transcripts, sneaker males are intersex rather than being either nest-holder or female-like, and their transcriptome is simultaneously demasculinized for nest-holder-biased transcripts and feminized for female-biased transcripts. These results indicate that evolutionary changes in reproductive plasticity can be achieved through regulation of gene expression, and in particular by varying the magnitude of expression of sex-biased genes, throughout the lifetime of the same individual.
6 citations (Crossref) [2022-09-21] _eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/mec.14408
Keywords: RNA-seq; Salaria pavo; alternative reproductive tactics; behavioural plasticity; neurogenomic state; sex-biased gene expression

Ontogenetic development of the inner ear saccule and utricle in the Lusitanian toadfish: Potential implications for auditory sensitivity - Chaves, Patrícia P.; Valdoria, Ciara M. C.; Amorim, M. Clara P.; Vasconcelos, Raquel O. (Hearing Research, 2017)
Studies addressing structure-function relationships of the fish auditory system during development are sparse compared to other taxa. The Batrachoididae has become an important group to investigate mechanisms of auditory plasticity and evolution of auditory-vocal systems. A recent study reported ontogenetic improvements in the inner ear saccule sensitivity of the Lusitanian toadfish, Halobatrachus didactylus, but whether this results from changes in the sensory morphology remains unknown. We investigated how the macula and organization of auditory receptors in the saccule and utricle change during growth in this species. Inner ear sensory epithelia were removed from the end organs of previously PFA-fixed specimens, from non-vocal posthatch fry (<1.4 cm, standard length) to adults (>23 cm). Epithelia were phalloidin-stained and analysed for area, shape, number and orientation patterns of hair cells (HC), and number and size of saccular supporting cells (SC). Saccular macula area expanded 41x in total, and significantly more (relative to body length) among vocal juveniles (2.3–2.9 cm). Saccular HC number increased 25x but HC density decreased, suggesting that HC addition is slower relative to epithelial growth. While SC density decreased, SC apical area increased, contributing to the epithelial expansion. The utricule revealed increased HC density (striolar region) and less epithelial expansion (5x) with growth, contrasting with the saccule that may have a different developmental pattern due to its larger size and main auditory functions. Both macula shape and HC orientation patterns were already established in the posthatch fry and retained throughout growth in both end organs. We suggest that previously reported ontogenetic improvements in saccular sensitivity might be associated with changes in HC number (not density), size and/or molecular mechanisms controlling HC sensitivity. This is one of the first studies investigating the ontogenetic development of the saccule and utricle in a vocal fish and how it potentially relates to auditory enhancement for acoustic communication.
5 citations (Crossref) [2022-09-21]
Keywords: Auditory sensitivity; Batrachoididae; Hair cell; Ontogeny; Saccule; Utricle

Catholic schools and inclusive education in Macao: a journey of a thousand miles - Correia, Ana; Teixeira, Vitor (EDUCA - International Catholic Journal of Education, 2017)

Non-Native Raters and Native Speech: Other Perspective for the Research on Comprehensibility of Second Language Input - Figueiredo, Sandra; Simões, Edlia; Martins, Margarida Alves; Fernandes da Silva, Carlos (synergy, 2017)
Abstract: This study examines how specific variables such as age, first language, nationality, school grade and socioeconomic status (SES) affect the comprehensibility of second language (L2) speech in 92 second/non-native language learners. Comprehensibility refers to the degree of speech understanding. Fluency, rhythm, grammatical features and word stressing are concurrent factors for the listening comprehension (and the listener comprehensibility) mainly in L2 context. Research evidence focused the quality and differences of speech samples produced by the L2 learners and the comprehensibility rated by native speakers. In reverse scenario there is less evidence on the judgment of L2 learners for speech samples produced by native speakers. In this study we analysed if the comprehensibility ability of 92 young Portuguese L2 learners differ in the following conditions: age, nationality, home language, school grade, proficiency and socioeconomic status. Speech (one text) was recorded by a native speaker and was judged by L2 speakers using 1-5 Likert scale for comprehension difficulty. Main results showed that neither age nor home language had influence for comprehensibility, but socioeconomic, nationality and grades accounted for statistical differences between the groups tested. Also, data suggested that phonetic features are more likely important for the beginner in second language learning compared to the semantic features of speech that heavily depend on vocabulary domain. Keywords: Speech comprehensibility, nationality, grades, socioeconomic status, second language. Read more →

Extending social networking into the secondary education sector - Kio, Su Iong (British Journal of Educational Technology, 2016)
Secondary schools do not have the same technical resources and capabilities as universities. They usually need to rely on ready-to-use tools to fulfill their information and communication technology (ICT) structure. Social networking site (SNS) has emerged as a practical solution to this need. However, few have collected empirical data on the application of SNS in a secondary school setting. This paper probes into the current condition of SNS usage among secondary school students using a sample of 851 students in Macau, a Special Administrative Region (SAR) of China. Data in terms of access, profile and activities are collected. The activities on SNSs are analyzed by regression techniques to produce a prediction model relating perceived academic benefit and SNS activities. The model yields a strong positive relationship between that benefit and activities such as raising questions and engaging in study-related discussions. The model also yields a weak dependency on activities such as searching for information and entertainment. The paper also evaluates the actual academic utilization of a Facebook Group for one class of secondary school students for a period of one year. At the end of the year, various opinion parameters are measured, and improvements are observed in most parameters.
8 citations (Crossref) [2022-09-21] _eprint: https://bera-journals.onlinelibrary.wiley.com/doi/pdf/10.1111/bjet.12259

Characterization of the Natural Soundscape of Zebrafish and Comparison with the Captive Noise Conditions - Lara, Rafael A.; Vasconcelos, Raquel O. (Zebrafish, 2019)
Zebrafish is a well-established model organism in hearing research. Although the acoustic environment is known to shape the structure and sensitivity of auditory systems, there is no information on the natural soundscape of this species. Moreover, zebrafish are typically reared in large-scale housing systems (HS), although their acoustic properties and potential effects on hearing remain unknown. We characterized the soundscape of both zebrafish natural habitats and laboratory captive conditions, and discussed possible impact on auditory sensitivity. Sound recordings were conducted in five distinct zebrafish habitats (Southwest India), from quieter stagnant environments with diverse biological/abiotic sounds to louder watercourses characterized by current and moving substrate sounds. Sound pressure level (SPL) varied between 98 and 126 dB re 1 μPa. Sound spectra presented most energy below 3000 Hz and quieter noise windows were found in the noisiest habitats matching the species best hearing range. Contrastingly, recordings from three zebrafish HS revealed higher SPL (122-143 dB) and most energy below 1000 Hz with more spectral peaks, which might cause significant auditory masking. This study establishes an important ground for future research on the adaptation of zebrafish auditory system to the natural soundscapes, and highlights the importance of controlling noise conditions in captivity.
16 citations (Crossref) [2022-09-21]
Keywords: Animals; Animals; Laboratory; Auditory Threshold; Batrachoidiformes; Ecosystem; Environment; Female; Hair Cells; Auditory; Hearing; Housing; Animal; India; Male; Neuronal Plasticity; Noise; Saccule and Utricle; Seasons; Sexual Behavior; Animal; Sound; Species Specificity; Vocalization; Animal; Zebrafish; ambient noise; hearing sensitivity; natural habitat; sound pressure level; soundscape

Use of stable isotopes to understand food webs in Macao wetlands - Chen, Qian; Liu, Yang; Ho, Wei-Tim; Chan, Shek Kiu; Li, Qiu-hua; Huang, Jian-Rong (Wetlands Ecology and Management, 2017)
In this study, components of the food-web in Macao wetlands were quantified using stable isotope ratio techniques based on carbon and nitrogen values. The δ13C and δ15N values of particulate organic matter (δ13CPOM and δ15NPOM, respectively) ranged from −30.64 ± 1.0 to −28.1 ± 0.7 ‰, and from −1.11 ± 0.8 to 3.98 ± 0.7 ‰, respectively. The δ13C values of consumer species ranged from −33.94 to −16.92 ‰, showing a wide range from lower values in a freshwater lake and inner bay to higher values in a mangrove forest. The distinct dietary habits of consumer species and the location-specific food source composition were the main factors affecting the δ13C values. The consumer 15N-isotope enrichment values suggested that there were three trophic levels; primary, secondary, and tertiary. The primary consumer trophic level was represented by freshwater herbivorous gastropods, filter-feeding bivalves, and plankton-feeding fish, with a mean δ15N value of 5.052 ‰. The secondary consumer level included four deposit-feeding fish species distributed in Fai Chi Kei Bay and deposit-feeding gastropods in the Lotus Flower Bridge flat, with a mean δ15N value of 6.794 ‰. The tertiary consumers group consisted of four crab species, one shrimp species, and four fish species in the Lotus Flower Bridge Flat, with a mean δ15N value of 13.473 ‰. Their diet mainly comprised organic debris, bottom fauna, and rotten animal tissues. This study confirms the applicability of the isotopic approach in food web studies.
8 citations (Crossref) [2022-09-21]

Wisdom in Aristotle and Aquinas: From Metaphysics to Mysticism - Eh, Edmond (Existenz: An International Journal in Philosophy, Religion, Politics, and the Arts, 2017)
This essay contains an attempt to trace the evolution of the concept of wisdom as found in the thought of Aristotle and Aquinas in terms of how the philosophical concept of wisdom as an intellectual virtue is understood and used to express the theological concept of wisdom as a gift of the Holy Spirit. The main aim is to understand how Aquinas derived the concept of wisdom from Aristotle's metaphysics and developed it in his mysticism. This research is based on a close study of Book Six of Aristotle's Nichomachean Ethics, the corresponding sections of Aquinas' Sententia libri Ethicorum and question forty-five of the second part of the second part of Aquinas' Summa Theologiae. The insights gained from the study are then used to decipher the theoretical meaning of Augustine's famous saying: "love and do what thou wilt" and to expound on the practical value of wisdom for religious leaders.
GSCC: 0000002

Chinese Religious Syncretism in Macau | Orientis Aura: Macau Perspectives in Religious Studies - Eh, Edmond (2017)
In this paper, I address the phenomenon of syncretism with respect to Chinese religions. An analysis of the syncretism that takes place between the three major Chinese religious traditions is first done in its personal and social dimensions. The social structure of Chinese religion is then used as a framework to understand how Buddhism and Daoism were made compatible with Confucianism. All this will serve as a background for the case study of Macau, where Chinese religious syncretism is very much alive. Three popular religious festivals are celebrated annually and simultaneously on the eighth day of the fourth lunar month, namely, zuilongjie (醉龍節) Feast of the Drunken Dragon, tangongdan (譚公誕) Tam Kung Festival and fodanjie (佛誕節) Feast of the Buddha.
GSCC: 0000000

What Kinds of Comparison Are Most Useful in the Study of World Philosophies? - Sivin, Nathan; Akasoy, Anna; Anderson, Warwick; Colas, Gérard; Eh, Edmond (Journal of World Philosophies, 2018)
GSCC: 0001339 Number: 2
Keywords: comparative history; connected history; cultural manifolds; diachronic; intellectual history; inter-cultural comparison; intra-cultural comparison; mutual pollination; postcolonial history; synchronic; transnational history

A Confucian Perspective on Tertiary Education for the Common Good - Eh, Edmond (The Journal of the Macau Ricci Institute, 2018)
Confucian education is best captured by the programme described in the Great Learning. Education is presented first as the process of self-cultivation for the sake of developing virtuous character. Self-cultivation then ...
GSCC: 0000010

Management Transition in South Korea: A Case Study - Chan, Wai Ip; Trimarchi, Michael; Negreiros, Joao (Asian Journal of Business and Management Sciences, 2012)
South Korea management system has been influenced significantly by their traditional social and religious beliefs for hundreds of years. Yet, the 1997 Asian financial crisis has gradually confirmed this shifted, from the Confucius mentality to a close Westernized system. This paper aims to evaluate this management transition in South Korea. The theoretical model of the convergent-divergent, as proposed by Chatterjee and Nankervis [2006], is applied to identify a number of critical factors. The aforementioned factors altogether have influenced the management system in four main vectors: (A) From seniority to meritocracy performance management; (B) From consultative to individualistic decision-making style; (C) From ignoring to embracing corporate governance; (D) From avoiding to improving environmental sustainability.

Financial Worldwide Crisis: The Anti-Counter Cycle of Australia - Pou, Boey Tang; Trimarchi, Michael; Negreiros, Joao (Journal of the Faculty of Economics and Administrative Sciences, Çankırı Karatekin University, 2013)
If Australia has been subject to major influences by the United States and European countries, why is its economy healthier than their counter partners? What are the economic foundations that underline this anti-counter cycle of financial worldwide crisis from Australia? What are some of the lessons that countries from Europe that have not fared during the current financial worldwide crisis should learn from Australia? The purpose of this paper is to review the present Australian management system. Four changes are identified including embracement of corporate governance, a shift to adopt more R&D activities, a shift to adopt environmental sustainability practices and emerging corporate social responsibility. On the conclusions settings, a recap and recommendation on how Portugal, a member of the PIGS (Portugal, Italy, Greece and Spain) Southern European Countries club forgot to embrace directives that have been applied in Australia, to avoid the actual financial and identity crisis.
Number: 2

Evaluation of Deterministic Spatial Interpolators with myGeoffice©: The Utah Grasshoppers Case - Negreiros, Joao; Phillips, Jenny O. L. (International Journal of Geology, Agriculture and Environmental Sciences, 2018)
The knowledge of spatial distribution of grasshoppers can be very relevant for agricultural planning purposes. On the other hand, the comparison of spatial interpolators for efficiency and reliability reasons is also a key factor to understand interpolation maps outcomes (versus reality). At last, but not least, the use of open Web geographical tools to disseminate true spatial inferential methods to address spatial issues is still quite limited (if none) in high schools and universities, particularly in Geography subjects. If the latter can be addressed with myGeoffice©, the first issue will use the Utah, USA, dataset (58 samples) to layout the spatial distribution of grasshoppers and understand the counties that are more pro to this kind of agriculture infestation. Inverse Distance Weighted (IDW), Moving Average (MA), Multi-quadratic, Inverse Multi-quadratic and Nearest Neighbor (NN) will produce interpolated surfaces of grasshopper’s properties. Efficiency of spatial interpolators was assessed in this writing based on the prediction error’s statistics derived from the difference between the estimation and the real samples on a cross-validation procedure. Remarkably, results show that NN was the most accurate one when compared with the remaining deterministic approaches at sample’s locations.

Transgenerational Entrepreneurship In Chinese Family Businesses: Proposal For A Model Of Work-Life Synergy - Phillips, Jenny O. L.; Osorio, Arturo E.; Alves, José (Zenodo, 2018)
Family business are the dominant form of business in the world, and Chinese family business (CFB) is a unique type of family business that relies on collective action to survive. This paper argues that in CFBs, entrepreneurial actions are transgenerational collective endeavors, and successors are groomed as stewards of the family legacy. Work-life relationship in CFBs is about synergy and not balance because the family identity is the business identity, and vice-versa. Using five in-depth case studies, this research introduces an alternative understanding of CFBs and proposes a model of work-life synergy in transgenerational entrepreneurship based on discussion of five theory-based propositions. This model explains that through emphasizing on the business family's shared value and entrepreneurial legacy, elements of trust, shared identity and stewardship of family members are enhanced which leads to collective action and goal of the business family, resulting in transgenerational entrepreneurship. Limitations and future research are presented.
Keywords: Chinese family business; family legacy; stewardship; transgenerational entrepreneurship; work-life synergy.

Open Innovation as Means of Building Social Capital: A Way to Globalization for Traditional SMEs - Phillips, Jenny O. L. (Journal of Strategic Innovation and Sustainability, 2018)
This research explores innovation of traditional SMEs that do not actively invest in innovation. Elements of open innovation have been identified in these firms in their effort to build social capital which they perceive as pertinent to their businesses. The result of the research shows that instead of using social capital as means for innovation, the unintentional practice of open innovation has contributed to the development of social capital, which further opens up potential for globalization. As a result, a model of open innovation as means of developing social capital for enhancing globalization potential for SMEs was developed.
1 citations (Crossref) [2022-09-21] Number: 2
Keywords: Innovation; SMEs; Social Capital; Sustainability

Web 2.0 Tool Recommendations for Teachers - Negreiros, Joao Garrott Marques; Lei, Weng Chi (International Journal of Innovation and Research in Educational Sciences, 2019)

Ten Spatial Problems with myGeoffice© for Teaching Purposes - Negreiros, Joao; Diakite, Ansoumane (Open Journal of Social Sciences, 2019)
For a long time, Geography did not hold a specific mathematical approach for any interpretation of space and this was the key reason why Geography degrees covered a wide variety of subjects such as demography, geology or topography to fulfill its curriculum. Yet from the 90’s, Geography finally created its own research agenda to meet four vital questions of any true geographer: “Where is …?”, “Is there a general spatial pattern?”, “What are the anomalies?” and “Why do these phenomena pursue certain spatial distribution?” The present review article addresses ten different spatial (point, regression and event) issues for learning and teaching aim where statistics play a major background role on the outcomes of myGeoffice© free Web GIS platform. These include cluster analysis, geographically weighted regression (GWR), ordinary least squares (OLS) regression, path analysis, minimum spanning tree, linear regression, space-time clustering and point patterns, for instance. Although the technical viewpoint of the algorithms is not explained at fully, this review paper makes a rather strong emphasis on the result’s interpretation, their respective meaning and when these techniques should be applied in a learning/teaching context.
0 citations (Crossref) [2022-09-21] Number: 7

Motives of Traditional and Emerging Donors in Aid Giving: Comparative Study between China and France - Diakite, Ansoumane D.; Phillips, Jenny O. L. (Journal of Social and Political Sciences, 2019)
Since the beginning of bilateral aid giving in the aftermath of the Second World War, the motives for aid giving have changed from being purely political and humanitarian to a mix of different interests. While poverty reduction is frequently stated as the goal of aid giving, it is commonplace for donors to use aid to advance their national interests. The rise of new, emerging donors is creating discussion in both the political and academic fields of aid giving. Traditional or western donors see emerging donors, such as China’s efforts in aid-giving as seeking the natural resources of the recipient countries. This paper provides a historical analysis of the aid-giving motivations underlying an emerging donor, China, and a traditional donor, France. The motives for China’s and France’s aid giving to African countries, with special focus on Guinea, show a great number of similarities.
1 citations (Crossref) [2022-09-21]
Keywords: Aid Giving Motives; Emerging Donor; Traditional Donor; Poverty Reduction

Lead: An iOS Application to Help in the Construction of New Habits - de Aguiar, André Wescley Oliveira; Bezerra, Jagni Dasa Horta; Marques, João Alexandre Lobo; de Alexandria, Auzuir Ripardo (International Journal of Information and Electronics Engineering, 2019)

Multi-view convolutional neural network with leader and long-tail particle swarm optimizer for enhancing heart disease and breast cancer detection - Lan, K.; Liu, L.; Li, T.; Chen, Y.; Fong, S.; Marques, J.A.L.; Wong, R.K.; Tang, R. (Neural Computing and Applications, 2020)
8 citations (Crossref) [2022-09-21]

Nonlinear characterization and complexity analysis of cardiotocographic examinations using entropy measures - Marques, J.A.L.; Cortez, P.C.; Madeiro, J.P.V.; Albuquerque, V.H.C.; Fong, S.J.; Schlindwein, F.S. (Journal of Supercomputing, 2020)
17 citations (Crossref) [2022-09-21]

Influência da nova estrutura fiscal de impostos de Angola na gestão de escolas privadas do municipio do Lobito - Armando Carlos Hombo Nogueira; Luis Miguel Pacheco; Marcus Antonio Almeida Rodrigues (Revista Gestao em Analise, 2019)
0 citations (Crossref) [2022-09-21]

Evaluating Mathematical Models for Morphological Classification of the QRS Complex - Do Vale Madeiro, J.P.; Barreto, D.; Marques, J.A.L.; Salinet, J.L. (Computing in Cardiology, 2019)

Multi-view Convolution Neural Network with Swarm Search Based Hyperparameter Optimization for Enhancing Heart Disease and Breast Cancer Detection - Lan, K.; Li, T.; Fong, S.; Marques, J.A.L.; Wong, R.K. (5th International Conference on Soft Computing and Machine Intelligence, ISCMI 2018, 2018)
2 citations (Crossref) [2022-09-21]

Automatic Cardiotocography Diagnostic System Based on Hilbert Transform and Adaptive Threshold Technique - Marques, J. A. Lobo; Cortez, P. C.; Madeiro, J. P. D. V.; Fong, S. J.; Schlindwein, F. S.; Albuquerque, V. H. C. D. (IEEE Access, 2019)
The visual analysis of cardiotocographic examinations is a very subjective process. The accurate detection and segmentation of the fetal heart rate (FHR) features and their correlation with the uterine contractions in time allow a better diagnostic and the possibility of anticipation of many problems related to fetal distress. This paper presents a computerized diagnostic aid system based on digital signal processing techniques to detect and segment changes in the FHR and the uterine tone signals automatically. After a pre-processing phase, the FHR baseline detection is calculated. An auxiliary signal called detection line is proposed to support the detection and segmentation processes. Then, the Hilbert transform is used with an adaptive threshold for identifying fiducial points on the fetal and maternal signals. For an antepartum (before labor) database, the positive predictivity value (PPV) is 96.80% for the FHR decelerations, and 96.18% for the FHR accelerations. For an intrapartum (during labor) database, the PPV found was 91.31% for the uterine contractions, 94.01% for the FHR decelerations, and 100% for the FHR accelerations. For the whole set of exams, PPV and SE were both 100% for the identification of FHR DIP II and prolonged decelerations.
13 citations (Crossref) [2022-09-21] Conference Name: IEEE Access
Keywords: Acceleration; Biomedical monitoring; Cardiography; Cardiotocography (CTG); Databases; FHR DIP II; FHR accelerations; FHR baseline detection; FHR decelerations; Fetal heart rate; Hilbert transform; Hilbert transforms; Monitoring; PPV; Transforms; accurate fetal heart rate feature detection; accurate fetal heart rate feature segmentation; adaptive threshold technique; antepartum database; automatic cardiotocography diagnostic system; auxiliary signal; cardiotocographic examinations; computerized diagnostic aid system; digital signal processing techniques; fetal distress; fetal heart rate (FHR); fetal signals; maternal signals; medical signal detection; medical signal processing; obstetrics; patient monitoring; positive predictivity value; preprocessing phase; segmentation processes; uterine contractions; uterine contractions (UC); uterine tone signals; visual analysis

On the probability flow in the Stock market I: The Black-Scholes case - Arraut, Ivan; Au, Alan; Tse, Alan Ching-biu; Marques, Joao Alexandre Lobo (arXiv.org, 2020)
It is known that the probability is not a conserved quantity in the stock market, given the fact that it corresponds to an open system. In this paper we analyze the flow of probability in this system by expressing the ideal Black-Scholes equation in the Hamiltonian form. We then analyze how the non-conservation of probability affects the stability of the prices of the Stocks. Finally, we find the conditions under which the probability might be conserved in the market, challenging in this way the non-Hermitian nature of the Black-Scholes Hamiltonian.
Place: Ithaca, United States University: Cornell University Library arXiv.org
Keywords: General Finance

Early Notices Regarding Creole Portuguese in Former Portuguese Timor - Baxter, Alan N.; Cardoso, Hugo C. (Journal of Language Contact, 2017)
4 citations (Crossref) [2022-09-21]

Social network predicts loss of fertilizations in nesting males of a fish with alternative reproductive tactics - Cardoso, Sara D.; Faustino, Ana I.; Costa, Silvia S.; Valério, Fábio; Gonçalves, David; Oliveira, Rui F. (acta ethologica, 2017)
Alternative reproductive tactics (ARTs) evolve when there is strong intra-sexual competition between conspecifics for access to mates. Typically, larger “bourgeois” males reproduce by securing the access to reproductive resources while smaller “parasitic” males reproduce by stealing fertilizations from larger males. A number of factors can influence the reproductive success of each tactic, including intrinsic (e.g. size) and extrinsic (e.g. tactic relative frequency) variables. An example where plastic ARTs occur is the peacock blenny Salaria pavo, with large males reproducing by defending nests and attracting females (bourgeois tactic) and small males reproducing by achieving sneaked fertilizations (parasitic tactic). In this study, we conducted field observations on individually tagged animals to determine their social network and collected eggs from 11 nests to determine the fertilization success of each male tactic. Paternity estimates for 550 offspring indicated an average fertilization success for nest-holder males of 95%. Nest-holder male morphological traits and social network parameters were tested as predictors of fertilization success, but only the number of sneakers present in the nest-holder’s social networks was found to be a predictor of paternity loss. Although male morphological traits had been previously found to be strongly correlated with reproductive success of nest-holder males, as measured by the number of eggs collected in the male’s nest, no correlation was found between any of the measured morphological traits and fertilization success for these males. The results suggest a stronger influence of the social environment than of morphological variables in the proportion of lost fertilizations by nest-holder males of this species.
3 citations (Crossref) [2022-09-21]

Are Work Engaged Employees Perceive Career Success? A Study of Hospitality at Macau - Kuok, A. C. H (Journal of Hospitality, 2020)
This study examined 206 casino dealers in hospitality at Macau to investigate the extent of their subjective career success and work engagement. Casino dealers were work engaged, but their subjective career success was fairly low, with significant difference between them, which indicates they have cognitive dissonance about their jobs. Several personality variables (emotional suppression and work ethic), organizational variables, i.e., organizational socialization (training, understanding, coworker support, future prospects), and distributive justice, were assessed in relation to subjective career success and work engagement. Organizational socialization, work ethic, and distributive justice were positively correlated with and predictors of subjective career success and work engagement; while emotion suppression was negatively correlated with and predictor of work engagement. This study provides evidence of extending the theories of subjective career success and work engagement in Chinese society and hospitality. Also, it identifies factors that could resolve the employees’ cognitive dissonance, and implementations for management were discussed.
Number: 1-2
Keywords: Subjective career success; emotion suppression; hospitality; human resources; socialization; work engagement

The Effect of Self-Efficacy and Role Understanding on Teachers’ Emotional Exhaustion and Work Engagement in Inclusive Education in Macao (SAR) - Kuok, A. C. H.; Teixeira, Vitor; Forlin, Chris; Monteiro, Elisa; Correia, Ana (International Journal of Disability, Development and Education, 2020)
This study examined responses from 508 full-time teachers working in inclusive schools in Macao (SAR). The intention was to understand the teachers’ perceptions about their roles and how they responded to inclusive practices in their school. Teachers’ perceived levels of emotional exhaustion and cognitive work engagement were assessed in relation to several professional competencies (self-efficacy with using inclusive instruction, collaborating with parents and paraprofessionals, and managing disruptive behaviours), as well as the organisational variable of role understanding. Regression analysis showed that teachers’ self-efficacy with using inclusive instruction was found to be the most powerful negative predictor of emotional exhaustion; while self-efficacy for managing disruptive behaviours was a positive predictor of teachers’ cognitive work engagement. Teachers’ level of understanding of their role and that of their schools was a negative predictor of emotional exhaustion and a positive predictor of cognitive work engagement. Moreover, it further confirmed that the concept of co-existence between work engagement and burnout can be applied to inclusive teachers. Results were interpreted in relation to management in inclusive schools in Macao and were followed by a discussion on the implications of enhancing inclusive education.
1 citations (Crossref) [2022-09-21]

A review of the Colloquium «Narrative, Media and Cognition» — a cartography of the borders of narrative - Castro, Maria Guilhermina; Caires, Carlos Sena; Ribas, Daniel; Palinhos, Jorge (Journal of Science and Technology of the Arts, 2015)
We present an overview and discussion of the Colloquium «Narrative, Media and Cognition», which took place at Porto's Centre of Catholic University of Portugal in July of 2015, under the organization of the Research Centre for Science and Technology of the Arts (CITAR). Several scholars of different areas presented research about the uses and advances in narrative study and practice in a broad range of areas, giving some important insights about the latest developments in Narrative Studies, Ontology of Narrative and the uses of Narrative in Art, Cinema, Performance, Journalism, Marketing and Literature, among other fields. After briefly describing the main points of each presentation in the Colloquium we try to draw some conclusions and possibilities raised by the Colloquium and take a glimpse of future paths that the use of Narrative can end up taking.
1 citations (Crossref) [2022-09-21] Artwork Size: 89-94 Páginas

User Preference on Artificial Reverberation and Delay Time Parameters - Pestana, Pedro Duarte; Reiss, Joshua; Barbosa, Álvaro (Journal of the Audio Engineering Society, 2017)
1 citations (Crossref) [2022-09-21] GSCC: 0000010

Capture and transformation of urban soundscape data for artistic creation - Gomes, Jose Alberto; Pinho, Nuno Peixoto De; Lopes, Filipe; Costa, Gustavo; Dias, Rui; Tudela, Diogo; Barbosa, Álvaro (Journal of Science and Technology of the Arts, 2014)
6 citations (Crossref) [2022-09-21] GSCC: 0000012

The creative industries as an integrated factor in a sustainable model for Macao's economic development - Azevedo, Margarida; Barbosa, Álvaro (Creative Industries Journal, 2014)
This article presents an insight into one of the regions with the fastest-growing economy, heavily based on an entertainment, gaming and tourism industry, and that is urgently looking for a sustainable model that articulates with complementary sectors within the cultural and creative industries – Macao. Macao is facing a major economic and social challenge; it has grown as a vulnerable economy relying almost exclusively on gaming revenues. Alternative activities to diversify the economy are urgently required to answer the competition risks haunting this industry. The cultural and creative industries could be a complementary activity – a vehicle for economic diversification. However, current public and private stakeholders for the cultural and creative sector might have been neglecting the unique cultural and heritage ecosystem of the territory, focusing on isolate opportunities and overlooking an inclusive and robust strategy. A sustainable model that attends to the local conditions and its people is required for alternative activities to become a meaningful sector for the social and economic development of Macao.
2 citations (Crossref) [2022-09-21] GSCC: 0000011

Privacy in sound-based social networks - Cordeiro, J.; Barbosa, A. (Communications in Computer and Information Science, 2014)
2 citations (Crossref) [2022-09-21] GSCC: 0000001

An eco-structuralism approach in soundscape (data) composition - Gomes, J.A.; Barbosa, A.; Penha, R. (ACM International Conference Proceeding Series, 2014)
1 citations (Crossref) [2022-09-21] GSCC: 0000004

NIME education at the school of arts of the portuguese catholic university/CITAR - Martins, L.G.; Barbosa, A. (Proceedings - 2013 Learning and Teaching in Computing and Engineering, LaTiCE 2013, 2013)
0 citations (Crossref) [2022-09-21] GSCC: 0000000

Murky shooting: The use of auditory (non-speech) feedback on mobile audiogames - Cordeiro, J.; Baltazar, A.; Barbosa, A. (ACM International Conference Proceeding Series, 2012)
0 citations (Crossref) [2022-09-21] GSCC: 0000007

Malacca Creole Portuguese in the 19th century: Evidence of a wider lectal range? - Baxter, Alan N. (Journal of Pidgin and Creole Languages, 2018)
Abstract Earlier linguistic research suggested that Malacca Creole Portuguese (MCP) had existed without diglossia with Portuguese ever since the Dutch conquest of Portuguese Malacca in 1642, yet it had experienced some contact with Portuguese in the 19th and 20th centuries. The present study adds significantly to this discussion. It considers a range of information from sociohistorical studies and archival sources (including linguistic data) relating to the Dutch (1642–1795, 1818–1823) and early British (1795–1818, 1823–1884) colonial periods. For the Dutch period, it is seen that contact with other Creole Portuguese communities is likely to have persisted for some time. Most significant, however, is the finding that 19th century texts in Portuguese and creole Portuguese, recently identified in archival sources in London and Graz, show that Portuguese continued to be part of the Malacca sociolinguistic setting until the early British period, and that missionary Indo-Portuguese also had a presence at that time. It is concluded that, rather than presenting a narrow lectal range akin to that of the MCP community in the late 20th century, the creole lectal grid in the 19th century was more complex, and included dimensions of a continuum in a diglossic relationship with Portuguese.
2 citations (Crossref) [2022-09-21]

Physiology, endocrinology and chemical communication in aggressive behaviour of fishes - Silva, Melina Coelho da; Canário, Adelino Vicente Mendonça; Hubbard, Peter Colin; Gonçalves, David (Journal of Fish Biology, 2021)
Fishes show remarkably diverse aggressive behaviour. Aggression is expressed to secure resources; adjusting aggression levels according to context is key to avoid negative consequences for fitness and survival. Nonetheless, despite its importance, the physiological basis of aggression in fishes is still poorly understood. Several reports suggest hormonal modulation of aggression, particularly by androgens, but contradictory studies have been published. Studies exploring the role of chemical communication in aggressive behaviour are also scant, and the pheromones involved remain to be unequivocally characterized. This is surprising as chemical communication is the most ancient form of information exchange and plays a variety of other roles in fishes. Furthermore, the study of chemical communication and aggression is relevant at the evolutionary, ecological and economic levels. A few pioneering studies support the hypothesis that aggressive behaviour, at least in some teleosts, is modulated by “dominance pheromones” that reflect the social status of the sender, but there is little information on the identity of the compounds involved. This review aims to provide a global view of aggressive behaviour in fishes and its underlying physiological mechanisms including the involvement of chemical communication, and discusses the potential use of dominance pheromones to improve fish welfare. Methodological considerations and future research directions are also outlined.
3 citations (Crossref) [2022-09-21]

The Criminalization of Verbal Sexual Harassment in Amending Macao's Criminal Code - Yang, Vincent (Socioeconomic Development Research, 2016)

Visions for Education among Chinese and Non-Chinese Student Teachers: Exploring Cultural Differences - Correia, Ana (The International Journal of Diversity in Education, 2015)
Using Habermas’s theory of communicative action, this study explores the educational visions held by a multi-cultural class of students enrolled in a teacher preparation programme set in a culturally and linguistic diverse urban environment with a recent history of colonialism. The purpose of the study was to analyse the educational and teaching visions put forward by student teachers in an essay during the course “Principles of Education,” which took place in the 2013–2014 academic year and to determine whether the variation in respondents’ vision statements was related to the students’ cultural backgrounds. The students’ awareness of the instructor’s grading role may have influenced the content of their vision statements, and thus Habermas’s theory of communicative action was selected as it allows one to focus on both the content and the process of communicative interaction. The current qualitative research presents data from twenty Macau-Chinese and twenty non-Chinese overseas students. Their visions for education and teaching were examined along the lines of culture. The findings revealed that the idealised representations of what education and teaching is, does and symbolise, varies along culture lines. Since urban educational environments are growing culturally diverse, it is recommended that additional attention be given to cultural awareness in teacher education programmes.
0 citations (Crossref) [2022-09-21]

Neurogenomic plasticity underlying alternative reproductive tactics in the peacock blenny (Salaria pavo) males - Cardoso, S.D.; Gonçalves, David Manuel Flores; Goessman, A.; Canário, Adelino Vicente Mendonça; Oliveira, R.F. (Molecular Ecology)

從即興戲劇體驗討論香港幼兒美感教育環境 - 何嘉莉 (亞洲戲劇教育學刊, 2018)

澳門《新城區總體規劃方案》之建議 - Pinheiro, Francisco Vizeu (澳門研究, 2017)

《澳門旅遊業發展總體規劃》文本建議 - Pinheiro, Francisco Vizeu (澳門研究, 2017)

⼆⼗世紀澳⾨錯位的記憶——《神州在望》作品簡析. - Zhou, L. (Journal of Macau Studies, 2017)

提升澳門文化遺產保護與管理的水平 - Pinheiro, Francisco Vizeu (澳門研究, 2015)

The Macau Forum and China's Soft Power in the Making: Training the Elite of the Development Portuguese Speaking Countries" - Tran, Émilie; Matias, José Carlos (China - An International Journal, 2015)

Coping with Merging and Advanced Market Risks - Xia, Harry (International Journal of Economics and Social Science, 2015)

教育治理背景下的本科訊息公開:基於政策証據視覺的分析教育發展研究 (CSSCI) - 孟瀏今 (2015)

Alternative pathway history in a fish with plastic reproductive tactic - Gonçalves, David (Functional Ecology, 2014)

Oestradiol and prostaglandin F2α regulate sexual display in female of a sex-role reversed fish - Gonçalves, David (2014)

Challenges of collborataive blend learning in undergraduate students - Monteiro, Elisa; Morrison, Keith (Education Research and Evaluation, 2014)

African Female Nascent Entrepreneurship In The Macao S.A.R. - Morais, Isabel (Urban Anthropology and Studies of Cultural Systems and World Economic Development, 2014)
African women from different countries and social classes, from those seeking refugee status to diplomats and peasants' daughters, have been arriving in increasing numbers on Chinese shores since the 1980s. The amazing stories of some of these "invisible" but dynamic women have been ignored, yet they reveal great diversity and deserve scholarly attention, as they provide rich material for studies on the African diaspora in China. This article focuses on African migration to Macao, a former Portuguese colony and primary migration destination in the Pearl Delta River Region, which currently hosts the densest African population in China. It explores both the more recent and the relatively longer-term migration of African women and university students to Macao, and examines the intersection of these communities resulting from the overlap between the ongoing global movements of African diasporas and new African migratory trends to China. The article draws on the life stories as well as the educational and entrepreneurial experiences of African women in Macao, and investigates the relevance of ethnic networks of trust and reciprocity for their communities' survival. This article places specific emphais on the experiences of African women, recognizing their achievements in the face of multiple intersections of racism and sexism on the part of both state and society, and reveals how the women employ a resistance strategy by reinforcing ethnic migrant networks.

教育輿情中的教育政策目標, 議題關注與價值表達: 以兩份十大教育新聞榜單的話語分析為例 - 陳霜葉; 孟瀏今 (北京大學教育評論, 2014)

Gender, sibling position and parental expectations: A study of Chinese college students - Found, Andrew; Sam, David (Journal of Family Studies, 2013)
Differences in parental expectations related to cultural background, gender and sibling position were investigated among Chinese college students in Macau. Three-hundred and forty-four Chinese college students completed a questionnaire which included measures of parental expectations and psychological distress, as well as information about their gender, cultural background (Mainland China or Macau) and sibling position. Participants born in mainland China reported significantly higher perceived parental expectations (PPE) compared with students from Macau. Contrary to predictions, there was no evidence of a difference in PPE in relation to gender or being the first-born sibling. These findings are discussed in terms of changes in family values and parental attitudes within Chinese society over the past few decades.
_eprint: https://doi.org/10.5172/jfs.2013.19.3.285
Keywords: Chinese; gender; parenting; siblings; students

The etiology of mental disorders: public endorsement of traditional Chinese beliefs in Macau - Found, Andrew; Duarte, Carlos (The International Journal of Social Psychiatry, 2013)
BACKGROUND: Public beliefs concerning the causes of mental disorders are important in their effective treatment. The relative importance of public beliefs related to the etiology of mental disorders among Chinese populations and their relationship to other attitudes to mental disorders are poorly understood. AIMS: To investigate the endorsement of beliefs related to the etiology of mental disorders in Macau, in particular, traditional Chinese beliefs, and to explore their relationship to general attitudes towards mental disorders. METHODS: A survey of 361 members of the public measured attitudes towards 32 possible causes of mental disorders as well as contact with and social distance from individuals with a mental disorder. RESULTS: The results indicated that traditional Chinese beliefs were ranked with relatively low importance compared with psychosocial causes. Traditional beliefs related to two underlying factors and were significantly higher in participants with lower education levels. There was a significant negative correlation between endorsement of traditional beliefs and contact with individuals with a mental disorder and a significant positive correlation between endorsement of traditional beliefs and desired social distance from individuals with a mental disorder. CONCLUSION: Factors underlying traditional Chinese beliefs concerning the causes of mental disorders are associated with more negative attitudes towards individuals with a mental disorder, with such beliefs more strongly endorsed by those with relatively lower education levels.
Keywords: Adolescent; Adult; Aged; Attitude to Health; Chinese; Female; Health Knowledge; Attitudes; Practice; Humans; Macau; Male; Medicine; Chinese Traditional; Mental Disorders; Mental disorder; Middle Aged; Surveys and Questionnaires; Young Adult; etiology; lay theories

Signos de los tiempos: desafío a la Nueva Evangelización. El Concilo Vaticano II. Uma Perspectiva teológia. Vicente Vide - José R. Villar (Eds.) San Pablo: Madrid, 2013: - Stilwell, Peter (2013)

加拿大網絡安全戰略及法律問題 - , - Yang, Vincent (中國法學- 2013年網絡資訊安全法特刊, 2013)

Anxious immobilities: an ethnography of coping with contagion (Covid-19) in Macau - Zuev, Dennis; Hannam, Kevin (Mobilities, 2020)
In February 2020, Macau became one of the first regions where the pandemic of coronavirus or Covid-19 affected the totality of social and economic life leading to increased anxieties over movement and distance. Although Macau has had very few actual cases of the virus – 46 in total –and no deaths from it, the Macau government rapidly instituted a lock down. The aim of this article is to reflect on how the social experience of being in lockdown can provide insights into understanding the type of experience or condition that we provisionally term ‘anxious immobility.’ Such a condition is characterized by a total disruption of everyday rhythms and specifically anxious waiting for the normalization of activity while being the subject of biosocial narratives of quarantine and socially responsible. The paper is based upon 3 months of ethnographic research conducted by two researchers based in Macau. We also reflect upon some aspects of the politics of mobilities in the light of disruptions and friction points between Hong Kong, Macau, mainland China, and the rest of the world.
13 citations (Crossref) [2022-09-21] GSCC: 0000008

"The will and the way of inclusive education in Macao", - Correia, Ana; Teixeira, Vitor (Asian Education and Development Studies, 2017)
1 citations (Crossref) [2022-09-21]

John Alexander Holm (1943-2015) - Baxter, Alan N. (Journal of Pidgin and Creole Languages, 2016)

Education in Religious Freedom: Path to Peace and Stability - Gassner, Franz (Orientis Aura, 2016)

Baptism as Christian Initiation in the New Testament - MONERA, A. (Orientis Aura, 2016)

Intersex Brain Transcriptome in Female-Mimicking Males of a Fish with Sequential Alternative Reproductive Tactics. - CARDOSO S.D., GONÇALVES D., GOESSMAN A., CANÁRIO A.V.M., OLIVEIRA R.F. (Molecular Ecology)

The Teaching of Computer Competences with Cooperative Learning in Macao: Working in Progress - WONG, K., NEGREIROS, J., NEVES, A. (International Journal for Digital Society)

Use of apparatuses in science laboratory: developmental characteristics of didactical interactions. (The International Education & Learning Review, 2018)

A defesa noticiosa do status quo - Simões, José Manuel (E-Revista de Estudos Interculturais, 2018)

Temporal variation in brain transcriptome is associated with the expression of female mimicry as a sequen-tial male alternative reproductive tactic in fish. - Cardoso, S.D., Gonçalves, D., Goesmann, A., Canário, A.V.M., & Oliveira, R.F. (Molecular Ecology, 2017)
6 citations (Crossref) [2022-09-21]

“Wisdom in Aristotle and Aquinas,” Existenz - Eh, E. (International Journal in Philosophy, Religion, Politics and the Arts, 2017)
GSCC: 0000002

Church in the Making: An Apophatic Ecclesiology of Consubstantiality - Eleutério, João Marques (Theological Studies, 2017)

Work engagement: Evolution of the concept and a new inventory. Psychological Thought, - Kuok, A.C.H.; Taormina, R.J. (2017)

Lusophony Risks to Be a Heritage with No Future - Leandro, F. J. (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2017)
0 citations (Crossref) [2022-09-21]

Examining the Factor Structure of the Victorian Gambling Screen in Chinese Casino Workers. - Mordeno, I.G.; Nalipay, M.J.N.; Coteriano, C.; Leong, S.U. (Current Psychology, 2017)
1 citations (Crossref) [2022-09-21]

Preserving Cultural Identity by Rehabilitation of Public Spaces, Case Study Analyses on the Historic Center of Macao. - Pinheiro, Francisco Vizeu (Urban Design, 2017)

Redesigning historic cities facing rapid tourism growth: The Case of Macao’s World Heritage Centre and San Ma Lou Avenue - Pinheiro, Francisco Vizeu (Worldwide Hospitality and Tourism, 2017)

Overall Opinion on Macau Urban Planning and the Five-Year Plan. - Pinheiro, Francisco Vizeu; Penny, W. (Journal of Macau Studies- Boletim de Estudos de Macau, 2017)